Fungal Extracellular Vesicles are Recoverable Across Variable Ultracentrifugation Speeds but Display Species-specific Profiles of Sedimentation - Luisa J. Jozefowicz; Bárbara T. Bezerra; Eva Veres; Zóra Szilovics; Cássia M. Souza; Amanda C. Camillo-Andrade; Hellen G. G. Santos; Paulo C. Carvalho; Marlon D. M. Santos; Flavia C. G. Reis; Attila Gacser; Marcio L. Rodrigues (The Journal of Membrane Biology, 2026)

A comprehensive overview of evolutionary relationships and geographic distributions of cownose rays: more valid taxa needing protective measures - Yasmim Trindade C. Cunha; Renata Daldin Leite; Lucas Gabriel Pereira da Silva; Vanessa Paes Cruz; Jorge Luiz S. Nunes; Matheus Marcos Rotundo; Paola Palacios-Barreto; Píndaro Diaz-Jaimes; Ana P. Barbosa Martins; M. Aaron Macneil; Chris G. Mull; José Augusto Pires Bitencourt; et al. (Reviews in Fish Biology and Fisheries, 2026)
Rays of the family Rhinopteridae Jordan & Evermann, 1896 are highly migratory and widely distributed in warm tropical and temperate waters. Along the Brazilian coast, the presence of two species has been recorded: Rhinoptera bonasus Mitchill, 1815 and Rhinoptera brasiliensis Müller, 1836. These stingrays are commonly caught as bycatch in trawl fisheries, however, the two species lack distinctive external morphological features that allow for reliable differentiation—species identification is primarily based on the shape and arrangement of teeth in the buccal plates. This study aimed to investigate the evolutionary history of the genus Rhinoptera and to explore which evolutionary drivers, such as biogeographic events or behavioral traits, have influenced its diversification. To achieve this, we analyzed both mitochondrial and nuclear genetic markers, focusing on the species occurring along the Brazilian coast. Specimens of both species were collected across various locations in Brazil, and additional sequences from other Rhinoptera species were obtained from GenBank. Our results reveal the presence of multiple cryptic species within Rhinoptera , particularly within R. bonasus , and likely in Rhinoptera steindachneri Evermann & Jenkins, 1891 and Rhinoptera javanica Müller & Henle, 1841. Notably, R. bonasus does not occur in Brazilian waters nor in parts of the Caribbean where a distinct cryptic sister lineage was identified. Based on our findings, we propose the resurrection of Rhinoptera lalandii Müller & Henle, 1841 as the species representing the lineage found along the Brazilian coast and the Eastern Atlantic Ocean. We suggest that philopatric behavior may represent one of several factors potentially influencing diversification within Rhinopteridae, although this hypothesis requires direct behavioral and population level validation. These findings highlight the urgent need for a comprehensive taxonomic revision of the family, as well as a reassessment of current conservation strategies to better reflect the hidden diversity within this group of species. Graphical abstract

The COVID-19 pandemic influenced the temporal dynamics of antimicrobial resistance markers and bacterial community across urban wastewater treatment plants - Celso G. B. Filho; Francisca A. S. Oliveira; Victor L. M. Rodrigues; Denise C. Hissa; Maisa V. H. Barros; Allysson A. de Farias; Gabriel T. Dantas; André B. dos Santos; Julio C. M. Ximenes; Vânia M. M. Melo (Brazilian Journal of Microbiology, 2026)
Urban wastewater systems represent important interfaces between human activity and the environmental occurrence of antimicrobial resistance (AMR) markers. We assessed the temporal dynamics of intI1 , ermB , and the 16 S rRNA gene by quantitative PCR across three wastewater systems (EPC, CJC, and JW) in Fortaleza, Brazil, from November 2021 to November 2023. Bacterial communities were additionally characterized by 16 S rRNA gene metabarcoding in 18 samples collected in December 2021 and January 2022. A synchronized decline in 16 S rRNA gene and intI1 concentrations beginning in late 2022 was observed across all three wastewater systems, suggesting a shift toward lower microbial abundance. The ermB gene showed higher and more variable concentrations during part of the pandemic period, followed by convergence toward lower levels; however, the absence of antimicrobial-consumption data precluded attribution of this pattern to changes in macrolide selective pressure. Normalized antimicrobial resistance marker abundances were comparatively stable at EPC and JW but more variable at CJC. EPC exhibited the highest ASV richness, whereas CJC and JW showed greater diversity according to Shannon and inverse Simpson indices. Beta-diversity analyses identified wastewater system as the principal factor associated with bacterial community structure, while the effect of sampling period was smaller and metric-dependent. Neither ermB nor intI1 was individually associated with community composition, although intI1 showed a limited effect after adjustment for wastewater system in one model. Physicochemical parameters were not significantly associated with normalized marker abundances in the exploratory paired analysis. Arcobacter , Acinetobacter , and other potentially relevant genera were detected, but no direct associations between these taxa and the monitored AMR markers could be established. These findings highlight the value of integrating longitudinal qPCR, microbiome profiling, and environmental characterization to improve the interpretation of targeted AMR markers in One Health wastewater surveillance.

Molecular surveillance of Bordetella pertussis during the 2024 outbreak in Southeast Brazil: allelic profiles and comparison to vaccine strain - Thiago J. Sousa; Felipe D. Gatti; Joana Z. Nodari; Gabriela C. de Mendonça; Anna Clara G. Có; Thabata C. D. Damasceno; Nayara C. Silva; Lílian S. Lavagnoli; Danielle G. P. Lyra; Jaqueline P. Goulart; Rodrigo Ribeiro-Rodrigues (Brazilian Journal of Microbiology, 2026)

Short-term air exposure triggers redox metabolic shifts in the reef-building coral Pavona cactus - Luiza de Castro Mastrangelo Dias; Marina Minari; Carol Cristina Vágula de Almeida Silva; Beatriz Rodrigues Guarinão; Luís Felipe Barcena Albertoni; Lucas do Nascimento Lima; Daniel C. Moreira; Marcelo Hermes-Lima; Helen Sadauskas-Henrique (Journal of Experimental Marine Biology and Ecology, 2026)

Temperature-dependent toxicity of insecticide chlorantraniliprole (Altacor®) in the aquatic primary producers Raphidocelis subcapitata and Lemna minor - Ana F. Marinho; Sara C. Antunes; Sara Rodrigues (Aquatic Botany, 2026)

The hidden power of trees: Do local trees combat excessive body weight in Southern Europe? - Ana C. Lourenço; Helena G. Nogueira; Daniela Rodrigues; Augusta Gama; Aristides M. Machado-Rodrigues; Maria Raquel G. Silva; Cristina Padez (Urban Forestry & Urban Greening, 2026)

A comparative evaluation of new prebiotic candidates. Part 2: In vitro assays using faecal inoculum from IBD patients - Sergio Martínez-Gómez; Joana Sousa; Ana Cordeiro; Sónia G. Barbosa; Ricardo Franco-Duarte; Ana C. Pinheiro; Ligia R. Rodrigues; Sara C. Silvério; Remedios Yáñez; José Luis Alonso (Food Research International, 2026)

Comprehensive characterization of walnut oil processing by-products: biochemical composition, bioactive properties, and polyphenol in vitro bioaccessibility and bioavailability - Rafael Mascoloti Spréa; Daniele Bobrowski Rodrigues; Tânia C.S. Pires; Ricardo C. Calhelha; María E. Brassesco; Manuela Pintado; Susana Santoyo; Elena Arranz; Miguel A. Prieto; Lillian Barros; Joana S. Amaral (Food Chemistry, 2026)

Early-life exposure to metals through breast milk and neonatal vulnerability in the Brazilian Amazon - Mônica Cunha; Marta Turull; Montse Marquès; Wanderley Rodrigues Bastos; Jean R.D. Guimarães; Rejane C. Marques; Ronaldo de Almeida; Walkimar Aleixo da Costa Júnior; Thiago Aluisio Maciel Pereira; Sergi Díez (Environmental Pollution, 2026)

First case of canine paraprostatic infection caused by a high-risk ST147 Klebsiella pneumoniae harboring multiple extended-spectrum-β-lactamase genes - Natalia C. Gaeta; Roberto Rodrigues da Rosa Filho; Carine Vieira do Amaral; Willian Seiji Honda; Jéssica Guilhem Alves; Lais Medrado do Nascimento; Carolina de Oliveira Ghirelli; Amanda Haisi; João Pessoa Araújo (Veterinary Research Communications, 2026)
Multidrug-resistant (MDR) Klebsiella pneumoniae , particularly high-risk clones such as sequence type (ST) 147, have been increasingly reported worldwide. However, data on their occurrence in reproductive disorders of companion animals remain limited. This study describes, for the first time, an extended-spectrum β-lactamase (ESBL)-producing K. pneumoniae ST147 isolated from a canine paraprostatic abscess. The isolate (UNISA-DOG-2025) was characterized by antimicrobial susceptibility testing and whole-genome sequencing. Phenotypic analysis revealed an MDR profile, supported by the detection of multiple resistance genes, including β-lactamases ( bla CTX−M−8 , bla CTX−M−15 , bla OXA−1 , bla OXA−9 ), as well as determinants conferring resistance to aminoglycosides, quinolones, sulfonamides, tetracyclines, and trimethoprim. Several of these genes were located on an in silico predicted conjugative IncM1 plasmid, suggesting potential for horizontal dissemination. Phylogenomic analysis demonstrated close relatedness to globally distributed ST147 strains, predominantly associated with human infections. To our knowledge, this is the first report of K. pneumoniae ST147 causing a canine paraprostatic abscess. These findings highlight the clinical relevance of MDR Enterobacterales in canine reproductive disorders and reinforce the need for antimicrobial stewardship and genomic surveillance in veterinary medicine.

Aging impact on canine extracellular vesicles production, size, and miRNA content - Clara Luna Marina; Alexandra Mazer Greuel; Lucas de O. Las-Casas; Evilly Lopes-Gomes; Sabrina Simplício de Araújo Romero Ferrari; Marcio Lourenço Rodrigues; Flavia C. G. dos Reis; Anamélia Lorenzetti Bocca; Simoneide Souza Titze-de-Almeida; Fernando Francisco Borges Resende; Fabiano José Ferreira de Sant’Ana; Ricardo Titze-de-Almeida (Veterinary Research Communications, 2026)
Increasing life expectancy has been accompanied by a higher prevalence of age-associated conditions, underscoring the need to better understand biological mechanisms of aging and to identify accessible biomarkers. Extracellular vesicles (EVs) are lipid-bilayer vesicles that mediate intercellular communication by transporting proteins, lipids, and regulatory RNAs, including microRNAs (miRNAs). Here, we investigated whether the abundance, morphology, and molecular cargo of plasma-derived EVs differ between young and senior dogs. Blood samples were obtained from 24 clinically healthy dogs in Gama (Federal District, Brazil), and plasma EVs were isolated by sequential centrifugation, filtration through a 0.22 μm filter, and ultracentrifugation. EVs concentration and size distribution were assessed by nanoparticle tracking analysis (NTA), morphology by transmission electron microscopy (TEM), and cargo by quantification of total protein and sterols using commercial assays. In addition, we quantified miR-19b, miR-29c, miR-7, miR-155, and miR-21 by Real Time Quantitative Polymerase Chain Reaction (RT-qPCR). Senior dogs exhibited a lower plasma EV yield and greater size heterogeneity, with a higher proportion of larger EVs. Total protein and sterol content per starting plasma volume were reduced in the senior group; however, sterol normalized per EV was increased, consistent with compositional remodeling of circulating vesicles with age. Finally, EV-associated miRNA levels were reduced in senior dogs, particularly miR-19b and miR-29c. Collectively, these findings indicate that canine aging is associated with marked changes in plasma EV abundance, morphology, and cargo, indicating that EVs could represent a promising tool for investigating age-related disorders in dogs.

Intestinal Histomorphometric Alterations During Experimental Strongyloidiasis in Mice Treated with Rosmarinus officinalis Essential Oil - Lorena Q. A. Tanaka; Kamilla A. M. Dutra; Nicolas M. H. da Silva; Izadora M. Assis; Gabriela A. C. Duarte; João B. A. Souza; Eleuza R. Machado; Ana Paula S. Perez; Rosângela M. Rodrigues (Acta Parasitologica, 2026)
Purpose Strongyloidiasis is an intestinal helminthiasis that can induce structural alterations in the intestinal mucosa during infection. The present study evaluated histomorphometric alterations of the small intestine in mice experimentally infected with Strongyloides venezuelensis and treated with Rosmarinus officinalis essential oil. Methods Infected animals were treated orally with R. officinalis essential oil (200 or 400 mg/kg), ivermectin or control treatments. Histomorphometric parameters of the small intestine were evaluated, including villus height, epithelial height, crypt depth, muscular layer thickness, brush border height and goblet cell counts. Parasitological parameters were also assessed to characterize the infection model. Results Histomorphometric analysis demonstrated that treatment with essential oil at 200 mg/kg was associated with recovery of villus and epithelial height, increased brush border and goblet cell numbers, as well as attenuation of muscular layer hypertrophy, suggesting preservation of mucosal structure during infection. The 400 mg/kg dose, although associated with greater reduction in parasite burden, was accompanied by increased crypt depth, indicating more intense proliferative remodeling of the intestinal mucosa. Ivermectin promoted the greatest reduction in parasite burden with marked elimination of eggs and females. Conclusion These findings indicate that R. officinalis essential oil modulates intestinal mucosal architecture during experimental strongyloidiasis and highlight its potential influence on host intestinal responses during infection.

A comparative evaluation of new prebiotic candidates. Part 1: Chemical and structural characterization, digestibility, and in vitro fermentation using faecal inoculum from healthy donors - Sergio Martínez-Gómez; Joana Sousa; Ana Cordeiro; Sónia G. Barbosa; Ricardo Franco-Duarte; Ana C. Pinheiro; Ligia R. Rodrigues; Sara C. Silvério; Remedios Yáñez; José Luis Alonso (Food Research International, 2026)

Fortifying Depurated Clams: Evaluation of the Antioxidant and Nutritional Impact of Microencapsulated Diets Containing Nannochloropsis sp. and Vitamin Supplementation - Vitória Pereira; Sílvia F. S. Pires; Pedro Bem-Haja; Andreia C. M. Rodrigues; Amadeu M. V. M. Soares; Luís E. C. Conceição; Mário Pacheco; Rui J. M. Rocha (Fishes, 2026)
Conventional bivalve depuration protocols may compromise organoleptic and nutritional quality, largely as a consequence of fasting. This study investigates an innovative post-depuration feeding strategy in the clam Ruditapes decussatus using microencapsulated diets containing Nannochloropsis sp. supplemented with either a standard dose of vitamins C and E (MV) or a high dose—4× the standard level—of these vitamins (MV+). A three-phase experiment was conducted comprising 24 h of depuration, 2 h of post-depuration feeding, and 6 days of refrigerated storage at 5 ± 1 °C. Clams were sampled after feeding (PF) and after refrigerated storage (PS) and assessed for condition index (CI), vitamin C and E contents, antioxidant defense markers, including catalase activity (CAT) and total glutathione (tGSH), and oxidative damage, assessed through lipid peroxidation (LPO). CI did not differ significantly among dietary treatments. At PF, dietary treatment modulated antioxidant-related responses, particularly in the MV+ group. In the digestive gland, MV+ showed significantly lower LPO than the Control at PF, whereas after refrigerated storage this response was reversed. These findings indicate that the potential benefits associated with vitamin-enriched post-depuration feeding were not fully retained, with increased LPO at PS indicating greater oxidative damage. Further research is required to optimize this feeding strategy and evaluate its feasibility at commercial scale.

eDNA-based assessment of microbial dynamics in response to persistent contaminants and degraded water quality in a hypereutrophic urban reservoir - Juliana S. M. Pimentel; Maria Clara V. M. Starling; Camila C. Amorim; Valquíria F. L. Viana; Alessandra S. Martins; Daniel A. S. Rodrigues; Luciana P. M. Brandão; Nadieh de Jonge; Niels O. G. Jørgensen; Louise Schlüter; Matt Simcik; Jeppe Lund Nielsen (Environmental Monitoring and Assessment, 2026)
Urban freshwater ecosystems are increasingly exposed to mixtures of pollutants, including per- and polyfluoroalkyl substances (PFAS). However, their ecological effects remain poorly understood, especially in tropical regions with limited sanitation infrastructure. This study investigated PFAS contamination, water quality, and microbial community structure in Pampulha Lake, a tropical urban reservoir in southeastern Brazil. Spatiotemporal patterns in prokaryotic and eukaryotic diversity were assessed over a year (2022–2023) using environmental DNA metabarcoding of 16S and 18S rRNA genes by integrating taxonomic data with PFAS concentrations and water quality. Physicochemical and multivariate analyses revealed strong seasonal and spatial heterogeneity, influenced by eutrophication, hydrological variability, and pollution gradients. Among the seven PFAS detected above quantification limits, PFBS and PFOA were the most common. Prokaryotic communities showed significant correlations with PFAS, especially with sulfonated forms, while eukaryotic communities were more stable. Diversity patterns highlighted microbial community sensitivity to environmental stress. Overall, results indicate that PFAS influenced microbial assemblages, supporting their inclusion in monitoring frameworks, and eDNA was proved effective for assessing ecological risks in tropical urban reservoirs.

Assessment of Exposure to Essential and Non-Essential Elements through Concentrations in Tissues of Chelonia mydas (Green turtles) from the South Atlantic, Northeast Brazil - Midiã S. Rodrigues; Iago J. S. da Silva; Cristina F. da Fonseca; Pierre C. Soares; Múcio L. B. Fernandes; Geraldo J. B. de Moura (Biological Trace Element Research, 2026)
This study aimed to evaluate the exposure of Chelonia mydas (green turtles) inhabiting the south coast of Pernambuco, Northeast Brazil, to essential and toxic elements. Concentrations of Al, Cd, Co, Cr, Cu, Fe, Mn, Mo, Ni, Pb, and Zn were determined in shell, muscle, liver, and kidney samples from 43 individuals using ICP-OES. Element concentrations varied according to tissue type. Specifically, the average concentrations of Al in shell (1064 mg kg −1 d.w.) and Fe in liver (2069 mg kg −1 d.w.) were the highest, whereas Al, Co, Cr, and Mo in muscle were the lowest and fell below the method's limit of quantification (LOQ). Meanwhile, Pb was above the LOQ only in muscle (average of 4.1 mg kg −1 d.w.). Cadmium levels were markedly elevated, with average concentrations of 0.15, 0.29, 12, and 49 mg kg −1 d.w. in shell, muscle, liver, and kidney, respectively; furthermore, concentrations in muscle, liver, and kidney were well above the limits established by Brazilian legislation (0.05, 0.5, and 1.0 mg kg −1 , respectively). High levels of Cd may be linked to the presence of fertilizers in coastal areas, the ingestion of contaminated food, and chronic exposure. Notably, fibropapillomatosis (FP) showed a significant relationship with shell Cu content, demonstrating that this metal is linked to the etiology and development of FP. Overall, multi-elemental profiling of sea turtle tissues can serve as a cost-effective surveillance tool for marine ecosystem monitoring and for detecting anthropogenic impacts on sea turtle health.

From invasive nuisance to biotechnological asset: LC–MS/MS chemical profiling and pharmacological potential of ascidian Styela plicata from Albufeira Lagoon, Portugal - Maria João Nunes; Catarina M. Luís; Vanda Marques; Bárbara Gonçalves; Luís C. Branco; Cecília M. P. Rodrigues; Rita G. Sobral; Susana P. Gaudêncio (Environmental Science and Pollution Research, 2026)

Comparative analysis of the antifungal potential of Ocimum basilicum essential oil, estragole, and its estragole/β-cyclodextrin complex in an adult zebrafish infection model - Francisco Lucas A. Batista; Antonia Thassya L. dos Santos; Francildo dos Santos Silva; Andressa Guilhermino dos Santos; Maria Audilene de Freitas; Maria Gabriely de L. Silva; Victor Juno Alencar Fonseca; Maria Rayane C. de Oliveira; Lucas Yure Santos da Silva; Lindaiane Bezerra Rodrigues; Maria Flaviana Bezerra Morais-Braga; Henrique Douglas M. Coutinho; et al. (South African Journal of Botany, 2026)

Raman elastic geobarometry from garnet amphibolites in the eastern margin of the Santa Quitéria continental magmatic arc, NE Brazil: New insights into the evolution of Western Gondwana - Felipe Aires; Renato Moraes; Mattia Gilio; Lucilene Santos; Armando Oliveira; André Luiz Silva Pestilho; Rafael Gordilho-Barbosa; Afonso Rodrigues de Almeida; Evilarde C. Uchôa Filho (Lithos, 2026)

Giant paraovarian cyst causing abdominal distention in a Swiss mouse (Mus musculus) - Daniel F. Barrantes Murillo; Luis J. Alfaro Quillas; Regina C. Rodrigues da Paz; Fernando H. Furlan Gouvêa; Caroline Argenta Pescador; Marcos de Almeida Souza (Journal of Comparative Pathology, 2026)

Phenolic profile, bioaccessibility, and bioactivity of Brazilian olive leaf infusions (Olea europaea L.) after simulated gastrointestinal digestion - Heloisa Rodrigues Pessoa; Beatriz Neris Lima; Graziana Difonzo; Antonella Pasqualone; Francesco Caponio; Lilia Zago; Danielly C. Ferraz da Costa (Food Bioscience, 2026)

Environmental assessment of antibiotic toxicity under climate change–related temperature and pH scenarios using Danio rerio - Bárbara S. Diogo; Sara Rodrigues; Oksana Golovko; Sara C. Antunes (Fish Physiology and Biochemistry, 2026)
Climate change induced temperature and pH shifts can alter aquatic environments, potentially intensifying antibiotic toxicity, disrupting the physiological balance of aquatic organisms. Few studies have examined combined effects of these abiotic environmental stressors and antibiotics on aquatic ecosystems in a potential climate change scenario. This study evaluated the toxicity of environmentally relevant concentrations of sulfamethoxazole (150 µg SMX/L), trimethoprim (30 µg TRIM/L), and their mixture (MIX: 150 µg SMX/L + 30 μg TRIM/L) in Danio rerio under two scenarios: standard (26 °C, pH 7.5) and climate changed (28 °C, pH 9.0). A multi-biomarker approach was performed to evaluate oxidative stress, lipid peroxidation, neurotransmission, energy metabolism, and DNA damage. Integrative assessment of an organism’s health showed that increasing pH and temperature intensified SMX and TRIM toxicity, shifting from marginally to highly toxic. Meanwhile, MIX toxicity increased from marginally to moderately toxic. Under standard conditions, SMX and TRIM caused major alterations (affecting antioxidant/detoxification mechanisms), while MIX induced severe alterations in D. rerio 's health status. Under a climate-changed scenario, all antibiotics led to severe alterations (lipid peroxidation, DNA damage, and energy metabolism disruption). These findings suggest that under a climate-changed scenario (higher temperature and pH increase), both individually and in mixtures, antibiotic toxicity leads to more severe effects on D. rerio . Given this, it is crucial to consider environmental factors when assessing antibiotic toxicity, as shifts in temperature and pH can significantly amplify their harmful effects. Understanding these interactions is essential for developing effective regulatory and conservation strategies to safeguard aquatic ecosystems from long-term ecological imbalances.

Spatial Scale Modulates the Effect of Habitat Amount on Diversity Patterns of Arachnid Assemblages Across Different Brazilian Ecosystems - André F. A. Lira; Adriano M. DeSouza; Thayna R. Brito‐Almeida; Hugo L. L. Neves; Gilberto G. Rodrigues; Carlos Henrique De‐Oliveira‐Nogueira; Ubiratã F. Souza; Alessandra R. S. Andrade; Rafael G. Jansen; Ana Lúcia Tourinho; Leonardo S. Carvalho; Laís M. Pordeus; et al. (Journal of Biogeography, 2026)
Aim We evaluated how native vegetation cover influences the diversity of arachnid assemblages across multiple spatial scales in major Brazilian ecosystems. Location Brazil (Amazon and Atlantic rainforests, Cerrado savanna and Caatinga dry forest). Taxon Arachnida (Opiliones, Pseudoscorpiones and Scorpiones). Methods We sampled arachnids at 120 sites using active search and litter sifting. Native vegetation cover was quantified at three spatial scales (100, 200 and 300 m buffers) using GIS data. Assemblage structure was assessed using abundance, species richness, and Hill numbers ( q = 0, 1 and 2). Generalized linear mixed models were used to evaluate responses across taxonomic groups and ecosystems. Results We recorded 3986 individuals from 179 species. Diversity responses to native vegetation cover were taxon‐, ecosystem‐ and scale‐dependent. Positive effects of vegetation cover were stronger and more consistent in rainforest than in savanna and dry forest ecosystems. In rainforests, most responses occurred at smaller spatial scales (100–200 m), whereas no significant effects were detected in the savanna. Opiliones richness showed limited variation with vegetation cover but differed in dominance structure among ecosystems. Scorpion assemblages were characterized by low richness and high dominance, while pseudoscorpions exhibited low evenness in more species‐rich sites, particularly in the Amazon. Main Conclusions Native vegetation cover plays an important role in structuring arachnid diversity in Brazil, but its effects vary across taxa, ecosystems and spatial scales. These findings highlight the need for taxon‐ and scale‐specific conservation strategies and reinforce the importance of multi‐scale approaches to biodiversity conservation in Neotropical landscapes under increasing anthropogenic pressure.

Inclusion of carotenoids and Eicosapentaenoic Acid (EPA) in sea urchin (Paracentrotus lividus) broodstock diets improves gonad development and oocyte quality - A. S. Gomes; A. F. Rodrigues; M. Neves; C. Roseiro; H. Cardoso; A. P. Violante; P. J. Gavaia; C. Suckling; S. Lourenço (Aquaculture International, 2026)

Late Quaternary change in sources and burial of organic carbon off Northeastern Brazil - Alice Maria da S. Rodrigues; Rodrigo de L. Sobrinho; Patrícia Piacsek; Ioanna Bouloubassi; Arnaud Huguet; Ana Luiza S. Albuquerque; Igor M. Venancio; Thiago P. Santos; Joana F. Cruz; Marcelo C. Bernardes (Quaternary Science Reviews, 2026)

Thermal limits of estuarine amphipods and their implications for aquaculture production - Daniela P. Rodrigues; Luísa Marques; Joana Teixeira; João Ferreira; João P. Sousa; Rafael C. Duarte; Ricardo Calado (Marine Environmental Research, 2026)

Hafnium and silicon isotope evidence for multiple unsilicified basaltic sources at the origin of Rhyacian TTG magmas in the Mineiro Belt (Brazil) - Syro Lacerda; Martin Guitreau; Leonardo Gonçalves; Hugo Moreira; Cristiane C. Gonçalves; Stéphany Rodrigues Lopes; Sandro Mauri; Marco Aurélio Pinheiro; Cassiano Costa e Castro; Régis Doucelance (Geochimica et Cosmochimica Acta, 2026)

Power dynamics in strategic environmental assessment: examining actors' relations in Portuguese urban planning processes - M. Pereira; M. Pereira; M.L. Fernandes; F. Teles; S. Moreno Pires; P. Silva; C. Rodrigues; C. Jalali; A. Polido (Environmental Impact Assessment Review, 2026)

Reproductive toxicity induced by a repeated 28-day oral exposure to a commercial mixture of the herbicides S-metolachlor and flumioxazin in male rats - Renata K. Carvalho; Diego S. Reis; Ana Luísa G. Santiago; Bruna M. Rodrigues; Jacqueline A. Leite; Walter D. Júnior; Virgínia Damin; Monica L. Andersen; Maingredy R. Souza; Paulo C. Ghedini; Hericles M. Campos; Daniela M. Silva; et al. (Chemico-Biological Interactions, 2026)

Effect of supplementation with different trace minerals sources and fibrolytic enzyme on the productive and reproductive performance of Nellore cows on pasture - Keuven S. Nascimento; Amanda C. M. Queiroz; Aline N. Rodrigues; Luiz F. Costa e Silva; Carlos R. Zilioti; James E. Pettigrew; Rodrigo S. Marques; Flávio D. Resende; Gustavo R. Siqueira (Tropical Animal Health and Production, 2026)

Assessment of Eucalyptus seedlings grown in biodegradable containers and their growth in clonal plantations - Vitor S. Brito; Emanuela F. Gama-Rodrigues; José L. M. Gonçalves; Alexandre V. Ferraz; José C. A. Júnior (New Forests, 2026)

Ecotoxicity assessment of dairy wastewater: environmental risks and regulatory needs - Magno Lange Albuquerque; Fernando Rodrigues-Silva; Alyson Rogério Ribeiro; Carollina M. Chávez; Gilcinéa de Cássia Santana; Alessandra da S. Martins; Camila C. Amorim; Maria Clara V. M. Starling (Ecotoxicology, 2026)

Brazil’s science–policy effort to monitor native vegetation restoration - André L. Giles; Marina G. Freitas; Ana L. V. Espada; Pedro Constantino; Bruno S. Francisco; Silvia B. Rodrigues; Alexandre B. Sampaio; Isis F. de Freitas; Gabriela C. S. Bueno; Raquel C. A. Lacerda; R. Edson; Kirsten Silvius; et al. (Ambio, 2026)
In its early years, the UN Decade on Ecosystem Restoration has mobilized unprecedented global commitments. Yet, measuring restoration success remains contested, particularly in megadiverse countries where the absence of standardized indicators and assessment protocols often leads to subjective decisions by environmental agencies. Here, we present a core set of leading indicators developed through a pioneering Brazil-led science–policy collaboration between environmental agencies and research institutions. The indicators capture early vegetation recovery within four years and whether restoration trajectories are sustained or at risk of reversal. The initiative also establishes a framework that bridges science and policy to deliver practical monitoring tools. It offers a model for other megadiverse countries with complex governance, showing how simple, standardized indicators can translate restoration pledges into measurable results for the UN Decade.

The Role of Gene Flow in the Diversification of the Monkey Treefrog Complex Across the South American Dry Diagonal - Felipe Camurugi; Vinícius A. São Pedro; Felipe Magalhães; Marcelo Gehara; Eliana F. Oliveira; Gabriel C. Costa; Frank T. Burbrink; Edward A. Myers; Guarino R. Colli; Miguel T. Rodrigues; Adrian A. Garda (Zoologica Scripta, 2026)
Understanding Neotropical megadiversity remains challenging due to fundamental taxonomic issues, including identifying and describing cryptic species and their distribution, and the limited knowledge of key factors driving biological diversification. Such challenges are especially prominent in diverse clades with high levels of cryptic species, such as many Neotropical frogs. Herein, we conduct a mitochondrial phylogenetic study on monkey treefrogs in the genus Pithecopus and a multilocus analysis of the P. hypochondrialis species group throughout its distribution in the South American dry diagonal (DD). Our goals were to infer the main lineages and identify historical factors that led to their divergence. Among nine currently recognised species, we found 14 well‐structured mitochondrial lineages in two main clades, which diversified during the Paleogene/Neogene transition. The lowland clade is widely distributed in the DD, and our multilocus analysis suggests it comprises seven geographically structured lineages: P. azureus , two lineages of P. hypochondrialis , two species and one lineage for the P. nordestinus complex, and Pithecopus sp. Considering the geomorphological history of the region, diversification may have been promoted by allopatric speciation during Miocene paleogeographic events, especially the Brazilian Plateau compartmentalization and fluctuations in the São Francisco River water volume. Furthermore, gene flow between some lineages may be explained by niche conservatism and demographic expansions during the late Pleistocene, a period marked by climatic fluctuations and biome shifts. Our results reinforce the importance of both Neogene tectonic activity and Quaternary climatic fluctuations in shaping the Neotropical biota.

Climate Predicts Tree Dispersal Strategies Across Brazil's Ecosystems - Fernanda C. Souza; Vinícius Andrade Maia; Renata Françoso; Matheus Coutinho Freitas de Oliveira; Ana Beatriz Ligo; Bruno X. Pinho; Jesús Aguirre‐Gutiérrez; Martin Sullivan; Larissa Rocha‐Santos; Laura de Brito Évora; Leonardo de Sousa Miranda; María Natalia Umaña; et al. (Global Ecology and Biogeography, 2026)
Aim We investigate the distribution of dispersal modes — endozoochory (via animal ingestion), synzoochory (via animal seed accumulation) and anemochory (via wind)—and seed mass of woody plants across Brazilian ecosystems, testing whether their relative abundance in local plant communities could be predicted by climate, edaphic factors and dispersal agents (e.g., the main vectors moving seeds). We expected climate to be the main predictor of dispersal strategy abundance. Location Brazilian ecosystems (Amazon, Atlantic Forest, Cerrado and Caatinga). Time Period 2004–2020. Major Taxa Studied Woody angiosperms, trees and shrubs. Methods We assigned seed mass to 1984 species and dispersal mode to 2203 species within 300 old‐growth and non‐flooded plots. We employed Random Forest regressions to assess the influence of water availability, temperature seasonality, soil fertility, wind and frugivorous primates on the community‐weighted means of seed mass and dispersal modes. We mapped predictions and estimated the area of applicability to identify regions where predictions were reliable. Results Climate was the main factor predicting tree dispersal strategies, followed by dispersal agents or soil properties. Endozoochory was prevalent in wetter regions with high water availability and greater diurnal temperature range. Anemochory was more common in drier regions with low water availability, stronger winds and greater diurnal temperature range, whereas synzoochory was more abundant in areas with low temperature seasonality. Heavier seeds were more prevalent in regions with less seasonal temperatures, smaller diurnal temperature ranges and weaker winds. Main Conclusions Climate is a key predictor of the distribution and prevalence of plants with contrasting dispersal modes and seed masses. We thus expect functional responses to environmental change associated with shifts in the relative abundance of dispersal strategies, with implications for ecosystem services. Our results also highlight the critical role of plot‐based datasets in improving our understanding of how environmental factors influence seed dispersal strategies across tropical ecosystems.

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

From turbulence modelling to machine learning integration in computational ship hydrodynamics using RANS - Ivan Sulovsky; Ermina Begović; George Papadakis; Kostas Belibassakis; Nastia Degiuli; Jasna Prpić-Oršić; Carlo Giorgio Grlj; Ivana Martić; Andro Bakica; Florian Sprenger; Junheng Zhang; Deniz Aktürk; et al. (Ocean Engineering, 2026)

Microscale sealed vessel (MSSV) technique in petroleum systems: a review - Sandra B. Jorge; André L.S. Pestilho; Juliana M. Sousa; Antônia M. Corrêa; Hemmely G. de S. Severino; Alice Maria S. Rodrigues; Kátia Z. Leal; Cleverson J.F. de Oliveira; Daniel S. Dubois; Marcelo C. Bernardes (Organic Geochemistry, 2026)

The impact of oxybenzone on the neurophysiological and oxidative stress response, dispersal and aggressiveness of the Invasive Red Swamp Crayfish (Procambarus clarkii) - Cristiana Lopes; Filipe Banha; Sílvia Pires; Pedro Brandão; Daniel Oliveira; Ana Luchiari; Pedro Anastácio; Andreia Rodrigues; Marta C. Soares (Environmental Toxicology and Pharmacology, 2026)

Highly efficient (MFe)zeolite catalysts for nimesulide degradation via Fenton-type oxidation - Carmen S.D. Rodrigues; Susana Costa; Olívia S.G.P. Soares; António M. Fonseca; Pier Parpot; Manuel F.R. Pereira; Luis M. Madeira; Elisabetta Rombi; Isabel C. Neves (Chemical Engineering Journal, 2026)

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Differential drought tolerance in two commercial açaí cultivars: Insights from gas exchange, chlorophyll fluorescence, and antioxidant responses - Patricia C. A. Navegantes; Wagner Romulo L. Lopes Filho; Flavio Henrique S. Rodrigues; Rosane Patricia F. Chaves; Roberto L. Cunha; Lucas C. Costa; Hugo A. Pinheiro (Trees, 2026)

Rainwater isotopic composition variability during extremely rainy years in the São Francisco River headwaters, southeastern Brazil - Marcela Aragão de Carvalho Ramos; Rafaela Rodrigues Gomes; Tomás Lyra Lutterbach; Vinícius dos Santos; Vladimir Eliodoro Costa; Zayra C. Sátyro; Didier Gastmans (Theoretical and Applied Climatology, 2026)

Machine learning-based stratification of chagas heart failure severity using ECG power spectral biomarkers - Pedro Ribeiro; João Alexandre Lobo Marques; Maria Inês Barbosa; Roberto C. Pedrosa; João Paulo do Vale Madeiro; Pedro Miguel Rodrigues (Medical & Biological Engineering & Computing, 2026)

Root-zone Application of Biochar and Compost Improves Maize Crop Performance, Nutrient Use Efficiency and Profitability Under Sub-humid Tropical Climate - Waliou A. Abiola; Pierre G. Tovihoudji; Rodrigue V. C. Diogo (Journal of Soil Science and Plant Nutrition, 2026)

Detection and mitigation of Paraphysomonas sp., a chrysophycean responsible for the collapse of industrial Tisochrysis lutea cultures - Mélissa José; Cristina Paulino; Lisa M. Schüler; Bruno Pinto; Mariana Carneiro; Alexandre M. C. Rodrigues; Filipe Pereira; Hugo Pereira; João C. S. Varela (Journal of Applied Phycology, 2026)
Microalgae are increasingly recognized as a sustainable resource to address challenges associated with climate change and population growth, owing to their capacity to produce high-quality biomass for applications in feed, food, and cosmeceuticals. However, the expansion of microalgae-based industries remains constrained by harmful biological contaminants (HBCs), which can rapidly reduce productivity, often signalled by visible changes in culture appearance (e.g., cell aggregation and discoloration), and may ultimately lead to culture collapse and substantial economic losses. In this study, the grazer Paraphysomonas sp. (Chrysophyceae) was identified as the most likely cause of Tisochrysis lutea culture collapse in a large-scale production facility using high-throughput amplicon sequencing of the 18S rDNA gene. To enable early detection of this HBC during the scale-up process, a species-specific primer pair targeting the 18S rDNA gene was developed and optimized, allowing detection of Paraphysomonas sp. at relative abundances as low as 0.1%. The contaminant was first detected at the final stage of scale-up, in a tubular photobioreactor. To further characterize the impact of the grazer and support mitigation strategies, its feeding behaviour was examined. Laboratory-scale mitigation trials showed that treatment with germanium dioxide (GeO 2 ) at 1 mg L⁻ 1 effectively delayed contaminant proliferation and prevented culture collapse without adversely affecting T. lutea growth. These findings highlight the value of integrating molecular monitoring with targeted mitigation strategies to improve early detection and management of HBCs in industrial microalgae production systems.

Conversion of MDF waste into CoCl2-functionalized activated carbon for enhanced phosphate removal from landfill leachate - A. G. dos Santos; L. C. S. Coelho; D. A. Bertuol; M. A. S. Rodrigues; E. H. Tanabe (International Journal of Environmental Science and Technology, 2026)

Inverse Bayesian Estimation of Time-Varying Pollutant Loads at River Margins - Bruno C. Lugão; Diego C. Knupp; Leonardo T. Stutz; Pedro Paulo G. W. Rodrigues (Environmental Modeling & Assessment, 2026)

Supervised Learning for Collagen Segmentation in Bright-Field Histology: A Comparative Evaluation of U-Net and MLP - Evelyn R. Silva; Lívia B. Souza; Fernanda S. Tenorio; Nilsa R. Damaceno-Rodrigues; Rita C. Marqueti; Karina R. Casali; Tatiana S. Cunha; Matheus C. Moraes (Annals of Biomedical Engineering, 2026)
Purpose Quantifying collagen in histological slides is essential for diagnosing and monitoring fibrosis. However, the combination of PicroSirius Red staining with polarized light microscopy, one of the standard techniques, requires expensive equipment and time-consuming procedures. This study investigated whether supervised machine learning algorithms applied to bright-field images could provide an automated and accurate method for collagen segmentation, reducing the dependence on polarized imaging. Methods A total of 140 histological images of renal, cardiac, and tendinous tissues from mice and rats stained with PicroSirius Red were analyzed. The images were fragmented into smaller patches, and the green channel was selected for non-polarized analysis. The reference standard was generated from polarized images binarized using ImageJ. Two supervised models were evaluated: (1) a Multilayer Perceptron (MLP) trained using five features (RGB intensities, median filter, and Wavelet), and (2) a U-Net architecture adapted to the image dimensions. Results Both models performed well, with the best results observed in rat tendon samples (Dice and precision > 80%). Performance was lower in mouse kidney images, possibly due to weaker staining and thinner collagen fibers. Overall, the MLP slightly outperformed the U-Net, which still showed comparable results. Conclusion The proposed methodology proved effective for collagen segmentation highlighting the potential of supervised learning to reduce costs and processing time in histological analysis. Future improvements include expanding the dataset and refining the reference standard to enhance robustness in biological tissue evaluation.

A framework for assessing the environmental safety of wastewater treated by advanced oxidation processes based on species sensitivity distribution - Fernando Rodrigues-Silva; Carla S. Santos; Ana I. Gomes; Vítor J.P. Vilar; Maria Clara V.M. Starling; Camila C. Amorim (Science of The Total Environment, 2026)

WITHDRAWN: Inflammatory markers levels and clinical characteristics in COVID-19 susceptibility and severity: A cross-sectional multicentric study - Lucas C. Pedro; Camila O. Arent; Flávia S. Niero; Caion A. Rodrigues; Margarete D. Bagatini; Gabriela G. de Oliveira; Zuleide Maria Ignácio; Larissa Joaquim; Fabricia Petronilho; João Quevedo; Alexandra I. Zugno; Luciane B. Ceretta; et al. (Next Research, 2026)

Environmental and cost trade-offs uncertainty in ecodesign: a new approach to communicate life cycle impacts - Carlos Hernandez; Luis C. Dias; Carla Rodrigues; Fausto Freire (Journal of Cleaner Production, 2026)

Different strategies to obtain laccase-based time-temperature indicator for monitoring of cold chain storage and management - Camila Regina Hackenhaar; Vinicius Zimmermann; Lucas dos Santos Linares; Victor Moreira Cannavon; Juan M. Bolivar; Roberto Fernandez-Lafuente; Rafael C. Rodrigues (Innovative Food Science & Emerging Technologies, 2026)

Lung deposition, health risks, and composition of PM2.5 collected in an industrial area in Southern Brazil - Camila N. Farias; Gabriel D. Barp; Eduardo Karnopp; Katarina O. Rodrigues; Marcos A. Hortellani; Jéssica C. Santos-Silva; Jorge E.S. Sarkis; Mariane Bonatti-Chaves; Sandra H.W. Medeiros; Pérola C. Vasconcellos (Atmospheric Pollution Research, 2026)

Synthesis and application of silver-doped glass waste pellets for drinking water treatment - J. S. C. Vieira; J. D. A. do Ano; A. R. Pereira; A. da Costa Reis; F. W. Carvalho; I. A. da Silva; M. R. de Melo Rodrigues; E. M. V. de Carvalho; D. L. P. Macuvele; G. J. Muchave (International Journal of Environmental Science and Technology, 2026)

The emergence of pathogens on fish in an impacted estuary and the role of non‐native piranhas in a potential bacterial infectious outbreak - Ryan Andrades; Helder C. Guabiroba; Kathiani V. Bastos; Vítor L. A. Rodrigues; Marcelo R. D. Santos; Clarisse M. Arpini; Mayra Cunha Flecher; Helen A. Pichler; Ciro C. Vilar; Maurício Hostim‐Silva; Jean‐Christophe Joyeux (Journal of Fish Biology, 2026)
As many tropical aquatic ecosystems worldwide, the Doce River estuary (DRE, southeastern Brazil) has increasingly faced multiple anthropogenic threats, including deforestation, mining, species introduction and water management. The 2015 collapse of the Fundão iron ore tailings dam severely changed water properties and increased heavy metal concentration in sediment. However, the potential synergistic effects of the observed threats on fish populations remain largely unknown. After detecting an elevated number of fin lesions in DRE fishes, we used the catfish Genidens genidens (Cuvier, 1829) to investigate whether such mutilations originated from fin‐nipping by non‐native piranha or emerged as a result of fin rot disease through bacterial infection. One third of the examined individuals had fin lesions in the DRE, whereas no conspecific exhibited such lesions in two control estuaries where piranhas are absent; lesions were restricted to the caudal fin, a region known to be targeted by fin‐nipping piranhas. Independently of the presence of fin lesion, culture of fins and livers indicated higher prevalence and variety of bacterial strains in DRE individuals than in a control area. Piranhas likely contribute to the fin lesions in DRE fishes. However, the higher prevalence and variety of bacterial pathogens as well as of liver and kidney disorders identified in fin‐healthy and mutilated fishes of the DRE suggest that the heavily metal‐polluted conditions in the DRE may be associated with the emergence of bacterial infections in fish.

Dry–Hot Compound Events Driving the 2024 Pantanal Wildfires - Liz B. C. Belém; Ronaldo Albuquerque; Leonardo F. Peres; Filippe L. M. Santos; Julia A. Rodrigues; Lucas S. Menezes; Patrícia S. Silva; Ricardo M. Trigo; Carlos C. DaCamara; Ana Russo; João Geirinhas; Geraldo A. Damasceno Junior; et al. (International Journal of Climatology, 2026)
The year 2024 was classified by the World Meteorological Organization (WMO) as the hottest on record, both globally and in Brazil. In the Pantanal, exceptional heat waves and intense droughts led to an early onset of the fire season in June, marked by high fire severity and large burned areas. Although the Pantanal has been increasingly affected by combined drought and heat events, the influence of these climatic extremes on fire activity and the associated atmospheric circulation patterns is not well understood. This study assesses the conditions prior to the fire and the simultaneous occurrence of heat waves and droughts based on satellite data and climate indices; 2024 was identified as the most severe drought year over the 1980–2024 period, where virtually the entire biome reached exceptional drought levels. Heat waves were accompanied by significant precipitation and soil moisture deficits, along with the absence of the flood pulse in the rivers, reinforcing the compound nature of the 2024 extreme events. Synoptic conditions revealed patterns favourable to persistent warming and intensified drought, while fire risk indices exceeded the 99th percentile. These results highlight the need for a holistic approach when analysing the climatic factors driving fires, thereby advancing understanding of compound events and supporting public policies aimed at both mitigating and adapting to the impacts of climate extremes in the Pantanal.

American Useful Plants in Post-Medieval Europe: Integrating Archaeobotanical and Historical Evidence - J. Irmišová; M. Ballesteros; J. J. Garay-Vázquez; C. Moricca; J. Skružná; T. Majerovičová; L. Speleers; S. Preiss; M. Badura; J. Wiethold; O. Brinkkemper; J. P. V. Tereso; et al. (Ethnobotany and Economic Botany, 2026)
The arrival of Europeans in the Americas in 1492 initiated new transatlantic connections that, through colonial expansion and trade networks, brought useful plants to Europe. This study investigates archaeobotanical and historical evidence for the introduction of American plants to Europe from the late fifteenth to the twentieth century. We compiled 183 archaeobotanical records from 14 countries, representing 24 taxa from 11 botanical families. We examined which American plant species were introduced to Europe during the post-medieval period, and how their uses and significance varied across regions and social contexts. Archaeobotanical data indicate that early introductions occurred predominantly in elite secular and ecclesiastical settings across Europe. Historical sources identify Spain as the first entry point, though other European countries yielded more records. The large number of archaeobotanical finds in the Netherlands and at the Habsburg court in Prague reflects the current state of research, site coverage, preservation, and data accessibility. The significance of these plants in Europe was shaped by economic value, prestige, ritual use, and medicinal properties. Our study highlights the importance of integrating archaeobotanical and historical sources and provides the most comprehensive account to date of material evidence tracing the cultural trajectories of American plants in Europe.

Chemical and Bioactivity Profiling of the Invasive Macroalga Rugulopteryx okamurae Collected in Southern Portugal Supporting Biotechnological Valorisation Approaches - Amandine D’Unienville; Lucas Lasnel; Wadi Macquigneau; Riccardo Trentin; Adriana C. S. Pais; Maria João Rodrigues; Sónia A. O. Santos; Luísa Custódio (Journal of Marine Science and Engineering, 2026)
The invasive brown macroalga Rugulopteryx okamurae has rapidly expanded across the Mediterranean–Atlantic region, generating severe ecological impacts. Nevertheless, the considerable amount of biomass available creates opportunities for valorisation within circular bioeconomy frameworks. This study provides an integrated characterization of the chemical profile and bioactivities of freshly collected floating biomass of R. okamurae from southern Portugal. Proximate composition was determined, and lipophilic (hexane) and hydrophilic (water) extracts were analyzed by GC–MS and spectrophotometric methods. Antioxidant activity was assessed using complementary radical-scavenging, reducing power, and metal-chelation assays, and enzyme inhibition was evaluated against targets associated with neurodegenerative, metabolic, and dermatological disorders. The lipophilic fraction was dominated by long-chain alkanes (≈101 mg/g extract) and sterols, particularly fucosterol (≈43 mg/g extract), but exhibited low radical-scavenging capacity (no EC50 reached in DPPH or ABTS assays), and no relevant enzyme inhibition. In contrast, the water extract contained measurable phlorotannins (6.61 mg PGE/g extract) and showed moderate antioxidant (ABTS: EC50 = 5.17 mg/mL; FRAP: EC50 = 0.78 mg/mL) and enzyme inhibition activities (BChE: IC50 = 5.17 mg/mL; tyrosinase: IC50 = 0.78 mg/mL). Compared with previous studies on R. okamurae, this work applies a systematic fractionation of biomass from southern Portugal into polar and non-polar fractions and, for the first time, correlates the resulting detailed chemical profiles with multiple bioactivities. This approach revealed a clear functional differentiation between fractions, with bioactivity being mainly associated with polar metabolites. Overall, these findings highlight the value of structured extraction strategies for biomass valorisation and support the sustainable management of R. okamurae.

How climate stressors intensify antibiotic toxicity: A histopathological study in zebrafish - Bárbara S. Diogo; Sara Rodrigues; Sara C. Antunes (Environmental Toxicology and Pharmacology, 2026)

Design and Evaluation of the Antibacterial Peptide FK18: a Therapeutic Approach for Mastitis in Dairy Animals - Tamaeh Monteiro-Alfredo; Camila de O. Gutierrez; Claudiane V. Almeida; Vinicius C. da Silva; Patrícia Gomes; Caio F. R. de Oliveira; Elisângela S. Madalozzo; Edson Crusca; Raquel M. Q. Orozco; Lucas Lima; Marlon H. Cardoso; Octávio L. Franco; et al. (Probiotics and Antimicrobial Proteins, 2026)

Targeting hypertension through natural phenolics: The multifaceted role of cinnamic acid and its derivatives - Samuel S. P. de Araujo; Brenda L. B. dos Santos; Waldilleny R. A. de Moura; Leonardo G. Rodrigues; Luiz G. S. Branco; Helio C. Salgado; Renato N. Soriano; Marina de T. Durand; João Paulo J. Sabino (Pflügers Archiv - European Journal of Physiology, 2026)

Melatonin Alleviates Aluminum Toxicity in Pfaffia glomerata by Modulating Tolerance Mechanisms - Michelle M. V. Almeida; Juliane M. Henschel; Tatiane D. Silva; Luiza E. G. Monteiro; Mateus S. Rodrigues; Tadeu R. Oliveira; Auxiliadora O. Martins; Sérgio H. S. Felipe; Evandro A. Fortini; Elyabe M. Matos; Lyderson F. Viccini; Diego S. Batista; et al. (Journal of Plant Growth Regulation, 2026)
Aluminum (Al) toxicity is the main factor limiting agricultural production in acidic soils around the world. In this scenario, melatonin (MET) has emerged as a promising approach to alleviate Al toxicity. Thus, we investigated morphophysiological responses of Pfaffia glomerata (Spreng.) Pedersen, a medicinal plant, to Al toxicity and MET application. Plants were grown in vitro for 40 days in MS medium (control) supplemented with Al, MET, and Al + MET. Aluminum had genotoxic effects, inducing DNA damages and endoreduplication, which resulted in growth arrest, mainly in roots. Al also decreased the photosynthetic rate and the contents of pigments, carbohydrates, amino acids, and proteins. On the other hand, all these effects were improved in plants supplemented with MET. This is supported by the up-accumulation of proteins involved in organic acids exudation (AHA2), photosynthesis (transketolase, rubisco activase, and photosystem I P700 apoprotein A2), amino acid biosynthesis (chorismate synthase 1 and aspartokinase/homoserine dehydrogenase), and cell expansion and differentiation (rough sheath 2, beta tubulin b6, and tubulin beta chain-like). Moreover, MET enhanced CAT, SOD, and GABA, reinforcing its antioxidant role and reducing DNA damage and endoreduplication, which preserved QC identity and root elongation. Al toxicity impaired growth and carbon–nitrogen metabolism, whereas MET mitigated these effects by boosting photosynthesis, antioxidant defenses, and Al sequestration, decreasing Al adherence to roots. Thus, MET serves as a protective molecule against Al toxicity in P. glomerata .

Cu(I)-N-Heterocyclic carbenes as potent inhibitors of SARS-CoV-2 replication - Igor Andrade Santos; Josielle V. Fontes; Gustavo C. Rodrigues; Mariana Ortiz de Godoy; Glaucius Oliva; Rafael V. C. Guido; Andres Merits; Camilla Abbehausen; Mark Harris; Ana Carolina Gomes Jardim (BioMetals, 2026)

Hypothalamic Atrophy and Textural Changes in Polyglutamine Ataxias - Livia Rodrigues; Thiago J. R. Rezende; Alberto R. M. Martinez; Breno Massuyama; Jose Luiz Pedroso; Orlando G. P. Barsottini; Juan Eugenio Iglesias; Simone Appenzeller; Letícia Rittner; Marcondes C. França (The Cerebellum, 2026)
Background. Spinocerebellar ataxia (SCA) presents a complex genetic landscape, with over 40 subtypes. These autosomal dominant disorders manifest late onset and severe disability, primarily impacting the cerebellum but also involving other nervous system structures. While a single study has linked hypothalamic atrophy to SCA3, further research is needed to confirm and/or expand this association. This study aimed to investigate hypothalamic involvement in PolyQ SCAs, focusing on SCA 1, 2, 3, and 6. Methods. We studied 135 adult patients with genetically confirmed SCA (SCA1, SCA2, SCA3, and SCA6) and 117 healthy controls. Hypothalamic subregions were segmented using H-SynEx, and both volumetric and texture features were extracted from MR images. Group differences were assessed with the Mann–Whitney U test, and associations with disease duration and severity (measured by SARA) were examined using Spearman’s rank correlation. Results. Significant atrophy of hypothalamic subregions was observed in SCA1, SCA3, and SCA6 when compared with controls, with the anterior subregion being affected in all cases. Texture analysis revealed widespread alterations in SCA1, SCA3, and SCA6 across all subregions. In SCA1 and SCA3, both volumetric and texture measures correlated with disease duration and SARA scores. These findings suggest that hypothalamic involvement in SCAs is complex and may occur before overt clinical manifestations. Key words: Ataxia, Polyglutamine disease, Hypothalamus, MRI, Volumetry

Experimental assessment of ambient gamma dose equivalent rates measured outdoors in the Republic of Benin from 2019 to 2020 - Arnaud A. Gbetchedji; Daniel S. Takou; N. Innocent Gbaï; Mahougnon B. Zinsou; Hubert C. Hounsossou; Thierry C. M. Medehouenou; Rodrigue S. Allodji (Environmental Monitoring and Assessment, 2026)

Quantification and characterization of collagen in experimentally induced wounds treated with different types of platelet-rich plasma gel - G. Haro de Melo; F. M. Moreira; G. G. Mori; L. F. Bento; D. V. Barrionuevo; C. B. Laposy; R. Giuffrida; A. F. F. Rodrigues; G. A. T. Ozaki; D. A. F. da Silva; F. L. Pacagnelli; R. M. B. Nogueira (Cell and Tissue Banking, 2026)
Due to its high concentration of growth factors, platelet-rich plasma (PRP) has become the subject of much research, either as an isolated or adjuvant treatment for wound repair. The fractal dimension has been used as an innovative method for the characterization and quantification of tissue structural alterations without any interference from the evaluator. The objective of this study was characterizing collagen types I and III in experimentally induced wounds and treated with different PRP sources by means of fractal dimension and other histological analyzes using blades stained with picrocirius-red and hematoxylin-eosin (HE). In statistical analysis, the variables presented a non-parametric distribution; thus, Mann-Whitney and Kruskall-Wallis tests ( p < 0,05) were performed using the Student-Newman-Keuls method. It was observed an increase of the collagen fibers by measuring the area with Threshold Color in the different treatments, especially with autologous PRP ( p = 0.009) and heterologous PRP ( p = 0.016). The fractal dimension of type I collagen had a significant increase for the autologous group ( p = 0.028) in relation to the control, but, on average ( p < 0.05), type III collagen was higher than type I. Fractal dimension was efficient to separately characterize type I and type III collagen fibers. In this study, collagenization was higher in autologous when compared to heterologous and homologous PRP treatments.

Forest residue removal undermines soil health and micronutrient transfer to trees, compromising sustainable productivity of Eucalyptus plantations - Antonio L. Florentino; Nariane de Andrade; Nikolas S. Mateus; Bruna E. Schiebelbein; Adam C. Rodrigues; Liamara S. Masullo; Alexandre V. Ferraz; Eduardo Mariano; Fernando D. Andreote; Carlos E.P. Cerri; Maurício R. Cherubin; Timothy R. Filley; et al. (Soil and Tillage Research, 2026)

Determinants of L-band backscatter in dry tropical ecosystems: Implications for biomass mapping - João M.B. Carreiras; Thomas Higginbottom; John L. Godlee; Sam Harrison; Lorena Benitez; Penelope J. Mograbi; Aurora Levesley; Karina Melgaço; David Milodowski; Georgia Pickavance; Geoff Wells; Edmar Almeida de Oliveira; et al. (Remote Sensing of Environment, 2026)

Behavioural drivers of on-farm biosecurity implementation in livestock: A literature overview with insights for research - Mehmet Murat Dogusan; Helena C. De Carvalho Ferreira; Sebastián Jesús Moya Durán; Lidiia Moskalenko; Marnie Louise Brennan; Daniele De Meneghi; Maria Rodrigues Da Costa; Giovanna Ciaravino; Rui Gaspar (Preventive Veterinary Medicine, 2026)

Diameter, height, and volume as macroscopic predictors of photocarcinogenesis in UV-induced SKH1 papules - Mehdi Boostani; Alaina F. Carman; Erin C. Tracy; Sean P. Murphy; Rhea Carmel Glen Rodrigues; Katalin Ferenczi; Gillian Weston; Olayemi Sokumbi; Gyorgy Paragh; Wendy J. Huss (Journal of Photochemistry and Photobiology B: Biology, 2026)

Corrigendum to “Microplastic pollution across the Brazilian coastline: Evidence from the MICROMar project, the largest coastal survey in the Global South” [Environ. Res. 286, Part 2, (2025) 122923] - Thiarlen Marinho da Luz; Rafaela Ribeiro de Brito; Raíssa de Oliveira Ferreira; Ariane Guimarães; Bárbara Beatriz da Silva Nunes; Aline Sueli de Lima Rodrigues; Abraão Tiago Batista Guimarães; Ítalo Nascimento Freitas; Stênio Gonçalves da Silva Matos; Élida Priscila Bogéa Carvalho; Juliana dos Santos Mendonça; Christine C. Gaylarde; et al. (Environmental Research, 2026)

Photoelectrocatalytic degradation of carbendazim using titanium‑tungsten oxide in a pilot-scale flow reactor - Joyce F. de Carvalho; Juliana de Almeida; Helena R. Tambelli; Ana Julia S. Rego; Maria Luiza P. da Silva; Débora N. Okamoto; Milene C. Codolo; Christiane de Arruda Rodrigues (Chemical Engineering Journal, 2026)

Layered zinc hydroxide–dipeptide hybrid integrated into silk-based 3D scaffolds aiming for biomedical applications - Denise Eulálio; Mariana Pires Figueiredo; Simone S. Silva; Luísa C. Rodrigues; Emanuel M. Fernandes; Albino Martins; Albina Franco; Diana Soares da Costa; Richard Landers; Fabrice Leroux; Christine Taviot-Gueho; Dalva Lúcia Araújo de Faria; et al. (Applied Clay Science, 2026)

Synthetic cannabinoids in hair: a review of recent findings and analytical methods by LC-MS/MS - Rafaela S. Pereira; Olívia B.O. Moreira; Marcone Augusto L. de Oliveira; Claudiane C. Canuto; Diogo O.C. Lemos; Lucas M. Duarte; Silvana V. Rodrigues (Analytica Chimica Acta, 2026)

Sulfated polysaccharides from Caulerpa sertularioides promote bone regeneration in hMSC-WJ and zebrafish models - Victor M. Rodrigues; Pablo F.F. Farias; Augusto M. Souza; Ana C. Luchiari; Hugo A.O. Rocha; Susana M.G. Moreira (Algal Research, 2026)

Microplastic pollution in Brazil's coastal marine surface waters: The first macroregional baseline from the global south - Thiarlen Marinho da Luz; Rafaela Ribeiro de Brito; Raíssa de Oliveira Ferreira; Ariane Guimarães; Bárbara Beatriz da Silva Nunes; Aline Sueli de Lima Rodrigues; Abraão Tiago Batista Guimarães; Ítalo Nascimento Freitas; Stênio Gonçalves da Silva Matos; Élida Priscila Bogéa Carvalho; Juliana dos Santos Mendonça; Christine C. Gaylarde; et al. (Marine Pollution Bulletin, 2026)

Pixel-level detection and classification of marine oil spills in aerial imagery with annotation uncertainty handling - Luiz G.C. Tavares; Wesley L. Passos; Bruno C. Martins; Mauricio de P. Rodrigues; Eduardo A.B. da Silva; Sergio L. Netto (Marine Pollution Bulletin, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Acute UV response of early erythema and late edema in SKH1 mice - Szabolcs Bozsányi; Rhea Carmel Glen Rodrigues; Ruby Acquah; Erin C. Tracy; Sean P. Murphy; Jocelyn Tracy; Li Yan; Mehdi Boostani; Hamid-Reza Rezvani; Wendy J. Huss; Gyorgy Paragh (Journal of Photochemistry and Photobiology B: Biology, 2026)

Advancing eutrophication mitigation through nature-based and hybrid solutions: A systematic review - Rafaela R. Morelato; Fernando Rodrigues-Silva; Guenther Carlos C. Viana; Camila C. Amorim (Journal of Environmental Chemical Engineering, 2026)

Cork stripping alters the seasonal carbon allocation patterns of Quercus suber in a dry year - Clara A. Pinto; Filipe Costa-e-Silva; Alexandra C. Correia; José Graça; Olfa Zarrouk; Teresa S. David; José C. Rodrigues; João S. Pereira; Maria Manuela Chaves; Carla Pinheiro (Forest Ecology and Management, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Effects of artificial shading on nest incubation and sex-ratio of Caretta caretta in Boa Vista Island, Cabo Verde - Sara Rodrigues; Sara Teles; Adolfo Marco; Sara C. Antunes (Marine Biology, 2026)

Dual drug co-encapsulation into liposomes and liposome-derived nanosystems for improved synergistic treatment of skin diseases - Sara Rodrigues; Francisco Veiga; Ana Cláudia Paiva-Santos; Patrícia C. Pires (Drug Delivery and Translational Research, 2026)

Uncertainty analysis of a CFD solver for predicting ship motions in head waves - M.I.P. Rodrigues; S. Wang; H. Islam; H.S. Abdelwahab; Jialong Jiao; C. Guedes Soares (Ocean Engineering, 2026)

Protected areas influence fire regimes globally - A. Cardil; M. Rodrigues; D. Ascoli; M. Ortega; T. Quiñones; M. Erdozain; I. Oliveras Menor; G.L. Spadoni; J. Ramírez; J.R. Molina; F. Mouillot; C.A. Silva; et al. (Journal of Environmental Management, 2026)

Tackling CECs and antimicrobial resistant bacteria in hospital wastewater using biological and AOP hybrid technologies - Eloísa Stéphanie da Silva; Alessandra S. Martins; Lara Fabian S. Ribeiro; Jhonatha Rodrigo Cordeiro-Moura; Daniel A.S. Rodrigues; Renata Cristina Picão; Maria Clara V. M. Starling; Camila C. Amorim (Bioresource Technology, 2026)

Hemocyte Apoptosis as a Biomarker of Environmental Stress in Aeglid Species (Decapoda: Anomura) - Renan A. P. dos Santos; Graziela G. Romagnoli; George S. Yasui; Isabela R. R. Moraes; Mariana V. Capparelli; Gabriel F. B. Rodrigues; Larissa R. C. de Oliveira; Antonio L. Castilho (Bulletin of Environmental Contamination and Toxicology, 2026)

Fine-scale patterns and drivers of ploidy state in lentic and lotic macrophyte assemblages across the world - Tatiana Lobato-de Magalhães; Kevin Murphy; Thomas A. Davidson; Jorge García-Girón; Andrey Efremov; Victor Chepinoga; Eugenio Molina-Navarro; Celeste Franceschini; Roger P. Mormul; Hui Fu; Rossano Bolpagni; Juri Nascimbene; et al. (Aquatic Botany, 2026)

All Reforestation Methods Can Support Tropical Tree Diversity Recovery, but Drivers and Species Composition Vary - Laura E. Boeschoten; Joannès Guillemot; Juliano van Melis; Lourens Poorter; Ricardo R. Rodrigues; Frans Bongers; Paulo G. Molin; Marielos Peña‐Claros; Vinicius C. Souza; Cássio A. P. Toledo; Patrick Faria Fernandes; Marcelo P. Ferreira; et al. (Global Change Biology, 2026)
Tropical landscapes are undergoing rapid transformation due to human activities and global change. Forest restoration has emerged as a key strategy to mitigate biodiversity loss and climate warming. However, a standardized assessment of how different restoration methods contribute to biodiversity recovery and conservation remains lacking. Here, we present the first comprehensive comparison of tree diversity restoration and the drivers of recovery across five main reforestation methods (naturally regenerating forests, biodiverse restoration plantings, short‐ and long‐rotation tree monocultures, agroforests) relative to three reference systems (agropastoral lands, degraded and conserved forest remnants). Tree inventories were conducted in 519 plots (900 m 2 each) across two forest types (rainforest and seasonally dry forest) in the Atlantic forest of São Paulo state, Brazil, encompassing over 39,000 trees and 869 species. We found that: (1) all reforestation methods except short‐rotation monoculture plots supported tree diversity recovery. In the rainforest, conserved remnant plots maintained the highest average Shannon diversity (Hill 1 = 29 ± 14), while naturally regenerating forests and restoration plantings approached the diversity of degraded remnant plots (15 ± 5). In seasonally dry forest, biodiverse restoration plantings and agroforests reached diversity levels comparable to conserved remnants (15 ± 6). Additionally, (2) recovery was influenced by forest age, climate (water availability), soil fertility, and landscape context, though the relative importance of these factors varied by method. Climate and landscape context were more influential for recovery in naturally regenerating forests, while soil conditions played a greater role in biodiverse restoration plantings. Lastly, (3) species composition in naturally regenerating forests most closely resembled that of conserved remnants. Conversely, restoration plantings and agroforests exhibited high compositional overlap across sites, reducing overall species richness. Our findings underscore the wide variation in biodiversity outcomes among and within reforestation methods, emphasizing that goals and strategies must align with local conditions to maximize benefits in complex tropical landscapes.

Why marine gammarids belong to the future portfolio of aquafeed ingredients - Ricardo Calado; Marta Carvalho; Luísa Marques; Daniela P. Rodrigues; João P. Sousa; Felisa Rey; Maria Rosário Domingues; Joana Filipa Fernandes; Ruben X. G. Silva; Diana Madeira; Arne M. Malzahn; Óscar Monroig; et al. (Frontiers in Marine Science, 2025)
The sustainable supply of n-3 long-chain polyunsaturated fatty acids ( n -3 LC-PUFA) remains a major challenge for global aquaculture. Although plant oils, microalgae, genetically modified crops, insects, krill, and fish by-products have been explored as alternative sources, none currently provides a stand-alone solution for meeting the growing demand of n -3 LC-PUFA in aquafeeds’ production. Here, we present marine gammarids as a potential complementary source of these fatty acids. Our Perspective article focuses on the nutritional attributes of marine gammarids, including their naturally high levels of eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), and considers their biological traits that support aquaculture practicality. We also examine the potential of marine gammarids for circular bioeconomy applications through trophic upgrading of low-value side streams. While evidence from feeding trials is limited, preliminary data suggest marine gammarids may maintain their high EPA and DHA content even when fed on low-quality diets. Critical research priorities include developing scalable production systems, optimising feed formulations, evaluating performance across key aquaculture species, and assessing ecological and operational feasibility. This Perspective also highlights the potential of marine gammarids to contribute to a diversified and resilient aquafeed portfolio. Although they are unlikely to replace fish meal or fish oil entirely, marine gammarids may serve as a strategic complementary ingredient.

Interaction between diagenesis and faulting in sandstone reservoirs: Inferences from the Groningen gas field - Job P.B. Arts; Dallyn Rodrigues; Fadi H. Nader; Martyn R. Drury; Liviu C. Matenco; Ernst Willingshofer; André R. Niemeijer (Journal of Structural Geology, 2025)

Individual and combined effects of a simulated heatwave and the emerging Phytophthora ×multiformis on European alder species - I. Gomes Marques; C. Vieites-Blanco; M.J. Barrento; A. Cupertino; J.N. Semedo; A.P. Rodrigues; P. Scotti-Campos; T. Jung; A. Solla; T.S. David; P.M. Rodríguez-González (Forest Ecology and Management, 2025)

Valorisation of olive oil by-products into pectic- and glucuronoxylo-oligosaccharides via one-step fermentation - Ana Cordeiro; Andreia Fernandes; Andreia S. Ferreira; Elisabete Coelho; Manuel A. Coimbra; Sara C. Silvério; Vasco Cadavez; António M. Peres; Lígia R. Rodrigues; Cláudia Amorim (Food Chemistry, 2025)

Microplastic pollution across the Brazilian coastline: Evidence from the MICROMar project, the largest coastal survey in the Global South - Thiarlen Marinho da Luz; Rafaela Ribeiro de Brito; Raíssa de Oliveira Ferreira; Ariane Guimarães; Bárbara Beatriz da Silva Nunes; Aline Sueli de Lima Rodrigues; Abraão Tiago Batista Guimarães; Ítalo Nascimento Freitas; Stênio Gonçalves da Silva Matos; Élida Priscila Bogéa Carvalho; Juliana dos Santos Mendonça; Christine C. Gaylarde; et al. (Environmental Research, 2025)

Deep-sea ecosystems of the North Atlantic Ocean: discovery, status, function and future challenges - A. Louise Allcock; Diva J. Amon; Amelia E.H. Bridges; Ana Colaço; Elva Escobar-Briones; Ana Hilário; Kerry L. Howell; Nélia C. Mestre; Frank E. Muller-Karger; Imants G. Priede; Paul V.R. Snelgrove; Kathleen Sullivan Sealey; et al. (Deep Sea Research Part I: Oceanographic Research Papers, 2025)

Soil–climate interactions drive above-ground biomass in the Caatinga, the largest Neotropical seasonally dry tropical forest - Alexandre T. Brunello; Domingos Cardoso; Peter W. Moonlight; Ítalo A. C. Coutinho; John Cunha; Mário M. do Espírito Santo; Magna S. B. de Moura; Luciano P. de Queiroz; Rubens M. dos Santos; Tiina Särkinen; Raquel C. Miatto; Tony C. de S. Oliveira; et al. (Plant and Soil, 2025)

Soil carbon dynamics, nutrient enhancement, and maize productivity under traditional cattle corralling practices in northern Benin - Awouminassi M. Atakoun; Pierre G. Tovihoudji; Rodrigue V. C. Diogo; William Amponsah; Murilo dos Santos Vianna; Thomas Gaiser; Nicholas Kyei-Baffour; Boateng Kyereh (Nutrient Cycling in Agroecosystems, 2025)

Harnessing organoid technology to model autoimmune pathways in rheumatological and inflammatory disorders - Amr Ali Mohamed Abdelgawwad El-Sehrawy; Teeba Ammar Rashid; Paul Rodrigues; Baneen C. Gabaal; Suhas Ballal; Abhayveer Singh; T. KRITHIGA; Mehul Manu; N. Esanmurodova; Jamal K. Abbas (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Barcoding the Caatinga biome bees: a practical review - Pedro Rodrigues; Cláudia Teixeira; Laura Guimarães; Nuno G. C. Ferreira (Molecular Biology Reports, 2025)
Bees play a critical role as pollinators in ecosystem services, contributing significantly to the sexual reproduction and diversity of plants. The Caatinga biome in Brazil, home to around 200 bee species, provides an ideal habitat for these species due to its unique climate conditions. However, this biome faces threats from anthropogenic processes, making it urgent to characterise the local bee populations efficiently. Traditional taxonomic surveys for bee identification are complex due to the lack of suitable keys and expertise required. As a result, molecular barcoding has emerged as a valuable tool, using genome regions to compare and identify bee species. However, little is known about Caatinga bees to develop these molecular tools further. This study addresses this gap, providing an updated list of 262 Caatinga bee species across 86 genera and identifying ~ 40 primer sets to aid in barcoding these species. The findings highlight the ongoing work needed to fully characterise the Caatinga biome’s bee distribution and species or subspecies to support more effective monitoring and conservation efforts.

Reactive Oxygen Species Regulation Across Retinitis Pigmentosa Animal Models: A 25-Year Systematized Review - Rafael de Freitas Azevedo-Repossi; Rafael Brito; Marcelo Cossenza; Alexandre dos Santos-Rodrigues; Gustavo Costa Ferreira; Hilda Petrs-Silva; Karin C. Calaza; Lucianne Fragel-Madeira (Molecular Neurobiology, 2025)

Geological and geomechanical properties of soft rocks from the Lower Jurassic Vale Das Fontes Formation (Lusitanian Basin, Portugal): an exploratory study - P. F. Moreira; C. F. Rodrigues; L. V. Duarte; J. P. Temporão de Sousa; A. Vega y de La Fuente; A. Maldonado-Zamora; M. J. Lemos de Sousa; H. I. Chaminé (Mediterranean Geoscience Reviews, 2025)

Evaluation of Chlorella vulgaris application as a biostimulant for lettuce growth in soilless culture - J. Vieira; M. Saque; F. Gama; C. Viana; L. Coelho; M. H. Rodrigues; J. Varela; H. Pereira; P. Palencia; M. Reis; M. Pestana; P. J. Correia (Journal of Applied Phycology, 2025)

Green infrastructure for urban climate mitigation and adaptation: methods, strategies, and typology selection based on ecosystem services - B. N. Rodrigues; A. L. F. Favoreti; V. E. Molina Júnior; C. M. Silva; F. B. Canteras (International Journal of Environmental Science and Technology, 2025)

SpiderATLAS : A Database of Spider Traits and Distributions in the Brazilian Atlantic Forest - Gabriel X. Boldorini; Paulo M. Martins; Antonio D. Brescovit; Adalberto J. Santos; Leonardo S. Carvalho; Ubirajara Oliveira; Philip Russo; Joyce C. B. Brito; Aparecida P. Barbosa; André Celso Bezerra Rodrigues; Aníbal Silva Cantalice; Arthur A. B. Rodrigues; et al. (Journal of Biogeography, 2025)
Aim Biodiversity shortfalls related to limited knowledge about geographic distribution (Wallacean) and species traits (Raunkiæran) are extremely common in many animal groups and perhaps more evident in invertebrate groups such as spiders. This lack of knowledge could present challenges for researchers investigating the response and effects of spiders along large spatial scales, particularly in the Global South. The aim of the SpiderATLAS is to facilitate research that links macroecology, biogeography, trait‐based ecology and global change biology. Location Brazilian Atlantic Forest, spanning virtually the entire eastern coastline of Brazil, encompassing 1,620,000 km 2 , 30 degrees of latitude (3° 42′ S to 33° 31′ S), and 22 degrees of longitude (34° 50′ W to 56° 45′ W). Taxon Spiders (Class Araneae), including 1648 species from 63 families. Methods We compiled the spatial distribution (i.e., occurrence data) and data on morphological characteristics and derived traits for spider species from species descriptions, taxonomic revisions and personal collection. Species occurrences were extracted from several data sources spanning from the 1880s to 2023. Data on the morphological traits of species were compiled from taxonomic and diversity inventory papers published between 1833 and 2024. Results We provide 9369 georeferenced point locations and six morphological traits (body length, prosoma length, prosoma width, prosoma height, femur I length, and patella I length) for 1648 spider species. Most data are available for females and males. The dataset and code are available to download from Dryad, World Spider Trait database, and the ZooTraits app. Main Conclusions The SpiderATLAS can be useful to access information on the distribution and traits of spiders, contributing to the development of macroecological, biogeographical and trait‐based ecology. This dataset can also facilitate the biodiversity conservation of one of the most abundant and important arthropod predators on the planet, in a biodiversity hotspot.

Under pressure: Daphnia magna’s responses to 4-chloroaniline exposure and climate-induced temperature rise - Daniela Rebelo; Sara C. Antunes; Sara Rodrigues (Environmental Science and Pollution Research, 2025)

Combining wood traits as a promising timber origin verification and its application in the Brazilian trade chain - Bruna Hornink; Daigard Ricardo Ortega-Rodriguez; Deoclecio J. Amorim; Peter Groenendijk; Kathelyn Paredes-Villanueva; José Guilherme Roquette; Ana Carolina M.C. Barbosa; Edson Vidal; Alexandre Bahia Gontijo; Monique S. Costa; Norma Rodrigues Nunes de Senna; Davi Neves de Lemos; et al. (Science of The Total Environment, 2025)

Ultrasound-enhanced bioaccessibility and pharmacological activities of curcumin in inclusion complexes - Matheus X. Oliveira; Irisvan S. Ribeiro; Francisca Vanessa C. Canafístula; Stephanie Ferreira M. Muniz; Lorena Maria F. Sampaio; Alyne Rodrigues A. Nobre; Fábio Oliveira S. Ribeiro; Raí E. Silva; Jessica Maria T. Souza; Erick Joniher B. Torres; José Delano Barreto M. Filho; Ana J. Araújo; et al. (Food Chemistry, 2025)

Corrigendum to “From waste to bioactive compounds: A response surface methodology approach to extract antioxidants from Pistacia vera shells for postprandial hyperglycaemia management” [Food Chem. 443 (2024) 138504] - Anna Elisabetta Maccarronello; Nunzio Cardullo; Ana Margarida Silva; Antonella Di Francesco; Paulo C. Costa; Francisca Rodrigues; Vera Muccilli (Food Chemistry, 2025)

Superionic conductor glass-ceramics for lithium extraction from aqueous solution - João Felipe Pierdoná; Laís P. Caminata; Antonio C. Hernandes; Guilherme Zepon; Ana C.M. Rodrigues; Juliana M.P. Almeida (Desalination, 2025)

Impact of geometry parameters of packed-bed reactor on continuous orange juice clarification using pectinase immobilized on genipin-activated chitosan beads - Vinícius Zimmermann; Eli Emanuel Esparza-Flores; Carolina Pedroso Partichelli; Vitor Manfroi; Rafael C. Rodrigues (Biocatalysis and Agricultural Biotechnology, 2025)

The use of electrodialysis for the removal of metals from aqueous solutions - C. L. S. dos Santos; M. S. Rodrigues; F. S. Moreira; V. L. Cardoso; M. M. de Resende (International Journal of Environmental Science and Technology, 2025)

Metabolomic profiles and antioxidant intake in female soccer players: a cross-sectional study - M. M. S. Gouveia; M. B. A. Nascimento; A. C. Crispim; E. R. da Rocha; M. P. P. Santos; E. S. Bento; T. M. Aquino; P. Balikian; N. A. Rodrigues; T. Ataide-Silva; G. G. de Araujo; F. A. B. Sousa (European Journal of Applied Physiology, 2025)

The Functional Role of Specific Habitats for the Daily Routine of Juvenile Spoonbills in Protected Coastal Wetlands - Manuela S. Rodrigues; Pedro M. Araújo; Jaime A. Ramos; Pedro C. Rodrigues; Afonso D. Rocha; João P. Silva; José A. Alves (Estuaries and Coasts, 2025)
Wetlands are decreasing globally and species that depend on these habitats must adjust their behaviour or may face population declines. Protected wetlands designed for the conservation of certain species may fail to meet their objectives if habitats critical for specific behaviours are degraded, even if other habitats remain unaffected. It is therefore important to better understand the functional role of specific coastal wetland habitats and when species need them. We investigated the behaviour of juvenile spoonbills ( Platalea leucorodia ) from two Portuguese protected wetlands: the Tagus estuary and Ria Formosa coastal lagoon. Forty-four juvenile spoonbills were equipped with GPS/GSM tags with a 3-axial accelerometer, which allowed integrating spatially explicit behaviour with land use data. We then explored how habitat use changes with diel and tidal cycles within these dynamic landscapes and assessed the functional role of habitats. Juvenile spoonbills vary their daily routines according to the composition of habitats in their natal wetland, with the diel cycle being more influential in the Tagus estuary, while in Ria Formosa both cycles (diel and tidal) were of similar relevance. Habitats were used differently within the study areas: intertidal flats accounted for 62.09% of feeding activity in Ria Formosa versus 47.16% in the Tagus estuary, where rice fields represented the highest feeding percentage (52.27%). This work highlights the need for species- and site-specific studies and can serve as a template for understanding habitat use by other species (or different life stages) to support the development of targeted conservation measures.

Ecotoxicological impacts of caffeine on Daphnia magna: insights from acute to chronic exposures - Sara Rodrigues; Cláudia Gonçalves; Oksana Golovko; Sara C. Antunes (Ecotoxicology, 2025)
Caffeine (CAF), a widely consumed central nervous system stimulant, has been detected in aquatic ecosystems, and several studies show that CAF affects non-target organisms. Although some ecotoxicological studies on CAF and aquatic organisms already exist, they mostly focus on marine organisms with concentrations relevant to those ecosystems. Thus, this study evaluated the ecotoxicological effects of CAF on Daphnia magna through four tests: acute exposure (48 h; 27–3000 mg/L; immobilization/mortality parameters), feeding inhibition assay evaluating immobilization/mortality parameters (24 h; 249–1000 mg/L), sub-chronic (10 days; 3.8–60 mg/L), and chronic (21 days; 4.6–35 mg/L) exposures, assessing life history parameters (age at first reproduction, fecundity, somatic growth rate, population growth rate, and reproductive output). In all assays, biochemical parameters like antioxidant defence biomarkers, lipid peroxidation, and cholinergic neurotransmission were evaluated. The results showed that CAF exposure caused feeding inhibition (EC 50 = 323 mg/L), reduced somatic growth and fecundity (CAF ≥ 10 mg/L; p < 0.05), and induced changes in antioxidant defences (CAF ≥ 10 mg/L; p < 0.05) and acetylcholinesterase activity (CAF ≥ 60 mg/L; p < 0.05). These findings demonstrate that CAF induces toxic effects in D. magna , compromising key biological functions like growth, reproduction, and metabolic pathways, highlighting the need to monitor CAF residues found in aquatic environments. Moreover, these results offer critical data for environmental regulation, as the assessed parameters showed sensitivity in evaluating caffeine toxicity in freshwater organisms.

Behavioral, regenerative, and reproductive responses of Girardia tigrina to imidacloprid exposure - Aline Arantes de Oliveira; Thays Millena Alves Pedroso; Andreia C. M. Rodrigues; Daniela de Melo e Silva; Renato Almeida Sarmento; Suzana Maria Loures de Oliveira Marcionílio; Hellem Victoria Ribeiro dos Santos; Aline Silvestre Pereira Dornelas; Althiéris de Souza Saraiva (Ecotoxicology, 2025)

Chemical profile of extracts from wild and farmed Chondrosia reniformis sponges - Maria João Nunes; Despoina Varamogianni-Mamatsi; Vanda Marques; Thekla I. Anastasiou; Eirini Kagiampaki; Emmanouela Vernadou; Thanos Dailianis; Nicolas Kalogerakis; Luís C. Branco; Cecília M. P. Rodrigues; Rita G. Sobral; Manolis Mandalakis; et al. (Aquaculture International, 2025)

Ancient Introgression Explains Mitochondrial Genome Capture and Mitonuclear Discordance Among South American Collared Tropidurus Lizards - Matheus M. A. Salles; André L. G. Carvalho; Adam D. Leaché; Nicolas Martinez; Frederick Bauer; Martha Motte; Viviana Espínola; Miguel T. Rodrigues; Carla Piantoni; Marcio R. Pie; André Olivotto; Guarino R. Colli; et al. (Molecular Ecology, 2025)
Mitonuclear discordance—evolutionary discrepancies between mitochondrial and nuclear DNA phylogenies—can arise from various factors, including introgression, incomplete lineage sorting, recent or ancient demographic fluctuations, sex‐biased dispersal asymmetries, among others. Understanding this phenomenon is crucial for accurately reconstructing evolutionary histories, as failing to account for discordance can lead to misinterpretations of species boundaries, phylogenetic relationships, and historical biogeographic patterns. We investigate the evolutionary drivers of mitonuclear discordance in the Tropidurus spinulosus species group, which contains nine species of lizards inhabiting open tropical and subtropical environments in South America. Using a combination of population genetic and phylogenomic approaches applied to mitochondrial and nuclear data, we identified different instances of gene flow that occurred in ancestral lineages of extant species. Our results point to a complex evolutionary history marked by prolonged isolation between species, demographic fluctuations, and potential episodes of secondary contact with genetic admixture. These conditions likely facilitated mitochondrial genome capture while diluting signals of nuclear introgression. Furthermore, we found no strong evidence supporting incomplete lineage sorting or natural selection as primary drivers of the observed mitonuclear discordance. Therefore, the unveiled patterns are most consistent with neutral demographic processes, coupled with ancient mitochondrial introgression, as the main factors underlying the mismatch between nuclear and mitochondrial phylogenies in this system. Future research could further explore the role of other demographic processes, such as asymmetric sex‐biased dispersal, in shaping these complex evolutionary patterns.

Myiasis-causing flies in anurans: new interactions, geographic distribution, and an updated list of records in the Neotropics - Franciele Cristina de Souza; Victor Morais Ghirotto; Alexandre Polletini Neto; Camila Saraiva dos Anjos; André Luís F. da Silva; Rodrigo Lingnau; Emeline da S. Ceccon; Cátia Antunes de Melo-Patiu †; Mirco Solé; Silionamã P. Dantas; Claudio Borteiro; Domingos de J. Rodrigues; et al. (Biologia, 2025)

Optimistic climate mitigation scenario halves projected range loss in a neotropical dolphin - Rodrigo Tardin; Guilherme Maricato; Jeremy J. Kiszka; Mauricio Cantor; Israel Maciel; Gabriel Melo-Santos; Laura May-Collado; Ana Carolina Meirelles; Maria Isabel C. Gonçalves; Fábio G. Daura-Jorge; Renata S. Sousa-Lima; Yvonnick Le Pendu; et al. (Ocean & Coastal Management, 2025)

Characterization and stability assessment of Crotalus durissus venom used in the anti-crotalic serum production - Adélia T.P. Coutinho; Patrícia C. Campos; Jaqueline L. dos Santos; Tâmara T.O. Rodrigues; Aline A. Martins; Marcos P.G. Mol; William de C. Borges; Márcia H. Borges (Toxicon, 2025)

Evaluating the efficacy of topical application of Genista tridentata (L.) (Fabaceae) leaf extract on wound healing in experimental diabetes - Inês Martins Laranjeira; Beatriz Gonçalves; Diana Rodrigues-Fonseca; Alberto C. P. Dias; Filipa Pinto-Ribeiro (Phytochemistry Letters, 2025)

Exploring Genista tridentata leaves extract: novel insights for functional food in diabetes management - Inês Martins Laranjeira; Marlene Silva; Diana Fonseca-Rodrigues; C. Gonçalves; A.C.P. Dias; F. Pinto-Ribeiro (Phytochemistry Letters, 2025)

Fault-related carbonates as evidence of continentalization during the Permian-Triassic of the Paraná Basin, Southern Brazil - P. Zacca; I.C. Rodrigues; A.M. Mizusaki; G. Cioccari; C. Urban (Journal of South American Earth Sciences, 2025)

Recovery of tree species functional composition in eucalypt plantations with natural regeneration differs among canopy strata - Laura H.P. Simões; Marielos Peña-Claros; Joannès Guillemot; Rens Brouwer; Frans Bongers; Lourens Poorter; Catherine T. de Almeida; Danilo R.A. Almeida; Miguel Cooper; Mathieu Decuyper; José G. Fernandes Neto; Matheus S. Fuza; et al. (Forest Ecology and Management, 2025)

Twelve-year residual effect of sewage sludge on the biogeochemical cycling of potentially toxic elements in tropical Eucalyptus plantation - Antonio L. Florentino; Alexandre V. Ferraz; Adam C. Rodrigues; Nikolas S. Mateus; Paulo H.S. Cardoso; Timothy R. Filley; Eduardo Mariano; José Lavres; José L.M. Gonçalves; Cassio H. Abreu-Junior (Forest Ecology and Management, 2025)

Luteal features and serum concentrations of progesterone and hCG in dairy goats submitted to estrus induction followed by intrauterine or intramuscular hCG administration - Alice L. Martins; Luana R. Côrtes; Juliana N.D. Rodrigues; Paulo Sergio C. Rangel; Ana Lucia R. e S. Maia; Felipe Z. Brandão; Luiz Gustavo B. Siqueira; Bruna W. de Freitas; Jeferson F. Fonseca (Domestic Animal Endocrinology, 2025)

Chronic toxicity of antibiotics and global warming in Danio rerio: Biomarker responses and toxicological effects - Bárbara S. Diogo; Sara Rodrigues; Bent Speksnijder; Oksana Golovko; Sara C. Antunes (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Microsynthesis, mass spectrometry data and acetylcholinesterase inhibition studies of carbamates related to the OPCW 1.A.16 Scheduled Chemicals - Diego G.R. Voris; Munique C. Jesus-Silva; Taynara Carvalho-Silva; Cíntia N. Ferreira; Monique Cardozo; Valdir F.da Veiga Junior; Alessandro B.C. Simas; Bruno G.M. Rodrigues; Isabelle K.da C. Nunes; Leandro B. Bernardo; Daniel A.S. Kitagawa; Antonio L.S. Lima; et al. (Chemico-Biological Interactions, 2025)

Exploring In Vitro Mesenchymal Stem Cell Osteodifferentiation via Vibrational Microspectroscopy: A Review - Daniela S. Bispo; Inês C. R. Graça; João A. Rodrigues; João T. S. Martins; Mariela M. Nolasco; Maria P. M. Marques; Helena I. S. Nogueira; João F. Mano; Mariana B. Oliveira; Paulo J. A. Ribeiro-Claro; Ana M. Gil (Stem Cell Reviews and Reports, 2025)
The application of vibrational microspectroscopy to the study of in vitro mesenchymal stem cells (MSC) osteogenic differentiation is a promising approach towards the understanding of the molecular processes involved in bone fabrication. Both infrared (IR) and Raman microspectroscopies have been applied, with a clear predominance of the latter. Bone marrow MSC have been the target of most studies, followed by those originating from dental/oral and adipose tissues. Interests have increasingly addressed single cell and extracellular matrix characterization at the molecular level. Most studies have focused on the characteristics and maturity of time-course mineralization, attempting to localize mineral aggregates formed onto the evolving collagen strands. Some reports have focused on time-dependent changes in protein structure and other components of extracellular matrix components. Besides spectral band examination through position, linewidth and shape, selected band ratios have proved largely informative to assess mineral species evolution and mineral-to-organic matrix interactions over time. The increasing use of multivariate analysis (or chemometrics) and machine learning strategies to detect finer spectral variations is evident, as is the promise of more recent IR and Raman variations to provide higher sensitivity and spatial resolution conditions. The label-free non-invasive nature of vibrational microspectroscopy makes it particularly promising for rapid and effective selection of suitable MSC donors, to support scale-up procedures for translation to the clinic. Some of the challenges to be faced are briefly discussed. Graphical Abstract

Addressing Critical Fungal Pathogens Under a One Health Perspective: Key Insights from the Portuguese Association of Medical Mycology - R. Sabino; F. Antunes; R. Araujo; A. R. Bezerra; J. Brandão; C. Carneiro; A. Carvalho; D. Carvalho; I. C. Conceição; F. Cota Medeiros; C. Cruz; E. Duarte; et al. (Mycopathologia, 2025)
Fungal infections have emerged as a significant public health concern, especially with the increasing incidence of severe mycoses caused by pathogens such as Aspergillus fumigatus , Candida auris , Candida albicans , and Cryptococcus neoformans . These fungi, listed as critical priorities by the World Health Organization, pose a heightened risk due to rising antifungal resistance and their severe impact on immunocompromised individuals. This article, coordinated by the Portuguese Association of Medical Mycology, highlights the importance of adopting a One Health perspective to address fungal threats comprehensively. Drawing on interdisciplinary collaboration, the association aims to foster greater awareness, improve diagnostic capabilities, and stimulate research and public health policies in Portugal but also at global level. The paper outlines key strategies for surveillance, prevention, and innovation in fungal diagnostics and therapeutics. Moreover, it emphasizes the urgent need for national coordination and international cooperation in managing fungal infections, advocating for integrative approaches that link human, animal, and environmental health. By presenting a consolidated overview of current challenges and future priorities, this work seeks to enhance preparedness and response mechanisms in the face of escalating fungal threats.

Are fish larvae contaminated before they start eating? First evidence of microplastic contamination in the yolk-sac of wild fish larvae - Sabrina M. Rodrigues; Francisca Espincho; Michael Elliott; C. Marisa R. Almeida; Sandra Ramos (Frontiers in Marine Science, 2025)
Microplastics (MPs) ingestion in wild fish during the early stages remains a field with scarce information and contradictory findings in laboratory studies. This study evaluated whether MPs contamination of larval fish stages begins at the commencement of the exogenous feeding phase and whether different species and ontogenetic development stages exhibit different profiles of MPs contamination. We assessed, for the first time, the presence of MPs in the larval stages of two species: the European sardine ( Sardina pilchardus ), a marine migrant species, and the common goby ( Pomatoschistus microps) , an estuarine resident species, inhabiting the Douro Estuary (NW Portugal). In both species, MPs were found even in the yolk-sac stage, when fish larvae still have endogenous feeding and do not actively prey on other organisms. This illustrates that fish larvae are already contaminated at a stage where the mouth is still not fully open, further indicating that MPs were not actively ingested. MPs contamination did not vary between species or throughout the ontogenetic development stages, showing similar levels of contamination and MPs contamination profiles. This novel study provides relevant insights into MPs contamination processes, showing that MPs contamination can occur early in the life cycle of fishes, from hatching onwards. Furthermore, the presence of MPs in fish larvae appears to be more dependent on the MPs that are in higher abundance in the surrounding water than fish larvae preferences or ecological guild, physical characteristics, or even the ontogenetic developmental stage.

Acid-modified titanate nanotubes for enhanced photocatalytic removal of contaminants of emerging concern in water - Guenther Carlos C. Viana; Djalma L.S. Maia; Daniel A.S. Rodrigues; Lara Fabian S. Ribeiro; Italo O. Mazali; Fernando Rodrigues-Silva; Maria Clara V.M. Starling; Thiago A. Neves; Camila C. Amorim (Journal of Water Process Engineering, 2025)

Preservation and detection of carotenoid pigments of Deinococcus radiodurans on mineral substrates under UV irradiation - Tamires Gallo; Fabio Rodrigues; Evelyn A.M. Sanchez; Fabio S. de Vicente; Veronica C. Teixeira; Evandro P. Silva; Marcia Rizzuto; Gabriel S. Teofilo-Guedes; Douglas Galante (Icarus, 2025)

Dual environmental stressors: How pH modulates antibiotic toxicity in Danio rerio? - Bárbara S. Diogo; Sara Rodrigues; Oksana Golovko; Sara C. Antunes (Environmental Toxicology and Pharmacology, 2025)

Consistent thermodynamics analysis of restrained steel columns in fire – Part 2: Application to the voxels-based Rayleigh-Ritz method - Pedro Dias Simão; João Paulo C. Rodrigues (Engineering Structures, 2025)

Consistent thermodynamics analysis of restrained steel columns in fire – Part 1: Theoretical developments for general application - Pedro Dias Simão; João Paulo C. Rodrigues (Engineering Structures, 2025)

Enteric methane emissions and thermal comfort indexes of Nellore steers in a livestock-forestry system in the Amazon biome - Alyce Monteiro; Flabiele S. Silva; Adibe L. Abdalla; Maguy Eugène; Luciano Barreto-Mendes; Renato A. R. Rodrigues; Ciro A. Magalhães; Bruno C. Pedreira (Tropical Animal Health and Production, 2025)

Supramolecular environment and androgen receptor binding of taraxerol: from molecular structure to potential bioactivity function - Lara L. G. C. Rodrigues; Vitor S. Duarte; Antônio S. N. Aguiar; Vitória A. M. Silva; Hamilton B. Napolitano; Leonardo L. Borges (Rendiconti Lincei. Scienze Fisiche e Naturali, 2025)

Application of graphene oxide incorporated into biopolymer microfibers as a novel adsorbent for removing pharmaceuticals from water - L. Pellenz; A. H. da Silva Júnior; C. R. S. de Oliveira; L. P. Mazur; L. H. I. Mei; N. M. Medeiros Rodrigues; A. A. U. de Souza; A. da Silva (International Journal of Environmental Science and Technology, 2025)

A novel approach for assessments of radiofrequency electromagnetic fields exposure in buildings near telecommunication infrastructure - Ricardo Q. de F.H. Silva; Marcio E.C. Rodrigues; Fred S.R. Pinheiro; Gutembergue S. da Silva; Marília da C. Muniz; Leonardo S. Pinto; Halysson B. Mendonça; Vicente A. de Sousa (Science of The Total Environment, 2025)

Estimating the air quality standard exceedance areas and the spatial representativeness of urban air quality stations applying microscale modelling - F. Martín; V. Rodrigues; J.L. Santiago; J. Sousa; J. Stocker; S. Janssen; R. Jackson; F. Russo; M.G. Villani; G. Tinarelli; D. Barbero; R. San José; et al. (Science of The Total Environment, 2025)

ESTIMET: Enhanced and Spatial-Temporal Improvement of MODIS EvapoTranspiration algorithm for all sky conditions in tropical biomes - Cinthia M.A. Claudino; Guillaume F. Bertrand; Rodolfo L.B. Nóbrega; Cristiano das N. Almeida; Ana Cláudia V. Gusmão; Suzana M.G.L. Montenegro; Bernardo B. Silva; Eduardo G. Patriota; Filipe C. Lemos; Jaqueline V. Coutinho; José Welton Gonçalo de Sousa; João M. Andrade; et al. (Remote Sensing of Environment, 2025)

Persistence of mcr-1-carrying E. coli in rabbit meat production: Challenges beyond long-term colistin withdrawal - Marisa Ribeiro-Almeida; Joana Mourão; Inês C. Rodrigues; André Pinto de Carvalho; Paulo Martins da Costa; Luísa Peixe; Patrícia Antunes (International Journal of Food Microbiology, 2025)

Analysis of the implementation of green-blue infrastructure for optimising recharge in coastal aquifers - Leandro Rodrigues Capítulo; Silvina C. Carretero; Samanta M. Anguiano; Carlos E. Dalto; Eduardo E. Kruse (Groundwater for Sustainable Development, 2025)

COVID-19 pandemic exacerbated food insecurity in South American countries - Carlos Frederico A. Vasconcelos-Neto; Michelle Jacob; Daniel Tregidgo; Denis Valle; Hani R. El Bizri; Sávio Marcelino Gomes; Julia E. Fa; Thais Q. Morcatty; Frederico Ozanan Barros Monteiro; Alessandra Scofield; Alessandra Matte; Willandia A. Chaves; et al. (Food Security, 2025)
The COVID-19 pandemic triggered unparalleled political, economic, and social ramifications, exacerbating global food insecurity (FI). To understand the overall impact of the pandemic and how different socio-economic groups were affected, we assessed prevalence and severity of FI in a sample of 18,997 households across seven countries in South America. We employed the Food Insecurity Experience Scale developed by the FAO. Our results showed that pre-pandemic, 4.5% of the sampled population across the entire continent faced Moderate FI, while 0.6% experienced severe FI. During the pandemic, Moderate FI increased to 16.9% (+ 12.4%), and Severe FI to 2.7% (+ 2.1%). By country, pre-pandemic households in Venezuela had the highest prevalence of Moderate FI (9.7%), with Peru experiencing the highest Severe FI frequency (1.1%). Peru had the greatest rise in Moderate (+ 23.9%) and Severe FI (+ 4.6%) during the pandemic. Low-income households, defined as those earning < 2 minimum wages per month, were most susceptible to FI. Uruguayan low-income families exhibited the most significant rise (+ 40.4%) in Moderate FI, while those in Peru experienced an increase of + 9.1% in Severe FI. This study measures the profound and far-reaching impact of the COVID-19 pandemic on FI in South America. Our findings also emphasise the critical importance of implementing effective public policy interventions to improve resilience against future shocks. This would enable policymakers to develop targeted strategies that address the immediate challenges posed by pandemics as well as laying the groundwork for a more resilient and sustainable food security landscape in the region.

Fermented brewer's spent grain as a sustainable feed ingredient impacts meagre (Argyrosomus regius) growth, intermediary metabolism, digestive enzymes, oxidative stress, and intestinal histology - T. Estevão-Rodrigues; H. Fernandes; S. Moutinho; A. Couto; I. Belo; C. Castro.; P. Pousão; J.M. Salgado; A. Oliva-Teles; H. Peres (Animal Feed Science and Technology, 2025)

Changes in community composition and functional diversity of European bats under climate change - Penelope C. Fialas; Luca Santini; Danilo Russo; Francisco Amorim; Hugo Rebelo; Roberto Novella‐Fernandez; Francisco Marques; Adi Domer; Adriana Vella; Adriano Martinoli; Aleksandra Figurek; Asaf Tsoar; et al. (Conservation Biology, 2025)
Climate change is predicted to drive geographical range shifts that will result in changes in species diversity and functional composition and have potential repercussions for ecosystem functioning. However, the effect of these changes on species composition and functional diversity (FD) remains unclear, especially for mammals, specifically bats. We used species distribution models and a comprehensive ecological and morphometrical trait database to estimate how projected future climate and land‐use changes could influence the distribution, composition, and FD of the European bat community. Future bat assemblages were predicted to undergo substantial shifts in geographic range and trait structure. Range suitability decreased substantially in southern Europe and increased in northern latitudes. Our findings highlight the potential for climate change to drive shifts in bat FD, which has implications for ecosystem function and resilience at a continental scale. It is important to incorporate FD in conservation strategies. These efforts should target species with key functional traits predicted to be lost and areas expected to experience losses in FD. Conservation strategies should include habitat and roost protection, enhancing landscape connectivity, and international monitoring to preserve bat populations and their ecosystem services.

Fatty acid profile of Gammarus locusta newly hatched offspring from the wild and from adults farmed on mono-specific macroalgal diets - João P. Sousa; Luísa Marques; Daniela P. Rodrigues; Felisa Rey; Manuel Albuquerque; Maria Rosário M. Domingues; Rafael C. Duarte; Ricardo Calado (Frontiers in Marine Science, 2025)
The accelerated growth of marine aquaculture targeting species that require formulated aquafeeds creates a pressing need to find new sustainable ingredients and additives that can secure a premium farming performance, as well as the nutritional value of farmed species. Marine gammarid amphipods can be an excellent source of essential fatty acids (FA), namely, long-chain n -3 polyunsaturated FA (LC-PUFA). However, their potential contribution to aquaculture feeds remains largely unexplored. The present work evaluated the effect of five mono-specific macroalgal diets ( Ulva sp., Fucus sp., Laminaria sp., Gracilaria sp., and Chondrus sp.) on the FA composition of the offspring of Gammarus locusta fed on these macroalgae and compared it with the offspring of wild conspecifics. Results revealed that offspring from wild G. locusta showed the highest amount of PUFA (4.95 ± 0.31 μg mg -1 DW), as well as essential FA, namely eicosapentaenoic acid (EPA, 20:5 n -3) (2.49 ± 0.21 μg mg -1 DW) and docosahexaenoic acid (DHA, 22:6 n -3) (0.87 ± 0.16 μg mg -1 DW). The treatment with the highest amount of PUFA and EPA was the one using Fucus sp. as a mono-specific macroalgal diet (4.46 ± 0.31 μg mg -1 DW and 2.42 ± 0.24 μg mg -1 DW, respectively). The best levels of DHA in offspring were recorded for specimens feeding on Chondrus sp. (0.56 ± 0.10 μg mg -1 DW). Significant differences in the abundance of stearic acid (18:0) and DHA were observed between the offspring of adults fed algal-based diets and those from the wild. These findings suggest that G. locusta selectively conserves and directly or indirectly biosynthesises essential FA for growth and reproduction, particularly LC-PUFA. Overall, G. locusta can perform a trophic upgrade of its diet, making this gammarid amphipod a promising additive for the formulation of high-quality aquafeeds supplying LC-PUFA.

Plastic contamination and lesions observed in Cory’s shearwaters (C. Borealis) from the Azores archipelago - a pilot study - M. Pinto; M. Almeida; G. Carreira; S. Garcia; C. Rodrigues (Journal of Comparative Pathology, 2025)

Survival analysis of female dogs and cats with rare and uncommon malignant mammary tumours - preliminary results - J.N. Pontes; C. Pereira; J. Rodrigues-Jesus; A. Santos; A. Catarina Figueira; S. Guedes; F. Seixas; M. dos Anjos Pires; A. Alves; F. Ferreira; J. Correia; P. Faísca; et al. (Journal of Comparative Pathology, 2025)

Comprehensive machine learning assessment of zebrafish behaviour and biochemical markers in response to caffeine exposure - Cláudia Teixeira; Sara Rodrigues; João Amorim; Bárbara S. Diogo; Ivo Pinto; António Paulo Carvalho; Sara C. Antunes; Luís Oliva Teles (Ecotoxicology, 2025)
Environmental exposure to caffeine (CAF) poses potential risks to aquatic ecosystems, affecting non-target species. This study investigated the chronic effects of environmentally relevant CAF concentrations, ranging from 0.16–50 µg/L, on zebrafish behaviour. A Kohonen-type artificial neural network classified zebrafish behaviour into nine behavioural classes based on a set of movement descriptors (mean meander, mean velocity, instantaneous velocity, distance to centre point, mean angular velocity and instantaneous acceleration), while a comprehensive analysis integrated behavioural classes previously defined and biochemical markers of oxidative stress, lipid peroxidation, reserve energy content, energetic pathways, and neurotoxicity. The discriminant analysis demonstrated that behaviour descriptors and biomarkers individually explained 38% and 67% of data variation, respectively, while the combination resulted in 19 models with 100% correct diagnosis. One of the models (Model A) seemed to suit the best dose-response relationship, incorporating key biomarkers including superoxide dismutase, catalase, glutathione peroxidase activities, and behavioural characteristics such as movement distance and velocity. This suggested methodology offers a different approach to evaluating CAF’s ecological impact, highlighting behavioural analysis as a valuable complement to traditional ecotoxicological assessments. This study provides a novel framework for understanding organism-level responses to environmental stressors (e.g., several anthropogenic compounds), utilising Mahalanobis distance as an integrative response index. This approach shows promise for broader application in assessing the impact of various aquatic contaminants on aquatic organisms (from bacteria to fish), potentially extending to pharmaceuticals, pesticides, and industrial pollutants.

Comparisons of Hyperostotic Bones in Two Species of the Genus Oligoplites Gill, 1863 in the Southern Brazilian Coast - Fernando A. P. Tuna; Ana Paula C. de Rodrigues; Gustavo P Filgueira; Rebeca s da Bianca; Wilson T. V. Machado; Márcia C. Salomão; Helena P. Lavrado (Journal of Fish Diseases, 2025)
The description of skeletal disorders is commonly reported in fish species raised through aquaculture; however, wild marine fish may also exhibit high frequencies of anomalies, particularly the development of hyperostosis, a condition that causes thickening of the bones. Specimens of Oligoplites saliens ( n = 15) and Oligoplites palometa ( n = 14) were radiographed to verify hyperostotic bone occurrences. Hyperostosis was detected in all individuals (> 400 mm TL) analysed for both species, occurring in six distinct regions of the skeleton (supraoccipital bone, cleithrum, dorsal pterygiophores, anal pterygiophore, haemal spines, and neural spines), regardless of the sex of the individuals. No hyperostosis was found in the neural and haemal spines of O. palometa and in the anal pterygiophore of O. saliens . Histological sections of the supraoccipital bone of O. saliens were conducted, revealing high porosity characterised by the presence of vascular channels in bones with hyperostosis. The species exhibited species‐specific patterns for the condition, demonstrating differences even among species of the same genus occurring in the same geographic area. This is the first record of hyperostosis for both species in Brazilian waters.

Total nutrient digestibility and small intestine starch digestion in Nellore and Nellore × Angus steers fed whole shelled corn-based diet with or without roughage - Priscilla D. Teixeira; Aline C. Rodrigues; Daniel R. Casagrande; Erick D. Batista; José M. Oliveira; Ana C.O. Santos; Pedro V.R. Paulino; Marcio M. Ladeira (Livestock Science, 2025)

Brazil nut or not? Uncovering the best source of selenium for chronic non-communicable disease - Renata Cristina Bezerra Rodrigues; Danielle Nascimento; Jessyca Brito; Ligia Soares Lima; Julie C. Lobo; Ludmila F.M.F. Cardozo; Denise Mafra (Food Bioscience, 2025)

The role of the P2X7 receptor in inactivated SARS-CoV-2-induced lung injury - N. C. Carvalho-Barbosa; Fabiana Cristina-Rodrigues; Jairo R. Temerozo; Thiago M. L. Souza; Andre L. Gouvêa; Claudio A. Canetti; Eleonora Kurtenbach; Dumith Chequer Bou-Habib; Claudia F. Benjamim; Christina M. Takiya; Luiz E. B. Savio; Robson Coutinho-Silva (Purinergic Signalling, 2025)

Cultivation of Gelidium floridanum in different nitrate concentrations: morphophysiological effects - Mariana F. Carvalho; Gabriela Rodrigues; Debora T. Pereira; Deonir Batista; Luciane C. Ouriques; Carmen Simioni (Journal of Applied Phycology, 2025)

The caatinga dry tropical forest: A highly efficient carbon sink in South America - Keila R. Mendes; Pablo E.S. Oliveira; José Romualdo S. Lima; Magna S.B. Moura; Eduardo S. Souza; Aldrin M. Perez-Marin; John Elton B.L. Cunha; Pedro R. Mutti; Gabriel B. Costa; Thales N. Martins de Sá; Paula A.A. Araujo; Rosaria R. Ferreira; et al. (Agricultural and Forest Meteorology, 2025)

Effects of aerobic exercise and cardiorespiratory fitness on white matter free water fraction in older adults: a 1-year randomized controlled trial - Takashi Tarumi; Junyeon Won; Tsubasa Tomoto; Norman Scheel; David C. Zhu; John Ashley; Karen M. Rodrigue; Kristen M. Kennedy; Denise C. Park; Rong Zhang (GeroScience, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Effects of soybean molasses on ruminal fermentation pattern, performance and meat quality of feedlot sheep - Sérgio A.G. Pereira-Junior; Juliana A. Torrecilhas; Rayanne V. Costa; Edivilson S. Castro Filho; Maria Carolina G. Arruda; João Pedro A. Bertoco; Andresa L. Feliciano; Julia L. Rodrigues; Rosemary L. Galati; Angélica C. dos Santos; Marcos R. Chiaratti; Ricardo P. Nociti; et al. (Small Ruminant Research, 2025)

Exploring plant functional traits and their relationship to biomass dynamics in secondary forests in Eastern Amazonia - Luane Botelho; Fernando Elias; Beatriz V. Barbosa; Karoline C. Silva; Vanessa Negrão-Rodrigues; Euciney E.S. Barbosa; Jucelino S. Coutinho; Joice Ferreira; Jos Barlow; Grazielle Sales Teodoro (Flora, 2025)

Optimizing torrefaction of banana waste (peels and rachis) for sustainable biocoal production in rural communities - Igor F. Mendonça; Gabriel S. do Vale; Rafael B.W. Evaristo; Rômulo C. Dutra; Pedro Paulo de Oliveira Rodrigues; Edgar A. Silveira; Grace Ghesti (Biomass and Bioenergy, 2025)

Estimation of diurnal and nocturnal radiation balance in tropical ecosystems - D. O. Maionchi; I. J. C. de Paulo; S. R. de Paulo; J. B. Marques; A. L. P. Junior; H. J. A. da Silva; R. S. Palácios; T. R. Rodrigues; T. A. dos Santos; A. M. S. Lima; M. S. Biudes; L. Sanches; et al. (Theoretical and Applied Climatology, 2025)

Self-assembly and 3D Bioprinting of Neurospheres and Evaluation of Caffeine and Photobiomodulation Effects in an Alzheimer’s Disease In Vitro Model - Geisa Rodrigues Salles; Alessandro E. C. Granato; Fernanda Tibolla Viero; Cristina Pacheco-Soares; Sérgio T. Ferreira; Marimelia Porcionatto; Henning Ulrich (Stem Cell Reviews and Reports, 2025)

Porcine circovirus type 2 (PCV2) in Brazil in the past 55 years (1967-2022): evolutionary rates and patterns - I. L. F. Rodrigues; A. C. M. Cruz; A. E. Souza; F. B. Knackfuss; C. H. C. Costa; B. V. Lago; R. L. Silveira; T. X. Castro (Archives of Virology, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Associations of cardiorespiratory fitness with brain white matter microstructural integrity and white matter hyperintensity volume across the adult lifespan - Junyeon Won; Takashi Tarumi; Tsubasa Tomoto; Kevin Shan; Karen M. Rodrigue; Kristen M. Kennedy; Denise C. Park; Rong Zhang (GeroScience, 2025)

Exploring the relationship between histological grading, fibrillar collagen alterations and nuclear phenotypes in canine mammary carcinomas - Danielle D.P. Cerce; Gabriela C. Cândido; Maysa B. de Almeida; Jhuan L. Silva; Fernanda G.G. Dias; Marcela A. Rodrigues (Journal of Comparative Pathology, 2025)

A Cryptococcus neoformans polysaccharide conjugate vaccine made with filtered polysaccharide elicits protective immunity in mice - Piotr R. Stempinski; Paola Ramos Irizarry; Scott A. McConnell; Livia C. Liporagi Lopes; Samuel Rodrigues Dos Santos Júnior; Maggie P. Wear; Arturo Casadevall (Fungal Biology, 2025)

Valorization of natural resources - development of a functional plant-based beverage - Filipa A. Fernandes; Custódio Roriz; Ricardo C. Calhelha; Paula Rodrigues; Tânia C.S.P. Pires; Miguel A. Prieto; Isabel C.F.R. Ferreira; Lillian Barros; Sandrina A. Heleno (Food Chemistry, 2025)

Probiotic-based adsorbent mitigates aflatoxin B1 toxicity in Piaractus mesopotamicus: assessing well-being via changes in tissue architecture and digestive enzyme activity - Henrique M. Ziemniczak; Leticia Maria Albuquerque Conceição; Antonio Cesar Godoy; Dacley Hertes Neu; Andressa Tellechea Rodrigues; Cristiane Meldau de Campos; Rubia Mara Gomes Acunha; Jefferson Rodrigues Gandra; Klaus C. Saturnino; Ulisses de Pádua Pereira; Claucia A. Honorato (Veterinary Research Communications, 2025)

Neuroinflammation in Severe COVID-19: The Dynamics of Inflammatory and Brain Injury Markers During Hospitalization - Carla Andretta Moreira Neves; Gilson P. Dorneles; Paula C. Teixeira; Paulo C. Santana Filho; Alessandra Peres; Carina Rodrigues Boeck; Liane N. Rotta; Claudia E. Thompson; Pedro R. T. Romão (Molecular Neurobiology, 2025)

Detection of an Alphacoronavirus in a Brazilian Bat (Molossus sp.) - C. L. Molina; M. M. Magalhães; A. C. Rodrigues; S. A. Taniwaki; S. O. de Souza Silva; G. A. König; P. E. Brandão (Journal of Molecular Evolution, 2025)

Unraveling the lipidome of Pavlova gyrans, a natural reservoir of bioactive lipids for biotechnological applications - Tiago Conde; Diana Lopes; Marisa Pinho; Tânia Melo; Natacha Coelho; Alexandre M. C. Rodrigues; Hugo Pereira; Pedro Domingues; Rosário Domingues (Journal of Applied Phycology, 2025)

Are flash droughts intensifying in Brazil? - Javier Tomasella; Marcelo Zeri; Ana Paula Martins do Amaral Cunha; Roger Rodrigues Torres; Nancy Laura Rios Gamarra; Lidiane C. O. Costa (Climate Dynamics, 2025)

Toward an integrated pantropical ocean observing system - Gregory R. Foltz; Yassir A. Eddebbar; Janet Sprintall; Antonietta Capotondi; Sophie Cravatte; Peter Brandt; Adrienne J. Sutton; Tamaryn Morris; Juliet Hermes; Clive R. McMahon; Michael J. McPhaden; Lev B. Looney; et al. (Frontiers in Marine Science, 2025)
Global climate is regulated by the ocean, which stores, releases, and transports large amounts of mass, heat, carbon, and oxygen. Understanding, monitoring, and predicting the exchanges of these quantities across the ocean’s surface, their interactions with the atmosphere, and their horizontal and vertical pathways through the global oceans, are key for advancing fundamental knowledge and improving forecasts and longer-term projections of climate, weather, and ocean ecosystems. The existing global observing system provides immense value for science and society in this regard by supplying the data essential for these advancements. The tropical ocean observing system in particular has been developed over decades, motivated in large part by the far-reaching and complex global impacts of tropical climate variability and change. However, changes in observing needs and priorities, new challenges associated with climate change, and advances in observing technologies demand periodic evaluations to ensure that stakeholders’ needs are met. Previous reviews and assessments of the tropical observing system have focused separately on individual basins and their associated observing needs. Here we provide a broader perspective covering the tropical observing system as a whole. Common gaps, needs, and recommendations are identified, and interbasin differences driven by socioeconomic disparities are discussed, building on the concept of an integrated pantropical observing system. Finally, recommendations for improved observations of tropical basin interactions, through oceanic and atmospheric pathways, are presented, emphasizing the benefits that can be achieved through closer interbasin coordination and international partnerships.

A biomarkers study of human skin fibroblasts exposition to glyphosate-based herbicide using an untargeted and targeted metabolomics approach - Josimar M. Batista; Dawidson A. Gomes; María J.G. Armijos; Michele A. Rodrigues; Helvécio C. Menezes; Zenilda L. Cardeal (Chemosphere, 2025)

Impact of cigarette butts elutriates on Artemia franciscana in a climate change context - S. Couto; S. Rodrigues; R. Patrão; M. Vieira; S.C. Antunes; C. Pinheiro (Marine Pollution Bulletin, 2025)

Evaluation of Scalibor® deltamethrin collar chronic exposure in dogs - Larissa T.P. Rodrigues; Andriele F. Qualhato; Carolle V.M. Sprícigo; Kelly C.A. Arantes; Rayanne H.S. da Silva; Alexandre C.M. Barros; Monica C. Vicente; Murilo R. Souza; Luiza G.F. de Paula; Danilo Roman-Campos; Artur S. Miranda; Danieli B. Martins; et al. (Research in Veterinary Science, 2025)

Characterization of the lipid profile of the equine sperm plasma membrane - D. Rodrigues; C. Ramires Neto; C. Freitas-Dell'Aqua; K.R. Belaz; D. Zampieri; A. Tata; M.N. Eberlin; F.F. de Souza; F.O. Papa; J.A. Dell'Aqua Júnior (Journal of Equine Veterinary Science, 2025)

An engineered, biocide-grafted TiO2-based nanohybrid material with enhanced photocatalytic and antimicrobial activity - Olga Ferreira; Mafalda Gil; Ana Carapeto; Andreia Barreto; Manuela Pereira; Mário S. Rodrigues; Lucas Habib; Luciana C. Gomes; Rita Teixeira-Santos; Filipe J.M. Mergulhão; Elisabete R. Silva (Journal of Cleaner Production, 2025)

Addressing the urgent climate and biodiversity crisis through strategic ecosystem restoration in Brazil - Luisa Fernanda Liévano-Latorre; Juliana M. de Almeida-Rocha; Alberto Akama; Hernani Alves Almeida; Ricardo Teixeira Gregório Andrade; Marcelo Rodrigues dos Anjos; Yasmine Antonini; Thaise de Oliveira Bahia; Flavia Rodrigues Barbosa; Reinaldo Imbrozio Barbosa; Claudia Franca Barros; Helena Godoy Bergallo; et al. (Biological Conservation, 2025)

Ceftazidime-avibactam tolerance and persistence among difficult-to-treat KPC-producing Klebsiella pneumoniae clinical isolates from bloodstream infections - N. Abichabki; G. G. Gaspar; L. R. Bortolato; D. A. F. S. Lima; L. N. Silva; R. H. C. Pocente; J. C. Ferreira; T. C. Ogasawara; D. Pereira; R. R. Guerra; C. Wilhelm; P. Barth; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Computational and experimental advances in liver-on-a-chip technology for cancer research: a systematic review - Violeta Carvalho; Mariana Ferreira; Raquel O. Rodrigues; Senhorinha F. C. F. Teixeira; Rui A. Lima (Biophysical Reviews, 2025)
The integration of numerical simulations with Liver-on-a-Chip (LoC) technology offers an innovative approach for studying liver physiology and pathology, especially in the context of liver cancer. Numerical simulations facilitate the optimization of microfluidic devices’ design and deepen the understanding of fluid flow and mass transfer. However, despite significant advancements, challenges such as replicating the full complexity of the liver microenvironment and scaling up for high-throughput screening persist. This systematic review explores the current advancements in LoC devices, with a particular emphasis on their combined use of numerical simulations and experimental studies in liver cancer research. A comprehensive search across multiple databases, including ScienceDirect, Wiley Online Library, Scopus, Springer Link, Web of Science, and PubMed, was conducted to gather relevant literature. Our findings indicate that the combination of both techniques in this field is still rare, resulting in a final selection of 13 original research papers. This review underscores the importance of continued interdisciplinary research to refine these technologies and enhance their application in personalized medicine and cancer therapy. By consolidating existing studies, this review aims to highlight key advancements, identify current challenges, and propose future directions for this rapidly evolving field.

HiDaFernPT : Historical data of spore availability for 121 fern and lycopod taxa in Portugal (1926–2013) - Sérgio Timóteo; Ruben Heleno; Filipe Covelo; Joaquim Santos; Pedro Lopes; António C. Gouveia; Arménio Matos; Agostinho Salgado; M. Teresa Girão da Cruz; João Farminhão; Marta Horta; Guilherme Barreto; et al. (Ecology, 2025)
Species phenology is being altered by ongoing climate changes with yet underappreciated consequences for ecological processes and ecosystem stability. Contrary to what happens with some key life events of flowering plants, comparatively little information exists about fern and lycophyte phenology and how it is affected by the current climatic changes. In part, this stems from the lack of long‐term datasets. Here we provide information on the collection day and site of the spores of 121 native and introduced fern (Polypodiopsida) and lycopod (Lycopodiopsida) taxa for the Index Seminum of the Botanic Garden of the University of Coimbra. Spores were collected from spontaneous and cultivated individuals across Portugal between 1926 and 2013. The database includes 3383 curated records with information on the species, or infraspecific taxa (including authority), and are fully georeferenced and provided with a confidence interval for the collection site. Taxonomy was first curated manually by in‐house botanists and then harmonized according to the Global Biodiversity Information Facility (GBIF) backbone taxonomy. The data are released under a Creative Commons Attribution Non Commercial (CC‐BY‐NC 4.0) license.

Pre-exposure of Lactobacillus acidophilus to stress conditions impacts the metabolites and bioaccessibility of calcium and carotenoids in fermented dairy products - Juliana S. Graça; Joyce G.S. Silva; Laísa G. Dias; Ana Augusta Odorissi Xavier; Elenilson G. Alves-Filho; Tatiana C. Pimentel; Edy S. Brito; Sueli Rodrigues; Juliana A.L. Pallone; Lilian R.B. Mariutti; Adriana Z. Mercadante; Neura Bragagnolo; et al. (Food Research International, 2025)

Improving survival and growth of caprine preantral follicles cultured in medium commonly used for MSC: Role of oxidative stress regulation and epigenetic changes - Ana F.B. Silva; Laritza F. Lima; Anna C.A. Ferreira; Ariclécio C. Oliveira; Napoleão M.A. Neto; Benner G. Alves; Ana P.R. Rodrigues; Eduardo L. Gastal; Vilceu Bordignon; José R. Figueiredo (Domestic Animal Endocrinology, 2025)

Ecotoxicity of bioinsecticide spinosad to soil organisms: Commercial formulation versus active ingredient - Alexandre Moreira; Verónica Nogueira; Sirine Bouguerra; Sara C. Antunes; Sara Rodrigues (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Current constraints to reconcile tropical forest restoration and bioeconomy - Pedro Medrado Krainovic; Diego Oliveira Brandão; Angélica Faria Resende; Stella Z. Schons; Leonardo Munhoz; Jean Paul Metzger; Nathália C. Nascimento; Ricardo Ribeiro Rodrigues; Pedro H. S. Brancalion; Joannès Guillemot; Sergio de-Miguel (Sustainability Science, 2025)
Large-scale forest restoration is vital for delivering a broad array of ecosystem services benefits to society. However, it is often perceived as an economically noncompetitive land use choice. Integrating economic opportunities into restoration aligns socioeconomic and environmental goals, reducing conflicts between forest production and conservation-oriented management decisions. Supply chains focusing on high-value goods can enhance the reach of forest restoration efforts and unite ecological and economic benefits in a multifunctional manner. The bioeconomy has emerged as a potential but critical driver for attracting investments in restoration. We outline the challenges and solutions to reconcile forest restoration and bioeconomy, specifically about (i) native timber production, (ii) non-timber forest products, (iii) biotechnological products, and (iv) intangible ecosystem services. This requires collaborative and multidisciplinary efforts to improve investment in large-scale projects. The intricacies of these issues intersect with research development, market dynamics, legal frameworks, and regulatory paradigms, underscoring the necessity for nuanced and tailored public policy interventions. These integrated approaches should enable tropical countries to lead the global forest-based economy and usher in a new era of forest restoration. Graphical abstract

Optical immunosensor panel using quantum dot-antibody conjugates for highly sensitive detection of carbohydrate antigen 19–9 (CA19-9) - Daniela Oliveira; Pedro Oliveira; Ana Xu; Eduarda Rodrigues; Susana G. Guerreiro; Rafael C. Castro; David S.M. Ribeiro; João L.M. Santos; Ana Margarida L. Piloto (Analytica Chimica Acta, 2025)

Social immune response reflects infection progression in a soldierless termite - Luiza Helena Bueno da Silva; Aryel C. Goes; Andre Rodrigues; Vincent Fourcassié; Dino McMahon; Ives Haifig (Behavioral Ecology and Sociobiology, 2025)

Elevational Range Impacts Connectivity and Predicted Deme Sizes From Models of Habitat Suitability - Connor M. French; Roberta P. Damasceno; Mariana M. Vasconcellos; Miguel T. Rodrigues; Ana C. Carnaval; Michael J. Hickerson (Molecular Ecology, 2025)
In integrative distributional, demographic and coalescent (iDDC) modelling, a critical component is the statistical relationship between habitat suitability and local population sizes. This study explores this relationship in two Enyalius lizard species from the Brazilian Atlantic Forest: the high‐elevation E. iheringii and low‐elevation E. catenatus and how this transformation affects spatiotemporal demographic inference. Most previous iDDC studies assumed a linear relationship, but this study hypothesises that the relationship may be nonlinear, especially for high‐elevation species with broader environmental tolerances. We test two key hypotheses: (1) The habitat suitability to population size relationship is nonlinear for E. iheringii (high‐elevation) and linear for E. catenatus (low‐elevation); and (2) E. iheringii exhibits higher effective migration across populations than E. catenatus . Our findings provide clear support for hypothesis (2), but mixed support for hypothesis (1), with strong model support for a nonlinear transformation in the high‐elevation E. iheringii and some (albeit weak) support for a nonlinear transformation also in E. catenatus . The iDDC models allow us to generate landscape‐wide maps of predicted genetic diversity for both species, revealing that genetic diversity predictions for the high‐elevation E. iheringii align with estimated patterns of historical range stability, whereas predictions for low‐elevation E. catenatus are distinct from range‐wide stability predictions. This research highlights the importance of accurately modelling the habitat suitability to population size relationship in iDDC studies, contributing to our understanding of species' demographic responses to environmental changes.

Integrative species delimitation and biogeography of the Rhinella margaritifera species group (Amphibia, Anura, Bufonidae) suggest an intense diversification throughout Amazonia during the last 10 million years - Antoine Fouquet; Miqueias Ferrão; Miguel T. Rodrigues; Fernanda P. Werneck; Ivan Prates; Leandro J.C.L. Moraes; Tomas Hrbek; Juan C. Chaparro; Albertina P. Lima; Renata Perez; Andre Pansonato; Vinicius T. Carvalho; et al. (Systematics and Biodiversity, 2024)

Airborne DNA: State of the art – Established methods and missing pieces in the molecular genetic detection of airborne microorganisms, viruses and plant particles - C.-E. Pogner; C. Antunes; G.P. Apangu; N. Bruffaerts; S. Celenk; A. Cristofori; N. González Roldán; A. Grinn-Gofroń; B. Lara; M. Lika; D. Magyar; M. Martinez-Bracero; et al. (Science of The Total Environment, 2024)

Retraction notice to “Toxicity of spike fragments SARS-CoV-2 S protein for zebrafish: A tool to study its hazardous for human health?” [Sci. Total Environ. 813 (2022) / 152345] - Bianca H. Ventura Fernandes; Natália Martins Feitosa; Ana Paula Barbosa; Camila Gasque Bomfim; Anali M.B. Garnique; Ivana F. Rosa; Maira S. Rodrigues; Lucas B. Doretto; Daniel F. Costa; Bruno Camargo-dos-Santos; Gabrielli A. Franco; João Favero Neto; et al. (Science of The Total Environment, 2024)

A multicommuted system using bacterial cellulose for urease immobilization and copper (II)-MOF colorimetric sensor for urea spectrophotometric determination in milk - Julyana C. Rodrigues; Caio S. Bezerra; Lidiane M.A. Lima; Danielle D. Neves; Ana Paula S. Paim; Wagner E. Silva; André F. Lavorante (Food Chemistry, 2024)

Microbiota diversity of three Brazilian native fishes during ice and frozen storage - Rafaela C. Baptista; Ilario Ferrocino; Matheus Pavani; Tatiane M. Guerreiro; Antonio A. Câmara; Émilie Lang; Juliana L.P. dos Santos; Rodrigo R. Catharino; Elenilson G. Alves Filho; Sueli Rodrigues; Edy S. de Brito; Magdevis Y.R. Caturla; et al. (Food Microbiology, 2024)

SUMOylation of rice DELLA SLR1 modulates transcriptional responses and improves yield under salt stress - Telma Fernandes; Nuno M. Gonçalves; Cleverson C. Matiolli; Mafalda A. A. Rodrigues; Pedro M. Barros; M. Margarida Oliveira; Isabel A. Abreu (Planta, 2024)
Main conclusion SUMOylation of SLR1 at K2 protects productivity under salt stress, possibly by modulation of SLR1 interactome. Abstract DELLA proteins modulate GA signaling and are major regulators of plant plasticity to endure stress. DELLAs are mostly regulated at the post-translational level, and their activity relies on the interaction with upstream regulators and transcription factors (TFs). SUMOylation is a post-translational modification (PTM) capable of changing protein interaction and has been found to influence DELLA activity in Arabidopsis. We determined that SUMOylation of the single rice DELLA, SLENDER RICE1 (SLR1), occurs in a lysine residue different from the one identified in Arabidopsis REPRESSOR OF GA (RGA). Artificially increasing the SUMOylated SLR1 levels attenuated the penalty of salt stress on rice yield. Gene expression analysis revealed that the overexpression of SUMOylated SLR1 can regulate GA biosynthesis, which could partially explain the sustained productivity upon salt stress imposition. Furthermore, SLR1 SUMOylation blocked the interaction with the growth regulator YAB4, which may fine-tune GA20ox2 expression. We also identified novel SLR1 interactors: bZIP23, bHLH089, bHLH094, and OSH1. All those interactions were impaired in the presence of SUMOylated SLR1. Mechanistically, we propose that SUMOylation of SLR1 disrupts its interaction with several transcription factors implicated in GA-dependent growth and ABA-dependent salinity tolerance to modulate downstream gene expression. We found that SLR1 SUMOylation represents a novel mechanism modulating DELLA activity, which attenuates the impact of stress on plant performance.

Gender Differences on the Awareness of Human Papillomavirus Infection and Vaccination - Vivian Heimbecker; Santina C. Bordini; Ana Carolina Rodrigues; Nina M. de Alencar; Nicholas S. Blanco; Fernanda Fitz; Gabriela B. Moura; Marian Dumitru; Adriana F. Mercadante; Larissa M. Alvarenga; Cristina L. B. Monteiro; Camila Marconi (Journal of Cancer Education, 2024)

Effect of connection elements on shear strength of wooden pieces for structural use - Hellen M. A. C. Rodrigues; Evelize A. Amaral; Rodrigo A Pereira; José Benedito Guimarães Junior; Paulo R. G. Hein (Journal of the Indian Academy of Wood Science, 2024)

Historical land use changes lead to massive loss of soil carbon stocks in a recovering, semiarid mangrove - José Vítor Rodrigues; Luiz C. Cotovicz; Natalia Beloto; Maria Regina Gmach; Luís Ernesto Arruda Bezerra (Marine Pollution Bulletin, 2024)

Impact of run-of-river damming on increasing phytoplankton biomass and species shift in a large Amazonian river - Alfonso Pineda; Beatriz Melissa Campos; Felipe Zanon; Renata Felicio; Luzia C. Rodrigues (Science of The Total Environment, 2024)

Geochemistry of fine-grained sedimentary rocks: Implications for source area, paleoweathering, paleoclimate, and provenance of the Santa Maria Formation (Triassic, Paraná Basin, Brazil) - Isaque C. Rodrigues; Anderson J. Maraschin; André W. Borba; Ana M.P. Mizusaki (Journal of South American Earth Sciences, 2024)

Has unsustainable groundwater use induced low flow regimes in the Urucuia Aquifer System? An urgent call for integrated water management - André F. Rodrigues; Bruno M. Brentan; Marta V. Ottoni; Jhones S. Amorim; Maria A.A. Mourão; Nilton Curi; Junior C. Avanzi; Carlos R. de Mello (Journal of Environmental Management, 2024)

Depth estimation of pre-Kalahari basement in Southern Angola using seismic noise measurements and drill-hole data - J. Carvalho; D. Alves; J. Borges; B. Caldeira; D. Cordeiro; A. Machadinho; A. Oliveira; E.C. Ramalho; J.F. Rodrigues; J.M. Llorente; M. Ditutala; J.L. García-Lobón; et al. (Journal of Applied Geophysics, 2024)

Juvenile-related tolerance to papaya sticky disease (PSD): proteomic, ultrastructural, and physiological events - Silas P. Rodrigues; Eduardo de A. Soares; Tathiana F. Sá Antunes; Marlonni Maurastoni; Leidy J. Madroñero; Sabrina G. Broetto; Lucas E. C. Nunes; Brunno R. F. Verçoza; David S. Buss; Diolina M. Silva; Juliany C. F. Rodrigues; José A. Ventura; et al. (Plant Cell Reports, 2024)

Contribution to the Iberian thermomediterranean oak woods (Spain, Portugal): the importance of their teaching for the training of experts in environmental management - Cano E.; Piñar Fuentes J.C.; Cano Ortiz A.; Quinto Canas R.; Rodrigues Meireles C.; Mauro R.; Pinto Gomes C.J.; Spampinato G.; Musarella C. M. (Plant Biosystems, 2024)

Patterns and Drivers of Taxonomic and Functional Change in Large Oceanic Island Bird Assemblages - Filipa C. Soares; Ricardo F. de Lima; Ana S. L. Rodrigues; Pedro Cardoso; Thomas J. Matthews; Jorge M. Palmeirim (Global Ecology and Biogeography, 2024)
Aim We map global patterns of taxonomic and functional change between past (pre‐human impacts) and present (after anthropogenic extinctions and introductions) in large oceanic island bird assemblages and investigate if these patterns can be explained by island characteristics and anthropogenic factors. Location Sixty‐four oceanic islands (>100 km 2 ). Time Period Late Holocene. Major Taxa Studied Terrestrial and freshwater bird species. Methods We compiled information on extinct, extant native and introduced bird species for all islands and used a probabilistic hypervolume approach to build a multi‐dimensional trait space and calculate several functional diversity metrics before and after extinctions and introductions. We identified which islands are global hotspots of human‐induced transformation by mapping multiple facets of biotic change and investigated intrinsic island characteristics and anthropogenic factors as drivers for these observed patterns. Results The Hawaiian and Mascarene islands stand out as hotspots of taxonomic and functional change, but all islands changed taxonomically and functionally, mostly gaining species but losing functional richness. Taxonomic and functional changes vary across islands but are often consistent within the same archipelago. Island isolation and surface can explain some of the observed variations, but anthropogenic factors, namely human occupation, also shaped both taxonomic and functional changes. Islands with higher human pressure, as well as larger islands with high elevation ranges, tended to have greater losses in functional richness. Main Conclusions Most biodiversity change assessments are still largely based exclusively on taxonomic diversity, which is particularly worrying in the case of oceanic islands given that the magnitude of functional diversity change is often considerably larger. We call for comprehensive assessments of changes in both taxonomic and functional diversity across oceanic islands in order to better understand the drivers of these changes and, in turn, predict future trends.

Multi‐Taxa Responses to Climate Change in the Amazon Forest - Carlos A. S. Rodrigues‐Filho; Flávia R. C. Costa; Juliana Schietti; Anselmo Nogueira; Rafael Pereira Leitão; Juliana Menger; Gabriel Borba; Caian Souza Gerolamo; Stefano S. Avilla; Thaise Emilio; Carolina Volkmer de Castilho; Douglas Aviz Bastos; et al. (Global Change Biology, 2024)
Tropical biodiversity is undergoing unprecedented changes due to the hydrological cycle intensification, characterized by more intense droughts and wet seasons. This raises concerns about the resilience of animal and plant communities to such extremes and the existence of potential refugia—areas theorized to safeguard biological communities from adverse climate impacts. Over 20 years of monitoring in Central Amazonia, we investigated the short‐term and long‐term effects of hydrological cycle intensification on bird, fish, ant, and palm communities. We explored whether the ‘insurance effect’ of climate trends (droughts buffered by preceded wet seasons) or ‘environmental refugia’ (droughts or floods buffered by topographic features) could lessen the impact of climate events on community composition, richness, evenness, and species rank. Pronounced abundance changes were observed among animal species, whereas palm species showed relative temporal stability. Birds and fish were more affected by the immediate and long‐term severity of droughts and wet periods, while ants responded primarily to short‐term drought impacts. Conversely, palm communities exhibited delayed responses to climate extremes, primarily in long‐term comparisons. As expected, the proposed ‘insurance effect’ mitigates the long‐term impacts of extreme climate events on animal and plant community trends. However, less extreme hydrological conditions linked to topographic features did not provide effective ‘environmental refugia’ for animals or plants during adverse climate conditions. These outcomes underscore the complex and varied biological responses to ongoing climate change, challenging the prevailing assumptions about the efficacy of environmental refugia and highlighting the nuanced resilience of biodiversity in Central Amazonia.

Hydrocarbon composition of oils spilt on the Brazilian coast in 2019 and 2022 - Antônia M. Corrêa; Felipe F. Campos; Marcus F. Tenório; Alice M.S. Rodrigues; Carlos D. Pérez; Fabiano Thompson; Andressa S. Batista; Pedro V. Gatts; Carlos E. de Rezende; Kátia Z. Leal; Marcelo C. Bernardes (Marine Pollution Bulletin, 2024)

Occurrence and potential ecological risks of PFAS in Pampulha Lake, Brazil, a UNESCO world heritage site - Maria Clara V.M. Starling; Daniel A.S. Rodrigues; Gisele A. Miranda; Suna Jo; Camila C. Amorim; Gerald T. Ankley; Matt Simcik (Science of The Total Environment, 2024)

The ADnet Bayesian belief network for alder decline: Integrating empirical data and expert knowledge - Inês Gomes Marques; Cristina Vieites-Blanco; Patricia M. Rodríguez-González; Pedro Segurado; Marlene Marques; Maria J. Barrento; Maria R. Fernandes; Arthur Cupertino; Helena Almeida; Idoia Biurrun; Tamara Corcobado; Filipe Costa e Silva; et al. (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Pennsylvanian epicontinental sea dynamics in Western Gondwana: Stratigraphic, petrographic, and C, O, and Sr isotopic insights from the Itaituba Formation, Amazonas Basin - Maria D. Traslaviña-Bueno; Juliana C. Marques; Afonso C. Nogueira; Pedro A. Silva; Juan S. Gomez-Neita; Amanda G. Rodrigues; André A. Martins; Paulo A. Souza; Ana K. Scomazzon; Marcia E. Longhim (Journal of South American Earth Sciences, 2024)

Silicon-mediated resistance in maize against infection by Colletotrichum graminicola - Ana C. R. Mochko; Bruno N. Silva; Lillian M. Oliveira; Leandro C. Silva; Fabrício A. Rodrigues (Plant and Soil, 2024)

Sonification of electronic dynamical systems: Spectral characteristics and sound evaluation using EEG features - G. Acosta Martínez; E. Guevara; E. S. Kolosovas-Machuca; P. G. Rodrigues; D. C. Soriano; E. Tristán Hernández; L. J. Ontañón-García (Cognitive Neurodynamics, 2024)

Gray matter based spatial statistics framework in the 1-month brain: insights into gray matter microstructure in infancy - Marissa A. DiPiero; Patrik Goncalves Rodrigues; McKaylie Justman; Sophia Roche; Elizabeth Bond; Jose Guerrero Gonzalez; Richard J. Davidson; Elizabeth M. Planalp; Douglas C. Dean (Brain Structure and Function, 2024)

Joining forces to fight wildfires: Science and management in a protected area of Pantanal, Brazil - Patrícia S. Silva; Julia A. Rodrigues; Joana Nogueira; Livia C. Moura; Alexandre Enout; Cristina Cuiabália; Carlos C. DaCamara; Allan A. Pereira; Renata Libonati (Environmental Science & Policy, 2024)

How a mega-dam in the Amazon’s largest tributary altered the drivers of planktonic communities - Alfonso Pineda; Luiz Felipe Machado Velho; Priscilla de Carvalho; Luzia C. Rodrigues (Hydrobiologia, 2024)

Wind dispersed tree species have greater maximum height - Ferry Slik; Bruno X. Pinho; Daniel M. Griffith; Edward Webb; Akhilesh Singh Raghubanshi; Adriano C. Quaresma; Aida Cuni Sanchez; Aisha Sultana; Alexandre F. Souza; Andreas Ensslin; Andreas Hemp; Andrew Lowe; et al. (Global Ecology and Biogeography, 2024)
Aim We test the hypothesis that wind dispersal is more common among emergent tree species given that being tall increases the likelihood of effective seed dispersal. Location Americas, Africa and the Asia‐Pacific. Time period 1970–2020. Major taxa studied Gymnosperms and Angiosperms. Methods We used a dataset consisting of tree inventories from 2821 plots across three biogeographic regions (Americas, Africa and Asia‐Pacific), including dry and wet forests, to determine the maximum height and dispersal strategy of 5314 tree species. A web search was used to determine whether species were wind‐dispersed. We compared differences in tree species maximum height between biogeographic regions and examined the relationship between species maximum height and wind dispersal using logistic regression. We also tested whether emergent tree species, that is species with at least one individual taller than the 95% height percentile in one or more plots, were disproportionally wind‐dispersed in dry and wet forests within each biogeographic region. Results Our dataset provides maximum height values for 5314 tree species, of which more than half (2914) had no record of this trait in existing global databases. We found that, on average, tree species in the Americas have lower maximum heights compared to those in Africa and the Asia Pacific. The probability of wind dispersal increased significantly with tree species maximum height and was significantly higher among emergent than non‐emergent tree species in both dry and wet forests in all three biogeographic regions. Main conclusion Wind dispersal is more prevalent in tall, emergent tree species than in non‐emergent species and may thus be an important factor in the evolution of tree species maximum height. By providing the most comprehensive dataset so far of tree species maximum height and wind dispersal strategies, this study paves the way for advancing our understanding of the eco‐evolutionary drivers of tree size.

Resistance training improves cardiac function in older women: a randomized controlled trial - Ricardo J. Rodrigues; Paolo M. Cunha; João P. Nunes; Lauro C. Vianna; Patrícia C. Brum; Danilo S. Bocalini; Andrei C. Sposito; Luis C. Miguita Junior; Max D. Oliveira; Elaine Batistella; Rodrigo R. Fernandes; Paulo S. Junior; et al. (GeroScience, 2024)

From bacteria to fish: ecotoxicological insights into sulfamethoxazole and trimethoprim - Bárbara S. Diogo; Sara Rodrigues; Oksana Golovko; Sara C. Antunes (Environmental Science and Pollution Research, 2024)
Sulfamethoxazole (SMX) and trimethoprim (TRIM) are two of the most used antibiotics in the last 50 years, to prevent and treat bacterial infections; however, the available literature about toxicity to non-target organisms is quite discrepant and incomplete. This study aims to assess the SMX and TRIM ecotoxicological effects in standard species: Aliivibrio fischeri (bioluminescence inhibition), Escherichia coli ATCC 25922 (growth inhibition), Lemna minor (growth inhibition and biochemical biomarkers), Daphnia magna (immobilization/mortality, life history traits, and biochemical biomarkers), and Danio rerio (survival, hatching, abnormalities, and biochemical biomarkers). The species tested showed different acute sensitivities to SMX ( A. fischeri < D. magna < E. coli < L. minor ) and TRIM ( L. minor < A. fischeri < D. magna < E. coli ) . Overall, TRIM reveals less toxicity than SMX, except for E. coli (Ecotoxicological approach based on Antimicrobial Susceptibility Testing – EcoAST procedure). Both antibiotics affect individually (e.g., growth and survival) and sub-individually (e.g., antioxidant defenses) L. minor , D. magna , and D. rerio . This study allowed us to generate relevant data and fill gaps in the literature regarding the effects of SMX and TRIM in aquatic organisms. The here-obtained results can be used to (i) complete and re-evaluate the Safety Data Sheet to improve the assessment of environmental safety and management of national and international entities; (ii) clarify the environmental risks of these antibiotics in aquatic ecosystems reinforcing the inclusion in the 4th Watch List of priority substances to be monitored in whole inland waters by the Water Framework Directive; and (iii) combat the development of antimicrobial resistance, as well as supporting the definition of environmental measurements in the context of European One Health Action Plan. However, it is essential to continue studying these antibiotics to better understand their toxicity at ecologically relevant concentrations and their long-term effects under different climatic change scenarios.

Continuous UV-C/H2O2 and UV-C/Chlorine applied to municipal secondary effluent and nanofiltration retentate: Removal of contaminants of emerging concern, ecotoxicity, and reuse potential - Fernando Rodrigues-Silva; Carla S. Santos; Joaquín A. Marrero; Rosa Montes; José Benito Quintana; Rosario Rodil; Olga C. Nunes; Maria Clara V.M. Starling; Camila C. Amorim; Ana I. Gomes; Vítor J.P. Vilar (Chemosphere, 2024)

Using quartz OSL signals from SAR cycles for sediment provenance studies - P.E. Souza; N. Porat; A.O. Sawakuchi; C.B.L. Cruz; C. Breda; F.C.G. Rodrigues; S.C. Oliveira; F.N. Pupim (Quaternary Geochronology, 2024)

Intake, digestibility, serum metabolites, and growth performance of male feedlot lambs fed different fat sources - Henry D.R. Alba; José E. de Freitas; Laudí C. Leite; José A.G. Azevêdo; Stefanie A. Santos; Douglas dos S. Pina; Luis G.A. Cirne; Carlindo S. Rodrigues; Manuela S.L. Tosto; Silvia C. Bento; Amanda B. Grimaldi; Gleidson G.P. de Carvalho (Livestock Science, 2024)

Insights on the regional thermal evolution from semianthracite petrology of the Fengfeng coalfield, China - Na Wang; Joan S. Esterle; Sandra Rodrigues; James C. Hower; Shifeng Dai (International Journal of Coal Geology, 2024)

Uncovering microplastics contamination in canned seafood - Diogo M. Silva; C. Marisa R. Almeida; Francisco A. Guardiola; Rúben Pereira; Sabrina M. Rodrigues; Sandra Ramos (Food Chemistry, 2024)

The role of microRNAs in NBS-LRR gene expression and its implications for plant immunity and crop development - J. C. M. Rodrigues; J. Carrijo; R. M. Anjos; N. B. Cunha; P. Grynberg; F. J. L. Aragão; G. R. Vianna (Transgenic Research, 2024)

Adsorption of methane by modified-biochar aiming to improve the gaseous fuels storage/transport capacity: process evaluation and modeling - Ederson F. Klitzke; Felipe Ketzer; Manuelle O. P. Almeida; Jean F. F. Calisto; João H. C. Wancura; Clovis A. Rodrigues; José Vladimir Oliveira; Jacir Dal Magro (Environmental Science and Pollution Research, 2024)

Assessing nine devices to reduce bycatch in the pink shrimp Penaeus paulensis fisheries: Lessons from field experiments with fyke nets - Samanta Silveira; Dérien L.V. Duarte; Lucas dos S. Rodrigues; Luiz Felipe C. Dumont (Regional Studies in Marine Science, 2024)

Exogenous enzymes for gluten-free beer production: A review of the industrial practice and its implications for scientific research - Carolina Pedroso Partichelli; Vitória Costa Conter Silveira; Vitor Manfroi; Rafael C. Rodrigues (Innovative Food Science & Emerging Technologies, 2024)

Zircon U-Pb and Lu-Hf isotopes reveal the crustal evolution of the SW Angolan Shield (Congo Craton) - Ezequiel Ferreira; Jérémie Lehmann; José Feliciano Rodrigues; Ben Hayes; Enrique Merino-Martínez; Lorenzo Milani; Grant M. Bybee; Trishya M. Owen‑Smith; José Luis García-Lobón; Colombo C. G. Tassinari; Henriette Ueckermann; Kei Sato; et al. (Gondwana Research, 2024)

Impact of a run-of-river dam in an Amazonian large river on the spatial and temporal patterns of phytoplankton beta diversity - Felipe M. Zanon; Alfonso Pineda; Fernando M. Lansac-Tôha; Luzia C. Rodrigues (Biological Conservation, 2024)

Chronic Cadmium Exposure can Alter Energy Allocation to Physiological Functions in the Shrimp Penaeus vannamei - Juliana Rodrigues da Costa; Mariana V. Capparelli; Pedro Magalhães Padilha; Emanuelle Borges; Andressa C. Ramaglia; Michelle Roberta dos Santos; Alessandra Augusto (Archives of Environmental Contamination and Toxicology, 2024)

Geography and ecology shape the phylogenetic composition of Amazonian tree communities - Bruno Garcia Luize; David Bauman; Hans ter Steege; Clarisse Palma‐Silva; Iêda Leão do Amaral; Luiz de Souza Coelho; Francisca Dionízia de Almeida Matos; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Florian Wittmann; Carolina V. Castilho; Marcelo de Jesus Veiga Carim; et al. (Journal of Biogeography, 2024)
Aim Amazonia hosts more tree species from numerous evolutionary lineages, both young and ancient, than any other biogeographic region. Previous studies have shown that tree lineages colonized multiple edaphic environments and dispersed widely across Amazonia, leading to a hypothesis, which we test, that lineages should not be strongly associated with either geographic regions or edaphic forest types. Location Amazonia. Taxon Angiosperms (Magnoliids; Monocots; Eudicots). Methods Data for the abundance of 5082 tree species in 1989 plots were combined with a mega‐phylogeny. We applied evolutionary ordination to assess how phylogenetic composition varies across Amazonia. We used variation partitioning and Moran's eigenvector maps (MEM) to test and quantify the separate and joint contributions of spatial and environmental variables to explain the phylogenetic composition of plots. We tested the indicator value of lineages for geographic regions and edaphic forest types and mapped associations onto the phylogeny. Results In the terra firme and várzea forest types, the phylogenetic composition varies by geographic region, but the igapó and white‐sand forest types retain a unique evolutionary signature regardless of region. Overall, we find that soil chemistry, climate and topography explain 24% of the variation in phylogenetic composition, with 79% of that variation being spatially structured ( R 2 = 19% overall for combined spatial/environmental effects). The phylogenetic composition also shows substantial spatial patterns not related to the environmental variables we quantified ( R 2 = 28%). A greater number of lineages were significant indicators of geographic regions than forest types. Main Conclusion Numerous tree lineages, including some ancient ones (>66 Ma), show strong associations with geographic regions and edaphic forest types of Amazonia. This shows that specialization in specific edaphic environments has played a long‐standing role in the evolutionary assembly of Amazonian forests. Furthermore, many lineages, even those that have dispersed across Amazonia, dominate within a specific region, likely because of phylogenetically conserved niches for environmental conditions that are prevalent within regions.

Cytotoxic screening of plants from the Brazilian Atlantic Forest has led to the identification of Casearia arborea and Sorocea hilarii as sources of antitumor compounds - L. A. Rodrigues; A. A. Almeida; A. P. Agrizii; N. Pacheco; B. C. R. Carvalho; A. C. Zanatta; M. Kohlhoff; C. M. M. E. Torres; G. C. Bressan; J. P. V. Leite (Natural Product Research, 2024)

Evidence of plastics contamination and sewage-derived residues in a Brazilian Hope Spot for conservation of marine biodiversity - Cagarras Islands and surrounding waters - Raquel A.F. Neves; Nathália Rodrigues; Guilherme de Luca; Maria Alene A. Oliveira; Thuany F. Carvalho; Nicole S. Santos; Maria Eduarda S. Adelino; Luiza Belli Caldas; Agatha Miralha; Clarissa Naveira; Antonio J.S. Rodrigues; Igor C. Miyahira; et al. (Marine Pollution Bulletin, 2024)

Saline as solvent and ethanol-based purification process for the extraction of proteins and isoflavones from wet okara - Rafaela T. Privatti; Maria C. Capellini; Keila K. Aracava; Silvana M.P. Pugine; Mariza P. de Melo; Christianne E.C. Rodrigues (Food Chemistry, 2024)

From waste to bioactive compounds: A response surface methodology approach to extract antioxidants from Pistacia vera shells for postprandial hyperglycaemia management - Anna Elisabetta Maccarronello; Nunzio Cardullo; Ana Margarida Silva; Antonella Di Francesco; Paulo C. Costa; Francisca Rodrigues; Vera Muccilli (Food Chemistry, 2024)

Biopesticide spinosad: Unraveling ecotoxicological effects on zebrafish, Danio rerio - Inês Amaral; Sara C. Antunes; Daniela Rebelo; António Paulo Carvalho; Sara Rodrigues (Environmental Toxicology and Pharmacology, 2024)

Encapsulation of hydrophobic active ingredients in plant proteins: modulation of interfacial properties and encapsulation efficiency - Janaína G Fernandes; Ramila C Rodrigues; Laura Pereira; Paulo C Stringheta; Pedro H Campelo; Evandro Martins (Current Opinion in Food Science, 2024)

Proximal sensors for modeling clay mineralogy and characterization of soil textural fractions developed from contrasting parent materials - Fernanda Magno Silva; Sérgio Henrique Godinho Silva; Renata Andrade; João Augusto Coblinski; Alberto Vasconcellos Inda; Gustavo Frosi; Suane de Souza Franco Lima; Michele Duarte de Menezes; Tiago Rodrigues Tavares; Luiz Roberto Guimarães Guilherme; David C. Weindorf; Nilton Curi (CATENA, 2024)

Do hurricanes or freezing events regulate the sustainability of subtropical mangroves on the Gulf of Mexico coast? - Marcelo C. L. Cohen; Qiang Yao; Adriana V. de Souza; Kam-biu Liu; Sergio Nunes; Erika Rodrigues; Luiz C. R. Pessenda; Nicholas Culligan (Regional Environmental Change, 2024)

Aspergillosis in Critically Ill Patients with and Without COVID-19 in a Tertiary Hospital in Southern Brazil - Mariana Rodrigues Trápaga; Vanice Rodrigues Poester; Rossana Patrícia Basso; Bianca dos Santos Blan; Lívia Silveira Munhoz; Alessandro C. Pasqualotto; Talita da Fontoura Werner; Maria Letícia Figurelli; David A. Stevens; Andrea von Groll; Melissa Orzechowski Xavier (Mycopathologia, 2024)

The cost of genetic diagnosis of suspected hereditary pediatric cataracts with whole-exome sequencing from a middle-income country perspective: a mixed costing analysis - Luiza M. Neves; Márcia Pinto; Olivia A. Zin; Daniela P. Cunha; Bruna N. S. Agonigi; Fabiana L. Motta; Leonardo H. F. Gomes; Dafne D. G. Horovitz; Daltro C. Almeida; Jocieli Malacarne; Leticia Guida; Andressa Braga; et al. (Journal of Community Genetics, 2024)
Up to 25% of pediatric cataract cases are inherited. There is sparse information in the literature regarding the cost of whole-exome sequencing (WES) for suspected hereditary pediatric cataracts. Molecular diagnosis of suspected hereditary pediatric cataracts is important for comprehensive genetic counseling. We performed a partial economic evaluation with a mixed costing analysis, using reimbursement data and microcosting approach with a bottom-up technique to estimate the cost of using WES for genetic diagnosis of suspected hereditary pediatric cataracts from the perspective of the Brazilian governmental health care system. One hundred and ten participants from twenty-nine families in Rio de Janeiro (RJ) were included. Costs of consumables, staff and equipment were calculated. Two scenarios were created: (1) The reference scenario included patients from RJ with suspected hereditary pediatric cataracts plus two family members. (2) The alternative scenario considered other genetic diseases, resulting in 5,280 exams per month. Sensitivity analysis was also performed. In the reference scenario, the total cost per exam was 700.09 United States dollars (USD), and in the alternative scenario, the total cost was 559.23 USD. The cost of WES alone was 527.85 USD in the reference scenario and 386.98 USD in the alternative scenario. Sensitivity analysis revealed that the largest costs were associated with consumables in both scenarios. Economic evaluations can help inform policy decisions, especially in middle-income countries such as Brazil.

Where is ocean literacy in oceanic islands’ schools? The Azores case - Ana C. Costa; Diana Freitas; Ana I. Santos; Andrea Z. Botelho; Manuela I. Parente; André Behr; Ana M. Rodrigues; Hélia Guerra; José Cascalho; Armando Mendes (Marine Policy, 2024)

A framework for enabling conditions for wastewater reuse - Paulo M. Rodrigues; Francisco S. Pinto; Rui C. Marques (Sustainable Production and Consumption, 2024)

Using dispersion models at microscale to assess long-term air pollution in urban hot spots: A FAIRMODE joint intercomparison exercise for a case study in Antwerp - F. Martín; S. Janssen; V. Rodrigues; J. Sousa; J.L. Santiago; E. Rivas; J. Stocker; R. Jackson; F. Russo; M.G. Villani; G. Tinarelli; D. Barbero; et al. (Science of The Total Environment, 2024)

Comparative virulence of Colletotrichum chrysophilum and Colletotrichum nymphaeae on apple leaves - Antonio J. Andrello; Aline C. Velho; Vanessa F. Soares; Ruan S. de Godoy; Mateus B. de Freitas; Rosa M. Valdebenito-Sanhueza; Franceli Rodrigues Kulcheski; Marciel J. Stadnik (Physiological and Molecular Plant Pathology, 2024)

Provenance of volcano-sedimentary features using tourmaline and REE compositional analysis, in the Paraná Basin, southern Brazil - Isaque C. Rodrigues; Ana M.P. Mizusaki; Glaucia N. Queiroga; Cassiana R.L. Michelin; Fernando R. Rios (Journal of South American Earth Sciences, 2024)

Two decades of clear-cutting threats in the Brazilian Amazonian protected areas around the Jirau, Santo Antônio, and Belo Monte large dams - Silvia Sayuri Mandai; Evandro Albiach Branco; Evandro Mateus Moretto; Jocilene Dantas Barros; Guilherme Prado Alves; Renata Utsunomiya; Gustavo Felipe Balué Arcoverde; Cyro Assahira; Caroline C. Arantes; Guilherme de Sousa Lobo; Miquéias Freitas Calvi; Carolina Rodrigues da Costa Doria; et al. (Journal of Environmental Management, 2024)

Omega-3 fatty acids from fish by-products: Innovative extraction and application in food and feed - Matilde Rodrigues; Ana Rosa; André Almeida; Rui Martins; T.ânia Ribeiro; Manuela Pintado; Raquel F.S. Gonçalves; Ana C. Pinheiro; António J.M. Fonseca; Margarida R.G. Maia; Ana R.J. Cabrita; Lillian Barros; et al. (Food and Bioproducts Processing, 2024)

Feeding behaviour of feedlot lambs offered different amounts of concentrate with or without protected fat - Cláudia L.S. Lima; Douglas dos S. Pina; Gleidson G.P. de Carvalho; Henry D.R. Alba; Maria L.G.M. L. de Araújo, Susiane de C. Matos; Stefanie A. Santos; Maria L.O. Chaves; Carlindo S. Rodrigues; Manuela S.L. Tosto (Applied Animal Behaviour Science, 2024)

Lost in the dark: Antipatharia-Symbiodiniaceae association in the deep waters of the Red Sea - Silvia Vicario; Tullia I. Terraneo; Carolina Bocanegra Castano; Giovanni Chimienti; Nicolas Oury; Silvia Vimercati; Benjamin C. C. Hume; Fabio Marchese; Megan K. B. Nolan; Ameer A. Eweida; Sam J. Purkis; Mattie Rodrigue; et al. (Frontiers in Marine Science, 2024)
Black corals (Hexacorallia: Antipatharia) are a major component of mesophotic and deep marine ecosystems. Due to their preference for light deprived environments, black corals have historically been considered azooxanthellate, yet recent works have found them in association with dinoflagellates of the family Symbiodiniaceae down to 396 m depth. While corals and Symbiodiniaceae generally establish a symbiotic relationship in shallow water environments, the implications of this association is less well understood at deeper depths, where low light penetration cannot sustain efficient photosynthetic activity for the algae. However, Symbiodinaceae are not obligate autotrophs, and their capacity for heterotrophic feeding categorizes them as mixotrophs. In this study, we investigated the presence and diversity of Symbiodiniaceae associated with the deep-sea black coral Bathypathes thermophila (Antipatharia: Schizopathidae), collected from 204 to 655 m depth in the Saudi Arabian Red Sea. Using high-throughput sequencing of the ITS2 region, we report (1) the deepest record to date of Symbiodiniaceae associated with an anthozoan from 655 m, and (2) the first Red Sea record of Antipatharia in association with Symbiodiniaceae. Our analyses revealed that 14 out of 27 colonies of B. thermophila were associated with Symbiodiniaceae of the genera Cladocopium and Durusdinium . We unveiled 16 novel ITS2 type profiles, possibly unique to black corals and/or to these depths, along with seven profiles that were already known from shallow-water hard corals. No significant pattern was detected in terms of community diversity in relation to depth or sampling locality. Our study supports the existence of black corals-Symbiodiniaceae association and warrants further research to better understand the evolutionary processes and physiological mechanisms driving this association, specifically in light deprived environments.

Differentiating Bagasse and Straw as Feedstocks for Sugarcane Cellulosic Ethanol: Insights from Pilot-Scale Pretreatments - Viviane M. Nascimento; Simone C. Nakanishi; Carlos Alberto de Oliveira Filho; Absai da Conceição Gomes; Aline Machado de Castro; Ana Paula Rodrigues Torres; Christian Alejandro Queipo; Danuza Nogueira Moyses; Felipe de Oliveira Brito; Luiz Fernando Martins Bandeira; Carlos Driemeier (BioEnergy Research, 2024)

Landscape Ecology Meets Disease Ecology in the Tropical America: Patterns, Trends, and Future Directions - Matheus C. S. Mancini; Julia Rodrigues Barreto; Raquel L. Carvalho; Renata L. Muylaert; Ricardo Corasa Arrais; Paula R. Prist (Current Landscape Ecology Reports, 2024)

Mindful eating questionnaire: Validation and reliability in Brazilian adults with type 2 diabetes mellitus - Danielle Aparecida Caetano Rodrigues; Aline Marcadenti; Rachel H.V. Machado; Angela C. Bersch-Ferreira; Edilaine C.S. Gherardi-Donato; Driele Quinhoneiro; Jussara Carnevale de Almeida; Viviane Sahade Souza; Simone Raimondi de Souza; Fernanda Michielin Busnello; Daniela Corrêa Ferreira; Josefina Bressan; et al. (Appetite, 2024)

How do microplastics alter molluscicidal activity? Effects of weathered microplastics and niclosamide in developing freshwater snails - Cândido C. Rodrigues; Cyntia A.Y. Harayashiki; Eufrásia S. Pereira; Gabriel L.S. Rodrigues; Bruno J. Neves; Thiago L. Rocha (Science of The Total Environment, 2024)

Applying multi-criteria decision analysis to combine life cycle assessment with circularity indicators - Erika Barrak; Carla Rodrigues; Carlos Henggeler Antunes; Fausto Freire; Luis C. Dias (Journal of Cleaner Production, 2024)

Inflammatory infiltrate in the feline mammary gland: healthy, non-neoplastic, benign and malignant lesions - J. Rodrigues-Jesus; A.C. Figueira; C. Marrinhas; G.N. Petrucci; H. Gregório; F. Tinoco; A. Goulart; H. Felga; H. Vilhena; A. Canadas-Sousa; P. Dias-Pereira (Journal of Comparative Pathology, 2024)

Chilled Pacu (Piaractus mesopotamicus) fillets: Modeling Pseudomonas spp. and psychrotrophic bacteria growth and monitoring spoilage indicators by 1H NMR and GC–MS during storage - Rafaela C. Baptista; Rodrigo B.A. Oliveira; Antonio A. Câmara; Émilie Lang; Juliana L.P. dos Santos; Matheus Pavani; Tatiane M. Guerreiro; Rodrigo R. Catharino; Elenilson G.A. Filho; Sueli Rodrigues; Edy S. de Brito; Verônica O. Alvarenga; et al. (International Journal of Food Microbiology, 2024)

The vicariant role of Caribbean formation in driving speciation in American loliginid squids: the case of Doryteuthis pealeii (Lesueur 1821) - João Bráullio Luna Sales; Frank E. Anderson; Bianca Lima Paiva; Yasmim T. C. Cunha; Alan Érik Souza Rodrigues; Yrlene Ferreira; Luis Fernando S. Rodrigues-Filho; Paul W. Shaw; Manuel Haimovici; Unai Markaida; Jonathan S. Ready; Iracilda Sampaio (Marine Biology, 2024)

A comprehensive strategy for the conservation of forest tree genetic diversity: an example with the protected Pinus nigra subsp. salzmannii (Dunal) Franco in France - C. Scotti-Saintagne; A. de Sousa Rodrigues; A. Roig; B. Fady (Conservation Genetics, 2024)

Compositional and functional response of bacterial communities and soil greenhouse gas fluxes in pastures after a strong precipitation-induced event - Karen C.F. Santaren; Natassia M. Armacolo; Fabiano C. Balieiro; Renato A.R. Rodrigues; Bruno J.R. Alves; Ademir Fontana; Caio T.C.C. Rachid (Applied Soil Ecology, 2024)

Consistent Symbiodiniaceae community assemblage in a mesophotic-specialist coral along the Saudi Arabian Red Sea - Silvia Vimercati; Tullia I. Terraneo; Carolina Bocanegra Castano; Federica Barreca; Benjamin C. C. Hume; Fabio Marchese; Mustapha Ouhssain; Alexandra Steckbauer; Giovanni Chimienti; Ameer A. Eweida; Christian R. Voolstra; Mattie Rodrigue; et al. (Frontiers in Marine Science, 2024)
Introduction The Red Sea is a narrow rift basin characterized by latitudinal environmental gradients which shape the diversity and distribution of reef-dwelling organisms. Studies on Symbiodiniaceae associated with select hard coral taxa present species- specific assemblages and concordant variation patterns from the North to southeast Red Sea coast at depths shallower than 30 m. At mesophotic depths, however, algal diversity studies are rare. Here, we characterize for the first-time host-associated algal communities of a mesophotic specialist coral species, Leptoseris cf. striatus , along the Saudi Arabian Red Sea coast. Methods We sampled 56 coral colonies spanning the eastern Red Sea coastline from the Northern Red Sea to the Farasan Banks in the South, and across two sampling periods, Fall 2020 and Spring 2022. We used Next Generation Sequencing of the ITS2 marker region in conjunction with SymPortal to denote algal assemblages. Results and discussion Our results show a relatively stable coral species-specific interaction with algae from the genus Cladocopium along the examined latitudinal gradient, with the appearance, in a smaller proportion, of presumed thermally tolerant algal taxa in the genera Symbiodinium and Durusdinium during the warmer season (Fall 2020). Contrary to shallow water corals, our results do not show a change in Symbiodiniaceae community composition from North to South in this mesophotic specialist species. However, our study highlights for the first time that symbiont communities are subject to change over time at mesophotic depth, which could represent an important phenomenon to address in future studies.

Repeated water deficit events trigger adjustments in enzymatic antioxidant system in oil palm - Wagner Romulo L. Lopes Filho; Flavio Henrique S. Rodrigues; Rosane Patrícia F. Chaves; Roberto L. Cunha; Lucas C. Costa; Hugo A. Pinheiro (Theoretical and Experimental Plant Physiology, 2024)

Occurrence of antibiotics, hormones and PFAs in surface water from a Nile tilapia aquaculture facility in a Brazilian hydroelectric reservoir - Daniel Aparecido da S. Rodrigues; Maria Clara V.M. Starling; André Luiz C. de Barros; Mônica C. Santos; Eloísa Stéphanie da Silva; Guenther Carlos C. Viana; Lara Fabian da S. Ribeiro; Matt F. Simcik; Camila C. Amorim (Chemosphere, 2024)

Performance of spray nozzles and droplet size on glufosinate deposition and weed biological efficacy - Evandro P. Prado; Júlio C. Guerreiro; Pedro J. Ferreira-Filho; Vagner do Nascimento; Samuel Ferrari; Fernando S. Galindo; Marina Funichello; Carlos G. Raetano; Paulo H. Pagliari; Rodolfo G. Chechetto; Arthur D. Rodrigues Neto (Crop Protection, 2024)

Extraction of phenolic compounds from grape pomace using ohmic heating: Chemical composition, bioactivity and bioaccessibility - P. Ferreira-Santos; C. Nobre; R.M. Rodrigues; Z. Genisheva; C. Botelho; J.A. Teixeira (Food Chemistry, 2024)

Cookie composition analysis by Fourier transform near infrared spectroscopy coupled to chemometric analysis - Cristina Quintelas; Cláudia Rodrigues; Clara Sousa; Eugénio C. Ferreira; António L. Amaral (Food Chemistry, 2024)

Spatial accumulation of flood-driven riverside litter in two Northern Atlantic Rivers - G. Pace; J. Lourenço; C.A. Ribeiro; C. Rodrigues; C. Pascoal; F. Cássio (Environmental Pollution, 2024)

Intensification of Amazon River Prawn Hatchery - Michelle Pinheiro Vetorelli; Laurindo André Rodrigues; Janaina Mitsue Kimpara; Wagner C. Valenti (Fishes, 2024)
The effects of the intensification on the performance of the Amazon River prawn hatchery carried out in a simple recirculation system were investigated. Newly hatched larvae were stocked in 120 L tanks at 80, 100, 120 and 140 larvae L−1 in a closed recirculating system. The experiment used a randomized block design with five replicates. An exponential equation was adjusted to express the relationship between the stocking density and productivity (postlarvae L−1). The development, larval quality, survival and postlarval (PL) dry weight did not significantly differ among the treatments (p > 0.05). When 80 larvae were stocked, the productivity (54 ± 11 PL L−1) was lower than those at higher densities (p

Rising mollusk bivalves from the ashes: Geologic, biostratigraphic and evolutionary implications from tuff data in the Permian Corumbataí Formation, Paraná Basin, Brazil - B. Christofoletti; L.V. Warren; F.G. Varejão; M.G. Simões; L.E. Gómez-Peral; C. Lana; M.G. Rodrigues; M.L. Assine (Journal of South American Earth Sciences, 2024)

Eucalyptus plantation reduces diversity and disrupts predator-prey correlations of soil invertebrates within Atlantic Forest - Felipe Martello; Wesley Dáttilo; Débora Rodrigues Souza-Campana; Hugo Reis Medeiros; Rogério R. Silva; Milton Cezar Ribeiro; Maria Santina C. Morini (Forest Ecology and Management, 2024)

Allometric models for non-destructive estimation of the leaflet area in acai (Euterpe oleracea Mart.) - Samara K. A. de Sousa; Rodrigo G. M. Nascimento; Flavio Henrique S. Rodrigues; Rafael G. Viana; Lucas C. da Costa; Hugo A. Pinheiro (Trees, 2024)

Mating system and inbreeding depression in Hymenaea stigonocarpa - Darlin U.G. Zaruma; Alexandre M. Sebbenn; Bruno C. Rossini; Ana C.F. Pardo; Marcela A.M. Silvestre; Jose Cambuim; Alexandre M. da Silva; Silvelise Pupin; Carlos J. Rodrigues; Celso L. Marino; Mário L.T. de Moraes (Tree Genetics & Genomes, 2024)

Effects of Acacia mearnsii tannins on growth performance, footpad dermatitis, nutrient digestibility, intestinal permeability, and meat quality of broiler chickens - Guilherme L. Godoy; Beatriz N. Rodrigues; Jessica C. Agilar; Valeria Biselo; Danielle D. Brutti; Greicy S. Maysonnave; Catarina Stefanello (Animal Feed Science and Technology, 2024)

Understanding temporal variability across trophic levels and spatial scales in freshwater ecosystems - Tadeu Siqueira; Charles P. Hawkins; Julian D. Olden; Jonathan Tonkin; Lise Comte; Victor S. Saito; Thomas L. Anderson; Gedimar P. Barbosa; Núria Bonada; Claudia C. Bonecker; Miguel Cañedo‐Argüelles; Thibault Datry; et al. (Ecology, 2024)
A tenet of ecology is that temporal variability in ecological structure and processes tends to decrease with increasing spatial scales (from locales to regions) and levels of biological organization (from populations to communities). However, patterns in temporal variability across trophic levels and the mechanisms that produce them remain poorly understood. Here we analyzed the abundance time series of spatially structured communities (i.e., metacommunities) spanning basal resources to top predators from 355 freshwater sites across three continents. Specifically, we used a hierarchical partitioning method to disentangle the propagation of temporal variability in abundance across spatial scales and trophic levels. We then used structural equation modeling to determine if the strength and direction of relationships between temporal variability, synchrony, biodiversity, and environmental and spatial settings depended on trophic level and spatial scale. We found that temporal variability in abundance decreased from producers to tertiary consumers but did so mainly at the local scale. Species population synchrony within sites increased with trophic level, whereas synchrony among communities decreased. At the local scale, temporal variability in precipitation and species diversity were associated with population variability (linear partial coefficient, β = 0.23) and population synchrony (β = −0.39) similarly across trophic levels, respectively. At the regional scale, community synchrony was not related to climatic or spatial predictors, but the strength of relationships between metacommunity variability and community synchrony decreased systematically from top predators (β = 0.73) to secondary consumers (β = 0.54), to primary consumers (β = 0.30) to producers (β = 0). Our results suggest that mobile predators may often stabilize metacommunities by buffering variability that originates at the base of food webs. This finding illustrates that the trophic structure of metacommunities, which integrates variation in organismal body size and its correlates, should be considered when investigating ecological stability in natural systems. More broadly, our work advances the notion that temporal stability is an emergent property of ecosystems that may be threatened in complex ways by biodiversity loss and habitat fragmentation.

Pest termite Cryptotermes havilandi (Sjöstedt, 1900) (Blattodea: Isoptera: Kalotermitidae) as an invasive species of natural ecosystems in northeastern Brazil - Renan Rodrigues Ferreira; Ricardo Koroiva; Flávia Maria S. Moura; Sara Rikeley Paulino Monteiro; Rozzanna Esther C. R. Figueirêdo; Matilde Vasconcelos Ernesto; Alexandre Vasconcellos (International Journal of Tropical Insect Science, 2024)

Dynamics of CO2, CH4, and N2O in Ria Formosa coastal lagoon (southwestern Iberia) and export to the Gulf of Cadiz - A. Sierra; C. Correia; T. Ortega; J. Forja; M. Rodrigues; A. Cravo (Science of The Total Environment, 2024)

Impact of exposure to atmospheric particulate matter in human skin-derived fibroblast cells: A metabolomics approach for the class of amino acids based on GC×GC-Q-TOFMS/MS - Samantha C.H. Rodrigues; Helvécio C. Menezes; Dawidson A. Gomes; Zenilda L. Cardeal (Journal of Hazardous Materials, 2024)

Bioactive compounds from Actinidia arguta fruit as a new strategy to fight glioblastoma - Catarina Macedo; Paulo C. Costa; Francisca Rodrigues (Food Research International, 2024)

Experimental and Theoretical Investigation of the Effect of Cellulose Nanowhiskers on the Pb(II) Adsorption by Superabsorbent Hydrogel Nanocomposites - André R. Fajardo; Robson S. Oliboni; Carlos E. C. de Magalhães; Maria G. M. Chaves; Francisco H. A. Rodrigues (Water, Air, & Soil Pollution, 2024)

Fungal Cultivars of Higher Attine Ants Promote Escovopsis Chemotropism - Karina B. de Oliveira; Aryel C. Goes; Airton D. Silva; Paulo C. Vieira; Andre Rodrigues (Current Microbiology, 2024)

Effects of feeding mycotoxin-contaminated diets and the use of an adsorbent on the intake, digestibility, rumen fermentation, nitrogen balance and physiological parameters in the blood of Nellore steers - Luis Henrique C. Batista; Gustavo R. Siqueira; Luiz F. Costa e Silva; Anne Koontz; Yury T. Granja-Salcedo; Igor M. Ferreira; Iorrano A. Cidrini; Karla A. Oliveira; Amanda Caroliny M. de Queiroz; Aline N. Rodrigues; Flávio D. de Resende (Animal Feed Science and Technology, 2024)

Blue carbon stock heterogeneity in Brazilian mangrove forests: A systematic review - Natalia Beloto; Luiz C. Cotovicz Jr.; José Vítor Machado Rodrigues; Maria Regina Gmach; Martin Zimmer; Véronique Helfer; Marcelo O. Soares; Luis Ernesto Arruda Bezerra (Marine Pollution Bulletin, 2023)

Impacts on South America moisture transport under Amazon deforestation and 2 °C global warming - Murilo Ruv Lemes; Gilvan Sampaio; Luis Garcia-Carreras; Gilberto Fisch; Lincoln Muniz Alves; Richard Bassett; Richard Betts; Jelena Maksic; Marília Harumi Shimizu; Roger Rodrigues Torres; Marcelo Guatura; Luana Santamaria Basso; et al. (Science of The Total Environment, 2023)

How did a tailings spill change the distribution of legacy organochlorine compounds in a Southeast Atlantic inner shelf area: Is a hidden danger being transferred to the ocean? - Ana Caroline Cabral; Amanda Câmara de Souza; Fabian Sá; Renato Rodrigues Neto; César C. Martins (Science of The Total Environment, 2023)

Effects of chemical aging on carbonaceous materials: Stability of water-dispersible colloids and their influence on the aggregation of natural-soil colloid - Laís G. Fregolente; Maria T. Rodrigues; Naiara C. Oliveira; Bruno Sousa Araújo; Ícaro V. Nascimento; Antonio G. Souza Filho; Amauri J. Paula; Mirian C.G. Costa; Jaedson C.A. Mota; Odair P. Ferreira (Science of The Total Environment, 2023)

Facemasks: An insight into their abundance in wetlands, degradation, and potential ecotoxicity - Ana Paço; Ana M. Oliveira; Diogo A. Ferreira-Filipe; Andreia C.M. Rodrigues; Rui J.M. Rocha; Amadeu M.V.M. Soares; Armando C. Duarte; Ana L. Patrício Silva; Teresa Rocha-Santos (Science of The Total Environment, 2023)

Catalyst-free persulfate activation by UV/visible radiation for secondary urban wastewater disinfection - Mário R.C. Calaixo; Sara Ribeirinho-Soares; Luis M. Madeira; Olga C. Nunes; Carmen S.D. Rodrigues (Journal of Environmental Management, 2023)

Solar photocatalysis using post-consumer alkaline batteries for degrading contaminants of emerging concern in surface water - Guenther Carlos C. Viana; Elisângela Maria R. Rocha; Elisandra Scapin; Arthur Cahino; Iris Rebeca D. Leite; Daniel A. Bertuol; José D. Ardisson; Daniel Aparecido S. Rodrigues; Camila C. Amorim (Journal of Environmental Chemical Engineering, 2023)

Acid hydrolysis conditions do affect the non-extractable phenolic compounds composition from grape peel and seed - Caroline Carboni Martins; Alessandro Kahmann; Michel José Anzanello; Rafael C. Rodrigues; Eliseu Rodrigues; Giovana Domeneghini Mercali (Food Research International, 2023)

A meta-analytical review of turbidity effects on fish mobility - Jean N. Rodrigues; Jean C. G. Ortega; Danielle K. Petsch; Andre A. Padial; Dieison A. Moi; Bruno R. S. Figueiredo (Reviews in Fish Biology and Fisheries, 2023)

A limitless Brazilian scientist: Professor Travassos and his contribution to cancer biology - Elaine G. Rodrigues; Andrey S. Dobroff; Denise C. Arruda; Dayane B. Tada; Thaysa Paschoalin; Luciano Polonelli (Brazilian Journal of Microbiology, 2023)

The amphibian's spleen as a source of biomarkers for ecotoxicity assessment: Historical review and trends - Elisabete Tsukada; Cândido C. Rodrigues; Jaqueline C. Jacintho; Lilian Franco-Belussi; Monica Jones-Costa; Fábio Camargo Abdalla; Thiago Lopes Rocha; Raquel F. Salla (Science of The Total Environment, 2023)

A multi-criteria framework for the ecodesign of bio-based materials at early development stages - Jade Müller-Carneiro; Carla Rodrigues; Luís C. Dias; Carlos Henggeler Antunes; Adriano L.A. Mattos; Fausto Freire (Journal of Cleaner Production, 2023)

Chitosan with modified porosity and crosslinked with genipin: A dynamic system structurally characterized - Elí Emanuel Esparza-Flores; Larissa Bertoldo Siquiera; Fernanda Dias Cardoso; Tania Haas Costa; Edilson Valmir Benvenutti; Iliana E. Medina-Ramírez; Mercedes Perullini; Patricio R. Santagapita; Rafael C. Rodrigues; Plinho F. Hertz (Food Hydrocolloids, 2023)

Forecasting air pollutants using classification models: a case study in the Bay of Algeciras (Spain) - M. I. Rodríguez-García; M. C. Ribeiro Rodrigues; J. González-Enrique; J. J. Ruiz-Aguilar; I. J. Turias (Stochastic Environmental Research and Risk Assessment, 2023)
The main goal of this work is to obtain reliable predictions of pollutant concentrations related to maritime traffic (SO 2 , PM 10 , NO 2 , NO X , and NO) in the Bay of Algeciras, located in Andalusia, the south of Spain. Furthermore, the objective is to predict future air quality levels of the principal maritime traffic-related pollutants in the Bay of Algeciras as a function of the rest of the pollutants, the meteorological variables, and vessel data. In this sense, three scenarios were analysed for comparison, namely Alcornocales Park and the cities of La Línea and Algeciras. A database of hourly records of air pollution immissions, meteorological measurements in the Bay of Algeciras region and a database of maritime traffic in the port of Algeciras during the years 2017 to 2019 were used. A resampling procedure using a five-fold cross-validation procedure to assure the generalisation capabilities of the tested models was designed to compute the pollutant predictions with different classification models and also with artificial neural networks using different numbers of hidden layers and units. This procedure enabled appropriate and reliable multiple comparisons among the tested models and facilitated the selection of a set of top-performing prediction models. The models have been compared using several quality classification indexes such as sensitivity, specificity, accuracy, and precision. The distance ( d 1 ) to the perfect classifier (1, 1, 1, 1) was also used as a discriminant feature, which allowed for the selection of the best models. Concerning the number of variables, an analysis was conducted to identify the most relevant ones for each pollutant. This approach aimed to obtain models with fewer inputs, facilitating the design of an optimised monitoring network. These more compact models have proven to be the optimal choice in many cases. The obtained sensitivities in the best models were 0.98 for SO 2 , 0.97 for PM 10 , 0.82 for NO 2 and NO X , and 0.83 for NO. These results demonstrate the potential of the models to forecast air pollution in a port city or a complex scenario and to be used by citizens and authorities to prevent exposure to pollutants and to make decisions concerning air quality.

Are the ecotoxicological tools viable to evaluate the effectiveness of wastewater treatment plant effluents? - B. S. Diogo; S. Rodrigues; O. M. Lage; S. C. Antunes (International Journal of Environmental Science and Technology, 2023)
Ecotoxicological tools have proved to be sensitive and appropriate for the evaluation of the effectiveness of treatments used in wastewater treatment plants (WWTP). The objective of this study was to assess the applicability of bioassays and biomarkers to evaluate the efficiency of different treatments throughout WWTP samples[A—raw influent, B—preliminary effluent, C—final effluent, and D—receiving stream], seasonally over 1 year, through a multispecies approach: i) bacterial cell viability [ Escherichia coli , Rhodopirellulla rubra , Arthrobacter sp., and Pseudomonas putida ]; ii) microalgae Raphidocelis subcapitata and the macrophyte Lemna minor growth inhibition; and iii) microcrustacean Daphnia magna acute and feeding rate assays. Total chlorophyll, malondialdehyde, and proline levels were evaluated in L. minor , and catalase, glutathione-S-transferase activities, and thiobarbituric acid reactive substances levels were quantified in D. magna , after exposure to wastewater samples. Overall, the tested species showed different sensitivities, P. putida = Arthrobacter sp. = R. rubra < R. subcapitata < E. coli = D. magna = L. minor , to the collected samples. The results obtained in D. magna and L. minor assays demonstrated that these organisms can be used in programs for monitoring and environmental assessment of wastewater effluents. The present study demonstrates the usefulness of ecotoxicological tools, with multispecies and different endpoints, to assess the effectiveness of WWTPs. Moreover, it is important to ensure that WWTP implements a monitoring program to minimize the discharge of effluents that compromise the environment in order to guarantee the good ecological quality of the environmental ecosystems.

Prolonged drought influences the taxonomic and functional structure of fish assemblages in estuaries along the Brazilian semiarid coast - Ronaldo C. Gurgel-Lourenço; Carlos A. S. Rodrigues-Filho; Leonardo M. Pinto; Jorge I. Sánchez-Botero (Hydrobiologia, 2023)

Long-term memory in Staphylococcus aureus α-hemolysin ion channel kinetics - M. P. Silva; C. G. Rodrigues; D. C. Machado; R. A. Nogueira (European Biophysics Journal, 2023)

Sustainable treatment of municipal secondary effluent from UASB systems by solar photo-Fenton: CECs removal and toxicity control - Fernando Rodrigues-Silva; Maria Clara V.M. Starling; Daniel Aparecido S. Rodrigues; Camila C. Amorim (Journal of Environmental Chemical Engineering, 2023)

Wheat craft beer made from AFB1-contaminated wheat malt contains detectable mycotoxins, retains quality attributes, but differs in some fermentation metabolites - Fabrícia França Bezerril; Tatiana Colombo Pimentel; Karine Peixoto de Aquino; Danieli C. Schabo; Marcy Heli Paiva Rodrigues; Marcos dos Santos Lima; Donald W. Schaffner; Eliana B. Furlong; Marciane Magnani (Food Research International, 2023)

Flexible thermoelectric energy harvesting system based on polymer composites - T. Rodrigues-Marinho; V. Correia; C.-R. Tubio; A. Ares-Pernas; M.-J. Abad; S. Lanceros-Méndez; P. Costa (Chemical Engineering Journal, 2023)

Anti-Candida Potential of Peptides from Immature and Ripe Fruits of Capsicum chinense Jacq - Marilucia C. Ribeiro; Rodrigo S. Gebara; Gabriel B. Taveira; André de O. Carvalho; Rosana Rodrigues; Erica O. Mello; Celso S. Nagano; Renata P. Chaves; Valdirene M. Gomes (Probiotics and Antimicrobial Proteins, 2023)

Effects of cyclic adenosine monophosphate modulating agents during oocyte pre-maturation and the role of melatonin on in vitro maturation of bovine cumulus-oocyte complexes - Bianca R. Silva; Laryssa G. Barrozo; Danisvânia R. Nascimento; Francisco C. Costa; Venância A.N. Azevedo; Laís R.F.M. Paulino; Everton P.F. Lopes; Ana L.P.S. Batista; Francisco L.N. Aguiar; Christina A. Peixoto; Mariana A.M. Donato; Ana P.R. Rodrigues; et al. (Animal Reproduction Science, 2023)

Effect of the combined use of monensin with virginiamycin or bacitracin on beef cattle performance, liver gluconeogenesis, lipid metabolism and intramuscular fat content - José M. Oliveira Júnior; Bruno G.C. Homem; Daniel Cunha; Ítalo B.G. Lima; Aline C. Rodrigues; Felipe C. Maciel; Edmilson H.R. Domingues; German D. Ramírez-Zamudio; Priscilla D. Teixeira; Tathyane R.S. Gionbelli; Matheus H. Moretti; Daniel R. Casagrande; et al. (Animal Feed Science and Technology, 2023)

Interactive effects of palladium (Pd) and microplastics (MPs) on metal bioaccumulation and biological responses in the Mediterranean mussel, Mytilus galloprovincialis - Joana Patrício Rodrigues; Juan Santos-Echeandía; Elena Chaves-Pozo; Juan Antonio Campillo; Teresa Rocha-Santos; Armando C. Duarte; José R. Rivera-Hernández; Juliana Valdés; Marina Albentosa (Marine Pollution Bulletin, 2023)

P23-05: Urinary monohydroxyl-polycyclic aromatic hydrocarbons and metals in firefighters with active participation in controlled structure fires - J. Teixeira; R. Azevedo; A. Almeida; F. Rodrigues; A. Santos-Silva; C. Delerue-Matos; M. Oliveira (Toxicology Letters, 2023)

P16-13: A step forward the in vitro toxicity assessment of firefighters’ exposure to controlled fires in human cell culture models - M.J. Bessa; J. Teixeira; C. Delerue-Matos; B. Sarmento; M. Oliveira; F. Rodrigues (Toxicology Letters, 2023)

P06-04: Development of the TOXIN Knowledge Graph for assisting animal-free risk assessment of cosmetic ingredients - S. Sepehri; J. Maushagen; G. Vrijens; C. Debruyne; R. Marcelino Rodrigues; A. Sanctorum; O. De Troyer; T. Vanhaecke (Toxicology Letters, 2023)

Plastisphere composition in a subtropical estuary: Influence of season, incubation time and polymer type on plastic biofouling - Tobias Sérvulo; Joe D. Taylor; Maíra C. Proietti; Lucas d.S. Rodrigues; Igor P. Puertas; Roberta A. Barutot; Ana L.d.F. Lacerda (Environmental Pollution, 2023)

Enhancing biotechnological applications of l-asparaginase: Immobilization on amino-epoxy-agarose for improved catalytic efficiency and stability - Denise W. de Melo; Roberto Fernandez-Lafuente; Rafael C. Rodrigues (Biocatalysis and Agricultural Biotechnology, 2023)

Effects of droughts, sea level rise, and increase in outfall discharges on phytoplankton in a temperate estuary (Tagus Estuary, Portugal) - Rui Cereja; Vanda Brotas; Ana C. Brito; Marta Rodrigues (Regional Environmental Change, 2023)
The effects of climate change on the estuarine environment are not fully understood. In temperate regions, droughts are expected to increase in frequency and severity, due to lower precipitation, and the mean sea level is expected to rise. This study aimed to assess how the estuarine environment will be affected by river flow’s reduction, mean sea level rise, and the increase in nutrients discharged from anthropogenic sources. Seven scenarios were simulated and analyzed in the Tagus estuary (Portugal), using the hydrodynamic and biogeochemical model SCHISM: (i) reference scenario, (ii) 10% increase of the wastewater treatment plant (WWTP) outfall’s discharge, (iii) 25% reduction of the river flow, (iv) 50% reduction of the river flow, (v) sea level rise of 0.5 m, (vi) sea level rise of 1 m, and (vii) the combination of 0.5 m of sea level rise and 25% reduction of the river flow. Both the reduction of the river flow and mean sea level rise led to higher salinities and lower nutrients and chlorophyll-a concentrations in the mid and upper areas of the estuary. The reduction in riverine nutrients in the estuary may increase the importance of nutrients from anthropogenic sources (e.g. WTTP discharges) in shaping the spatial variability of the phytoplankton communities in the future.

Silicon, magnesium, and their interaction on wheat resistance against blast - Marcela U. P. Araujo; Lillian M. Oliveira; Leandro C. Silva; Luiz F. C. C. Pinto; Isaias S. Cacique; Fabrício A. Rodrigues (Plant and Soil, 2023)

Topical formulations containing Trichilia catigua extract as therapeutic options for a genital and an acyclovir-resistant strain of herpes recurrent infection - Elisa Vicente Ribelato; Jéssica Wouk; Gabriela Gomes Celestino; Bianca Cerqueira Dias Rodrigues; Maria Laura Goussain Darido; Mario Gabriel Lopes Barboza; Tatiana Jabor Botura; Maylla Cardoso de Oliveira; Fábio Goulart de Andrade; Audrey A. S. G. Lonni; João Carlos Palazzo de Mello; Sérgio Paulo Dejato da Rocha; et al. (Brazilian Journal of Microbiology, 2023)

Giants of the Amazon: How does environmental variation drive the diversity patterns of large trees? - Robson Borges de Lima; Eric Bastos Görgens; Diego Armando S. da Silva; Cinthia Pereira de Oliveira; Anderson Pedro B. Batista; Rinaldo L. Caraciolo Ferreira; Flavia R. C. Costa; Renato A. Ferreira de Lima; Perseu da Silva Aparício; Jadson Coelho de Abreu; José Antônio Aleixo da Silva; Aretha Franklin Guimaraes; et al. (Global Change Biology, 2023)
For more than three decades, major efforts in sampling and analyzing tree diversity in South America have focused almost exclusively on trees with stems of at least 10 and 2.5 cm diameter, showing highest species diversity in the wetter western and northern Amazon forests. By contrast, little attention has been paid to patterns and drivers of diversity in the largest canopy and emergent trees, which is surprising given these have dominant ecological functions. Here, we use a machine learning approach to quantify the importance of environmental factors and apply it to generate spatial predictions of the species diversity of all trees (dbh ≥ 10 cm) and for very large trees (dbh ≥ 70 cm) using data from 243 forest plots (108,450 trees and 2832 species) distributed across different forest types and biogeographic regions of the Brazilian Amazon. The diversity of large trees and of all trees was significantly associated with three environmental factors, but in contrasting ways across regions and forest types. Environmental variables associated with disturbances, for example, the lightning flash rate and wind speed, as well as the fraction of photosynthetically active radiation, tend to govern the diversity of large trees. Upland rainforests in the Guiana Shield and Roraima regions had a high diversity of large trees. By contrast, variables associated with resources tend to govern tree diversity in general. Places such as the province of Imeri and the northern portion of the province of Madeira stand out for their high diversity of species in general. Climatic and topographic stability and functional adaptation mechanisms promote ideal conditions for species diversity. Finally, we mapped general patterns of tree species diversity in the Brazilian Amazon, which differ substantially depending on size class.

Larvicidal potential of extracts and isolated compounds from Piper cubeba fruits against Aedes aegypti (Diptera: Culicidae) larvae - Ana Carolina Gomes; Alexandre Borges; Daniela Garcia Zoca; Marcio Luís Andrade e Silva; Aline Rafaela da Silva Rodrigues Machado; Alex Martins Machado; Mario F. C. Santos; Rosangela da Silva de Laurentiz (Natural Product Research, 2023)

Development of a multigrid operational forecast system for the oceanic region off Rio de Janeiro State - Fernando T.C. Barreto; Franciane E. Curbani; Gabriel M. Zielinsky; Matheus B.L. da Silva; Kaio C. Lacerda; Douglas F. Rodrigues (Ocean Modelling, 2023)

Volcano-sedimentary interactions – A key to understand Cretaceous paleoenvironments in the Paraná basin (southern Brazil) - Fernando R. Rios; Ana M.P. Mizusaki; Cassiana R.L. Michelin; Isaque C. Rodrigues (Journal of South American Earth Sciences, 2023)

Zeolite associated with silicification in a volcano-sedimentary context, southern Brazil - Isaque C. Rodrigues; Ana M.P. Mizusaki; Glaucia N. Queiroga; Cassiana R.L. Michelin; Fernando R. Rios (Journal of South American Earth Sciences, 2023)

Volcanoclastic and epiclastic diagenesis of sandstones associated with volcano-sedimentary deposits from the upper Jurassic, Lower cretaceous, Paraná Basin, southern Brazil - Fernando R. Rios; Ana M.P. Mizusaki; Cassiana R.L. Michelin; Isaque C. Rodrigues (Journal of South American Earth Sciences, 2023)

The potential of almonds, hazelnuts, and walnuts SFE-CO2 extracts as sources of bread flavouring ingredients - Júlia C. Kessler; Vanessa Vieira; Isabel M. Martins; Yaidelin A. Manrique; Patrícia Ferreira; Ricardo C. Calhelha; Andreia Afonso; Lillian Barros; Alírio E. Rodrigues; Madalena M. Dias (Food Chemistry, 2023)

[8] and [10]-Gingerol reduces urothelial damage in ifosfamide-induced hemorrhagic cystitis via JAK/STAT/FOXO signaling pathway via IL-10 - Francisco C. S. Ferreira; Marco Clementino; Francisco A. P. Rodrigues; Herlice N. Veras; Dainesy S. Martins; Marcus L. Queiroga; Mikael A. Lima; Dayara O. Silva; Thiago M. de Freitas; Samilly A. Ribeiro; Mario R. L. Mota; James A. da Silva; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Carbon dioxide separation and capture by adsorption: a review - Mohsen Karimi; Mohammad Shirzad; José A. C. Silva; Alírio E. Rodrigues (Environmental Chemistry Letters, 2023)

On the correlation between thermal imagery and fugitive CH4 emissions from MSW landfills - Marcela C. Rodrigues; Edgar A. Silveira; Antonio C.P. Brasil Junior (Waste Management, 2023)

Detailed characterization of iron-rich tailings after the Fundão dam failure, Brazil, with inclusion of proximal sensors data, as a secure basis for environmental and agricultural restoration - Rafaella T. Silva de Sá; Marcelo Tesser Antunes Prianti; Renata Andrade; Aline Oliveira Silva; Éder Rodrigues Batista; Jessé Valentim dos Santos; Fernanda Magno Silva; Marco Aurélio Carbone Carneiro; Luiz Roberto Guimarães Guilherme; Somsubhra Chakraborty; David C. Weindorf; Nilton Curi; et al. (Environmental Research, 2023)

Removal of Reactive Dyes from a Real Bichromatic Textile Effluent Employing Bio-Based Nanomagnetic Adsorbents - Kátia C. H. Bezerra; Jacqueline R. Nascimento; Tiago D. Martins; Sherlan G. Lemos; Elma N. V. M. Carrilho; Christiane de A. Rodrigues; Geórgia Labuto (Water, Air, & Soil Pollution, 2023)

Optimizing Reservoir Water Management in a Changing Climate - Pedro Beça; António C. Rodrigues; João P. Nunes; Paulo Diogo; Babar Mujtaba (Water Resources Management, 2023)
One of the UN agenda 2030 Sustainable Development goals is associated with water availability and its sustainable management. The present study intends to improve multipurpose reservoir management under climate change scenarios in water scarce regions such as the Mediterranean. Implemented methods include the sequential use of climate model results, hydrological modelling, and reservoir water balance simulation, which are used to estimate future water availability. This work focuses on developing an innovative reservoir management approach based on rule curves and a dynamic assessment of water needs, to improve the management of reservoirs that are dependent on a water transfer system. The proposed methods are implemented in two reservoirs located in a typical Mediterranean river basin and assessed under long-term climate change scenarios up to the year 2100. The results show that the proposed approach can ensure 100% of the urban water supply, improve the reliability of the irrigation supply from 75% to 86–91%, and provide 92–98% of the river ecological flow. It is also demonstrated that this management approach is beneficial, particularly in the case of multipurpose reservoirs in watersheds facing water scarcity risks, to optimize the balance between supply reliability, water transfer volumes, and costs.

An exonuclease V homologue is expressed predominantly during early megasporogenesis in apomictic Brachiaria brizantha - Diva M. A. Dusi; Elizângela R. Alves; Gláucia B. Cabral; Luciane V. Mello; Daniel J. Rigden; Érica D. Silveira; Márcio Alves-Ferreira; Larissa A. Guimarães; Ana Cristina M. M. Gomes; Júlio C. M. Rodrigues; Vera T. C. Carneiro (Planta, 2023)

From ecological functions to ecosystem services: linking coastal lagoons biodiversity with human well-being - Jorge L. Rodrigues-Filho; Rafael L. Macêdo; Hugo Sarmento; Victor R. A. Pimenta; Cecilia Alonso; Clarissa R. Teixeira; Paulo R. Pagliosa; Sérgio A. Netto; Natália C. L. Santos; Fábio G. Daura-Jorge; Odete Rocha; Paulo Horta; et al. (Hydrobiologia, 2023)

A new species of mailed catfish of genus Rhadinoloricaria (Siluriformes: Loricariidae: Loricariinae) from Rio Negro basin, Brazil - Jefferson L. Crispim‐Rodrigues; Maxwell J. Bernt; Brandon T. Waltz; Gabriel S. C. Silva; Ricardo C. Benine; Claudio Oliveira; Raphaël Covain; Fábio F. Roxo (Journal of Fish Biology, 2023)
During a recent collection expedition to the Rio Negro, in the state of Amazonas, Brazil, eight individuals of an unknown species were collected, with a combination of characteristics that placed the species in the genus Rhadinoloricaria . Furthermore, the presence of two autapomorphic characteristics, including numerous elongated papillae on the lower lip and unbranched barbelets on the margin of lower lip, suggests that it is a new species. From morphological and phylogenetic analyses, including the sequencing of specific genes to calculate the maximum likelihood analyses, coupled with osteological computed tomography (CT) scan analyses, the authors corroborated that the specimens represent a new species of Rhadinoloricaria , described in the present study.

Microplastics altered cellular responses, physiology, behaviour, and regeneration of planarians feeding on contaminated prey - Sara A.M. Silva; Joana C. Prata; Patrícia Dias-Pereira; Andreia C.M. Rodrigues; Amadeu M.V.M. Soares; Renato A. Sarmento; Teresa Rocha-Santos; Carlos Gravato; Ana L. Patrício Silva (Science of The Total Environment, 2023)

Green solvents for the selective extraction of bioactive compounds from by-products of the coffee production chain - Mariana Rodrigues da Silva; Rebecca E. Jelley; Renato Lajarim Carneiro; Bruno Fedrizzi; Cameron C. Weber; Cristiano Soleo Funari (Innovative Food Science & Emerging Technologies, 2023)

Identification of Clinical Trichosporon asteroides Strains by MALDI-TOF Mass Spectrometry: Evaluation of the Bruker Daltonics Commercial System and an In-House Developed Library - Elaine Cristina Francisco; Mexx Ebbing; Arnaldo Lopes Colombo; Ferry Hagen; Guilherme M. Chaves; Ana Verena A. Mendes; Marcio de Oliveira Silva; Maria Goreth de Andrade Barberino; Rejane Pereira Neves; Monica Borges Botura; Rosane C. Hahn; João Nóbrega de Almeida Junior; et al. (Mycopathologia, 2023)

Structural MRI Texture Analysis for Detecting Alzheimer’s Disease - Joana Silva; Bruno C. Bispo; Pedro M. Rodrigues (Journal of Medical and Biological Engineering, 2023)
Purpose: Alzheimer’s disease (AD) has the highest worldwide prevalence of all neurodegenerative disorders, no cure, and low ratios of diagnosis accuracy at its early stage where treatments have some effect and can give some years of life quality to patients. This work aims to develop an automatic method to detect AD in 3 different stages, namely, control (CN), mild-cognitive impairment (MCI), and AD itself, using structural magnetic resonance imaging (sMRI). Methods: A set of co-occurrence matrix and texture statistical measures (contrast, correlation, energy, homogeneity, entropy, variance, and standard deviation) were extracted from a two-level discrete wavelet transform decomposition of sMRI images. The discriminant capacity of the measures was analyzed and the most discriminant ones were selected to be used as features for feeding classical machine learning (cML) algorithms and a convolution neural network (CNN). Results: The cML algorithms achieved the following classification accuracies: 93.3% for AD vs CN, 87.7% for AD vs MCI, 88.2% for CN vs MCI, and 75.3% for All vs All. The CNN achieved the following classification accuracies: 82.2% for AD vs CN, 75.4% for AD vs MCI, 83.8% for CN vs MCI, and 64% for All vs All. Conclusion: In the evaluated cases, cML provided higher discrimination results than CNN. For the All vs All comparison, the proposed method surpasses by 4% the discrimination accuracy of the state-of-the-art methods that use structural MRI.

Effect of fish downstream supply chain on wealth creation: the case of tambatinga in the Brazilian Midnorth - F. Gilson; M. B. New; L. A. Rodrigues; W. C. Valenti (Aquaculture International, 2023)

Multiproxy reconstruction of late quaternary upper ocean temperature in the subtropical southwestern Atlantic - Joana F. Cruz; Ioanna Bouloubassi; Arnaud Huguet; Alice M.S. Rodrigues; Thiago P. Santos; Igor M. Venancio; Douglas Lessa; Rodrigo L. Sobrinho; Rodrigo A. Nascimento; Marcelo C. Bernardes (Quaternary Science Reviews, 2023)

A forecast effects of climate change and anthropogenic compounds in Gambusia holbrooki: ecotoxicological effects of salinity and metformin - Maria Sousa; Sara Rodrigues; Carlo Pretti; Valentina Meucci; Federica Battaglia; Rosa Freitas; Sara C Antunes (Aquatic Toxicology, 2023)

Colchicine reduces the activation of NLRP3 inflammasome in COVID-19 patients - N. B. Amaral; T. S. Rodrigues; M. C. Giannini; M. I. Lopes; L. P. Bonjorno; P. I. S. O. Menezes; S. M. Dib; S. L. G. Gigante; M. N. Benatti; U. C. Rezek; L. L. Emrich-Filho; B. A. Sousa; et al. (Inflammation Research, 2023)

The global EPTO database: Worldwide occurrences of aquatic insects - Afroditi Grigoropoulou; Suhaila Ab Hamid; Raúl Acosta; Emmanuel Olusegun Akindele; Salman A. Al‐Shami; Florian Altermatt; Giuseppe Amatulli; David G. Angeler; Francis O. Arimoro; Jukka Aroviita; Anna Astorga‐Roine; Rafael Costa Bastos; et al. (Global Ecology and Biogeography, 2023)
Motivation Aquatic insects comprise 64% of freshwater animal diversity and are widely used as bioindicators to assess water quality impairment and freshwater ecosystem health, as well as to test ecological hypotheses. Despite their importance, a comprehensive, global database of aquatic insect occurrences for mapping freshwater biodiversity in macroecological studies and applied freshwater research is missing. We aim to fill this gap and present the Global EPTO Database , which includes worldwide geo‐referenced aquatic insect occurrence records for four major taxa groups: Ephemeroptera, Plecoptera, Trichoptera and Odonata (EPTO). Main type of variables contained A total of 8,368,467 occurrence records globally, of which 8,319,689 (99%) are publicly available. The records are attributed to the corresponding drainage basin and sub‐catchment based on the Hydrography90m dataset and are accompanied by the elevation value, the freshwater ecoregion and the protection status of their location. Spatial location and grain The database covers the global extent, with 86% of the observation records having coordinates with at least four decimal digits (11.1 m precision at the equator) in the World Geodetic System 1984 (WGS84) coordinate reference system. Time period and grain Sampling years span from 1951 to 2021. Ninety‐nine percent of the records have information on the year of the observation, 95% on the year and month, while 94% have a complete date. In the case of seven sub‐datasets, exact dates can be retrieved upon communication with the data contributors. Major taxa and level of measurement Ephemeroptera, Plecoptera, Trichoptera and Odonata, standardized at the genus taxonomic level. We provide species names for 7,727,980 (93%) records without further taxonomic verification. Software format The entire tab‐separated value (.csv) database can be downloaded and visualized at https://glowabio.org/project/epto_database/ . Fifty individual datasets are also available at https://fred.igb‐berlin.de , while six datasets have restricted access. For the latter, we share metadata and the contact details of the authors.

From the shallow to the mesophotic: a characterization of Symbiodiniaceae diversity in the Red Sea NEOM region - Tullia I. Terraneo; Mustapha Ouhssain; Carolina Bocanegra Castano; Manuel Aranda; Benjamin C. C. Hume; Fabio Marchese; Silvia Vimercati; Giovanni Chimienti; Ameer A. Eweida; Christian R. Voolstra; Burton H. Jones; Sam J. Purkis; et al. (Frontiers in Marine Science, 2023)
Introduction The northern Red Sea has been coined a refuge for reef corals due to the exceptional thermal tolerance of these organisms. With ocean warming threatening coral reefs worldwide, a panoptic characterization of corals living in extreme conditions may provide insights into future responses of corals to environmental change. Among other factors, the genotype of the endosymbiotic algae in the family Symbiodiniaceae has been shown to have major implications on the distribution and resilience of their coral hosts. In this study, we aim at genotyping the Symbiodiniaceae communities associated with three depth generalist and one depth specialist coral species, characterized by the ability to withstand environmental conditions that are apparently limiting for other corals and occurring in a unique geographical region. Methods We sampled 50 corals from the northern Saudi Arabian Red Sea and the Gulf of Aqaba, covering a 97 m bathymetric gradient. We used high-throughput ITS2 gene sequencing and recovered different patterns of host–algal associations. Results and discussion The majority of the recovered algal genotypes appeared host- and environment-specific, while others were more widely distributed. At large, coral specimens were overwhelmingly associated with symbionts from the genus Cladocopium and specifically with many previously undescribed genotypes. This suggests the selection of specific genotypes, which might confer resistance and/or resilience to their host counterparts. Interestingly, we found a limited association with Durusdinium spp. and other known tolerant taxa in mesophotic corals in the northern Red Sea, but not in the Gulf of Aqaba. The broad absence of Durusdinium spp., typically ascribed to be stress tolerant, warrants further investigation into Symbiodiniaceae species that convey environmental resilience. Our data will serve as a baseline to explore the occurrence of specific symbionts that might be contributing to coral acclimation and adaptation and to assay how biodiversity might be impacted if subjected to increasing stressors.

Integrated ecosystem assessment around islands of the tropical South Mid-Atlantic Ridge - Amanda R. Rodrigues; Sergio R. Floeter; Vicente Gomes; Débora S. Ferrari; Vinicius J. Giglio; Fernanda C. Silva; Ana M. R. Liedke; Carlos E. L. Ferreira; Kerry Howell; Maria A. Gasalla (Frontiers in Marine Science, 2023)
The South Mid Atlantic Ridge comprises three main oceanic islands in the equatorial and tropical portions of the Atlantic Ocean. These islands are isolated from each other and equidistant from both the continental margins of South America and Africa, sharing common patterns but with different types of human use and pressures. Moreover, the areas beyond national jurisdiction between those islands are visited and exploited by distant fishing fleets and include large areas of shipping activity for commodities. Here, a pioneering integrated ecosystem assessment (IEA) process is constructed for the region among Saint Peter and Saint Paul’s Archipelago (Brazil), Saint Helena Island and Ascension Island (UK overseas territories). For that, we used a qualitative assessment of risks arising from anthropogenic activities, representing a novel contribution to the field. The Options for Delivering Ecosystem-Based Marine Management (ODEMM) approach was applied to trace sector–pressure–component pathways. A ‘linkage framework’ was outlined including pressures affecting each ecosystem component, and supported a process of knowledge attributions that scored the impact risks. All results were validated with regional stakeholders through workshops, including local and international management bodies, non-governmental organizations (NGOs) and scientists. The approach focused on a significant area among encompassing the open ocean, shallow and deep-sea biomes, analyzing the main sectors and pressures affecting the ecological components. Our results identified 14 sectors and 16 key pressures associated with 23 ecosystem components, totaling 780 impact chains. Fishing, shipping, wastewater, and tourism/recreation appeared as the top impacting sectors. Fishing and shipping were the most connected with ecosystem components links. Litter, species extraction, contaminants, and bycatch were the pressures that had the highest risk of impact values. Lastly, demersal and pelagic fish and pelagic and demersal elasmobranchs were the groups with the highest risk related to overall impacts, which were supported by local and regional evidence from long term monitoring programs and local studies. Our study demonstrated that these seemingly pristine islands and oceanic waters are already experiencing human impacts that should be addressed by local both conservation measures and international agreements. We also highlight the pressures that should be prioritized for better monitoring and policy, as well as those linkage components that have been less investigated.

WITHDRAWN: Quantification of quartz microstructural features - Benedito C. Rodrigues; Jorge Pamplona; Mark Peternell; Martin Schwindinger (Journal of Structural Geology, 2023)

Impact of climate changes in the suitable areas for Coffea arabica L. production in Mozambique: Agroforestry as an alternative management system to strengthen crop sustainability - Crimildo T. Cassamo; David Draper; Maria M. Romeiras; Isabel Marques; Rogério Chiulele; Marisa Rodrigues; Marc Stalmans; Fábio L. Partelli; Ana Ribeiro-Barros; José C. Ramalho (Agriculture, Ecosystems & Environment, 2023)

Later prehistoric tin mining in the Ervedosa mine (Vinhais, Portugal): evidence and context - Emmanuelle Meunier; Filipa Dias; João Fonte; Alexandre Lima; Alexandra Rodrigues; Carlo Bottaini; Rui J. C. Silva; João P. Veiga; Manuel F. C. Pereira; Elin Figueiredo (Archaeological and Anthropological Sciences, 2023)

Increased ATP Release and Higher Impact of Adenosine A2A Receptors on Corticostriatal Plasticity in a Rat Model of Presymptomatic Parkinson’s Disease - Francisco Q. Gonçalves; Filipe C. Matheus; Henrique B. Silva; Joana I. Real; Daniel Rial; Ricardo J. Rodrigues; Jean-Pierre Oses; António C. Silva; Nélio Gonçalves; Rui D. Prediger; Ângelo R. Tomé; Rodrigo A. Cunha (Molecular Neurobiology, 2023)
Extracellular ATP can be a danger signal, but its role in striatal circuits afflicted in Parkinson’s disease (PD) is unclear and was now investigated. ATP was particularly released at high stimulation intensities from purified striatal nerve terminals of mice, which were endowed with different ATP-P2 receptors (P2R), although P2R antagonists did not alter corticostriatal transmission or plasticity. Instead, ATP was extracellularly catabolized into adenosine through CD73 to activate adenosine A 2A receptors (A 2A R) modulating corticostriatal long-term potentiation (LTP) in mice. In the presymptomatic phase of a 6-hydroxydopamine rat model of PD, ATP release from striatal nerve terminals was increased and was responsible for a greater impact of CD73 and A 2A R on corticostriatal LTP. These observations identify increased ATP release and ATP-derived formation of extracellular adenosine bolstering A 2A R activation as a key pathway responsible for abnormal synaptic plasticity in circuits involved in the onset of PD motor symptoms. The translation of these findings to humans prompts extending the use of A 2A R antagonists from only co-adjuvants of motor control in Parkinsonian patients to neuroprotective drugs delaying the onset of motor symptoms.

Hypereutrophic conditions limit the removal of suspended particulate matter by the invasive bivalve Mytilopsis leucophaeata (Conrad, 1831) (Dreissenidae) - Nathália Rodrigues; Danielle Ribeiro; Igor C. Miyahira; Samira G. M. Portugal; Luciano N. Santos; Raquel A. F. Neves (Hydrobiologia, 2023)

Correction to: The Role of Vicariance and Paleoclimatic Shifts in the Diversification of Uranoscodon superciliosus (Squamata, Tropiduridae) of the Amazonian Floodplains - Manuela V. dos Santos; Ana L. C. Prudente; Miguel T. Rodrigues; Marcelo J. Sturaro (Evolutionary Biology, 2023)

Rainfall effects on vertical profiles of airborne fungi over a mixed land-use context at the Brazilian Atlantic Forest biodiversity hotspot - Maurício C. Mantoani; Ana P.M. Emygdio; Cristiane Degobbi; Camila Ribeiro Sapucci; Lara C.C. Guerra; Maria A.F.S. Dias; Pedro L.S. Dias; Rafael H.S. Zanetti; Fábio Rodrigues; Gabriel G. Araujo; Dulcilena M.C. Silva; Valter Batista Duo Filho; et al. (Agricultural and Forest Meteorology, 2023)

Pre-assessments of plant conservation status in islands: the case of French Overseas Territories - S. Véron; A. Bernard; E. Lebreton; C. Rodrigues-Vaz; M. Durand; L. Procopio; M. Hélion; M. Gayot; G. Viscardi; G. A. Krupnick; C. M. S. Carrington; V. Boullet; et al. (Biodiversity and Conservation, 2023)

Disinfection of treated urban effluents for reuse by combination of coagulation/flocculation and Fenton processes - João P.F. Venâncio; Sara Ribeirinho-Soares; Luísa C. Lopes; Luis M. Madeira; Olga C. Nunes; Carmen S.D. Rodrigues (Environmental Research, 2023)

Direct evaluation of fire resistance for restrained steel columns in frames using consistent rigid-plastic models and energy formulations - Pedro Dias Simão; João Paulo C. Rodrigues (Engineering Structures, 2023)

Effect of starvation and pesticide exposure on neutral lipid composition of the digestive gland of males of the apple snails Pomacea canaliculata - S.M.L. Lavarías; G.B. Peterson; L.C. Lagrutta; C. Tropea; J.E. Colman Lerner; A. Rodrigues Capítulo; A. Ves-Losada (Aquatic Toxicology, 2023)

Methyl benzoate and nerolidol attract the cyclocephaline beetle Cyclocephala paraguayensis to trumpet flowers - Arodí P. Favaris; Amanda C. Túler; Weliton D. Silva; Marvin Pec; Sérgio R. Rodrigues; Artur C. D. Maia; José Maurício S. Bento (The Science of Nature, 2023)

The antidepressant-like effect elicited by vitamin D3 is associated with BDNF/TrkB-related synaptic protein synthesis - Bruna R. Kouba; Ana Clara N. C. Torrá; Anderson Camargo; Ana Lúcia S. Rodrigues (Metabolic Brain Disease, 2023)

Endotoxin tolerance and low activation of TLR-4/NF-κB axis in monocytes of COVID-19 patients - Gilson P. Dorneles; Paula C. Teixeira; Alessandra Peres; Luiz Carlos Rodrigues Júnior; Simone Gonçalves da Fonseca; Marta Chagas Monteiro; Sarah Eller; Tiago F. Oliveira; Eliana M. Wendland; Pedro R. T. Romão (Journal of Molecular Medicine, 2023)

Pharmacological evaluation of antinociceptive and anti-inflammatory activities of LQFM202: a new piperazine derivative - Aline N. Martins; Dionys de Souza Almeida; Iziara F. Florentino; Lorrane K. da Silva Moreira; Larissa C. Turones; Daniel C. Batista; Lucas S. Machado; Boniek G. Vaz; Luciano M. Lião; Gerlon de Almeida Ribeiro Oliveira; José Luís Rodrigues Martins; James Oluwagbamigbe Fajemiroye; et al. (Inflammopharmacology, 2023)

Strategy to reduce acetic acid in sugarcane bagasse hemicellulose hydrolysate concomitantly with xylitol production by the promising yeast Cyberlindnera xylosilytica in a bioreactor - Fernanda Palladino; Rita C. L. B. Rodrigues; Sinval Pedroso da Silva; Carlos A. Rosa (Biotechnology Letters, 2023)

Microplastic contamination in large migratory fishes collected in the open Atlantic Ocean - Rúben Pereira; Sabrina M. Rodrigues; Diogo Silva; Vânia Freitas; C. Marisa R. Almeida; Sandra Ramos (Marine Pollution Bulletin, 2023)

Improving the accuracy of beef cattle methane inventories in Latin America and Caribbean countries - Guilhermo F.S. Congio; André Bannink; Olga L. Mayorga; João P.P. Rodrigues; Adeline Bougouin; Ermias Kebreab; Paulo C.F. Carvalho; Telma T. Berchielli; Maria E.Z. Mercadante; Sebastião C. Valadares-Filho; Ana L.C.C. Borges; Alexandre Berndt; et al. (Science of The Total Environment, 2023)

Granulated biomass fly ash coupled with fenton process for pulp and paper wastewater treatment - João Peres Ribeiro; Nuno C. Cruz; Márcia C. Neves; Sónia M. Rodrigues; Luís A.C. Tarelho; Maria Isabel Nunes (Environmental Pollution, 2023)

Vibration control systems in a building prototype: Application of SMA coil springs in diagonal bracing and TMD - Yuri J.O. Moraes; Marcelo C. Rodrigues; Antonio A. Silva; Estephanie N.D. Grassi; Carlos J. Araújo (Engineering Structures, 2023)

Impacts of the use of biological pest control on the technical efficiency of the Brazilian agricultural sector - L. C. C. Rodrigues; R. M. Fortini; M. C. R. Neves (International Journal of Environmental Science and Technology, 2023)

Mouse organoids as an in vitro tool to study the in vivo intestinal response to cytotoxicants - F. Jardi; C. Kelly; C. Teague; H. Fowler-Williams; D. C. Sevin; D. Rodrigues; H. Jo; S. Ferreira; B. Herpers; M. Van Heerden; T. de Kok; C. Pin; et al. (Archives of Toxicology, 2023)

Geographic patterns of tree dispersal modes in Amazonia and their ecological correlates - Diego F. Correa; Pablo R. Stevenson; Maria Natalia Umaña; Luiz de Souza Coelho; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Iêda Leão do Amaral; Florian Wittmann; Francisca Dionízia de Almeida Matos; Carolina V. Castilho; Oliver L. Phillips; Juan Ernesto Guevara; et al. (Global Ecology and Biogeography, 2023)
Aim To investigate the geographic patterns and ecological correlates in the geographic distribution of the most common tree dispersal modes in Amazonia (endozoochory, synzoochory, anemochory and hydrochory). We examined if the proportional abundance of these dispersal modes could be explained by the availability of dispersal agents (disperser‐availability hypothesis) and/or the availability of resources for constructing zoochorous fruits (resource‐availability hypothesis). Time period Tree‐inventory plots established between 1934 and 2019. Major taxa studied Trees with a diameter at breast height (DBH) ≥ 9.55 cm. Location Amazonia, here defined as the lowland rain forests of the Amazon River basin and the Guiana Shield. Methods We assigned dispersal modes to a total of 5433 species and morphospecies within 1877 tree‐inventory plots across terra‐firme, seasonally flooded, and permanently flooded forests. We investigated geographic patterns in the proportional abundance of dispersal modes. We performed an abundance‐weighted mean pairwise distance (MPD) test and fit generalized linear models (GLMs) to explain the geographic distribution of dispersal modes. Results Anemochory was significantly, positively associated with mean annual wind speed, and hydrochory was significantly higher in flooded forests. Dispersal modes did not consistently show significant associations with the availability of resources for constructing zoochorous fruits. A lower dissimilarity in dispersal modes, resulting from a higher dominance of endozoochory, occurred in terra‐firme forests (excluding podzols) compared to flooded forests. Main conclusions The disperser‐availability hypothesis was well supported for abiotic dispersal modes (anemochory and hydrochory). The availability of resources for constructing zoochorous fruits seems an unlikely explanation for the distribution of dispersal modes in Amazonia. The association between frugivores and the proportional abundance of zoochory requires further research, as tree recruitment not only depends on dispersal vectors but also on conditions that favour or limit seedling recruitment across forest types.

Rock n' Seeds: A database of seed functional traits and germination experiments from Brazilian rock outcrop vegetation - Carlos A. Ordóñez‐Parra; Roberta L. C. Dayrell; Daniel Negreiros; Antônio C. S. Andrade; Letícia G. Andrade; Yasmine Antonini; Leilane C. Barreto; Fernanda de V. Barros; Vanessa da Cruz Carvalho; Blanca Auxiliadora Dugarte Corredor; Antônio Cláudio Davide; Alexandre A. Duarte; et al. (Ecology, 2023)
Advancing functional ecology depends fundamentally on the availability of data on reproductive traits, including those from tropical plants, which have been historically underrepresented in global trait databases. Although some valuable databases have been created recently, they are mainly restricted to temperate areas and vegetative traits such as leaf and wood traits. Here, we present Rock n' Seeds, a database of seed functional traits and germination experiments from Brazilian rock outcrop vegetation, recognized as outstanding centers of diversity and endemism. Data were compiled through a systematic literature search, resulting in 103 publications from which seed functional traits were extracted. The database includes information on 16 functional traits for 383 taxa from 148 genera, 50 families, and 25 orders. These 16 traits include two dispersal, six production, four morphological, two biophysical, and two germination traits—the major axes of the seed ecological spectrum. The database also provides raw data for 48 germination experiments, for a total of 10,187 records for 281 taxa. Germination experiments in the database assessed the effect of a wide range of abiotic and biotic factors on germination and different dormancy‐breaking treatments. Notably, 8255 of these records include daily germination counts. This input will facilitate synthesizing germination data and using this database for a myriad of ecological questions. Given the variety of seed traits and the extensive germination information made available by this database, we expect it to be a valuable resource advancing comparative functional ecology and guiding seed‐based restoration and biodiversity conservation in tropical megadiverse ecosystems. There are no copyright restrictions on the data; please cite this paper when using the current data in publications; also the authors would appreciate notification of how the data are used in publications.

Diversification of the Pristimantis conspicillatus group (Anura: Craugastoridae) within distinct neotropical areas throughout the Neogene - Antoine Fouquet; Alexandre Réjaud; Miguel T. Rodrigues; Santiago R. Ron; Juan C. Chaparro; Mariela Osorno; Fernanda P. Werneck; Tomas Hrbek; Albertina P. Lima; Teresa Camacho-Badani; Andres F. Jaramillo-Martinez; Jérôme Chave (Systematics and Biodiversity, 2022)

Species diversity and systematics of the Leptodactylus melanonotus group (Anura, Leptodactylidae): review of diagnostic traits and a new species from the Eastern Guiana Shield - Thiago R. Carvalho; Antoine Fouquet; Mariana L. Lyra; Ariovaldo A. Giaretta; C. Eduardo Costa-Campos; Miguel T. Rodrigues; Célio F. B. Haddad; Santiago R. Ron (Systematics and Biodiversity, 2022)

Applications of advanced diffusion MRI in early brain development: a comprehensive review - Marissa DiPiero; Patrik Goncalves Rodrigues; Alyssa Gromala; Douglas C. Dean (Brain Structure and Function, 2022)

Withalutin, a new cytotoxic withanolide from Athenaea velutina (Sendtn.) D’Arcy - Alisson A. Almeida; Betania B. Cota; Laís A. Rodrigues; Luana L. Dutra; Markus Kohlhoff; Gustavo C. Bressan; Geraldo C. Brandão; João P. V. Leite (Natural Product Research, 2022)

Triiodothyronine Treatment reverses Depression-Like Behavior in a triple-transgenic animal model of Alzheimer’s Disease - Andréa V. Maglione; Bruna P. P. do Nascimento; Miriam O. Ribeiro; Talytha J. L. de Souza; Renata E. C. da Silva; Monica A. Sato; Carlos A. A. Penatti; Luiz R. G. Britto; Janaina S. de Souza; Rui M.B. Maciel; Rodrigo Rodrigues da Conceição; Roberto Laureano-Melo; et al. (Metabolic Brain Disease, 2022)

Environmental disaster in mining areas: routes of exposure to metals in the Doce River basin - A. R. de Matos; H. T. da Silva; M. C. S. da Faria; B. M. Freire; R. M. Pereira; B. L. Batista; J. L. Rodrigues (International Journal of Environmental Science and Technology, 2022)

The Role of Vicariance and Paleoclimatic Shifts in the Diversification of Uranoscodon superciliosus (Squamata, Tropiduridae) of the Amazonian Floodplains - Manuela V. dos Santos; Ana L. C. Prudente; Miguel T. Rodrigues; Marcelo J. Sturaro (Evolutionary Biology, 2022)

Mercury methylation upon coastal sediment resuspension: a worst-case approach under dark conditions - Christiane N. Monte; Ana Paula C. Rodrigues; Petrus M. A. Galvão; Gabriela C. Pontes; Olaf Malm; Júlio C. Wasserman; Wilson Machado (Environmental Monitoring and Assessment, 2022)

New Wave Energy Converter Design Inspired by the Nenuphar Plant - Hugo Díaz; José Miguel Rodrigues; C. Guedes Soares (Journal of Marine Science and Engineering, 2022)
This paper presents the Nenuphar concept, an innovative wave energy converter designed to use the kinetic and the potential energy of sea waves, based on the motions of seven modules. First, the main characteristics of the Nenuphar and its work principle are presented. Afterwards, the mathematical formulation of its dynamics is introduced and its validation with a simplified device. A specific MATLAB code was developed to determine the dynamics of hinged, multi-directional bodies. Then, the system’s behaviour was analysed under different wave conditions. The system performance was not strongly dependent on the wave characteristics or the device inclination angle. This initial study confirms the Nenuphar as a potential technology to extract energy from waves.

Cerrado deforestation threatens regional climate and water availability for agriculture and ecosystems - Ariane A. Rodrigues; Marcia N. Macedo; Divino V. Silvério; Leandro Maracahipes; Michael T. Coe; Paulo M. Brando; Julia Z. Shimbo; Raoni Rajão; Britaldo Soares‐Filho; Mercedes M. C. Bustamante (Global Change Biology, 2022)
The Brazilian Cerrado is one of the most biodiverse savannas in the world, yet 46% of its original cover has been cleared to make way for crops and pastures. These extensive land‐use transitions (LUTs) are expected to influence regional climate by reducing evapotranspiration (ET), increasing land surface temperature (LST), and ultimately reducing precipitation. Here, we quantify the impacts of LUTs on ET and LST in the Cerrado by combining MODIS satellite data with annual land use and land cover maps from 2006 to 2019. We performed regression analyses to quantify the effects of six common LUTs on ET and LST across the entire gradient of Cerrado landscapes. Results indicate that clearing forests for cropland or pasture increased average LST by ~3.5°C and reduced mean annual ET by 44% and 39%, respectively. Transitions from woody savannas to cropland or pasture increased average LST by 1.9°C and reduced mean annual ET by 27% and 21%, respectively. Converting native grasslands to cropland or pasture increased average LST by 0.9 and 0.6°C, respectively. Conversely, grassland‐to‐pasture transitions increased mean annual ET by 15%. To date, land changes have caused a 10% reduction in water recycled to the atmosphere annually and a 0.9°C increase in average LST across the biome, compared to the historic baseline under native vegetation. Global climate changes from increased atmospheric greenhouse gas concentrations will only exacerbate these effects. Considering potential future scenarios, we found that abandoning deforestation control policies or allowing legal deforestation to continue (at least 28.4 Mha) would further reduce yearly ET (by −9% and −3%, respectively) and increase average LST (by +0.7 and +0.3°C, respectively) by 2050. In contrast, policies encouraging zero deforestation and restoration of the 5.2 Mha of illegally deforested areas would partially offset the warming and drying impacts of land‐use change.

The need for European harmonization of Nutrivigilance in a public health perspective: a comprehensive review - G. Vo Van Regnault; M. C. Costa; A. Adanić Pajić; A. P. Bico; S. Bischofova; U. Blaznik; F. Menniti-Ippolito; K. Pilegaard; C. Rodrigues; I. Margaritis (Critical Reviews in Food Science and Nutrition, 2022)

Hyperglycemia alters N-glycans on colon cancer cells through increased production of activated monosaccharides - H. F. Loponte; I. A. Oliveira; B. C. Rodrigues; R. Nunes-da-Fonseca; R. Mohana-Borges; F. Alisson-Silva; W. B. Dias; A. R. Todeschini (Glycoconjugate Journal, 2022)

The success of algae with luxury P uptake and mixotrophy in P-limiting periphyton within-reservoir spatial heterogeneity - Carla Ferragut; Thiago Rodrigues dos Santos; Barbara Golebski Pellegrini; Mariane Lima Souza; Eduardo P. C. Gomes (Hydrobiologia, 2022)

The TCP transcription factor HvTB2 heterodimerizes with VRS5 and controls spike architecture in barley - Tatiana de Souza Moraes; Sam W. van Es; Inmaculada Hernández-Pinzón; Gwendolyn K. Kirschner; Froukje van der Wal; Sylvia Rodrigues da Silveira; Jacqueline Busscher-Lange; Gerco C. Angenent; Matthew Moscou; Richard G. H. Immink; G. Wilma van Esse (Plant Reproduction, 2022)
Key message Understanding the molecular network, including protein-protein interactions, of VRS5 provide new routes towards the identification of other key regulators of plant architecture in barley. Abstract The TCP transcriptional regulator TEOSINTE BRANCHED 1 (TB1) is a key regulator of plant architecture. In barley, an important cereal crop, HvTB1 (also referred to as VULGARE SIX-ROWED spike (VRS) 5), inhibits the outgrowth of side shoots, or tillers, and grains. Despite its key role in barley development, there is limited knowledge on the molecular network that is utilized by VRS5. In this work, we performed protein–protein interaction studies of VRS5. Our analysis shows that VRS5 potentially interacts with a diverse set of proteins, including other class II TCP’s, NF-Y TF, but also chromatin remodelers. Zooming in on the interaction capacity of VRS5 with other TCP TFs shows that VRS5 preferably interacts with other class II TCP TFs in the TB1 clade. Induced mutagenesis through CRISPR–Cas of one of the putative VRS5 interactors, HvTB2 (also referred to as COMPOSITUM 1 and BRANCHED AND INDETERMINATE SPIKELET 1), resulted in plants that have lost their characteristic unbranched spike architecture. More specifically, hvtb2 mutants exhibited branches arising at the main spike, suggesting that HvTB2 acts as inhibitor of branching. Our protein–protein interaction studies of VRS5 resulted in the identification of HvTB2 as putative interactor of VRS5, another key regulator of spike architecture in barley. The study presented here provides a first step to underpin the protein–protein interactome of VRS5 and to identify other, yet unknown, key regulators of barley plant architecture.

Small mammal diversity of a poorly known and threatened Amazon region, the Tapajós Area of Endemism - Joyce Rodrigues do Prado; Rita G. Rocha; Heitor Bissoli-Silva; Ana Cristina Mendes-Oliveira; Regeane C. L. Pontes; Paula Cristina R. de A Maués; Leonora Pires Costa (Biodiversity and Conservation, 2022)

Are the current commercially available oximes capable of reactivating acetylcholinesterase inhibited by the nerve agents of the A-series? - Marcelo C. Santos; Fernanda D. Botelho; Arlan S. Gonçalves; Daniel A. S. Kitagawa; Caio V. N. Borges; Taynara Carvalho-Silva; Leandro B. Bernardo; Cíntia N. Ferreira; Rafael B. Rodrigues; Denise C. Ferreira Neto; Eugenie Nepovimova; Kamil Kuča; et al. (Archives of Toxicology, 2022)

Corrigendum to the paper: Reassessing the systematics of Leptodeira (Serpentes, Dipsadidae) with emphasis in the South American species - João C. L. Costa; Roberta Graboski; Felipe G. Grazziotin; Hussam Zaher; Miguel T. Rodrigues; Ana Lúcia da C. Prudente (Zoologica Scripta, 2022)

AMAZONIA CAMTRAP: A data set of mammal, bird, and reptile species recorded with camera traps in the Amazon forest - Ana Carolina Antunes; Anelise Montanarin; Diogo Maia Gräbin; Erison Carlos dos Santos Monteiro; Fernando Ferreira de Pinho; Guilherme Costa Alvarenga; Jorge Ahumada; Robert B. Wallace; Emiliano Esterci Ramalho; Adrian Paul Ashton Barnett; Alex Bager; Alexandre Martins Costa Lopes; et al. (Ecology, 2022)
The Amazon forest has the highest biodiversity on Earth. However, information on Amazonian vertebrate diversity is still deficient and scattered across the published, peer‐reviewed, and gray literature and in unpublished raw data. Camera traps are an effective non‐invasive method of surveying vertebrates, applicable to different scales of time and space. In this study, we organized and standardized camera trap records from different Amazon regions to compile the most extensive data set of inventories of mammal, bird, and reptile species ever assembled for the area. The complete data set comprises 154,123 records of 317 species (185 birds, 119 mammals, and 13 reptiles) gathered from surveys from the Amazonian portion of eight countries (Brazil, Bolivia, Colombia, Ecuador, French Guiana, Peru, Suriname, and Venezuela). The most frequently recorded species per taxa were: mammals: Cuniculus paca (11,907 records); birds: Pauxi tuberosa (3713 records); and reptiles: Tupinambis teguixin (716 records). The information detailed in this data paper opens up opportunities for new ecological studies at different spatial and temporal scales, allowing for a more accurate evaluation of the effects of habitat loss, fragmentation, climate change, and other human‐mediated defaunation processes in one of the most important and threatened tropical environments in the world. The data set is not copyright restricted; please cite this data paper when using its data in publications and we also request that researchers and educators inform us of how they are using these data.

Sugarcane: A Promising Source of Green Carbon in the Circular Bioeconomy - Susan G. Karp; Walter J. M. Burgos; Luciana P. S. Vandenberghe; Kim V. Diestra; Luis A. Z. Torres; Adenise L. Woiciechowski; Luiz A. J. Letti; Gilberto V. M. Pereira; Vanete Thomaz-Soccol; Cristine Rodrigues; Júlio C. de Carvalho; Carlos R. Soccol (Sugar Tech, 2022)

On the replacement of traditional stabilizers by guaiacol in environmentally safe nitrocellulose-based propellants - Rodrigo L. B. Rodrigues; Ana Paula da Silva; Rogério Rosato; Maurício F. Lemos; Fernando C. Peixoto; Tanos C. C. França; Letivan G. Mendonça Filho (Clean Technologies and Environmental Policy, 2022)

Metabolomic Profiling of Phloem Sap from Different Pine Species and Implications on Black Capuchin - Lorena Mara A. Silva; Elenilson G. Alves Filho; Tigressa Helena S. Rodrigues; Francisca Jamila C. Louredo; Guilherme J. Zocolo; Kirley M. Canuto; Sandra B. Mikich; Dieter Liebsch; Adriana De Almeida; Edy S. De Brito (Journal of Chemical Ecology, 2022)

Pleurotus strains with remediation potential to remove toxic metals from Doce River contaminated by Samarco dam mine - M. P. O. Santos; M. V. N. Santos; R. S. Matos; A. S. Van Der Maas; M. C. S. Faria; B. L. Batista; J. L. Rodrigues; C. A. Bomfeti (International Journal of Environmental Science and Technology, 2022)

Wide tolerance to environmental conditions and substrate colonization mediates the invasion of false mussels (Bivalvia: Dreissenidae) in brackish systems - Antonio J. S. Rodrigues; Igor C. Miyahira; Nathália Rodrigues; Danielle Ribeiro; Luciano N. Santos; Raquel A. F. Neves (Biological Invasions, 2022)

Reassessing the systematics of Leptodeira (Serpentes, Dipsadidae) with emphasis in the South American species - João C. L. Costa; Roberta Graboski; Felipe G. Grazziotin; Hussam Zaher; Miguel T. Rodrigues; Ana Lúcia da C. Prudente (Zoologica Scripta, 2022)
Within the diverse subfamily Dipsadinae, Imantodini represents one of the few groups distributed in North, Central and South America. The tribe comprises the genera Leptodeira and Imantodes , from which Leptodeira is the most diverse, including 15 species and 11 subspecies, distributed from southern USA to central Argentina. Taxonomy and affinities among these taxa are poorly resolved, and the phylogenetic relationships among the South American diversity were never properly assessed before. Here, we investigate the phylogenetic relationships and the taxonomic status of Leptodeira spp. based on a comprehensive multilocus dataset with emphasis in the South American radiation. Besides assessing the phylogenetic relationship and species cohesion, we also evaluate the morphological variation among the South American diversity of Leptodeira . Our results support the monophyly of Imatodini and Leptodeira , while indicating that several individuals classified as Leptodeira annulata and L . septentrionalis do not cluster together within their respective species. Moreover, specimens identified as belonging to the subspecies L . a . annulata , L . a . cussiliris , L . s . ornata and L . s . polysticta do not group together suggesting the current classification includes non‐natural groups. The analysis of morphological evidence also supports the phylogenetics results, indicating that several clades can be recognized as evolutionary units presenting distinct phenotypes. To equate the taxonomy to our results, we propose a new taxonomic arrangement for Leptodeira in which we are: (1) redefining the composition of L . annulata and L . septentrionalis ; (2) elevating five subspecies to species level; (3) revalidating one species; (4) recognizing four species complexes; and (5) indicating the presence of hidden diversity (probably four undescribed species). Finally, we describe a new species ( Leptodeira tarairiu sp. nov.) from the open formations of South America (Cerrado and Caatinga), and we provide detailed redescriptions for all South American species of Leptodeira .

Asynchrony, density dependence, and persistence in an amphibian - Freya E. Rowland; Elizabeth S. Schyling; L. Kealoha Freidenburg; Mark C. Urban; Jonathan L. Richardson; A. Z. Andis Arietta; Susan B. Rodrigues; Adriana D. Rubinstein; Michael F. Benard; David K. Skelly (Ecology, 2022)
Understanding drivers of metapopulation dynamics remains a critical challenge for ecology and conservation. In particular, the degree of synchrony in metapopulation dynamics determines how resilient a metapopulation is to a widespread disturbance. In this study, we used 21 years of egg mass count data across 64 nonpermanent freshwater ponds in Connecticut, USA to evaluate patterns of abundance and growth and to assess regional as well as local factors in shaping the population dynamics of wood frogs ( Rana sylvatica = Lithobates sylvaticus ). In particular, we asked whether a species known to undergo metapopulation dynamics exhibited spatial synchrony in abundances. With the exception of a single year when breeding took place during severe drought conditions, our analyses revealed no evidence of synchrony despite close proximity (mean minimum distance

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

QSAR-Guided Proposition of N-(4-methanesulfonyl)Benzoyl-N’-(Pyrimidin-2-yl)Thioureas as Effective and Safer Herbicides - Natânia E. Rodrigues; Adriana C. de Faria; Ingrid V. Pereira; Elaine F. F. da Cunha; Matheus P. Freitas (Bulletin of Environmental Contamination and Toxicology, 2022)

Combined effects of bird extinctions and introductions in oceanic islands: Decreased functional diversity despite increased species richness - Filipa C. Soares; Ricardo F. de Lima; Jorge M. Palmeirim; Pedro Cardoso; Ana S. L. Rodrigues (Global Ecology and Biogeography, 2022)
Aim We analyse the consequences of species extinctions and introductions on the functional diversity and composition of island bird assemblages. Specifically, we ask if introduced species have compensated the functional loss resulting from species extinctions. Location Seventy‐four oceanic islands (> 100 km 2 ) in the Atlantic, Pacific and Indian Oceans. Time period Late Holocene. Major taxa studied Terrestrial and freshwater bird species. Methods We compiled a species list per island (extinct and extant, native and introduced), and then compiled traits per species. We used single‐trait analyses to assess the effects of past species extinctions and introductions on functional composition. Then, we used probabilistic hypervolumes in trait space to calculate functional richness and evenness of original versus present avifaunas of each island (and net change), and to estimate how functionally unique are extinct and introduced species on each island. Results The net effects of extinctions and introductions were: an increase in average species richness per island (alpha diversity), yet a decline in diversity across all islands (gamma diversity); an average increase in the prevalence of most functional traits, yet an average decline in functional richness and evenness, associated with the fact that extinct species were functionally more unique (when compared to extant natives) than introduced species. Main conclusions Introduced species are on average offsetting (and even surpassing) the losses of extinct species per island in terms of species richness, and they are increasing the prevalence of most functional traits. However, they are not compensating for the loss of functional richness due to extinctions. Current island bird assemblages are becoming functionally poorer, having lost unique species and being composed of functionally more redundant species. This is likely to have cascading repercussions on the functioning of island ecosystems. We highlight that taxonomic and functional biodiversity should be assessed simultaneously to understand the global impacts of human activities.

MAMMALS IN PORTUGAL : A data set of terrestrial, volant, and marine mammal occurrences in P ortugal - Clara Grilo; Beatriz C. Afonso; Filipe Afonso; Marta Alexandre; Sara Aliácar; Ana Almeida; Ivan Prego Alonso; Francisco Álvares; Paulo Alves; Paulo Célio Alves; Pedro Alves; Anabela Amado; et al. (Ecology, 2022)
Mammals are threatened worldwide, with ~26% of all species being included in the IUCN threatened categories. This overall pattern is primarily associated with habitat loss or degradation, and human persecution for terrestrial mammals, and pollution, open net fishing, climate change, and prey depletion for marine mammals. Mammals play a key role in maintaining ecosystems functionality and resilience, and therefore information on their distribution is crucial to delineate and support conservation actions. MAMMALS IN PORTUGAL is a publicly available data set compiling unpublished georeferenced occurrence records of 92 terrestrial, volant, and marine mammals in mainland Portugal and archipelagos of the Azores and Madeira that includes 105,026 data entries between 1873 and 2021 (72% of the data occurring in 2000 and 2021). The methods used to collect the data were: live observations/captures (43%), sign surveys (35%), camera trapping (16%), bioacoustics surveys (4%) and radiotracking, and inquiries that represent less than 1% of the records. The data set includes 13 types of records: (1) burrows | soil mounds | tunnel, (2) capture, (3) colony, (4) dead animal | hair | skulls | jaws, (5) genetic confirmation, (6) inquiries, (7) observation of live animal (8), observation in shelters, (9) photo trapping | video, (10) predators diet | pellets | pine cones/nuts, (11) scat | track | ditch, (12) telemetry and (13) vocalization | echolocation. The spatial uncertainty of most records ranges between 0 and 100 m (76%). Rodentia ( n =31,573) has the highest number of records followed by Chiroptera ( n = 18,857), Carnivora ( n = 18,594), Lagomorpha ( n = 17,496), Cetartiodactyla ( n = 11,568) and Eulipotyphla ( n = 7008). The data set includes records of species classified by the IUCN as threatened (e.g., Oryctolagus cuniculus [ n = 12,159], Monachus monachus [ n = 1,512], and Lynx pardinus [ n = 197]). We believe that this data set may stimulate the publication of other European countries data sets that would certainly contribute to ecology and conservation‐related research, and therefore assisting on the development of more accurate and tailored conservation management strategies for each species. There are no copyright restrictions; please cite this data paper when the data are used in publications.

Which birds are Brazilians seeing on urban and non-urban feeders? An analysis based on a collective online birding - Eduardo Roberto Alexandrino; Thaís Abreu Camboim; Flávia Guimarães Chaves; Alex Augusto Abreu Bovo; Marco Aurélio Galvão da Silva; Daniela Alves Maia da Silva; Margi Moss; Tatiana Pongiluppi Souza; Clarissa de Oliveira Santos; Caio Bezerra de Mattos Brito; Maristela Camolesi Alcantara; Karlla V. C. Barbosa; et al. (Ornithology Research, 2022)

RI75, a curcumin analogue, inhibits tumor necrosis factor-α and interleukin-6 production and exhibits antiallodynic and antiedematogenic activities in mice - Sarah O. A. M. Costa; Ianny B. Rodrigues; Alysson V. Braga; Bárbara C. M. Barbosa; Roger R. L. Silva; Felipe F. Rodrigues; Ivo S. F. Melo; Marcela Í. Morais; Brenda F. M. Castro; Armando S. Cunha Júnior; Vinícius G. Maltarollo; Renata B. Oliveira; et al. (Inflammopharmacology, 2022)

Colonization rather than fragmentation explains the geographical distribution and diversification of treefrogs endemic to Brazilian shield sky islands - Caroline Batistim Oswald; Priscila Lemes; Maria Tereza C. Thomé; Tiago Leite Pezzuti; Fabricio Rodrigues Santos; Paulo Christiano de Anchietta Garcia; Felipe Sá Fortes Leite; Rafael Félix de Magalhães (Journal of Biogeography, 2022)
Aim Geographical patterns of montane biodiversity worldwide are related to biotic and abiotic factors, such as historical climate dynamics and species dispersal capabilities, which affect the biota from population to community levels. Understanding of processes related to population diversification in extra‐Andean Neotropical mountains remains largely unknown. Here, we tested how colonization of new areas as opposed to fragmentation of geographical ranges influenced the distribution and diversification of frogs from Brazilian mountains. Location Espinhaço Range, the largest extra‐Andean mountain range in South America. Taxon Ledge treefrog Bokermannohyla saxicola . Methods We used multilocus DNA and morphometric data throughout the species' distribution to delimit lineages, infer phylogenetic relationships and estimate divergence times. We used ecological niche modelling ( ENM ) and approximate Bayesian computation ( ABC ) to reconstruct changes of geographical distribution and population sizes for testing alternative hypotheses of diversification concerning fragmentation and colonization. Results We found four evolutionary significant lineages that diverged from the Pliocene to the Early Pleistocene. All lineages were validated by DNA and morphometric data by independent and joint analyses. ENM showed that climatic fluctuations might have influenced the species' distribution, whereas ABC model selection further supports associated demographic changes. Taken together, a Pleistocene jump‐dispersal scenario best explains the diversification of the Bokermannohyla saxicola lineages. Main conclusions Endemism in the Espinhaço Range is usually explained by ancient diversification, associated with long‐term isolation of climatic stable areas following climate‐driven habitat fragmentation. Our results challenge this general view, indicating recent diversification, habitat expansion and colonization of new areas as important processes explaining the current distribution and genetic diversity of B. saxicola .

Light and thermal niches of ground‐foraging A mazonian insectivorous birds - Vitek Jirinec; Patricia F. Rodrigues; Bruna R. Amaral; Philip C Stouffer (Ecology, 2022)
Insectivores of the tropical rainforest floor are consistently among the most vulnerable birds to forest clearing and fragmentation. Several hypotheses attempt to explain this pattern, including sensitivity to extreme microclimates found near forest borders, particularly brighter and warmer conditions. Importantly, this “microclimate hypothesis” has additional implications for intact forest under global climate change that could be evaluated through direct assessment of the light and temperature environment of terrestrial insectivores. In this study, we harness novel technology to directly quantify the light and thermal niches of 10 species of terrestrial insectivores in undisturbed Amazonian rainforest. Loggers placed on birds ( N = 33) and their environment ( N = 9) recorded nearly continuous microclimate data from 2017 to 2019, amassing >5 million measurements. We found that midday light intensity in tree fall gaps (~39,000 lux) was >40 times higher than at the ground level of forest interior (950 lux). Light intensity registered by sensors placed on birds averaged 17.4 (range 3.9–41.5) lux, with species using only 4.3% (0.9%–10.4%) of available light on the forest floor. Birds therefore selected very dark microhabitats—the light environment was >2200 times brighter in tree fall gaps. Bird thermal niche was a function of ambient temperature as well as body temperature, which averaged >40.5°C but varied among species. Forest floor temperature peaked daily at 27.0°C, whereas bird loggers averaged 35.1°C (34.5–35.7°C) at midday. The antpitta Myrmothera campanisona and the antthrush Formicarius colma used thermal conditions closest to their body temperatures, whereas leaftossers ( Sclerurus spp.) and Myrmornis torquata occupied relatively cool microclimates. We found no general link between abundance trends and variation in species‐specific light and thermal niches. However, all species occupied markedly dim and cool microclimates. Because such conditions are rare outside the interior of primary forest, these results support the microclimate hypothesis in disturbed landscapes. Moreover, strong avoidance of conditions that are becoming more common under climate change highlights the vulnerability of terrestrial insectivores even in the absence of disturbance and may be the reason for enigmatic declines in Amazonia and elsewhere.

Novel Lethal Clostridial Infection in Florida Manatees (Trichechus manatus latirostris): Cause of the 2013 Unusual Mortality Event in the Indian River Lagoon - Jan H. Landsberg; Maki Tabuchi; David S. Rotstein; Kuttichantran Subramaniam; Thais C. S. Rodrigues; Thomas B. Waltzek; Nicole I. Stacy; Patrick W. Wilson; Yasunari Kiryu; Francisco A. Uzal; Martine de Wit (Frontiers in Marine Science, 2022)
The Indian River Lagoon (IRL) on Florida’s east coast is a biologically diverse estuary and an important habitat to the threatened Florida manatee ( Trichechus manatus latirostris ). An unusual mortality event (UME) was declared by the Working Group on Marine Mammal Unusual Mortality Events in 2013 after a marked increase in manatee deaths in the IRL of an unknown cause. This UME followed a dramatic reduction of seagrass coverage in the IRL due to chronic non-toxic phytoplankton blooms, with a resultant ecosystem shift to mixed macroalgal dominance. At least 199 manatee deaths fitting the UME case definition were documented in and adjacent to the IRL during 2012–2019; mortality was highest in 2013, when 111 of these deaths were documented. The case definition included carcasses in good nutritional condition, with multiorgan congestion or wet lungs consistent with drowning without trauma. The gastrointestinal compartments of manatee carcasses were filled with diverse macroalga species, and the contents were notably more fluid than usual. Gross intestinal findings included blebbing to segmental thickening of the wall. Microscopic lesions were primarily intestinal, including necrosis, edema, hemorrhage, mucosa-associated lymphoid changes, and inflammation, sometimes associated with Gram-positive bacterial rods. A multidisciplinary approach of environmental and carcass sampling found no causative evidence through tests for micro- and macroalgal biotoxins, trace metals, general toxin screening, or vitreum biochemistry. Microbiological, cytological, immunohistochemical, and molecular analyses of Clostridiales from intestinal samples identified Clostridioides difficile toxin A, toxins A/B and toxin A gene; Paeniclostridium sordellii lethal gene (and other potential virulence factors from a sequenced strain); and Clostridium perfringens alpha and epsilon toxin genes. The results from this 8 year-long investigation are indicative that the cause of death in this manatee UME was associated with clostridial infection, initiated by a shift to a predominantly macroalgal diet.

Electrostatic separation of polymer waste by tribocharging system based on friction with PVC - B. M. Rodrigues; C. Saron (International Journal of Environmental Science and Technology, 2022)

A comparison of stereo-videos and visual census methods for assessing subtropical rocky reef fish assemblage - Fernanda A. Rolim; Pedro F. C. Rodrigues; Tim Langlois; Leonardo M. Neves; Otto B. F. Gadig (Environmental Biology of Fishes, 2022)

Influence of spatial and environmental factors on the structure of a zooplankton metacommunity in an intermittent river - Eliêta A. Ramos; Cláudio Simões de Morais-Junior; Carlos A. S. Rodrigues-Filho; Jorge I. Sánchez-Botero; Mauro Melo Júnior; José L. C. Novaes (Aquatic Ecology, 2022)

Indigenous and local communities can boost seed supply in the UN decade on ecosystem restoration - Danilo Urzedo; Simone Pedrini; Daniel L. M. Vieira; Alexandre B. Sampaio; Bruna D. F. Souza; Eduardo Malta Campos-Filho; Fatima C. M. Piña-Rodrigues; Isabel B. Schmidt; Rodrigo G. P. Junqueira; Kingsley Dixon (Ambio, 2022)
The UN Decade of Ecosystem Restoration is poised to trigger the recovery of ecosystem services and transform structural injustices across the world in a way unparalleled in human history. The inclusion of diverse Indigenous and local communities to co-create robust native seed supply systems is the backbone to achieve the goals for the Decade. Here we show how community-based organizations have co-developed native seed supply strategies for landscape restoration from the bottom-up. We draw on the interconnections over two decades of seed networks in Brazil and the emerging Indigenous participation in native seed production in Australia. From an environmental justice perspective, we provide a participatory seed supply approach for local engagement, noting local geographical, social and cultural contexts. Meeting large-scale restoration goals requires the connection between local seed production and collaborative platforms to negotiate roles, rights and responsibilities between stakeholders. An enduring native seed supply must include a diversity of voices and autonomy of community groups that builds equitable participation in social, economic, and environmental benefits.

Pharmacological blockage of the AHR-CYP1A1 axis: a call for in vivo evidence - N. R. Coelho; A. B. Pimpão; M. J. Correia; T. C. Rodrigues; E. C. Monteiro; J. Morello; S. A. Pereira (Journal of Molecular Medicine, 2022)

Metformin effect in models of inflammation is associated with activation of ATP-dependent potassium channels and inhibition of tumor necrosis factor-α production - Paulo S. A. Augusto; Tamires C. Matsui; Alysson V. Braga; Felipe F. Rodrigues; Marcela I. Morais; Marcela M. G. B. Dutra; Carla R. A. Batista; Ivo S. F. Melo; Sarah O. A. M. Costa; Caryne M. Bertollo; Márcio M. Coelho; Renes R. Machado (Inflammopharmacology, 2022)

Climate and management effects on the herbaceous layer productivity of a cork oak woodland - M. C. Bicho; A. C. Correia; A. R. Rodrigues; J. Soares David; F. Costa-e-Silva (Agroforestry Systems, 2022)

Financial analysis of a complex agroforestry system for environmental restoration purpose in the Brazilian Rainforest - M. P. Padovan; F. F. Nogueira; F. G. Ruas; A. C. C. Rodrigues; M. F. Arco-Verde (Agroforestry Systems, 2022)

ATLANTIC POLLINATION: a data set of flowers and interaction with nectar‐feeding vertebrates from the Atlantic Forest - Joice Iamara‐Nogueira; Natália Targhetta; Gina Allain; Adriano Gambarini; Alessandra R. Pinto; Ana Maria Rui; Andréa C. Araújo; Ariadna Lopes; Brenda Pereira‐Silva; Bruna Bertagni de Camargo; Caio Graco Machado; Caio Missagia; et al. (Ecology, 2022)
Flowering plant species and their nectar‐feeding vertebrates exemplify some of the most remarkable biotic interactions in the Neotropics. In the Brazilian Atlantic Forest, several species of birds (especially hummingbirds), bats, and non‐flying mammals, as well as one lizard feed on nectar, often act as pollinators and contribute to seed output of flowering plants. We present a dataset containing information on flowering plants visited by nectar‐feeding vertebrates and sampled at 166 localities in the Brazilian Atlantic Forest. This dataset provides information on 1902 unique interactions among 515 species of flowering plants and 129 species of potential vertebrate pollinators and the patterns of species diversity across latitudes. All plant–vertebrate interactions compiled were recorded through direct observations of visits, and no inferences of pollinators based on floral syndromes were included. We also provide information on the most common plant traits used to understand the interactions between flowers and nectar‐feeding vertebrates: plant growth form, corolla length, rate of nectar production per hour in bagged flowers, nectar concentration, flower color and shape, time of anthesis, presence or absence of perceptible fragrance by human, and flowering phenology as well as the plant’s threat status by International Union for Conservation of Nature (IUCN) classification. For the vertebrates, status of threat by IUCN classification, body mass, bill or rostrum size are provided. Information on the frequency of visits and pollen deposition on the vertebrate’s body is provided from the original source when available. The highest number of unique interactions is recorded for birds (1771) followed by bats (110). For plants, Bromeliaceae contains the highest number of unique interactions (606), followed by Fabaceae (242) and Gesneriaceae (104). It is evident that there was geographical bias of the studies throughout the southeast of the Brazilian Atlantic Forest and that most effort was directed to flower–hummingbird interactions. However, it reflects a worldwide tendency of more plants interacting with birds compared with other vertebrate species. The lack of similar protocols among studies to collect basic data limits the comparisons among areas and generalizations. Nevertheless, this dataset represents a notable effort to organize and highlight the importance of vertebrate pollinators in this hotspot of biodiversity on Earth and represents the data currently available. No copyright or proprietary restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications or scientific events.

ATLANTIC ANTS: a data set of ants in Atlantic Forests of South America - Rogério R. Silva; Felipe Martello; Rodrigo Machado Feitosa; Otávio Guilherme M. Silva; Lívia Pires do Prado; Carlos Roberto F. Brandão; Emília Zoppas de Albuquerque; Maria Santina C. Morini; Jacques Hubert Charles Delabie; Erison Carlos dos Santos Monteiro; Agripino Emanuel Oliveira Alves; Alexander L. Wild; et al. (Ecology, 2022)
Ants, an ecologically successful and numerically dominant group of animals, play key ecological roles as soil engineers, predators, nutrient recyclers, and regulators of plant growth and reproduction in most terrestrial ecosystems. Further, ants are widely used as bioindicators of the ecological impact of land use. We gathered information of ant species in the Atlantic Forest of South America. The ATLANTIC ANTS data set, which is part of the ATLANTIC SERIES data papers, is a compilation of ant records from collections (18,713 records), unpublished data (29,651 records), and published sources (106,910 records; 1,059 references), including papers, theses, dissertations, and book chapters published from 1886 to 2020. In total, the data set contains 153,818 ant records from 7,636 study locations in the Atlantic Forest, representing 10 subfamilies, 99 genera, 1,114 ant species identified with updated taxonomic certainty, and 2,235 morphospecies codes. Our data set reflects the heterogeneity in ant records, which include ants sampled at the beginning of the taxonomic history of myrmecology (the 19th and 20th centuries) and more recent ant surveys designed to address specific questions in ecology and biology. The data set can be used by researchers to develop strategies to deal with different macroecological and region‐wide questions, focusing on assemblages, species occurrences, and distribution patterns. Furthermore, the data can be used to assess the consequences of changes in land use in the Atlantic Forest on different ecological processes. No copyright restrictions apply to the use of this data set, but we request that authors cite this data paper when using these data in publications or teaching events.

Prospecting for a quinoline containing selenium for comorbidities depression and memory impairment induced by restriction stress in mice - Renata L. de Oliveira; Guilherme T. Voss; Karline da C. Rodrigues; Mikaela P. Pinz; Julia V. Biondi; Nicole P. Becker; Eduardo Blodorn; William B. Domingues; Allya Larroza; Vinícius F. Campos; Diego Alves; Ethel A. Wilhelm; et al. (Psychopharmacology, 2022)

Important Key Process Simulations in the Field of Steel Metallurgy - A. Ludwig; C. M. G. Rodrigues; Z. Zhang; H. Zhang; E. Karimi-Sibaki; H. Barati; A. Vakhrushev; M. Al-Nasser; M. Wu; A. Kharicha (BHM Berg- und Hüttenmännische Monatshefte, 2022)
During the last decade, the chair for ‘Simulation and Modelling of Metallurgical Processes’ (SMMP) has worked on different metallurgical processes with the highlights of the following five industrial relevant topics: (i) modelling the as-cast structures of large steel castings; (ii) exploring the formation mechanisms of macrosegregation; (iii) describing magnetohydrodynamic and electrochemical phenomena in remelting processes, (iv) understanding how solidification and flow can be influenced by magnetohydrodynamics during steel continuous casting; and (v) describing nozzle clogging in steelmaking processes. In this contribution, the main achievements from the group on the above five topics are briefly described.

Pyramiding dsRNAs increases phytonematode tolerance in cotton plants - Maria E. Lisei-de-Sá; Paolo L. Rodrigues-Silva; Carolina V. Morgante; Bruno Paes de Melo; Isabela T. Lourenço-Tessutti; Fabricio B. M. Arraes; João P. A. Sousa; Rafael Galbieri; Regina M. S. Amorim; Camila B. J. de Lins; Leonardo L. P. Macedo; Valdeir J. Moreira; et al. (Planta, 2021)

Floating treatment wetland for nutrient removal and acute ecotoxicity improvement of untreated urban wastewater - L. H. Bauer; A. Arenzon; N. D. Molle; J. A. Rigotti; A. C. A. Borges; N. R. Machado; L. H. R. Rodrigues (International Journal of Environmental Science and Technology, 2021)

Stability of tropical forest tree carbon‐water relations in a rainfall exclusion treatment through shifts in effective water uptake depth - Alexandria L. Pivovaroff; Nate G. McDowell; Tayana Barrozo Rodrigues; Tim Brodribb; Lucas A. Cernusak; Brendan Choat; Charlotte Grossiord; Yoko Ishida; Kolby J. Jardine; Susan Laurance; Riley Leff; Weibin Li; et al. (Global Change Biology, 2021)
Increasing severity and frequency of drought is predicted for large portions of the terrestrial biosphere, with major impacts already documented in wet tropical forests. Using a 4‐year rainfall exclusion experiment in the Daintree Rainforest in northeast Australia, we examined canopy tree responses to reduced precipitation and soil water availability by quantifying seasonal changes in plant hydraulic and carbon traits for 11 tree species between control and drought treatments. Even with reduced soil volumetric water content in the upper 1 m of soil in the drought treatment, we found no significant difference between treatments for predawn and midday leaf water potential, photosynthesis, stomatal conductance, foliar stable carbon isotope composition, leaf mass per area, turgor loss point, xylem vessel anatomy, or leaf and stem nonstructural carbohydrates. While empirical measurements of aboveground traits revealed homeostatic maintenance of plant water status and traits in response to reduced soil moisture, modeled belowground dynamics revealed that trees in the drought treatment shifted the depth from which water was acquired to deeper soil layers. These findings reveal that belowground acclimation of tree water uptake depth may buffer tropical rainforests from more severe droughts that may arise in future with climate change.

Trophic downgrading decreases species asynchrony and community stability regardless of climate warming - Felipe Rezende; Pablo A. P. Antiqueira; Owen L. Petchey; Luiz Felipe M. Velho; Luzia C. Rodrigues; Gustavo Q. Romero (Ecology Letters, 2021)
Theory and some evidence suggest that biodiversity promotes stability. However, evidence of how trophic interactions and environmental changes modulate this relationship in multitrophic communities is lacking. Given the current scenario of biodiversity loss and climate changes, where top predators are disproportionately more affected, filling these knowledge gaps is crucial. We simulated climate warming and top predator loss in natural microcosms to investigate their direct and indirect effects on temporal stability of microbial communities and the role of underlying stabilising mechanisms. Community stability was insensitive to warming, but indirectly decreased due to top predator loss via increased mesopredator abundance and consequent reduction of species asynchrony and species stability. The magnitude of destabilising effects differed among trophic levels, being disproportionally higher at lower trophic levels (e.g. producers). Our study unravels major patterns and causal mechanisms by which trophic downgrading destabilises large food webs, regardless of climate warming scenarios.

Whiptail lizard lineage delimitation and population expansion as windows into the history of Amazonian open ecosystems - Lidia F. Martins; Erik L. Choueri; Alan F. S. Oliveira; Fabrícius M. C. B. Domingos; Gabriel H. O. Caetano; Vitor H. G. L. Cavalcante; Rafael N. Leite; Antoine Fouquet; Miguel T. Rodrigues; Ana C. Carnaval; Guarino R. Colli; Fernanda P. Werneck (Systematics and Biodiversity, 2021)

Dopaminergic Receptors as Neuroimmune Mediators in Experimental Autoimmune Encephalomyelitis - E. C. D. Gonçalves; V. Lieberknecht; V. V. Horewicz; B. D. Rabelo; F. A. Felipetti; A. L. S. Rodrigues; D. F. Martins; R. C. Dutra (Molecular Neurobiology, 2021)

Estimating critical level of $$\hbox {PM}_{{10}}$$ to affect hospital infant admissions in Vitória, Brazil - Alessandro J. Q. Sarnaglia; Luciana G. Godoi; Mariana C. Rodrigues (Stochastic Environmental Research and Risk Assessment, 2021)

Combined and isolated effects of alcohol consumption and sleep deprivation on maximal strength, muscle endurance and aerobic exercise performance in healthy men: a cross-over randomized controlled trial - Rodrigo Rodrigues; Rodrigo de Azevedo Franke; Bruno C. Teixeira; Rodrigo C. O. Macedo; André Luiz Lopes; Fernando Diefenthaeler; Álvaro Reischak-Oliveira; Bruno Manfredini Baroni; Marco Aurélio Vaz (Sleep and Biological Rhythms, 2021)

Tropical grass and legume pastures may alter lamb meat physical and chemical characteristics - V. S. Hampel; C. H. E. C. Poli; M. Joy; J. F. Tontini; T. Devincenzi; J. R. B. Pardos; R. E. F. Macedo; E. N. Nalério; A. G. F. Saccol; E. Rodrigues; V. Manfroi; N. M. Fajardo (Tropical Animal Health and Production, 2021)

Plastid role in phytomelanin synthesis in Piptocarpha axillaris (Less.) Baker stems (Asteraceae, Vernonieae) - Josiane Wolff Coutinho; Ana C. Rodrigues; Beatriz Appezzato-da-Glória; Eliana M. Oliveira; Fernanda M. C. Oliveira; Makeli G. Lusa (Protoplasma, 2021)

Identification of TIA1 mRNA targets during human neuronal development - Loryn P. Byres; Marat Mufteev; Kyoko E. Yuki; Wei Wei; Alina Piekna; Michael D. Wilson; Deivid C. Rodrigues; James Ellis (Molecular Biology Reports, 2021)
Background Neuronal development is a tightly controlled process involving multi-layered regulatory mechanisms. While transcriptional pathways regulating neurodevelopment are well characterized, post-transcriptional programs are still poorly understood. TIA1 is an RNA-binding protein that can regulate splicing, stability, or translation of target mRNAs, and has been shown to play critical roles in stress response and neurodevelopment. However, the identity of mRNAs regulated by TIA1 during neurodevelopment under unstressed conditions is still unknown. Methods and Results To identify the mRNAs targeted by TIA1 during the first stages of human neurodevelopment, we performed RNA immunoprecipitation-sequencing (RIP-seq) on human embryonic stem cells (hESCs) and derived neural progenitor cells (NPCs), and cortical neurons under unstressed conditions. While there was no change in TIA1 protein levels, the number of TIA1 targeted mRNAs decreased from pluripotent cells to neurons. We identified 2400, 845, and 330 TIA1 mRNA targets in hESCs, NPC, and neurons, respectively. The vast majority of mRNA targets in hESC were genes associated with neurodevelopment and included autism spectrum disorder-risk genes that were not bound in neurons. Additionally, we found that most TIA1 mRNA targets have reduced ribosomal engagement levels. Conclusion Our results reveal TIA1 mRNA targets in hESCs and during human neurodevelopment, indicate that translation repression is a key process targeted by TIA1 binding and implicate TIA1 function in neuronal differentiation.

Exhumation of an anatectic complex by channel flow and extrusion tectonics: structural and metamorphic evidence from the Porto–Viseu Metamorphic Belt, Central-Iberian Zone - T. Bento dos Santos; J. F. Rodrigues; P. Castro; B. Cotrim; I. Pereira; J. A. Ferreira; C. Meireles; N. Ferreira; P. Ferreira; A. Ribeiro; F. Guimarães (International Journal of Earth Sciences, 2021)

Total and Organic Mercury in Fish from Different Geographical Areas in the North Atlantic Ocean and Health Risk Assessment - H. C. Vieira; M. M. B. Ramirez; M. D. Bordalo; A. C. M. Rodrigues; A. M. V. M. Soares; S. N. Abreu; F. Morgado; J. Rendón-von Osten (Exposure and Health, 2021)

Mercury Accumulation and Elimination in Different Tissues of Zebrafish (Danio rerio) Exposed to a Mercury-Supplemented Diet - Hugo C. Vieira; Andreia C. M. Rodrigues; Amadeu M. V. M. Soares; Sizenando Abreu; Fernando Morgado (Journal of Marine Science and Engineering, 2021)
In this study, we evaluated the bioaccumulation of mercury in zebrafish (Danio rerio) exposed to mercury-contaminated food for 21 days and the depuration of mercury for a subsequent post-exposure period of 28 days. Four tissues (muscle, liver, gills, and skin) were analyzed for mercury content. Overall, data indicated that Hg accumulation in the liver is faster than in other tissues. Furthermore, the liver is the tissue with the highest accumulation rate per day (0.021 µg Hg g−1 day−1), followed by muscle, skin, and gills. Conversely, the Hg depuration rates in different tissues showed the following order: gills > skin > muscle > liver. The bioaccumulation factor values of liver and muscle increased linearly during the uptake period. The ratios between mercury concentration in liver and muscle during the experiment also increased during the uptake period and remained higher than 1 during the elimination period, suggesting that Danio rerio needed more than 4 weeks of depuration. Finally, the distribution of Hg in the water column during the accumulation period is Hg particulate > Hg dissolved, and during the depuration period it is the opposite, mercury particulate

Phaeodactylum tricornutum biomass in microdiets enhances Senegalese sole (Solea senegalensis) larval growth performance during weaning - André Barreto; Wilson Pinto; Andreia Rodrigues; Rui J. M. Rocha; Carlos Unamunzaga; Tomé Silva; Jorge Dias; Luis E. C. Conceição (Journal of Applied Phycology, 2021)

New insights into the mechanisms underlying 5-fluorouracil-induced intestinal toxicity based on transcriptomic and metabolomic responses in human intestinal organoids - Daniela Rodrigues; Terezinha de Souza; Luke Coyle; Matteo Di Piazza; Bram Herpers; Sofia Ferreira; Mian Zhang; Johanna Vappiani; Daniel C. Sévin; Attila Gabor; Anthony Lynch; Seung-Wook Chung; et al. (Archives of Toxicology, 2021)
5-Fluorouracil (5-FU) is a widely used chemotherapeutical that induces acute toxicity in the small and large intestine of patients. Symptoms can be severe and lead to the interruption of cancer treatments. However, there is limited understanding of the molecular mechanisms underlying 5-FU-induced intestinal toxicity. In this study, well-established 3D organoid models of human colon and small intestine (SI) were used to characterize 5-FU transcriptomic and metabolomic responses. Clinically relevant 5-FU concentrations for in vitro testing in organoids were established using physiologically based pharmacokinetic simulation of dosing regimens recommended for cancer patients, resulting in exposures to 10, 100 and 1000 µM. After treatment, different measurements were performed: cell viability and apoptosis; image analysis of cell morphological changes; RNA sequencing; and metabolome analysis of supernatant from organoids cultures. Based on analysis of the differentially expressed genes, the most prominent molecular pathways affected by 5-FU included cell cycle, p53 signalling, mitochondrial ATP synthesis and apoptosis. Short time-series expression miner demonstrated tissue-specific mechanisms affected by 5-FU, namely biosynthesis and transport of small molecules, and mRNA translation for colon; cell signalling mediated by Rho GTPases and fork-head box transcription factors for SI. Metabolomic analysis showed that in addition to the effects on TCA cycle and oxidative stress in both organoids, tissue-specific metabolic alterations were also induced by 5-FU. Multi-omics integration identified transcription factor E2F1, a regulator of cell cycle and apoptosis, as the best key node across all samples. These results provide new insights into 5-FU toxicity mechanisms and underline the relevance of human organoid models in the safety assessment in drug development.

ROS in vivo determination and antioxidant responses in rotifers Brachionus plicatilis fed with commercial yeast Saccharomyces cerevisiae or microalgae Nannochloropsis oculata - Ricardo Vieira Rodrigues; Lucas C. Maltez; Cristiano C. Ferreira; Thiago P. A. P. Oliveira; Luís A. Sampaio; José María Monserrat (Aquaculture International, 2021)

A Novel Orthoreovirus Isolated From Dead Stranded Harbor Seals From Puget Sound, Washington State, United States - Ole Nielsen; Thaís C. S. Rodrigues; Vsevolod L. Popov; Kuttichantran Subramaniam; Thomas B. Waltzek; Dyanna M. Lambourn; Stephen Raverty (Frontiers in Marine Science, 2021)
As part of an ongoing investigation of harbor seal ( Phoca vitulina ) mortalities within Puget Sound, Washington State, United States, between October 2007 and July 2008, 25 seal cases were submitted for histopathology and ancillary diagnostic testing, including additional attempted virus isolation. In vitro granular and refractile cytopathic effects (CPE) were consistently observed in Vero.DogSLAMtag cells inoculated with tissue homogenates from three seals. Transmission electron microscopy of infected Vero.DogSLAMtag cells revealed cytoplasmic clusters of icosahedral viral particles morphologically consistent with members of the family Reoviridae . The complete genome of a novel species within the genus Orthoreovirus , tentatively named phocid orthoreovirus 1 (PhRV1), was determined by next-generation sequencing and confirmed by rt-PCR in isolates from the three harbor seals. This is the first report of an orthoreovirus infection associated with dead stranded harbor seals. Aside from the CPE and ultrastructural findings, no consistent signalment, gross pathology, histopathology, or ancillary diagnostic findings were identified with PhRV1 infection. Further research is needed to determine the prevalence, tissue tropism, transmission, pathogenicity, zoonotic potential, and host range of orthoreoviruses in pinnipeds. This study demonstrates the value of thorough necropsy investigations and a multidisciplinary team approach to advance our understanding of marine mammal health.

Tidal and Physicochemical Effects on Phytoplankton Community Variability at Tagus Estuary (Portugal) - Rui Cereja; Vanda Brotas; Joana P. C. Cruz; Marta Rodrigues; Ana C. Brito (Frontiers in Marine Science, 2021)
The Tagus Estuary is one of the largest estuaries in Europe and merges large urban and industrial areas. Understanding phytoplankton community variability is key for an appropriate assessment of the estuarine ecological status. The objective of the present study was to assess the importance of the tidal influence over the phytoplankton community and to evaluate its main drivers of variation. Weekly sampling was performed at two stations on the Tagus Estuary with different anthropogenic pressures (Alcântara and Barreiro). The sampling covered periods with different tidal amplitude. Alcântara presented both the lowest and highest concentrations of dissolved inorganic nitrogen (DIN) and orthophosphate concentration (DIP), depending on the tidal height. Such high variability in this sampling station is probably due to its proximity to a sewage treatment station outfall and to the estuary mouth. In the present study, both seasonal and tidal variations influenced the chlorophyll a concentration of which the tidal cycle explained up to 50% of the chlorophyll a variations. Chlorophyll a displayed a seasonal trend with two peaks of phytoplankton biomass between spring and mid-summer. The main drivers of chlorophyll a variation were radiation, water temperature, tidal amplitude, salinity, river discharge, and the inorganic nutrients DIN and DSi. The estuarine phytoplankton community was mainly dominated by Bacillariophyceae, especially at Alcântara. Bacillariophyceae were less important at Barreiro, where communities had a higher representation from other phytoplankton groups, such as Cryptophyceae and Prasinophyceae. The drivers of variability in the community composition were similar to those influencing the total biomass. In conclusion, the spring-neap tidal cycle strongly influenced the phytoplankton community, both in terms of biomass and community composition. Of the several tidal conditions, spring tides were the tidal condition that presented both higher biomass and higher Bacillariophyceae representativity in the community.

The neurotherapeutic role of a selenium-functionalized quinoline in hypothalamic obese rats - Karline C. Rodrigues; Cristiani F. Bortolatto; Ketlyn P. da Motta; Renata L. de Oliveira; Jaini J. Paltian; Roberta Krüger; Silvane S. Roman; Silvana P. Boeira; Diego Alves; Ethel Antunes Wilhelm; Cristiane Luchese (Psychopharmacology, 2021)

Fire and water: the role of grass competition on juvenile tree growth and survival rates in a mesic savanna - P. Laris; L. Yang; F. Dembele; C. M. Rodrigue (Plant Ecology, 2021)

Plastic pollution: A focus on freshwater biodiversity - Valter M. Azevedo-Santos; Marcelo F. G. Brito; Pedro S. Manoel; Júlia F. Perroca; Jorge Luiz Rodrigues-Filho; Lucas R. P. Paschoal; Geslaine R. L. Gonçalves; Milena R. Wolf; Martín C. M. Blettler; Marcelo C. Andrade; André B. Nobile; Felipe P. Lima; et al. (Ambio, 2021)

A Concise Review on Induced Pluripotent Stem Cell-Derived Cardiomyocytes for Personalized Regenerative Medicine - Pallavi Pushp; Diogo E. S. Nogueira; Carlos A. V. Rodrigues; Frederico C. Ferreira; Joaquim M. S. Cabral; Mukesh Kumar Gupta (Stem Cell Reviews and Reports, 2021)

Potent Anti-Candida Fraction Isolated from Capsicum chinense Fruits Contains an Antimicrobial Peptide That is Similar to Plant Defensin and is Able to Inhibit the Activity of Different α-Amylase Enzymes - Mariana C. L. Aguieiras; Larissa M. Resende; Thaynã A. M. Souza; Celso S. Nagano; Renata P. Chaves; Gabriel B. Taveira; André O. Carvalho; Rosana Rodrigues; Valdirene M. Gomes; Érica O. Mello (Probiotics and Antimicrobial Proteins, 2021)

Soybean seed chemical treatment associated with inoculants: physiological and agronomical analyses - V. M. Santos; T. C. Oliveira; M. G. Mendes; C. H. Yamanaka; Willian Rodrigues Macedo (Plant Physiology Reports, 2021)

Correction to: A copper(II)-binding triazole derivative with ionophore properties is active against Candida spp. - A. Gaspar-Cordeiro; S. da Silva; M. Aguiar; C. Rodrigues-Pousada; H. Haas; L. M. P. Lima; C. Pimentel (JBIC Journal of Biological Inorganic Chemistry, 2021)

KIR2DL4 genetic diversity in a Brazilian population sample: implications for transcription regulation and protein diversity in samples with different ancestry backgrounds - Emiliana Weiss; Heloisa S. Andrade; Juliana Rodrigues Lara; Andreia S. Souza; Michelle A. Paz; Thálitta H. A. Lima; Iane O. P. Porto; Nayane S. B. Silva; Camila F. Bannwart Castro; Rejane M. T. Grotto; Eduardo A. Donadi; Celso T. Mendes-Junior; et al. (Immunogenetics, 2021)

Environmental correlates of taxonomic and phylogenetic diversity in the Atlantic Forest - Andrea Paz; Jason L. Brown; Carlos L. O. Cordeiro; Julian Aguirre‐Santoro; Claydson Assis; Renata Cecilia Amaro; Fabio Raposo do Amaral; Thuane Bochorny; Lucas F. Bacci; Mayara K. Caddah; Fernando d’Horta; Miriam Kaehler; et al. (Journal of Biogeography, 2021)
Aim There is little consensus on which environmental variables are best at predicting multiple dimensions of diversity. We ask whether there are common environmental correlates of diversity, despite ecological differences, across nine clades of plants and animals distributed along a single rainforest domain. For that, we compare the environmental correlates of species richness, phylogenetic diversity, and phylogenetic endemism. Location Brazilian Atlantic Forest. Taxon: Five clades of plants (Bromelioideae, Miconieae, Bertolonia , Cambessedesieae, and the Fridericia and allies) and four clades of animals (butterlies in the tribe Ithomiini, frogs in the genera Boana and Proceratophrys , and birds in the subfamily Thraupinae). Methods Using curated occurrence localities and phylogenetic data, we generated maps of (a) species richness, (b) phylogenetic diversity, (c) residuals of phylogenetic diversity regressed on species richness, and (d) phylogenetic endemism for all groups. We also compiled a set of 30 environmental descriptors, including records of current temperature and precipitation, climatic stability over time, and topography. Through a machine learning framework, we explored the environmental correlates of each of these diversity measures for each group. Results The environmental variables used here were strong predictors of diversity for all studied groups. However, models for phylogenetic endemism had lower predictive power. Although patterns of diversity are different among groups, correlates of diversity are consistent across taxa. For both species richness and phylogenetic diversity, current precipitation and precipitation stability over time were consistently ranked among the variables that strongly correlate with diversity patterns. The correlates of phylogenetic endemism were less homogeneous across groups. The results suggest that including climate stability over time is important when predicting diversity measures that reflect historical components. Main conclusions Investigating environmental correlates of diversity for multiple clades and diversity measures in a single geographic area allows for a better understanding of common patterns across taxa. This study shows that environmental conditions, particularly precipitation, are good predictors of the patterns of species richness and phylogenetic diversity‐but not phylogenetic endemism‐across different Atlantic Forest groups.

Using richness of native and non-native aquatic species along a climatic gradient to test the intermediate disturbance hypothesis - Luciano N. Santos; Ana Clara S. Franco; Joice S. de Souza; Igor C. Miyahira; Antonio Jailson S. Rodrigues; Isabela Cristina B. Gonçalves; Natascha Krepsky; Helga A. B. Monte; Clarissa Naveira; Tatiana M. B. Cabrini; Rayane R. S. Abude; Matheus Augusto; et al. (Hydrobiologia, 2021)

Genomic data from the Brazilian sibilator frog reveal contrasting pleistocene dynamics and regionalism in two South American dry biomes - Maria Tereza C. Thomé; Bryan C. Carstens; Miguel T. Rodrigues; João Alexandrino; Célio F. B. Haddad (Journal of Biogeography, 2021)
Aim Knowledge about the Neotropical dry formations, particularly the Caatinga, remains rudimentary compared to other biotas in the region. Here we address several biogeographical hypotheses by combining intense geographical and genomic sampling obtained for the Brazilian sibilator frog. We specifically test predictions related to the putative roles of past climate shifts (Pleistocene and Holocene) and local geographical barriers (past and current courses of the São Francisco River, SFR) in causing population differentiation in this species. Location Caatinga and eastern Cerrado. Taxon Brazilian sibilator frog Leptodactylus troglodytes . Methods We sequenced up to ~15,000 single nucleotide polymorphisms for 159 samples from 61 locations. We inferred genetic structure using spatial clustering and examined population sizes through time. We estimated the relationship among populations using phylogenetic reconstruction, estimated historical distributions with ecological niche modelling and inferred demographic history under isolation‐with‐migration models. Results Genetic diversity in L. troglodytes corresponds to biome boundaries, with one population in the Cerrado and two populations in the Caatinga, separated by the SFR. Demographic model selection indicates the Caatinga populations expanded since the end of the Pleistocene while the Cerrado population declined. Within the Caatinga, population expansion began earlier and was more extreme in the north. A continuous stability area maintained the two Caatinga populations, which share a common origin and began diverging in the mid‐Pleistocene, first with symmetric gene flow and later under pronounced migration from the north. Main conclusions We could not reject a role of past climate change in causing diversification of relictual populations in the Cerrado, but we found no evidence of multiple refuges or long‐term isolation within the Caatinga. Instead, diversification in this biome appears to be caused by the SFR acting as a ‘soft barrier’ that constrains migration over an extended period of time.

Principles and applications of non-thermal technologies and alternative chemical compounds in meat and fish - Denes K. A. Rosario; Bruna L. Rodrigues; Patricia C. Bernardes; Carlos A. Conte-Junior (Critical Reviews in Food Science and Nutrition, 2021)

Glycoside hydrolases from the tunics of two Antarctic ascidians (Ascidia challengeri and Pyura bouvetensis) and the tropical species Phallusia nigra - Elisa K. S. Ramos; Stéfanie C. L. dos Santos; Kerolyn K. Kuroki; Letícia Benavalli; Gannabathula S. Vani; Valter J. Cobo; Takahisa Hayashi; Edson Rodrigues; Cecilia N. K. Suda (Polar Biology, 2021)

Evaluation of Cerebellar Function and Integrity of Adult Rats After Long-Term Exposure to Aluminum at Equivalent Urban Region Consumption Concentrations - Rafael Monteiro Fernandes; Priscila Cunha Nascimento; Maria Karolina Martins; Walessa Alana Bragança Aragão; Luis Felipe Sarmiento Rivera; Leonardo Oliveira Bittencourt; Sabrina C. Cartágenes; Maria Elena Crespo-Lopez; Cristiane do Socorro Ferraz Maia; Rafael Rodrigues Lima (Biological Trace Element Research, 2021)

Scale‐dependent patterns of metacommunity structuring in aquatic organisms across floodplain systems - Fernando M. Lansac‐Tôha; Luis M. Bini; Jani Heino; Bianca R. Meira; Bianca T. Segovia; Carla S. Pavanelli; Claudia C. Bonecker; Claudia P. de Deus; Evanilde Benedito; Geziele M. Alves; Gislaine I. Manetta; Juliana D. Dias; et al. (Journal of Biogeography, 2021)
Aim Evaluating how groups of organisms vary in dispersal capability and how environmental, spatial and temporal signals vary across multiple scales is critical to elucidating metacommunity theory. We examined whether the relative contributions of environmental, spatial and hydrological factors have different effects on organismal groups with different dispersal abilities at three spatial scales, and how this knowledge contributes to our understanding of metacommunity dynamics. Location Four major Brazilian floodplains, with the largest distance among them of 2,300 Km. Taxon 10 aquatic organismal groups, ranging from bacterioplankton to fish. Methods We sampled lakes connected to the main river in the low‐ and high‐water periods of each floodplain between 2011 and 2012. Different biological groups were analysed across three hierarchical spatial scales (fine, intermediate and subcontinental) within and between floodplain systems. We applied a series of partial redundancy analyses to estimate the relative contributions of environmental factors, spatial factors and hydrological period for each biological group. Results At the fine spatial scale, predominantly environmental factors and hydrological period structure metacommunities, although less so for microorganisms than for micro‐invertebrates and macro‐organisms. The relative importance of environmental factors increased at the intermediate spatial scale. At the subcontinental scale, the relative importance of spatial factors increased for all biological groups, but environmental factors remained the primary regulators of microorganisms even at the largest scale. Main conclusions This study design allowed us to make more robust inferences about the mechanisms responsible for regulating community structure of distinct biological groups at different spatial scales. Our results suggest that biological groups displaying distinct body size likely determine the spatial extent at which environmental, spatial and hydrological processes prevail as the primary regulators of community structure. These findings are important in guiding the conservation and management of floodplain biodiversity because these systems are naturally highly heterogeneous in space and time.

Feeding behavior of feedlot-finished crossbred bulls fed palm kernel cake - Mateus de M. Lisboa; Robério R. Silva; Fabiano F. da Silva; Maria M. S. Pereira; Gabriel D. Costa; Fabrício B. L. Mendes; Sinvaldo O. de Souza; Marceliana da C. Santos; Laoan B. O. Rodrigues; Henry D. R. Alba; Gleidson G. P. de Carvalho (Tropical Animal Health and Production, 2021)

The usefulness of Olanzapine plasma concentrations in monitoring treatment efficacy and metabolic disturbances in first-episode psychosis - J. A. Arnaiz; C. Rodrigues-Silva; G. Mezquida; S. Amoretti; M. J. Cuesta; D. Fraguas; A. Lobo; A. González-Pinto; M. C. Díaz-Caneja; I. Corripio; E. Vieta; I. Baeza; et al. (Psychopharmacology, 2021)

Minimizing the Wallacean shortfall: a small sample reveals new occurrences of ground-dwelling spiders in native Cerrado and exotic pastures in the Midwestern Brazil - César M. A. Correa; Anderson Puker; Vinícius B. Rodrigues; Vanesca Korasaki; Paulo C. Motta (International Journal of Tropical Insect Science, 2021)

The CORDEX Flagship Pilot Study in southeastern South America: a comparative study of statistical and dynamical downscaling models in simulating daily extreme precipitation events - M. L. Bettolli; S. A. Solman; R. P. da Rocha; M. Llopart; J. M. Gutierrez; J. Fernández; M. E. Olmo; A. Lavin-Gullon; S. C. Chou; D. Carneiro Rodrigues; E. Coppola; R. Balmaceda Huarte; et al. (Climate Dynamics, 2021)

Purification of arsenic-contaminated water using iron molybdate filters and monitoring of their genotoxic, mutagenic, and cytotoxic effects through bioassays - Rodrigo C. Hott; Thainá S. Magalhães; Luiz F. O. Maia; Kallel S. F. Santos; Guilherme L. Rodrigues; Luiz C. A. Oliveira; Márcio C. Pereira; Márcia C. S. Faria; Alessandra P. Carli; Caio C. Souza Alves; Jairo L. Rodrigues (Environmental Science and Pollution Research, 2021)

Reliability of evidence‐review methods in restoration ecology - João P. Romanelli; Paula Meli; Rafaela P. Naves; Marcelo C. Alves; Ricardo R. Rodrigues (Conservation Biology, 2021)
In restoration science, evidence reviews play a crucial role in summarizing research findings in practice and policy. However, if unreliable or inappropriate methods are used to review evidence, decisions based on these reviews may not accurately reflect the available evidence base. To assess the current value of restoration reviews, we examined a sample of meta‐analyses and narrative syntheses (n = 91) with the Collaboration for Environmental Evidence Synthesis Assessment Tool (CEESAT), which uses detailed criteria to assesses the method of policy‐relevant evidence synthesis according to elements important for objectivity, transparency, and comprehensiveness. Overall, reviews scored low based on this standard: median score 16 out of 39, modal score 15, and mean 16.6. Meta‐analyses scored higher than narrative syntheses (median 17 vs. 5, respectively), although there were some outlier narrative syntheses that had high scores, suggesting that quantitative synthesis does not solely reflect the reliability of a review. In general, criteria spanning the more fundamental review stages (i.e., searching for studies and including studies) received low scores for both synthesis types. Conversely, criteria comprising the later stages of the review (i.e., critical appraisal, data extraction, and data synthesis) were generally well described in meta‐analyses; thus, these criteria achieved the highest individual CEESAT scores. We argue that restoration ecology is well positioned to advance so‐called evidence‐based restoration, but review authors should elucidate their conceptual understanding of evidence syntheses and recognize that conducting reliable reviews demands the same methodological rigor and reporting standards used in primary research. Given the potential of evidence reviews to inform management, policy, and research, it is of vital importance that the overall methodological reliability of restoration reviews be improved.

Different wavelengths of visible light influence the conidial production and tolerance to ultra-violet radiation of the plant pathogens Colletotrichum acutatum and Fusarium fujikuroi - Tacyana P. C. Costa; Eliane M. Rodrigues; Luciana P. Dias; Breno Pupin; Paulo C. Ferreira; Drauzio E. N. Rangel (European Journal of Plant Pathology, 2021)

Antioxidant activity and enzyme inhibitory potential of Euphorbia resinifera and E. officinarum honeys from Morocco and plant aqueous extracts - Oumaima Boutoub; Soukaina El-Guendouz; Letícia M. Estevinho; Vanessa B. Paula; Smail Aazza; Lahsen El Ghadraoui; Brígida Rodrigues; Sara Raposo; Jorge Carlier; Maria C. Costa; Maria G. Miguel (Environmental Science and Pollution Research, 2021)

In vitro bioassay guided anti-dermatophyte and cytotoxic activities from Piper umbellatum L. Miq. led to 4-nerolidylcatechol - Jolindo A. Freitas; Rodrigo Sorrechia; Flávio A. S. Politi; André G. Santos; Edvânio R. Rodrigues; Lourdes C. Santos; Ana M. Fusco-Almeida; Andrew A. Oliveira; Rafael V. C. Guido; Rosemeire C. L. R. Pietro (Natural Product Research, 2020)

Violacein antimicrobial activity on Staphylococcus epidermidis biofilm - H. V. Dodou; A. H. M. Batista; S. C. Medeiros; G. W. P. Sales; M. L. Rodrigues; P. I. O. Pereira; P. C. N. Nogueira; E. R. Silveira; T. B. Grangeiro; N. A. P. Nogueira (Natural Product Research, 2020)

Does leaf flushing in the dry season affect leaf traits and herbivory in a tropical dry forest? - Jhonathan O. Silva; Mário M. Espírito-Santo; Joselândio C. Santos; Priscyla M. S. Rodrigues (The Science of Nature, 2020)

Combined Soil and Foliar Nitrogen Fertilization Effects on Rainfed Almond Tree Performance - Maria C. Morais; Alfredo Aires; David Barreales; M. Ângelo Rodrigues; António C. Ribeiro; Berta Gonçalves; Ana P. Silva (Journal of Soil Science and Plant Nutrition, 2020)

A copper(II)-binding triazole derivative with ionophore properties is active against Candida spp. - A. Gaspar-Cordeiro; S. da Silva; M. Aguiar; C. Rodrigues-Pousada; H. Haas; L. M. P. Lima; C. Pimentel (JBIC Journal of Biological Inorganic Chemistry, 2020)

Assessing VIIRS capabilities to improve burned area mapping over the Brazilian Cerrado - Filippe L.M. Santos; Renata Libonati; Leonardo F. Peres; Allan A. Pereira; Luiza C. Narcizo; Julia A. Rodrigues; Duarte Oom; José M. C. Pereira; Wilfrid Schroeder; Alberto W. Setzer (International Journal of Remote Sensing, 2020)

Ayahuasca blocks the reinstatement of methylphenidate-induced conditioned place preference in mice: behavioral and brain Fos expression evaluations - Henrique S. Reis; Isa R. S. Rodrigues; Alexia Anjos-Santos; Matheus Libarino-Santos; Yasmim A. Serra; Elisângela G. Cata-Preta; Daniella Oliveira-Campos; Natali D. Kisaki; Thaísa Barros-Santos; Thais S. Yokoyama; Fabio C. Cruz; Alexandre J. Oliveira-Lima; et al. (Psychopharmacology, 2020)

Inoculation with the endophytic bacterium Herbaspirillum seropedicae promotes growth, nutrient uptake and photosynthetic efficiency in rice - Alessandro C. Ramos; Juliana Melo; Sávio B. de Souza; Amanda A. Bertolazi; Renderson A. Silva; Weverton P. Rodrigues; Eliemar Campostrini; Fábio L. Olivares; Frederico J. Eutrópio; Cristina Cruz; Teresa Dias (Planta, 2020)

Historical biogeography identifies a possible role of Miocene wetlands in the diversification of the Amazonian rocket frogs (Aromobatidae: Allobates ) - Alexandre Réjaud; Miguel T. Rodrigues; Andrew J. Crawford; Santiago Castroviejo‐Fisher; Andrés F. Jaramillo; Juan C. Chaparro; Frank Glaw; Giussepe Gagliardi‐Urrutia; Jiří Moravec; Ignacio J. De la Riva; Pedro Perez; Albertina P. Lima; et al. (Journal of Biogeography, 2020)
Aim We investigate the spatiotemporal context of the diversification of Allobates , a widespread genus of Amazonian frogs with high species diversity particularly in western Amazonia. We tested if that diversity originated in situ or through repeated dispersals from other Amazonian areas and if this diversification took place during or after the Pebas system, a vast lacustrine system occupying most western Amazonia between 23 and 10 million years ago (Mya). Location Amazonia. Taxon Allobates (Anura: Aromobatidae). Methods We gathered a spatially and taxonomically extensive sampling of mitochondrial DNA sequences from 932 Allobates specimens to delimit Operational Taxonomic Units (OTUs). Complete mitogenomes of these OTUs were assembled to reconstruct a time‐calibrated phylogeny used to infer the historical and spatial origin of the Amazonian Allobates lineages. Results Phylogenetic analyses and ancestral area reconstruction suggested that most of the western Amazonian lineages resulted from in situ diversification and that these events occurred between the inferred origin of the genus (25 Mya) and 10 Mya, with a possible peak between 14 and 10 Mya. Dispersal among areas mostly occurred from western Amazonia towards the Brazilian and the Guiana Shields. Closely related Allobates OTUs display an allopatric pattern of distribution, matching interfluves delimited by modern Amazonian rivers. Main Conclusions In western Amazonia, diversification of Allobates appears to have been simultaneous with the last stages of the Pebas system (14–10 Mya). Subsequently (within the last 10 Mya), modern Amazonian river courses shaped the distribution pattern of Allobates species and possibly promoted allopatric speciation.

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Damming reduced the functional richness and caused the shift to a new functional state of the phytoplankton in a subtropical region - Alfonso Pineda; Patrícia Iatskiu; Susicley Jati; Aline C. M. Paula; Bárbara F. Zanco; Claudia C. Bonecker; Geovani A. Moresco; Laura A. Ortega; Yasmin R. Souza; Luzia C. Rodrigues (Hydrobiologia, 2020)

Gonadal remodeling and hormonal regulation during sex change of juvenile dusky grouper Epinephelus marginatus (Teleostei, Serranidae), an endangered protogynous hermaphrodite fish - J. A. Rodrigues-Filho; C. E. O. Garcia; C. G. Chehade; E. G. Sanches; M. I. Borella; F. L. Lo Nostro; B. C. Araújo; G. S. Branco; R. G. Moreira (Fish Physiology and Biochemistry, 2020)

Correction to: Carbon sequestration and nutrient cycling in agroforestry systems on degraded soils of Eastern Amazon, Brazil - Danielle Celentano; Guillaume Xavier Rousseau; Larissa Santos Paixão; Francisneide Lourenço; Ernesto Gómez Cardozo; Thiago Oliveira Rodrigues; Hulda Rocha e Silva; Júlio Medina; Tatiane Marques C. de Sousa; Ariadne Enes Rocha; Fabrício de Oliveira Reis (Agroforestry Systems, 2020)

Carbon sequestration and nutrient cycling in agroforestry systems on degraded soils of Eastern Amazon, Brazil - Danielle Celentano; Guillaume Xavier Rousseau; Larissa Santos Paixão; Francisneide Lourenço; Ernesto Gómez Cardozo; Thiago Oliveira Rodrigues; Hulda Rocha e Silva; Júlio Medina; Tatiane Marques C. de Sousa; Ariadne Enes Rocha; Fabrício de Oliveira Reis (Agroforestry Systems, 2020)

Spatial distribution of the level of return of extreme precipitation events in Northeast Brazil - Daniele T. Rodrigues; Weber A. Gonçalves; Maria H. C. Spyrides; Cláudio M. Santos e Silva; Diego O. de Souza (International Journal of Climatology, 2020)
This study aimed to estimate levels of return of extreme daily precipitation events, associating them with natural disasters in Northeast Brazil (NEB), a region characterized by different climatic conditions and low rates of social and economic development. For this, generalized Pareto distribution (GPD) models were adjusted to the daily extreme precipitation data estimated by the Tropical Rainfall Measuring Mission (TRMM) 3B42 product of the multisatellite precipitation analysis for a period of 16 years (2000–2015). In addition, the estimates of the GPD model were compared using two data sources, TRMM and pluviometer. The investigation showed that the results of the GPD model estimated by means of the extreme data from the rain gauge and the TRMM were statistically the same, with 95% confidence. Thus, using the data referring to the 2,082 grid points of the TRMM, it was possible to map the spatial distribution of the estimates of the levels of return of extreme precipitation to the return periods of 2, 5 and 10 years, per seasonal period. In general, the results indicated that the intensity of expected extreme precipitation depends on the seasonal period and the place of occurrence of precipitation. The eastern NEB stood out as the region where the highest intensities of extreme precipitation are expected. Extreme precipitation values of up to 178 mm are expected in 2 years. The areas where natural disasters occurred in the years 2016, 2017 and 2018 are similar to those in which the highest rainfall intensities are expected. The results of this study can allow the evaluation of the spatial distribution of risks related to extreme precipitation events, and therefore, support the planning of regional public policies and environmental management for the prevention of natural disasters in NEB.

SERK genes identification and expression analysis during somatic embryogenesis and sporogenesis of sexual and apomictic Brachiaria brizantha (Syn. Urochloa brizantha) - Andréa D. Koehler; André S. T. Irsigler; Vera T. C. Carneiro; Glaucia B. Cabral; Júlio C. M. Rodrigues; Ana Cristina M. M. Gomes; Roberto C. Togawa; Marcos M. C. Costa; Adriana Pinheiro Martinelli; Diva Maria de Alencar Dusi (Planta, 2020)

Retrospective study of porcine circovirus 3 (PCV3) in swine tissue from Brazil (1967–2018) - I. L. F. Rodrigues; A. C. M. Cruz; A. E. Souza; F. B. Knackfuss; C. H. C. Costa; R. L. Silveira; T. X. Castro (Brazilian Journal of Microbiology, 2020)

Ion Pair Strategy in Solid Lipid Nanoparticles: a Targeted Approach to Improve Epidermal Targeting with Controlled Adapalene Release, Resulting Reduced Skin Irritation - Linna B. O. Rodrigues; Flávia A. Lima; Camila P. B. Alves; Elisângela Martins-Santos; Marta M. G. Aguiar; Cleida A. Oliveira; Rodrigo L. Oréfice; Lucas A. M. Ferreira; Gisele A. C. Goulart (Pharmaceutical Research, 2020)

Task load modulates tDCS effects on brain network for phonological processing - Lílian Rodrigues de Almeida; Paul A. Pope; Peter C. Hansen (Cognitive Processing, 2020)
Motor participation in phonological processing can be modulated by task nature across the speech perception to speech production range. The pars opercularis of the left inferior frontal gyrus (LIFG) would be increasingly active across this range, because of changing motor demands. Here, we investigated with simultaneous tDCS and fMRI whether the task load modulation of tDCS effects translates into predictable patterns of functional connectivity. Findings were analysed under the “multi-node framework”, according to which task load and the network structure underlying cognitive functions are modulators of tDCS effects. In a within-subject study, participants ( N = 20) performed categorical perception, lexical decision and word naming tasks [which differentially recruit the target of stimulation (LIFG)], which were repeatedly administered in three tDCS sessions (anodal, cathodal and sham). The LIFG, left superior temporal gyrus and their right homologues formed the target network subserving phonological processing. C-tDCS inhibition and A-tDCS excitation should increase with task load. Correspondingly, the larger the task load, the larger the relevance of the target for the task and smaller the room for compensation of C-tDCS inhibition by less relevant nodes. Functional connectivity analyses were performed with partial correlations, and network compensation globally inferred by comparing the relative number of significant connections each condition induced relative to sham. Overall, simultaneous tDCS and fMRI was adequate to show that motor participation in phonological processing is modulated by task nature. Network responses induced by C-tDCS across phonological processing tasks matched predictions. A-tDCS effects were attributed to optimisation of network efficiency.

Evaluation of gully development over several years using GIS and fractal analysis: a case study of the Palmital watershed, Minas Gerais (Brazil) - L. S. C. Real; S. Crestana; R. R. M. Ferreira; V. G. S. Rodrigues (Environmental Monitoring and Assessment, 2020)

PAH Profiles in Suspended Particulate Matter from an Urbanized River Within the Brazilian Amazon - L. C. Sousa; C. C. S. Rodrigues; R. A. Mendes; J. A. M. Corrêa (Bulletin of Environmental Contamination and Toxicology, 2020)

Cellular oxidative damage and impairment on the photosynthetic apparatus caused by Asian Soybean Rust on soybeans are alleviated by nickel - Andersom M. Einhardt; Sandro Ferreira; Gabriel M. F. Souza; Ana C. R. Mochko; Fabrício A. Rodrigues (Acta Physiologiae Plantarum, 2020)

Natural Enemies of the Harrisia Cactus Mealybug and Other Hypogeococcus Species (Hemiptera: Pseudococcidae) in Puerto Rico: Identification and Taxonomic Notes on Primary and Secondary Parasitoids - S. V. Triapitsyn; S. D. Hight; G. A. Logarzo; M. B. Aguirre; J. C. Verle Rodrigues; V. A. Trjapitzin; Z. Rivera Ocasio; M. L. Rivera-Vázquez; M. J. West Ortiz; Y. Rodríguez Reyes (Neotropical Entomology, 2020)

The oviposition behavior of fall armyworm moths is unlikely to compromise the refuge strategy in genetically modified Bt crops - Jaciara Gonçalves; João Victor C. Rodrigues; Oscar F. Santos-Amaya; Silvana V. Paula-Moraes; Eliseu José G. Pereira (Journal of Pest Science, 2020)

Evolutionary and Functional Implications of Incisor Enamel Microstructure Diversity in Notoungulata (Placentalia, Mammalia) - Andréa Filippo; Daniela C. Kalthoff; Guillaume Billet; Helder Gomes Rodrigues (Journal of Mammalian Evolution, 2020)

Ouabain reduces the expression of the adhesion molecule CD18 in neutrophils - Luiz Henrique Agra Cavalcante-Silva; Éssia de Almeida Lima; Deyse C. M. Carvalho; Sandra Rodrigues-Mascarenhas (Inflammopharmacology, 2020)

Cytotoxic Effect of Prodigiosin, Natural Red Pigment, Isolated from Serratia marcescens UFPEDA 398 - J. C. L. Lapenda; V. P. Alves; M. L. Adam; M. D. Rodrigues; S. C. Nascimento (Indian Journal of Microbiology, 2020)

Clindamycin inhibits nociceptive response by reducing tumor necrosis factor-α and CXCL-1 production and activating opioidergic mechanisms - Felipe F. Rodrigues; Marcela I. Morais; Ivo S. F. Melo; Paulo S. A. Augusto; Marcela M. G. B. Dutra; Sarah O. A. M. Costa; Fábio C. Costa; Franciele A. Goulart; Alysson V. Braga; Márcio M. Coelho; Renes R. Machado (Inflammopharmacology, 2020)

Gold-Coated Superparamagnetic Iron Oxide Nanoparticles Attenuate Collagen-Induced Arthritis after Magnetic Targeting - Maria Fernanda Hornos Carneiro; Ana Rita T. Machado; Lusânia M. G. Antunes; Talita E. Souza; Victor A. Freitas; Luiz C. A. Oliveira; Jairo L. Rodrigues; Marcio C. Pereira; Fernando Barbosa (Biological Trace Element Research, 2020)

Correction to: Ecological restoration as a strategy for mitigating and adapting to climate change: lessons and challenges from Brazil - Mercedes M. C. Bustamante; José Salomão Silva; Aldicir Scariot; Alexandre Bonesso Sampaio; Daniel Luis Mascia Vieira; Edenise Garcia; Edson Sano; Geraldo Wilson Fernandes; Giselda Durigan; Iris Roitman; Isabel Figueiredo; Ricardo Ribeiro Rodrigues; et al. (Mitigation and Adaptation Strategies for Global Change, 2020)

Diet and foraging opportunism of the Guiana dolphin ( Sotalia guianensis ) in the Abrolhos Bank, Brazil - Vitor Leonardo A. Rodrigues; Leonardo L. Wedekin; Milton César C. Marcondes; Lupércio Barbosa; Ana Paula C. Farro (Marine Mammal Science, 2020)
Diet analysis allows exploring how coastal dolphins interact with the environment and their role in the marine food webs. We studied the diet and feeding ecology of the Guiana dolphin, Sotalia guianensis , through analysis of stomach content from 42 animals stranded on the eastern coast of Brazil. A total of 1,336 semidigested prey items (fish, otoliths, cephalopod beaks, and crustaceans) were identified. Teleost fish comprised the most frequent food item (92% of the total), followed by cephalopods, and crustaceans. Prey belonged to 34 taxa and richness in individual stomachs varied from 1 to 15 prey taxa. Prey were generally small, but showed a significant trend to increase in size with dolphin length. The main prey of Guiana dolphins were demersal, estuarine, and sound‐making fish such as catfish and sciaenids. No sex‐related differences in diet were found. Diet composition varied seasonally and occurrence of prey items was coherent with breeding or high abundance periods of some fish species and squids. Our study shows the importance of demersal prey from estuarine and soft‐sediment habitats to Guiana dolphin in the Abrolhos Bank and reveals that feeding habits are generalist and opportunistic, with diet reflecting the seasonal abundance and availability of prey.

Climate change impacts under representative concentration pathway scenarios on streamflow and droughts of basins in the Brazilian Cerrado biome - Jéssica A. M. Rodrigues; Marcelo R. Viola; Lívia A. Alvarenga; Carlos R. de Mello; Sin C. Chou; Vinícius A. de Oliveira; Venkatesh Uddameri; Marco A. V. Morais (International Journal of Climatology, 2020)
Brazilian Cerrado biome is the largest and richest tropical savanna in the world. In order to understand the effects of climate changes on the hydrology of the Cerrado basins, this paper investigates the hydrological impacts of climate change throughout the 21st century under different emissions scenarios on the streamflow and on the droughts in the Sono, Manuel Alves da Natividade and Palma basins, located in the Brazilian Cerrado. For this purpose, the SWAT hydrological model driven by the downscaling of the HadGEM2‐ES and MIROC5 global climate models associated with RCP4.5 and RCP8.5 scenarios were used in three time slices (2011–2040, 2041–2070 and 2071–2099). The Standardized Precipitation Index (SPI) and the Standardized Streamflow Index (SSFI) were used to characterize droughts. In general, the results showed that the duration, intensity and frequency of the meteorological and hydrological droughts are expected to increase during the future periods. However, the hydrological droughts are projected to be larger than the meteorological droughts. Reductions in the streamflow are indicated in all future time slices and under both RCPs, especially, during dry periods, which may cause negative impacts in the ecological functions of the Cerrado biome, risk for reduction of the recharge of aquifers and risk for the electric energy production in northern Brazil.

The Galactose-Binding Lectin Isolated from Vatairea macrocarpa Seeds Enhances the Effect of Antibiotics Against Staphylococcus aureus–Resistant Strain - Valdenice F. Santos; Maria S. Costa; Fábia F. Campina; Renato R. Rodrigues; Ana L. E. Santos; Felipe M. Pereira; Karla L. R. Batista; Rafael C. Silva; Raquel O. Pereira; Bruno A. M. Rocha; Henrique D. M. Coutinho; Claudener S. Teixeira (Probiotics and Antimicrobial Proteins, 2020)

Deleterious effects of chronic mercury exposure on in vitro LTP, memory process, and oxidative stress - Leandro F. Oliveira; Laís D. Rodrigues; Giancarlo M. Cardillo; Mariana B. Nejm; Marcia Guimarães-Marques; Selvin Z. Reyes-Garcia; Karolini Zuqui; Dalton V. Vassallo; Ana C. Fiorini; Carla A. Scorza; Fulvio A. Scorza (Environmental Science and Pollution Research, 2020)

Phylogenetic analysis revealed that Salmonella Typhimurium ST313 isolated from humans and food in Brazil presented a high genomic similarity - Amanda Ap. Seribelli; Júlia C. Gonzales; Fernanda de Almeida; Leandro Benevides; Marta I. Cazentini Medeiros; Dália dos Prazeres Rodrigues; Siomar de C. Soares; Marc W. Allard; Juliana P. Falcão (Brazilian Journal of Microbiology, 2020)

Metacommunity organization in an intermittent river in Brazil: the importance of riverine networks for regional biodiversity - Carlos A. S. Rodrigues-Filho; Ronaldo C. Gurgel-Lourenço; Eliêta A. Ramos; José L. C. Novaes; Danielle S. Garcez; Rodrigo S. Costa; Jorge I. Sánchez-Botero (Aquatic Ecology, 2020)

Do improved pastures enhance soil quality of cork oak woodlands in the Alentejo region (Portugal)? - A. R. Rodrigues; F. Costa e Silva; A. C. Correia; M. C. Bicho; M. Madeira; J. Coutinho (Agroforestry Systems, 2020)

Hidden in the DNA: How multiple historical processes and natural history traits shaped patterns of cryptic diversity in an Amazon leaf‐litter lizard Loxopholis osvaldoi (Squamata: Gymnophthalmidae) - Sergio Marques-Souza; Katia C. Machado Pellegrino; Tuliana Oliveira Brunes; Ana Carolina Carnaval; Roberta Pacheco Damasceno; Manoela Lima de Oliveira Borges; Carlos Candia Gallardo; Miguel Trefaut Rodrigues (Journal of Biogeography, 2020)
Aim To investigate the cryptic diversity and diversification timing in the putatively low‐dispersal Amazonian leaf‐litter lizard Loxopholis osvaldoi , and to ask how geography (rivers, isolation by distance, IBD), ecological drivers (isolation by environment, IBE) and historical factors (climatic refugia) explain intraspecific genetic variation. Location Central Amazonia, Brazil. Taxon Squamata; Gymnophthalmidae; Loxopholis osvaldoi. Methods We sequenced two mitochondrial and two nuclear markers in 157 individuals. Phylogeographic structure and the occurrence of independent evolving lineages where explored through phylogenetic and coalescent analyses. A species tree and divergence dates of lineages were inferred with *BEAST, employing multiple DNA substitution rates. The potential genetic impacts of geographical distance among localities, the environment and the position of localities in relation to main rivers were tested by redundancy analysis (RDA). Results We detected 11 independently evolving and largely divergent intraspecific lineages. Lineage distribution patterns are complex and do not match any conspicuous barrier to gene flow, except for the Amazon River. Most lineages appear to have originated in the lower Miocene and Pliocene, in disagreement with the Pleistocene refuge hypothesis. IBD, IBE and rivers appear to have acted in concert establishing and maintaining genetic structure. However, when controlling for other explanatory variables, IBD explains significantly more variation than rivers, IBE or historical factors. Main Conclusions Our results strongly suggest that L . osvaldoi is a species complex. Future taxonomic work should use an integrative approach to explore whether morphological variation is present and congruent with the genetic data. While the use of a sensitive dating analysis allowed us to better describe the diversification history of L . osvaldoi , the lack of a spatial model of Neogene river dynamics prevents the test of specific, more informative river barrier hypotheses. The data suggest that nonlinear correlation analyses (e.g. RDA) should be preferred to detect factors that affect phylogeographic patterns in the Amazon, instead of linear multiple regressions (e.g. Mantel tests). Given the high level of cryptic diversity detected within this and other Amazonian species, we caution against hypothesis tests based solely on the distribution of nominal taxa, which can provide a rather incomplete view of the processes behind Amazonian diversity.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

The Fitness and Economic Benefits of Rearing the Parasitoid Telenomus podisi Under Fluctuating Temperature Regime - N L Castellanos; A F Bueno; K Haddi; E C Silveira; H S Rodrigues; E Hirose; G Smagghe; E E Oliveira (Neotropical Entomology, 2019)

Physiological and biochemical responses of soybean to white mold affected by manganese phosphite and fluazinam - M. I. C. Novaes; D. Debona; I. R. F. Fagundes-Nacarath; V. V. Brás; F. A. Rodrigues (Acta Physiologiae Plantarum, 2019)

Effects of ammoniated pearl millet silage on intake, feeding behavior, and blood metabolites in feedlot lambs - Thomaz C. G. de C. Rodrigues; Poliane M. Freitas; Edson M. Santos; Gherman G. L. de Araújo; Aureliano J. V. Pires; Maria C. C. Ayres; Lorendane M. de Carvalho; Jocely G. Souza; Gleidson G. P. de Carvalho (Tropical Animal Health and Production, 2019)

Synthesis, structural characterization, and cytotoxic evaluation of chalcone derivatives - Paulo N. Bandeira; Telma L. G. Lemos; Hélcio S. Santos; Mylena C. S. de Carvalho; Daniel P. Pinheiro; Manoel O. de Moraes Filho; Cláudia Pessoa; Francisco W. A. Barros-Nepomuceno; Tigressa H. S. Rodrigues; Paulo R. V. Ribeiro; Herbert S. Magalhães; Alexandre M. R. Teixeira (Medicinal Chemistry Research, 2019)

Testing main Amazonian rivers as barriers across time and space within widespread taxa - Renata M. Pirani; Fernanda P. Werneck; Andréa T. Thomaz; Mariah L. Kenney; Marcelo J. Sturaro; Teresa C. S. Ávila‐Pires; Pedro L. V. Peloso; Miguel T. Rodrigues; L. Lacey Knowles (Journal of Biogeography, 2019)
Aim Present Amazonian diversity patterns can result from many different mechanisms and, consequently, the factors contributing to divergence across regions and/or taxa may differ. Nevertheless, the river‐barrier hypothesis is still widely invoked as a causal process in divergence of Amazonian species. Here we use model‐based phylogeographic analyses to test the extent to which major Amazonian rivers act similarly as barriers across time and space in two broadly distributed Amazonian taxa. Local Amazon rain forest. Taxon The lizard Gonatodes humeralis (Sphaerodactylidae) and the tree frog Dendropsophus leucophyllatus (Hylidae). Methods We obtained RADseq data for samples distributed across main river barriers, representing main Areas of Endemism previously proposed for the region. We conduct model‐based phylogeographic and genetic differentiation analyses across each population pair. Results Measures of genetic differentiation (based on F ST calculated from genomic data) show that all rivers are associated with significant genetic differentiation. Parameters estimated under investigated divergence models showed that divergence times for populations separated by each of the 11 bordering rivers were all fairly recent. The degree of differentiation consistently varied between taxa and among rivers, which is not an artifact of any corresponding difference in the genetic diversities of the respective taxa, or to amounts of migration based on analyses of the site‐frequency spectrum. Main conclusions Taken together, our results support a dispersal (rather than vicariance) history, without strong evidence of congruence between these species and rivers. However, once a species crossed a river, populations separated by each and every river have remained isolated—in this sense, rivers act similarly as barriers to any further gene flow. This result suggests differing degrees of persistence and gives rise to the seeming contradiction that the divergence process indeed varies across time, space and species, even though major Amazonian rivers have acted as secondary barriers to gene flow in the focal taxa.

Ecological restoration as a strategy for mitigating and adapting to climate change: lessons and challenges from Brazil - Mercedes M. C. Bustamante; José Salomão Silva; Aldicir Scariot; Alexandre Bonesso Sampaio; Daniel Luis Mascia; Edenise Garcia; Edson Sano; Geraldo Wilson Fernandes; Giselda Durigan; Iris Roitman; Isabel Figueiredo; Ricardo Ribeiro Rodrigues; et al. (Mitigation and Adaptation Strategies for Global Change, 2019)

Flavonoids from Plinia cauliflora (Mart.) Kausel (Myrtaceae) with antifungal activity - Tatiana M. Souza-Moreira; Juliana A. Severi; Edvânio Ramos Rodrigues; Mayara Ivani de Paula; Jolindo A. Freitas; Wagner Vilegas; Rosemeire C. L. R. Pietro (Natural Product Research, 2019)

Distribution of Distances Between Symmetric Words in the Human Genome: Analysis of Regular Peaks - Carlos A. C. Bastos; Vera Afreixo; João M. O. S. Rodrigues; Armando J. Pinho; Raquel M. Silva (Interdisciplinary Sciences: Computational Life Sciences, 2019)

Deciphering Fungal Extracellular Vesicles: From Cell Biology to Pathogenesis - Vanessa K. A. Silva; Marcio L. Rodrigues; Robin C. May (Current Clinical Microbiology Reports, 2019)

The Retina as a Window or Mirror of the Brain Changes Detected in Alzheimer’s Disease: Critical Aspects to Unravel - Samuel Chiquita; Ana C. Rodrigues-Neves; Filipa I. Baptista; Rafael Carecho; Paula I. Moreira; Miguel Castelo-Branco; António F. Ambrósio (Molecular Neurobiology, 2019)

Space-time recurrences for functional connectivity evaluation and feature extraction in motor imagery brain-computer interfaces - Paula G. Rodrigues; Carlos A. Stefano Filho; Romis Attux; Gabriela Castellano; Diogo C. Soriano (Medical & Biological Engineering & Computing, 2019)

Generation and validation of genetic markers for the selection of carioca dry bean genotypes with the slow-darkening seed coat trait - Renata C. Alvares; Robert Stonehouse; Thiago L. P. O. Souza; Patrícia G. S. Melo; Phillip N. Miklas; Kirstin E. Bett; Leonardo C. Melo; Luana A. Rodrigues; Lorena L. Souza; Helton S. Pereira (Euphytica, 2019)

Assessing the ecological status of fluvial ecosystems employing a macroinvertebrate multi-taxon and multi-biomarker approach - Carolina Rodrigues; Ana Bio; Laura Guimarães; Virgínia C. Fernandes; Cristina Delerue-Matos; Natividade Vieira (Environmental Monitoring and Assessment, 2019)

Occurrence and Environmental Distribution of 5 UV Filters During the Summer Season in Different Water Bodies - S. K. Fagervold; A. S. Rodrigues; C. Rohée; R. Roe; M. Bourrain; D. Stien; P. Lebaron (Water, Air, & Soil Pollution, 2019)

Involvement of the Cholinergic Parameters and Glial Cells in Learning Delay Induced by Glutaric Acid: Protection by N-Acetylcysteine - Fernanda Silva Rodrigues; Viviane Nogueira de Zorzi; Marla Parizzi Funghetto; Fernanda Haupental; Alexandra Seide Cardoso; Sara Marchesan; Andréia M. Cardoso; Maria Rosa C. Schinger; Alencar Kolinski Machado; Ivana Beatrice Mânica da Cruz; Marta Maria Medeiros Frescura Duarte; Léder L. Xavier; et al. (Molecular Neurobiology, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Seed desiccation tolerance/sensitivity of tree species from Brazilian biodiversity hotspots: considerations for conservation - Rafaella C. Mayrinck; Larissa C. Vilela; Thalita M. Pereira; Ailton G. Rodrigues-Junior; Antonio C. Davide; Tatiana A. A. Vaz (Trees, 2019)

Early Interaction of Alternaria infectoria Conidia with Macrophages - M. C. Almeida; D. Antunes; B. M. A. Silva; L. Rodrigues; M. Mota; O. Borges; C. Fernandes; T. Gonçalves (Mycopathologia, 2019)

Evaluation of the effects of extracts of Maytenus imbricata (Celastraceae) on the treatment of inflammatory and metabolic dysfunction induced by high-refined carbohydrate diet - C. C. Veloso; M. C. Oliveira; V. G. Rodrigues; C. C. Oliveira; L. P. Duarte; M. M. Teixeira; A. V. M. Ferreira; A. C. Perez (Inflammopharmacology, 2019)

ATLANTIC BIRD TRAITS : a data set of bird morphological traits from the Atlantic forests of South America - Rodolpho Credo Rodrigues; Érica Hasui; Julia Camara Assis; João Carlos Castro Pena; Renata L. Muylaert; Vinicius Rodrigues Tonetti; Felipe Martello; André Luis Regolin; Thiago Vernaschi Vieira da Costa; Mauro Pichorim; Eduardo Carrano; Leonardo Esteves Lopes; et al. (Ecology, 2019)
Scientists have long been trying to understand why the Neotropical region holds the highest diversity of birds on Earth. Recently, there has been increased interest in morphological variation between and within species, and in how climate, topography, and anthropogenic pressures may explain and affect phenotypic variation. Because morphological data are not always available for many species at the local or regional scale, we are limited in our understanding of intra‐ and interspecies spatial morphological variation. Here, we present the ATLANTIC BIRD TRAITS , a data set that includes measurements of up to 44 morphological traits in 67,197 bird records from 2,790 populations distributed throughout the Atlantic forests of South America. This data set comprises information, compiled over two centuries (1820–2018), for 711 bird species, which represent 80% of all known bird diversity in the Atlantic Forest. Among the most commonly reported traits are sex ( n = 65,717), age ( n = 63,852), body mass ( n = 58,768), flight molt presence ( n = 44,941), molt presence ( n = 44,847), body molt presence ( n = 44,606), tail length ( n = 43,005), reproductive stage ( n = 42,588), bill length ( n = 37,409), body length ( n = 28,394), right wing length ( n = 21,950), tarsus length ( n = 20,342), and wing length ( n = 18,071). The most frequently recorded species are Chiroxiphia caudata ( n = 1,837), Turdus albicollis ( n = 1,658), Trichothraupis melanops ( n = 1,468), Turdus leucomelas ( n = 1,436), and Basileuterus culicivorus ( n = 1,384). The species recorded in the greatest number of sampling localities are Basileuterus culicivorus ( n = 243), Trichothraupis melanops ( n = 242), Chiroxiphia caudata ( n = 210), Platyrinchus mystaceus ( n = 208), and Turdus rufiventris ( n = 191). ATLANTIC BIRD TRAITS ( ABT ) is the most comprehensive data set on measurements of bird morphological traits found in a biodiversity hotspot; it provides data for basic and applied research at multiple scales, from individual to community, and from the local to the macroecological perspectives. No copyright or proprietary restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications or teaching and educational activities.

Multidisciplinary Scientific Cruise to the Rio Grande Rise - Luigi Jovane; James R. Hein; Isobel A. Yeo; Mariana Benites; Natascha M. Bergo; Paulo V. F. Corrêa; Daniel M. Couto; Ayrton D. Guimarães; Sarah A. Howarth; Henrique R. Miguel; Kira L. Mizell; Denise S. Moura; et al. (Frontiers in Marine Science, 2019)

The Tropical Atlantic Observing System - G. R. Foltz; P. Brandt; I. Richter; B. Rodríguez-Fonseca; F. Hernandez; M. Dengler; R. R. Rodrigues; J. O. Schmidt; L. Yu; N. Lefevre; L. Cotrim Da Cunha; M. J. McPhaden; et al. (Frontiers in Marine Science, 2019)
The tropical Atlantic is home to multiple coupled climate variations covering a wide range of timescales and impacting societally relevant phenomena such as continental rainfall, Atlantic hurricane activity, oceanic biological productivity, and atmospheric circulation in the equatorial Pacific. The tropical Atlantic also connects the southern and northern branches of the Atlantic meridional overturning circulation and receives freshwater input from some of the world’s largest rivers. To address these diverse, unique, and interconnected research challenges, a rich network of ocean observations has developed, building on the backbone of the Prediction and Research Moored Array in the Tropical Atlantic (PIRATA). This network has evolved naturally over time and out of necessity in order to address the most important outstanding scientific questions and to improve predictions of tropical Atlantic severe weather and global climate variability and change. The tropical Atlantic observing system is motivated by goals to understand and better predict phenomena such as tropical Atlantic interannual to decadal variability and climate change; multidecadal variability and its links to the meridional overturning circulation; air-sea fluxes of CO 2 and their implications for the fate of anthropogenic CO 2 ; the Amazon River plume and its interactions with biogeochemistry, vertical mixing, and hurricanes; the highly productive eastern boundary and equatorial upwelling systems; and oceanic oxygen minimum zones, their impacts on biogeochemical cycles and marine ecosystems, and their feedbacks to climate. Past success of the tropical Atlantic observing system is the result of an international commitment to sustained observations and scientific cooperation, a willingness to evolve with changing research and monitoring needs, and a desire to share data openly with the scientific community and operational centers. The observing system must continue to evolve in order to meet an expanding set of research priorities and operational challenges. This paper discusses the tropical Atlantic observing system, including emerging scientific questions that demand sustained ocean observations, the potential for further integration of the observing system, and the requirements for sustaining and enhancing the tropical Atlantic observing system.

Histopathological effects in gills and liver of Sparus aurata following acute and chronic exposures to erythromycin and oxytetracycline - Sara Rodrigues; Sara C. Antunes; Bruno Nunes; Alberto Teodorico Correia (Environmental Science and Pollution Research, 2019)

Geostatistical stationary space-time covariance functions modeling of Yellow Sigatoka progress in banana crop - J. D. P. Rodrigues; M. C. Alves; A. S. Freitas; E. A. Pozza; M. S. Oliveira; H. J. P. Alves (Australasian Plant Pathology, 2019)

Control of Non-migrating Bar Morphodynamics on Survival of Populus nigra Seedlings during Floods - C. L. Wintenberger; S. Rodrigues; S. Greulich; J. G. Bréhéret; P. Jugé; M. Tal; A. Dubois; M. Villar (Wetlands, 2019)

Pyrene degradation by marine-derived ascomycete: process optimization, toxicity, and metabolic analyses - Maria R. S. Vasconcelos; Gabriela A. L. Vieira; Igor V. R. Otero; Rafaella C. Bonugli-Santos; Marili V. N. Rodrigues; Vera L. G. Rehder; Milene Ferro; Sinésio Boaventura; Maurício Bacci; Lara D. Sette (Environmental Science and Pollution Research, 2019)

Isolation by instability: Historical climate change shapes population structure and genomic divergence of treefrogs in the Neotropical Cerrado savanna - Mariana M. Vasconcellos; Guarino R. Colli; Jesse N. Weber; Edgardo M. Ortiz; Miguel T. Rodrigues; David C. Cannatella (Molecular Ecology, 2019)
Although the impact of Pleistocene glacial cycles on the diversification of the tropical biota was once dismissed, increasing evidence suggests that Pleistocene climatic fluctuations greatly affected the distribution and population divergence of tropical organisms. Landscape genomic analyses coupled with paleoclimatic distribution models provide a powerful way to understand the consequences of past climate changes on the present‐day tropical biota. Using genome‐wide SNP data and mitochondrial DNA, combined with projections of the species distribution across the late Quaternary until the present, we evaluate the effect of paleoclimatic shifts on the genetic structure and population differentiation of Hypsiboas lundii , a treefrog endemic to the South American Cerrado savanna. Our results show a recent and strong genetic divergence in H. lundii across the Cerrado landscape, yielding four genetic clusters that do not seem congruent with any current physical barrier to gene flow. Isolation by distance (IBD) explains some of the population differentiation, but we also find strong support for past climate changes promoting range shifts and structuring populations even in the presence of IBD. Post‐Pleistocene population persistence in four main areas of historical stable climate in the Cerrado seems to have played a major role establishing the present genetic structure of this treefrog. This pattern is consistent with a model of reduced gene flow in areas with high climatic instability promoting isolation of populations, defined here as “isolation by instability,” highlighting the effects of Pleistocene climatic fluctuations structuring populations in tropical savannas.

Allochthonous versus autochthonous organic matter sustaining macroconsumers in a subtropical sandy beach revealed by stable isotopes - A. M. Garcia; M. C. L. M. Oliveira; C. Odebrecht; J. L. A. Colling; J. P. Vieira; F. L. Rodrigues; R. F. Bastos (Marine Biology Research, 2019)

Correction to: Occurrence of anti-Leptospira spp. antibodies in Rhipidomys spp. from a forest fragment of the Brazilian Cerrado - D. O. Gomes; G. B. Ramos; V. B. A. Alves; A. Z. Ciuffa; L. P. Cuccato; T. F. M. dos Reis; A. M. C. Lima; M. G. Coelho; G. V. Tolesano-Pascoli; V. S. Rodrigues; M. P. J. Szabó; V. N. Ramos (Tropical Animal Health and Production, 2019)

Effect of temperature on the thermal conductivity of a granite with high heat production from Central Portugal - M. M. Miranda; C. R. Matos; N. V. Rodrigues; A. J. S. C. Pereira; J. J. Costa (Journal of Iberian Geology, 2019)

Glyphosate detection: methods, needs and challenges - A. L. Valle; F. C. C. Mello; R. P. Alves-Balvedi; L. P. Rodrigues; L. R. Goulart (Environmental Chemistry Letters, 2019)

Eucalyptus rust climatic risk as affected by topography and ENSO phenomenon - R. S. Nóia Júnior; F. Schwerz; J. L. Safanelli; J. C. Rodrigues; P. C. Sentelhas (Australasian Plant Pathology, 2019)

Molecular phylogeny and hemipenial diversity of South American species of Amerotyphlops (Typhlopidae, Scolecophidia) - Roberta Graboski; Juan C. Arredondo; Felipe G. Grazziotin; Ariane A. A. da Silva; Ana L. C. Prudente; Miguel T. Rodrigues; Sandro L. Bonatto; Hussam Zaher (Zoologica Scripta, 2019)
Typhlopidae is the most diverse family of Scolecophidia, with 269 species. Amerotyphlops was recently erected within subfamily Typhlopinae and comprises fifteen species distributed from Mexico to Argentina and the southern Lesser Antilles. Despite recent advances, affinities among typhlopines remain poorly explored, and the phylogenetic relationships and morphology of the South American (SA) species were never accessed before. Here, we performed a phylogenetic analysis including 106 species of Typhlopidae and ten genes. Our dataset represents the most comprehensive for SA species, containing seven of eight recognized species. Corroborating previous studies, we recovered the main groups of Typhlopoidea, and for typhlopines, we recovered with strong support two clades: (a) the Greater Antilles radiation, and the (b) Lesser Antilles and SA radiation. Within the SA radiation, we recovered four main lineages: (a) a clade formed by A. tasymicris and A. minuisquamus ; (b) a clade composed by A. reticulatus as the sister group of all other SA species; (c) a clade composed by A. brongersmianus as the sister group of a clade comprising all Northeast Brazilian Species (NBS); and (d) a clade of the NBS, including A. yonenagae , A. arenensis , A. paucisquamus, and A. amoipira . We supplemented our phylogenetic result with the description of hemipenial morphology for seven SA species and comment their relevance to the systematics of Typhlopinae. Hemipenes of SA Amerotyphlops follow the general pattern in scolecophidians (single organ with undivided sulcus). Only A. reticulatus and A. minuisquamus have organs with calcified spines. According to our results, hemipenial ornamentation have shown highly informative and could represent a potential source of systematic and taxonomic characters in that group. We also present an extensive review of the geographical distribution for all SA species. Our study represents the first integrative analysis of a poorly known evolutionary radiation of one of the most widespread SA fossorial snakes.

Pleistocene alkaline rocks of Martin Vaz volcano, South Atlantic: low-degree partial melts of a CO 2 -metasomatized mantle plume - Anderson C. Santos; Mauro C. Geraldes; Wolfgang Siebel; Julio Mendes; Everton Bongiolo; Werlem H Santos; Thais C. V. Garrido; Sergio W. O. Rodrigues (International Geology Review, 2019)

Regulation of cell wall development in Brachypodium distachyon in vitro as affected by cytokinin and gas exchange - T. C. Mamedes-Rodrigues; D. S. Batista; T. A. Napoleão; E. A. Fortini; A. C. F. Cruz; M. G. C. Costa; W. C. Otoni (Plant Cell, Tissue and Organ Culture (PCTOC), 2019)

Dopaminergic Lesion in the Olfactory Bulb Restores Olfaction and Induces Depressive-Like Behaviors in a 6-OHDA Model of Parkinson’s Disease - Jessica L. Ilkiw; Luana C. Kmita; Adriano D. S. Targa; Ana Carolina D. Noseda; Lais S. Rodrigues; Flávia W. C. Dorieux; Juliane Fagotti; Patrícia dos Santos; Marcelo M. S. Lima (Molecular Neurobiology, 2019)

Toxicity of erythromycin to Oncorhynchus mykiss at different biochemical levels: detoxification metabolism, energetic balance, and neurological impairment - Sara Rodrigues; Sara C. Antunes; Alberto T. Correia; Bruno Nunes (Environmental Science and Pollution Research, 2019)

Crispoic acid, a new compound from Laelia marginata (Orchidaceae), and biological evaluations against parasites, human cancer cell lines and Zika virus - Andrezza C. Belloto; Gredson K. Souza; Paula C. Perin; Ivania T. A. Schuquel; Silvana M. O. Santin; Lucas U. R. Chiavelli; Francielle P. Garcia; Vanessa Kaplum; Jean H. S. Rodrigues; Débora B. Scariot; Rodrigo Delvecchio; Erik Machado-Ferreira; et al. (Natural Product Research, 2018)

Risk Assessment of the Drinking Water Samples in the Rural Area from MG, Brazil - Mayra S. Santos; Maria C. R. M. Metzker; Guilherme L. Rodrigues; Luis R. S. Corrêa; Mayne L. V. Silva; Ana L. G. Barbosa; Márcia C. S. Faria; Jairo L. Rodrigues (International Journal of Environmental Research, 2018)

Soluble Compounds of Filamentous Fungi Harm the Symbiotic Fungus of Leafcutter Ants - Rodolfo Bizarria; Isabela C. Moia; Quimi V. Montoya; Danilo A. Polezel; Andre Rodrigues (Current Microbiology, 2018)

Current advances in gibberellic acid (GA3) production, patented technologies and potential applications - Marcela C. Camara; Luciana P. S. Vandenberghe; Cristine Rodrigues; Juliana de Oliveira; Craig Faulds; Emmanuel Bertrand; Carlos R. Soccol (Planta, 2018)

Phylogeography of Muller's termite frog suggests the vicariant role of the Central Brazilian Plateau - Eliana F. Oliveira; Marcelo Gehara; Vinícius A. São‐Pedro; Gabriel C. Costa; Frank T. Burbrink; Guarino R. Colli; Miguel T. Rodrigues; Adrian A. Garda (Journal of Biogeography, 2018)
Aim To test three different scenarios to account for the geographic distribution of genetic variation in Dermatonotus muelleri , a fossorial frog endemic of the South American diagonal of open formations ( DOF ) formed by Chaco, Cerrado, and Caatinga biomes: (a) The pan‐ DOF hypothesis, where these biomes behave as a single biogeographical unit and DOF species lack population structure; (b) the southwest‐northeast ( SW ‐ NE ) hypothesis, where structured populations along the DOF have either asymmetric or unidirectional gene flow in the northeast direction; (c) the vicariance hypothesis, where a pattern of population structure with no or reduced gene flow is observed. Location Caatinga, Cerrado, and Chaco in South America. Methods We sampled 179 individuals across the species distribution and sequenced one mitochondrial and two nuclear markers. We evaluated population structure, the presence, direction, and asymmetry of gene flow, and demographic changes to test three different phylogeographic hypotheses for D. muelleri using a model‐based simulation approach. Results We found two geographically structured lineages with no gene flow, refuting pan‐ DOF hypothesis. The Southwest lineage occurs in Chaco and western Cerrado and the Northeast lineage in eastern Cerrado and Caatinga. Our results support the model with demographic change for the Northeast lineage and constant size for Southwest lineage. The vicariance model with divergence time estimated around 4 Ma was preferred. Main conclusions Vicariance was the best explanation for the geographic distribution of genetic variation in Dermatonotus . Divergence time supports the role of Neogene orogeny in central Brazil for the splitting of Dermatonotus lineages. The influence of Pleistocene climatic fluctuations seems restricted to changes in one lineage's population size. Therefore, both ancient and recent events shaped the phylogeography of Dermatonotus . Genetic divergence, lack of gene flow, and the presence of a geographic barrier between lineages indicate the existence of a cryptic, undescribed species in northeastern Brazil.

Pan‐tropical prediction of forest structure from the largest trees - Jean‐François Bastin; Ervan Rutishauser; James R. Kellner; Sassan Saatchi; Raphael Pélissier; Bruno Hérault; Ferry Slik; Jan Bogaert; Charles De Cannière; Andrew R. Marshall; John Poulsen; Patricia Alvarez‐Loyayza; et al. (Global Ecology and Biogeography, 2018)
Aim Large tropical trees form the interface between ground and airborne observations, offering a unique opportunity to capture forest properties remotely and to investigate their variations on broad scales. However, despite rapid development of metrics to characterize the forest canopy from remotely sensed data, a gap remains between aerial and field inventories. To close this gap, we propose a new pan‐tropical model to predict plot‐level forest structure properties and biomass from only the largest trees. Location Pan‐tropical. Time period Early 21st century. Major taxa studied Woody plants. Methods Using a dataset of 867 plots distributed among 118 sites across the tropics, we tested the prediction of the quadratic mean diameter, basal area, Lorey's height, community wood density and aboveground biomass (AGB) from the i th largest trees. Results Measuring the largest trees in tropical forests enables unbiased predictions of plot‐ and site‐level forest structure. The 20 largest trees per hectare predicted quadratic mean diameter, basal area, Lorey's height, community wood density and AGB with 12, 16, 4, 4 and 17.7% of relative error, respectively. Most of the remaining error in biomass prediction is driven by differences in the proportion of total biomass held in medium‐sized trees (50–70 cm diameter at breast height), which shows some continental dependency, with American tropical forests presenting the highest proportion of total biomass in these intermediate‐diameter classes relative to other continents. Main conclusions Our approach provides new information on tropical forest structure and can be used to generate accurate field estimates of tropical forest carbon stocks to support the calibration and validation of current and forthcoming space missions. It will reduce the cost of field inventories and contribute to scientific understanding of tropical forest ecosystems and response to climate change.

BRAZIL ROAD‐KILL: a data set of wildlife terrestrial vertebrate road‐kills - Clara Grilo; Michely R. Coimbra; Rafaela C. Cerqueira; Priscilla Barbosa; Rubem A. P. Dornas; Larissa O. Gonçalves; Fernanda Z. Teixeira; Igor Pfeifer Coelho; Brenda R. Schmidt; Diana L. K. Pacheco; Gabriela Schuck; Isadora B. Esperando; et al. (Ecology, 2018)
Mortality from collision with vehicles is the most visible impact of road traffic on wildlife. Mortality due to roads (hereafter road‐kill) can affect the dynamic of populations of many species and can, therefore, increase the risk of local decline or extinction. This is especially true in Brazil, where plans for road network upgrading and expansion overlaps biodiversity hotspot areas, which are of high importance for global conservation. Researchers, conservationists and road planners face the challenge to define a national strategy for road mitigation and wildlife conservation. The main goal of this dataset is a compilation of geo‐referenced road‐kill data from published and unpublished road surveys. This is the first Data Paper in the BRAZIL series (see ATLANTIC , NEOTROPICAL , and BRAZIL collections of Data Papers published in Ecology ), which aims make public road‐kill data for species in the Brazilian Regions. The dataset encompasses road‐kill records from 45 personal communications and 26 studies published in peer‐reviewed journals, theses and reports. The road‐kill dataset comprises 21,512 records, 83% of which are identified to the species level (n = 450 species). The dataset includes records of 31 amphibian species, 90 reptile species, 229 bird species, and 99 mammal species. One species is classified as Endangered, eight as Vulnerable and twelve as Near Threatened. The species with the highest number of records are: Didelphis albiventris (n = 1,549), Volatinia jacarina (n = 1,238), Cerdocyon thous (n = 1,135), Helicops infrataeniatus (n = 802), and Rhinella icterica (n = 692). Most of the records came from southern Brazil. However, observations of the road‐kill incidence for non‐Least Concern species are more spread across the country. This dataset can be used to identify which taxa seems to be vulnerable to traffic, analyze temporal and spatial patterns of road‐kill at local, regional and national scales and also used to understand the effects of road‐kill on population persistence. It may also contribute to studies that aims to understand the influence of landscape and environmental influences on road‐kills, improve our knowledge on road‐related strategies on biodiversity conservation and be used as complementary information on large‐scale and macroecological studies. No copyright or proprietary restrictions are associated with the use of this data set other than citation of this Data Paper.

Increasing levels of supplementation for crossbred steers on pasture during the dry period of the year - Daniele Soares Barroso Neves; Robério Rodrigues Silva; Fabiano Ferreira da Silva; Laize Vieira Santos; George Abreu Filho; Sinvaldo Oliveira de Souza; Marceliana da C. Santos; Weder Jansen Rocha; Ana Paula Gomes da Silva; Mateus de Melo Lisboa; Maria Magna Silva Pereira; Venício Macedo Carvalho (Tropical Animal Health and Production, 2018)

In Vivo Determination of Moisturizers Efficacy on Human Skin Hydration by Confocal Raman Spectroscopy - Vamshi Krishna Tippavajhala; Taciana D. Magrini; Daniele C. Matsuo; Michely G. P. Silva; Priscila P. Favero; Leonardo Rodrigues De Paula; Airton Abrahão Martin (AAPS PharmSciTech, 2018)

Front Cover - Pietro Kiyoshi Maruyama; Jesper Sonne; Jeferson Vizentin‐Bugoni; Ana M. Martín González; Thais B. Zanata; Stefan Abrahamczyk; Ruben Alarcón; Andréa C. Araujo; Francielle P. Araújo; Andrea C. Baquero; Edgar Chávez‐González; Aline G. Coelho; et al. (Global Ecology and Biogeography, 2018)

Functional diversity mediates macroecological variation in plant–hummingbird interaction networks - Pietro Kiyoshi Maruyama; Jesper Sonne; Jeferson Vizentin‐Bugoni; Ana M. Martín González; Thais B. Zanata; Stefan Abrahamczyk; Ruben Alarcón; Andréa C. Araujo; Francielle P. Araújo; Andrea C. Baquero; Edgar Chávez‐González; Aline G. Coelho; et al. (Global Ecology and Biogeography, 2018)
Aim Species interaction networks are known to vary in structure over large spatial scales. We investigated the hypothesis that environmental factors affect interaction network structure by influencing the functional diversity of ecological communities. Notably, we expect more functionally diverse communities to form interaction networks with a higher degree of niche partitioning. Location: Americas. Time period: Current. Major taxa studied: Hummingbirds and their nectar plants. Methods We used a large dataset comprising 74 quantitative plant–hummingbird interaction networks distributed across the Americas, along with morphological trait data for 158 hummingbird species. First, we used a model selection approach to evaluate associations between the environment (climate, topography and insularity), species richness and hummingbird functional diversity as predictors of network structure (niche partitioning, i.e., complementary specialization and modularity). Second, we used structural equation models (SEMs) to ask whether environmental predictors and species richness affect network structure directly and/or indirectly through their influence on hummingbird functional diversity. For a subset of 28 networks, we additionally evaluated whether plant functional diversity was associated with hummingbird functional diversity and network structure. Results Precipitation, insularity and plant richness, together with hummingbird functional diversity (specifically, functional dispersion), were consistently strong predictors of niche partitioning in plant–hummingbird networks. Moreover, SEMs showed that environmental predictors and plant richness affected network structure both directly and indirectly through their effects on hummingbird functional diversity. Plant functional diversity, however, was unrelated to hummingbird functional diversity and network structure. Main conclusions: We reveal the importance of hummingbird functional diversity for niche partitioning in plant–hummingbird interaction networks. The lack of support for similar effects for plant functional diversity potentially indicates that consumer functional diversity might be more important for structuring interaction networks than resource functional diversity. Changes in pollinator functional diversity are therefore likely to alter the structure of interaction networks and associated ecosystem functions.

Gaseous and liquid effluents treatment in bubble column reactors by advanced oxidation processes: A review - Vanessa N. Lima; Carmen S. D. Rodrigues; Ricardo A. C. Borges; Luis M. Madeira (Critical Reviews in Environmental Science and Technology, 2018)

The Híbrido de Timor germplasm: identification of molecular diversity and resistance sources to coffee berry disease and leaf rust - R. A. Silva; L. Zambolim; I. S. L. Castro; H. S. Rodrigues; C. D. Cruz; E. T. Caixeta (Euphytica, 2018)

Combined effects of insecticide exposure and predation risk on freshwater detritivores - Andreia C. M. Rodrigues; Maria D. Bordalo; Oksana Golovko; Olga Koba; Carlos Barata; Amadeu M. V. M. Soares; João L. T. Pestana (Ecotoxicology, 2018)

Time-shifting effects of methylphenidate on daily rhythms in the diurnal rodent Arvicanthis ansorgei - Jorge Mendoza; Hester C. van Diepen; Rob Rodrigues Pereira; Johanna H. Meijer (Psychopharmacology, 2018)

Mitochondrial genome analysis in penile carcinoma - L. F. Araujo; A. T. Terra; C. T. G. Sares; C. F. R. Sobreira; E. F. Faria; R. D. Machado; A. A. Rodrigues; V. F. Muglia; W. A. Silva; R. B. Reis (Molecular Biology Reports, 2018)

Targeting the mitochondrial VDAC in hepatocellular carcinoma using a polyclonal antibody-conjugated to a nitrosyl ruthenium complex - Loyanne C. B. Ramos; Fernando P. Rodrigues; Juliana C. Biazzotto; Sergio de Paula Machado; Leonardo D. Slep; Michael R. Hamblin; Roberto S. da Silva (JBIC Journal of Biological Inorganic Chemistry, 2018)

Validation of a robust LLE-GC-MS method for determination of trihalomethanes in environmental samples - Elton S. Franco; Válter L. Pádua; Alessandra Giani; Mariandry Rodríguez; Diego F. Silva; Ana F. A. Ferreira; Israel C. S. Júnior; Márcio C. Pereira; Jairo L. Rodrigues (Environmental Monitoring and Assessment, 2018)

Global Island Monitoring Scheme (GIMS): a proposal for the long-term coordinated survey and monitoring of native island forest biota - Paulo A. V. Borges; Pedro Cardoso; Holger Kreft; Robert J. Whittaker; Simone Fattorini; Brent C. Emerson; Artur Gil; Rosemary G. Gillespie; Thomas J. Matthews; Ana M. C. Santos; Manuel J. Steinbauer; Christophe Thébaud; et al. (Biodiversity and Conservation, 2018)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

P2X7 receptor and klotho expressions in diabetic nephropathy progression - A. M. Rodrigues; R. S. Serralha; C. Farias; G. R. Punaro; M. J. S. Fernandes; Elisa Mieko Suemitsu Higa (Purinergic Signalling, 2018)

Correction to: Organic phosphorus in the terrestrial environment: a perspective on the state of the art and future priorities - T. S. George; C. D. Giles; D. Menezes-Blackburn; L. M. Condron; A. C. Gama-Rodrigues; D. Jaisi; F. Lang; A. L. Neal; M. I. Stutter; D. S. Almeida; R. Bol; K. G. Cabugao; et al. (Plant and Soil, 2018)

Organic phosphorus in the terrestrial environment: a perspective on the state of the art and future priorities - T. S. George; C. D. Giles; D. Menezes-Blackburn; L. M. Condron; A. C. Gama-Rodrigues; D. Jaisi; F. Lang; A. L. Neal; M. I. Stutter; D. S. Almeida; R. Bol; K. G. Cabugao; et al. (Plant and Soil, 2018)

The Inventory of Geological Heritage of the State of São Paulo, Brazil: Methodological Basis, Results and Perspectives - Maria da Glória Motta Garcia; José Brilha; Flávia Fernanda de Lima; Jean Carlos Vargas; Annabel Pérez-Aguilar; Adriana Alves; Ginaldo Ademar da Cruz Campanha; Wânia Duleba; Frederico Meira Faleiros; Luiz Alberto Fernandes; Marisa de Souto Matos Fierz; Maria Judite Garcia; et al. (Geoheritage, 2018)

Vulnerability associated with “symptoms similar to those of mercury poisoning” in communities from Xingu River, Amazon basin - Flávio Mnaoel Rodrigues Da Silva-Junior; Ritta M. Oleinski; Antonia E. S. Azevedo; Kátia C. M. C. Monroe; Marina Dos Santos; Tatiane Britto Da Silveira; Adrianne Maria Netto De Oliveira; Maria Cristina Flores Soares; Tatiana Da Silva Pereira (Environmental Geochemistry and Health, 2018)

Detection of the antiviral activity of epicatechin isolated from Salacia crassifolia (Celastraceae) against Mayaro virus based on protein C homology modelling and virtual screening - P. G. Ferreira; A. C. Ferraz; J. E. Figueiredo; C. F. Lima; V. G. Rodrigues; A. G. Taranto; J. M. S. Ferreira; G. C. Brandão; S. A. Vieira-Filho; L. P. Duarte; C. L. de Brito Magalhães; J. C. de Magalhães (Archives of Virology, 2018)

Treatment with pentylenetetrazole (PTZ) and 4-aminopyridine (4-AP) differently affects survival, locomotor activity, and biochemical markers in Drosophila melanogaster - Deividi C. S. Soares; José L. R. Portela; Daniel H. Roos; Nathane R. Rodrigues; Karen K. Gomes; Giulianna E. Macedo; Thais Posser; Jeferson L. Franco; Waseem Hassan; Robson L. Puntel (Molecular and Cellular Biochemistry, 2018)

Purification of arsenic-contaminated water with K-jarosite filters - Rodrigo C. Hott; Luiz F. O. Maia; Mayra S. Santos; Márcia C. Faria; Luiz C. A. Oliveira; Márcio C. Pereira; Cleide A. Bomfeti; Jairo L. Rodrigues (Environmental Science and Pollution Research, 2018)

Transgenerational Effects of Toxicants: An Extension of the Daphnia 21-day Chronic Assay? - B. B. Castro; A. R. Freches; M. Rodrigues; B. Nunes; S. C. Antunes (Archives of Environmental Contamination and Toxicology, 2018)

Lignin and cellulose synthesis and antioxidative defense mechanisms are affected by light quality in Brachypodium distachyon - T. C. Mamedes-Rodrigues; D. S. Batista; T. A. Napoleão; A. C. F. Cruz; E. A. Fortini; F. T. S. Nogueira; E. Romanel; W. C. Otoni (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)

Sexual reproduction in the invasive bryozoan Amathia verticillata (Ctenostomatida: Vesiculariidae) - J. Micael; A. Gillon; N. Jardim; Pedro Rodrigues; A. C. Costa (Journal of Coastal Conservation, 2018)

Embryonic and larval development and fatty‐acid profile of Epinephelus marginatus spawned in captivity: tools applied to captive rearing - P. H. Mello; B. C. Araújo; M. F. Campos; J. A. Rodrigues‐Filho; C. E. O. Garcia; R. G. Moreira (Journal of Fish Biology, 2018)
Development, ontogeny of the digestive system and the fatty‐acid (FA) profile, were analysed during development of Epinephelus marginatus . Larvae were analysed 7 and 17 days post fertilization (dpf) to evaluate fatty‐acid profile and morphological variables, respectively. Epinephelus marginatus larvae have relatively slow development of digestive structures, but were able to capture, ingest and digest prey by 5 dpf. Eggs were composed of high percentages of polyunsaturated fatty acids (PUFA) in phospholipids. The percentage of n3 PUFAs was higher than n6, especially docosahexaenoic acid (DHA), which exhibited higher levels compared with other marine species during the first 3 days of development, both in terms of phospholipids and triglycerides. The larvae present a high content of docosahexaenoic acid–eicosapentaenoic acid (DHA–EPA) and, during this phase, live food of small size was required (copepods or SS‐strain Brachionus rotundiformes ), enriched with DHA–EPA. These results may guide future studies on the contribution of FAs required during this stage of the life cycle of E. marginatus , to advance knowledge of the use of these FAs throughout ontogeny and contribute to the culture of this species commercial production or restocking.

Regenerative potential, metabolic profile, and genetic stability of Brachypodium distachyon embryogenic calli as affected by successive subcultures - T. C. Mamedes-Rodrigues; D. S. Batista; N. M. Vieira; E. M. Matos; D. Fernandes; A. Nunes-Nesi; C. D. Cruz; L. F. Viccini; F. T. S. Nogueira; W. C. Otoni (Protoplasma, 2018)

Area-wide spatial survey of the likelihood of insecticide control failure in the neotropical brown stink bug Euschistus heros - Edmar S. Tuelher; Éder H. da Silva; Hígor S. Rodrigues; Edson Hirose; Raul Narciso C. Guedes; Eugênio E. Oliveira (Journal of Pest Science, 2018)

Seismic assessment of a heavy-timber frame structure with ring-doweled moment-resisting connections - Leonardo G. Rodrigues; Jorge M. Branco; Luís A. C. Neves; André R. Barbosa (Bulletin of Earthquake Engineering, 2018)

Tingenone, a pentacyclic triterpene, induces peripheral antinociception due to cannabinoid receptors activation in mice - C. C. Veloso; R. C. M. Ferreira; V. G. Rodrigues; L. P. Duarte; A. Klein; I. D. Duarte; T. R. L. Romero; A. C. Perez (Inflammopharmacology, 2018)

ATLANTIC BIRDS : a data set of bird species from the Brazilian Atlantic Forest - Érica Hasui; Jean Paul Metzger; Rafael G. Pimentel; Luís Fábio Silveira; Alex A. d. A. Bovo; Alexandre C. Martensen; Alexandre Uezu; André L. Regolin; Arthur Â. Bispo de Oliveira; Cassiano A. F. R. Gatto; Charles Duca; Christian B. Andretti; et al. (Ecology, 2018)
South America holds 30% of the world's avifauna, with the Atlantic Forest representing one of the richest regions of the Neotropics. Here we have compiled a data set on Brazilian Atlantic Forest bird occurrence (150,423) and abundance samples ( N = 832 bird species; 33,119 bird individuals) using multiple methods, including qualitative surveys, mist nets, point counts, and line transects). We used four main sources of data: museum collections, on‐line databases, literature sources, and unpublished reports. The data set comprises 4,122 localities and data from 1815 to 2017. Most studies were conducted in the Florestas de Interior (1,510 localities) and Serra do Mar (1,280 localities) biogeographic sub‐regions. Considering the three main quantitative methods (mist net, point count, and line transect), we compiled abundance data for 745 species in 576 communities. In the data set, the most frequent species were Basileuterus culicivorus , Cyclaris gujanensis , and Conophaga lineata . There were 71 singletons, such as Lipaugus conditus and Calyptura cristata . We suggest that this small number of records reinforces the critical situation of these taxa in the Atlantic Forest. The information provided in this data set can be used for macroecological studies and to foster conservation strategies in this biodiversity hotspot. No copyright restrictions are associated with the data set. Please cite this Data Paper if data are used in publications and teaching events.

A first glance into the nutritional properties of the sea cucumber Parastichopus regalis from the Mediterranean Sea (SE Spain) - Christina C Roggatz; Mercedes González-Wangüemert; Hugo Pereira; Catarina Vizetto-Duarte; Maria João Rodrigues; Luísa Barreira; Manuela Moreira da Silva; João Varela; Luísa Custódio (Natural Product Research, 2018)

Mining noise affects loud call structures and emission patterns of wild black-fronted titi monkeys - M. H. L. Duarte; M. C. Kaizer; R. J. Young; M. Rodrigues; R. S. Sousa-Lima (Primates, 2018)

Commuter exposure to black carbon particles on diesel buses, on bicycles and on foot: a case study in a Brazilian city - Admir Créso Targino; Marcos Vinicius C. Rodrigues; Patricia Krecl; Yago Alonso Cipoli; João Paulo M. Ribeiro (Environmental Science and Pollution Research, 2018)

The invisibility of fisheries in the process of hydropower development across the Amazon - Carolina Rodrigues da Costa Doria; Simone Athayde; Elineide E. Marques; Maria Alice Leite Lima; Jynessa Dutka-Gianelli; Mauro Luis Ruffino; David Kaplan; Carlos E. C. Freitas; Victoria N. Isaac (Ambio, 2017)

In situ germination of two tropical recalcitrant seeds and changes in activity of ROS-scavenging enzymes - Elizabeth R. Marques; Tatiana A. A. Vaz; Ailton G. Rodrigues-Junior; Antonio C. Davide; Anderson C. José (Trees, 2017)

Organosulfur compound protects against memory decline induced by scopolamine through modulation of oxidative stress and Na+/K+ ATPase activity in mice - Fernanda D. da Silva; Mikaela P. Pinz; Renata L. de Oliveira; Karline C. Rodrigues; Francine R. Ianiski; Mariana M. Bassaco; Claudio C. Silveira; Cristiano R. Jesse; Silvane S. Roman; Ethel A. Wilhelm; Cristiane Luchese (Metabolic Brain Disease, 2017)

Biogeography of mutualistic fungi cultivated by leafcutter ants - Ulrich G. Mueller; Heather D. Ishak; Sofia M. Bruschi; Chad C. Smith; Jacob J. Herman; Scott E. Solomon; Alexander S. Mikheyev; Christian Rabeling; Jarrod J. Scott; Michael Cooper; Andre Rodrigues; Adriana Ortiz; et al. (Molecular Ecology, 2017)
Leafcutter ants propagate co‐evolving fungi for food. The nearly 50 species of leafcutter ants ( Atta , Acromyrmex ) range from Argentina to the United States, with the greatest species diversity in southern South America. We elucidate the biogeography of fungi cultivated by leafcutter ants using DNA sequence and microsatellite‐marker analyses of 474 cultivars collected across the leafcutter range. Fungal cultivars belong to two clades (Clade‐A and Clade‐B). The dominant and widespread Clade‐A cultivars form three genotype clusters, with their relative prevalence corresponding to southern South America, northern South America, Central and North America. Admixture between Clade‐A populations supports genetic exchange within a single species, Leucocoprinus gongylophorus . Some leafcutter species that cut grass as fungicultural substrate are specialized to cultivate Clade‐B fungi, whereas leafcutters preferring dicot plants appear specialized on Clade‐A fungi. Cultivar sharing between sympatric leafcutter species occurs frequently such that cultivars of Atta are not distinct from those of Acromyrmex . Leafcutters specialized on Clade‐B fungi occur only in South America. Diversity of Clade‐A fungi is greatest in South America, but minimal in Central and North America. Maximum cultivar diversity in South America is predicted by the Kusnezov–Fowler hypothesis that leafcutter ants originated in subtropical South America and only dicot‐specialized leafcutter ants migrated out of South America, but the cultivar diversity becomes also compatible with a recently proposed hypothesis of a Central American origin by postulating that leafcutter ants acquired novel cultivars many times from other nonleafcutter fungus‐growing ants during their migrations from Central America across South America. We evaluate these biogeographic hypotheses in the light of estimated dates for the origins of leafcutter ants and their cultivars.

Molecular phylogenetic diversity in the widespread lizard Cercosaura ocellata (Reptilia: Gymnophthalmidae) in South America - Marcelo José Sturaro; Teresa C. S. Avila-Pires; Miguel T. Rodrigues (Systematics and Biodiversity, 2017)

Spittlebugs (Hemiptera: Cercopidae) and their host plants: a strategy for pasture diversification - R. Alvarenga; Alexander M. Auad; Jair C. Moraes; Sandra E. B. Silva; Brunno S. Rodrigues; Giani B. Silva (Applied Entomology and Zoology, 2017)

ATLANTIC ‐ CAMTRAPS : a dataset of medium and large terrestrial mammal communities in the Atlantic Forest of South America - Fernando Lima; Gabrielle Beca; Renata L. Muylaert; Clinton N. Jenkins; Miriam L. L. Perilli; Ana Maria O. Paschoal; Rodrigo L. Massara; Adriano P. Paglia; Adriano G. Chiarello; Maurício E. Graipel; Jorge J. Cherem; André L. Regolin; et al. (Ecology, 2017)
Our understanding of mammal ecology has always been hindered by the difficulties of observing species in closed tropical forests. Camera trapping has become a major advance for monitoring terrestrial mammals in biodiversity rich ecosystems. Here we compiled one of the largest datasets of inventories of terrestrial mammal communities for the Neotropical region based on camera trapping studies. The dataset comprises 170 surveys of medium to large terrestrial mammals using camera traps conducted in 144 areas by 74 studies, covering six vegetation types of tropical and subtropical Atlantic Forest of South America (Brazil and Argentina), and present data on species composition and richness. The complete dataset comprises 53,438 independent records of 83 species of mammals, includes 10 species of marsupials, 15 rodents, 20 carnivores, eight ungulates and six armadillos. Species richness averaged 13 species (±6.07 SD ) per site. Only six species occurred in more than 50% of the sites: the domestic dog Canis familiaris , crab‐eating fox Cerdocyon thous , tayra Eira barbara , south American coati Nasua nasua , crab‐eating raccoon Procyon cancrivorus and the nine‐banded armadillo Dasypus novemcinctus . The information contained in this dataset can be used to understand macroecological patterns of biodiversity, community, and population structure, but also to evaluate the ecological consequences of fragmentation, defaunation, and trophic interactions.

Wax Removal and Diamondback Moth Performance in Collards Cultivars - G. A. Silva; R. M. Pereira; N. Rodrigues-Silva; T. C. Souza; D. O. Ferreira; E. A. Queiroz; G. A. R. Silva; M. C. Picanço (Neotropical Entomology, 2017)

MPP+-Lesioned Mice: an Experimental Model of Motor, Emotional, Memory/Learning, and Striatal Neurochemical Dysfunctions - Mauricio P. Cunha; Francis L. Pazini; Vicente Lieberknecht; Josiane Budni; Ágatha Oliveira; Júlia M. Rosa; Gianni Mancini; Leidiane Mazzardo; André R. Colla; Marina C. Leite; Adair R. S. Santos; Daniel F. Martins; et al. (Molecular Neurobiology, 2017)

Atorvastatin Protects from Aβ1–40-Induced Cell Damage and Depressive-Like Behavior via ProBDNF Cleavage - Fabiana K. Ludka; Maurício P. Cunha; Tharine Dal-Cim; Luisa Bandeira Binder; Leandra C. Constantino; Caio M. Massari; Wagner C. Martins; Ana Lúcia S. Rodrigues; Carla I. Tasca (Molecular Neurobiology, 2017)

Evaluation of Mycotube, a modified version of Lowenstein–Jensen (LJ) medium, for efficient recovery of Mycobacterium tuberculosis (MTB) - R. Nambiar; S. Chatellier; N. Bereksi; A. van Belkum; N. Singh; B. Barua; A. Shetty; C. Rodrigues (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Transcriptional profiling by RNA sequencing of black pepper (Piper nigrum L.) roots infected by Fusarium solani f. sp. piperis - Edith C. O. Moreira; Daniel G. Pinheiro; Sheila M. C. Gordo; Simone M. Rodrigues; Elaine Pessoa; Hubert Schaller; Oriel F. de Lemos; Artur Silva; Horacio Schneider; Wilson A. Silva; Iracilda Sampaio; Sylvain Darnet (Acta Physiologiae Plantarum, 2017)

Study of macro and microelements in fish from the Cienfuegos Bay. Relationship with its content in sediments - M. Peña-Icart; E. Rodrigues Pereira-Filho; L. Lopes Fialho; J. A. Nóbrega; C. Alonso-Hernández; Y. Bolaños-Alvarez; A. Muñoz-Caravaca; M. S. Pomares-Alfonso (Environmental Monitoring and Assessment, 2017)

Richness of periphytic algae and its relationship with hydrological attributes - Vanessa M. Algarte; Natália S. Siqueira; Daiane T. Ruwer; Nicolli C. Osório; Liliana Rodrigues (Brazilian Journal of Botany, 2017)

N-acylhydrazones containing thiophene nucleus: a new anticancer class - Laura N. F. Cardoso; Thais C. M. Nogueira; Felipe A. R. Rodrigues; Augusto Cesar Aragão Oliveira; Maria Claudia dos Santos Luciano; Claudia Pessoa; Marcus V. N. de Souza (Medicinal Chemistry Research, 2017)

Biology of the relict fungus-farming ant Apterostigma megacephala Lattke, including descriptions of the male, gyne, and larva - J. Sosa-Calvo; A. Ješovnik; C. T. Lopes; A. Rodrigues; C. Rabeling; M. Bacci; H. L. Vasconcelos; T. R. Schultz (Insectes Sociaux, 2017)

Comparative study of urban development and groundwater condition in coastal areas of Buenos Aires, Argentina - Leandro Rodrigues Capítulo; Silvina C. Carretero; Eduardo E. Kruse (Hydrogeology Journal, 2017)

Global patterns of interaction specialization in bird–flower networks - Thais B. Zanata; Bo Dalsgaard; Fernando C. Passos; Peter A. Cotton; James J. Roper; Pietro K. Maruyama; Erich Fischer; Matthias Schleuning; Ana M. Martín González; Jeferson Vizentin‐Bugoni; Donald C. Franklin; Stefan Abrahamczyk; et al. (Journal of Biogeography, 2017)
Aim Among the world's three major nectar‐feeding bird taxa, hummingbirds are the most phenotypically specialized for nectarivory, followed by sunbirds, while the honeyeaters are the least phenotypically specialized taxa. We tested whether this phenotypic specialization gradient is also found in the interaction patterns with their floral resources. Location Americas, Africa, Asia and Oceania/Australia. Methods We compiled interaction networks between birds and floral resources for 79 hummingbird, nine sunbird and 33 honeyeater communities. Interaction specialization was quantified through connectance ( C ), complementary specialization ( H 2 ′), binary ( Q B ) and weighted modularity ( Q ), with both observed and null‐model corrected values. We compared interaction specialization among the three types of bird–flower communities, both independently and while controlling for potential confounding variables, such as plant species richness, asymmetry, latitude, insularity, topography, sampling methods and intensity. Results Hummingbird–flower networks were more specialized than honeyeater–flower networks. Specifically, hummingbird–flower networks had a lower proportion of realized interactions (lower C ), decreased niche overlap (greater H 2 ′) and greater modularity (greater Q B ). However, we found no significant differences between hummingbird– and sunbird–flower networks, nor between sunbird– and honeyeater–flower networks. Main conclusions As expected, hummingbirds and their floral resources have greater interaction specialization than honeyeaters, possibly because of greater phenotypic specialization and greater floral resource richness in the New World. Interaction specialization in sunbird–flower communities was similar to both hummingbird–flower and honeyeater–flower communities. This may either be due to the relatively small number of sunbird–flower networks available, or because sunbird–flower communities share features of both hummingbird–flower communities (specialized floral shapes) and honeyeater–flower communities (fewer floral resources). These results suggest a link between interaction specialization and both phenotypic specialization and floral resource richness within bird–flower communities at a global scale.

Ashes from fluidized bed combustion of residual forest biomass: recycling to soil as a viable management option - Nuno C. Cruz; Sónia M. Rodrigues; Lina Carvalho; Armando C. Duarte; Eduarda Pereira; Paul F.A.M. Römkens; Luís A.C. Tarelho (Environmental Science and Pollution Research, 2017)

P transformations in cacao agroforests soils in the Atlantic forest region of Bahia, Brazil - S. Aleixo; A. C. Gama-Rodrigues; M. G. Costa; M. V. S. Sales; E. F. Gama-Rodrigues; J. R. B. Marques (Agroforestry Systems, 2017)

Copper effect in petroleum hydrocarbons biodegradation by microorganisms associated to Juncus maritimus: role of autochthonous bioaugmentation - I. P. F. M. Montenegro; A. P. Mucha; I. Reis; P. Rodrigues; C. M. R. Almeida (International Journal of Environmental Science and Technology, 2017)

Application of solar photo-Fenton toward toxicity removal and textile wastewater reuse - Maria Clara V. M. Starling; Paulo Henrique Rodrigues dos Santos; Felipe Antônio Ribeiro de Souza; Sílvia Corrêa Oliveira; Mônica M. D. Leão; Camila C. Amorim (Environmental Science and Pollution Research, 2017)

Benthic dinoflagellate blooms in tropical intertidal rock pools: elucidation of photoprotection mechanisms - J. S. Patil; R. V. Rodrigues; P. Paul; K. Sathish; M. Rafi; A. C. Anil (Marine Biology, 2017)

Occurrence of anti-Leptospira spp. antibodies in Rhipidomys spp. from a forest fragment of the Brazilian Cerrado - D. O. Gomes; G. B. Ramos; V. B. A. Alves; A. Z. Ciuffa; L. P. Cuccato; T. F. M. dos Reis; A. M. C. Lima; M. C. Gonçalves; G. V. Tolesano; V. S. Rodrigues; M. P. J. Szabó (Tropical Animal Health and Production, 2017)

Pramipexole, a Dopamine D2/D3 Receptor-Preferring Agonist, Prevents Experimental Autoimmune Encephalomyelitis Development in Mice - Vicente Lieberknecht; Stella C. Junqueira; Mauricio P. Cunha; Thaís A. Barbosa; Luiz F. de Souza; Igor S. Coelho; Adair R. S. Santos; Ana Lúcia S. Rodrigues; Alcir L. Dafré; Rafael C. Dutra (Molecular Neurobiology, 2017)

Exploring 1,2,3-triazole derivatives by using in vitro and in silico assays to target new antifungal agents and treat Candidiasis - Taísa F. Santos; Jéssica B. de Jesus; Paulo M. Neufeld; Alessandro K. Jordão; Vinícius R. Campos; Anna C. Cunha; Helena C. Castro; Maria C. B. V. de Souza; Vitor F. Ferreira; Carlos R. Rodrigues; Paula A. Abreu (Medicinal Chemistry Research, 2017)

Synthesis, antimicrobial activity and cytotoxic investigation of novel trifluoromethylated tetrazolo[1,5-a]pyrimidines - Elisandra Scapin; Clarissa P. Frizzo; Leticia V. Rodrigues; Geórgia C. Zimmer; Rodrigo A. Vaucher; Michelle R. Sagrillo; Janice L. Giongo; Carlos A. M. Afonso; Patrícia Rijo; Nilo Zanatta; Helio G. Bonacorso; Marcos A. P. Martins (Medicinal Chemistry Research, 2017)

3-D distribution of the radioelements in the granitic rocks of northern and central Portugal and geothermal implications - R. Lamas; M. M. Miranda; A. J. S. C. Pereira; L. J. P. F. Neves; N. Ferreira; N. V. Rodrigues (Journal of Iberian Geology, 2017)

Exceptional Symmetry by Genomic Word - Vera Afreixo; João M. O. S. Rodrigues; Carlos A. C. Bastos; Ana H. M. P. Tavares; Raquel M. Silva (Interdisciplinary Sciences: Computational Life Sciences, 2017)

Adaptative processes, control measures, genetic background, and resilience of malaria vectors and environmental changes in the Amazon region - W. P. Tadei; I. B. Rodrigues; M. S. Rafael; R. T. M. Sampaio; H. G. Mesquita; V. C. S. Pinheiro; J. A. C. Zequi; R. A. Roque; J. M. M. dos Santos (Hydrobiologia, 2017)

Elucidating constraints for differentiation of major human Klebsiella pneumoniae clones using MALDI-TOF MS - C. Rodrigues; Â. Novais; C. Sousa; H. Ramos; T. M. Coque; R. Cantón; J. A. Lopes; L. Peixe (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Extraction and electrophoretic analysis of large dsRNAs from desiccated plant tissues infected with plant viruses and biotrophic fungi - S. Khankhum; C. Escalante; E. Rodrigues de Souto and; R. A. Valverde (European Journal of Plant Pathology, 2017)

Drought tolerance in two oil palm hybrids as related to adjustments in carbon metabolism and vegetative growth - Priscilla A. Silva; Vanessa S. Cosme; Kátia C. B. Rodrigues; Kelly S. C. Detmann; Fábio M. Leão; Roberto L. Cunha; Reginaldo A. Festucci Buselli; Fábio M. DaMatta; Hugo A. Pinheiro (Acta Physiologiae Plantarum, 2017)

Methylene Blue Adsorption on Chitosan-g-Poly(Acrylic Acid)/Rice Husk Ash Superabsorbent Composite: Kinetics, Equilibrium, and Thermodynamics - Marcelo G. Vaz; Antonio G. B. Pereira; André R. Fajardo; Antônio C. N. Azevedo; Francisco H. A. Rodrigues (Water, Air, & Soil Pollution, 2017)

Multibiomarker responses in aquatic insect Belostoma elegans (Hemiptera) to organic pollution in freshwater system - S. Lavarías; C. Ocon; V. López van Oosterom; A. Laino; D. A. Medesani; A. Fassiano; H. Garda; J. Donadelli; M. Ríos de Molina; A. Rodrigues Capítulo (Environmental Science and Pollution Research, 2017)

Bacterial host and reporter gene optimization for genetically encoded whole cell biosensors - Catherine Brutesco; Sandra Prévéral; Camille Escoffier; Elodie C. T. Descamps; Elsa Prudent; Julien Cayron; Louis Dumas; Manon Ricquebourg; Géraldine Adryanczyk-Perrier; Arjan de Groot; Daniel Garcia; Agnès Rodrigue; et al. (Environmental Science and Pollution Research, 2017)

Rainbow trout (Oncorhynchus mykiss) pro-oxidant and genotoxic responses following acute and chronic exposure to the antibiotic oxytetracycline - Sara Rodrigues; Sara C. Antunes; Alberto T. Correia; Bruno Nunes (Ecotoxicology, 2017)

Differential Impact of Acclimation and Acute Water Deprivation in the Expression of Key Transcription Factors in Soybean Roots - Fábia Guimarães-Dias; Anna C. Neves-Borges; Alessandra J. Conforte; Leonardo Giovanella-Kampmann; André V. J. Ferreira; Regina M. S. Amorim; Magda A. Benevent; Maria Eugênia Lisei de Sá; Rosilene O. Mesquita; Fabiana A. Rodrigues; Alexandre L. Nepomuceno; Eduardo Romano; et al. (Plant Molecular Biology Reporter, 2016)

Adsorption of arsenic from water and its recovery as a highly active photocatalyst - Rodrigo C. Hott; Thaina G. Andrade; Mayra S. Santos; Anne C. F. Lima; Márcia C. S. Faria; Cleide A. Bomfeti; Fernando Barbosa; Luiz F. O. Maia; Luiz C. A. Oliveira; Márcio C. Pereira; Jairo L. Rodrigues (Environmental Science and Pollution Research, 2016)

Antarctic strict anaerobic microbiota from Deschampsia antarctica vascular plants rhizosphere reveals high ecology and biotechnology relevance - Rafael José Marques Peixoto; Karla Rodrigues Miranda; Leandro Araujo Lobo; Alessandra Granato; Pedro de Carvalho Maalouf; Hugo Emiliano de Jesus; Caio T. C. C. Rachid; Saulo Roni Moraes; Henrique Fragoso dos Santos; Raquel Silva Peixoto; Alexandre Soares Rosado; Regina Maria Cavalcanti Pilotto Domingues (Extremophiles, 2016)

Behavior of Atrazine and Its Degradation Products Deethylatrazine and Deisopropylatrazine in Oxisol Samples - Maristela F. Amadori; Marcio B. Rodrigues; Caio C. Rebouças; Patricio G. Peralta-Zamora; Marco T. Grassi; Gilberto Abate (Water, Air, & Soil Pollution, 2016)

Effect of petroleum hydrocarbons in copper phytoremediation by a salt marsh plant (Juncus maritimus) and the role of autochthonous bioaugmentation - I. P. F. M. Montenegro; A. P. Mucha; I. Reis; P. Rodrigues; C. M. R. Almeida (Environmental Science and Pollution Research, 2016)

A mid‐ P leistocene rainforest corridor enabled synchronous invasions of the A tlantic F orest by A mazonian anole lizards - Ivan Prates; Danielle Rivera; Miguel T. Rodrigues; Ana C. Carnaval (Molecular Ecology, 2016)
Shifts in the geographic distribution of habitats over time can promote dispersal and vicariance, thereby influencing large‐scale biogeographic patterns and ecological processes. An example is that of transient corridors of suitable habitat across disjunct but ecologically similar regions, which have been associated with climate change over time. Such connections likely played a role in the assembly of tropical communities, especially within the highly diverse Amazonian and Atlantic rainforests of South America. Although these forests are presently separated by open and dry ecosystems, paleoclimatic and phylogenetic evidence suggest that they have been transiently connected in the past. However, little is known about the timing, magnitude and the distribution of former forest connections. We employ sequence data at multiple loci from three codistributed arboreal lizards ( Anolis punctatus , Anolis ortonii and Polychrus marmoratus ) to infer the phylogenetic relationships among Amazonian and Atlantic Forest populations and to test alternative historical demographic scenarios of colonization and vicariance using coalescent simulations and approximate Bayesian computation ( ABC ). Data from the better‐sampled Anolis species support colonization of the Atlantic Forest from eastern Amazonia. Hierarchical ABC indicates that the three species colonized the Atlantic Forest synchronously during the mid‐Pleistocene. We find support of population bottlenecks associated with founder events in the two Anolis , but not in P. marmoratus , consistently with their distinct ecological tolerances. Our findings support that climatic fluctuations provided key opportunities for dispersal and forest colonization in eastern South America through the cessation of environmental barriers. Evidence of species‐specific histories strengthens assertions that biological attributes play a role in responses to shared environmental change.

Essential oils to control ichthyophthiriasis in pacu, Piaractus mesopotamicus (Holmberg): special emphasis on treatment with Melaleuca alternifolia - G M R Valladão; S U Gallani; C V Ikefuti; C da Cruz; N Levy‐Pereira; M V N Rodrigues; F Pilarski (Journal of Fish Diseases, 2016)
In vitro effect of the Melaleuca alternifolia , Lavandula angustifolia and Mentha piperita essential oils ( EO s) against Ichthyophthirius multifiliis and in vivo effect of M. alternifolia for treating ichthyophthiriasis in one of the most important South American fish, Piaractus mesopotamicus (Holmberg), were evaluated. The in vitro test consisted of three EO s, each at concentrations of 57 μL L −1 , 114 μL L −1 , 227 μL L −1 and 455 μL L −1 , which were assessed once an hour for 4 h in microtitre plates (96 wells). The in vitro results demonstrated that all tested EO s showed a cytotoxic effect against I. multifiliis compared to control groups ( P 0.05). The in vivo treatment for white spot disease was performed in a bath for 2 h day −1 for 5 days using the M. alternifolia EO (50 μL L −1 ). In this study, 53.33% of the fish severely infected by I. multifiliis survived after the treatment with M. alternifolia (50 μL L −1 ) and the parasitological analysis has shown an efficacy of nearly 100% in the skin and gills, while all the fish in the control group died. Furthermore, the potential positive effect of M. alternifolia EO against two emergent opportunistic bacteria in South America Edwardsiella tarda and Citrobacter freundii was discussed.

First report of the nutritional profile and antioxidant potential of Holothuria arguinensis , a new resource for aquaculture in Europe - Christina C. Roggatz; Mercedes González-Wangüemert; Hugo Pereira; Maria João Rodrigues; Manuela Moreira da Silva; Luísa Barreira; João Varela; Luísa Custódio (Natural Product Research, 2016)

Indomethacin treatment reduces microglia activation and increases numbers of neuroblasts in the subventricular zone and ischaemic striatum after focal ischaemia - Rosana S Lopes; Marcelo M Cardoso; Arthur O Sampaio; Mario Santos Barbosa; Celice C Souza; Michelle C da Silva; Elane Magno N Ferreira; Marco Aurelio M Freire; Rafael Rodrigues Lima; Walace Gomes-Leal (Journal of Biosciences, 2016)

Prevalence of the genus Cladosporium on the integument of leaf-cutting ants characterized by 454 pyrosequencing - A. P. M. Duarte; M. Ferro; A. Rodrigues; M. Bacci; N. S. Nagamoto; L. C. Forti; F. C. Pagnocca (Antonie van Leeuwenhoek, 2016)

Distribution patterns of the ghost crab Ocypode cursor on sandy beaches of a tropical island in the Cabo Verde archipelago, Eastern Central Atlantic - E Rodrigues; R Freitas; N de C Delgado; A Soares-Gomes (African Journal of Marine Science, 2016)

Whole genome and exome sequencing realignment supports the assignment of KCNJ12, KCNJ17, and KCNJ18 paralogous genes in thyrotoxic periodic paralysis locus: functional characterization of two polymorphic Kir2.6 isoforms - Rolf M. Paninka; Diego R. Mazzotti; Marina M. L. Kizys; Angela C. Vidi; Hélio Rodrigues; Silas P. Silva; Ilda S. Kunii; Gilberto K. Furuzawa; Manoel Arcisio-Miranda; Magnus R. Dias-da-Silva (Molecular Genetics and Genomics, 2016)

Cytokines profile and its correlation with endothelial damage and oxidative stress in patients with type 1 diabetes mellitus and nephropathy - Rodrigo M. C. Pestana; Caroline P. Domingueti; Rita C. F. Duarte; Rodrigo B. Fóscolo; Janice S. Reis; Ana Maria S. Rodrigues; Laís B. Martins; Lirlândia P. Sousa; Daniela P. Lage; Cláudia N. Ferreira; Adaliene V. M. Ferreira; Ana P. Fernandes; et al. (Immunologic Research, 2016)

Modulation of aquaporins 3 and 9 after exposure of ovine ovarian tissue to cryoprotectants followed by in vitro culture - A. D. Sales; A. B. G. Duarte; R. R. Santos; K. A. Alves; L. F. Lima; G. Q. Rodrigues; I. R. Brito; C. H. Lobo; J. B. Bruno; Y. Locatelli; J. R. Figueiredo; A. P. R. Rodrigues (Cell and Tissue Research, 2016)

Advantages and limitations of chemical extraction tests to predict mercury soil-plant transfer in soil risk evaluations - R. J. R. Monteiro; S. M. Rodrigues; N. Cruz; B. Henriques; A. C. Duarte; P. F. A. M. Römkens; E. Pereira (Environmental Science and Pollution Research, 2016)

Using the mini-VIDAS® Easy Salmonella protocol to assess contamination in transitional and coastal waters - M. J. Rodrigues; K. Martins; D. Garcia; S. M. F. Ferreira; S. C. Gonçalves; S. Mendes; M. F. L. Lemos (Archives of Microbiology, 2016)

Enhancing the biodiesel manufacturing process by use of glycerin to produce hyacinth fragrance - Cauê A. C. Silva; Flávia C. A. Figueiredo; Raphael Rodrigues; Mirela I. Sairre; Maraisa Gonçalves; Ines Matos; Isabel M. Fonseca; Dalmo Mandelli; Wagner A. Carvalho (Clean Technologies and Environmental Policy, 2016)

“Watching the Detectives” report of the general assembly of the EU project DETECTIVE Brussels, 24–25 November 2015 - Ruani N. Fernando; Umesh Chaudhari; Sylvia E. Escher; Jan G. Hengstler; Jürgen Hescheler; Paul Jennings; Hector C. Keun; Jos C. S. Kleinjans; Raivo Kolde; Laxmikanth Kollipara; Annette Kopp-Schneider; Alice Limonciel; et al. (Archives of Toxicology, 2016)

Oviposition in Heliconius erato (Lepidoptera, Nymphalidae): how Essential Is Drumming Behavior for Host-Plant Selection? - Sabrina C. Thiele; Daniela Rodrigues; Gilson R.P. Moreira (Journal of Insect Behavior, 2016)

Atmospheric Flow over a Mountainous Region by a One-Way Coupled Approach Based on Reynolds-Averaged Turbulence Modelling - C. Veiga Rodrigues; J. M. L. M. Palma; Á. H. Rodrigues (Boundary-Layer Meteorology, 2016)

Recurrent connections between Amazon and Atlantic forests shaped diversity in Caatinga four‐eyed frogs - Maria Tereza C. Thomé; Fernando Sequeira; Francisco Brusquetti; Bryan Carstens; Célio F. B. Haddad; Miguel Trefaut Rodrigues; João Alexandrino (Journal of Biogeography, 2016)
Aim The Caatinga is a widespread but poorly known biome in South America. Its historical stability is controversial and different types of evidence provide support to contrasting hypotheses. We investigate how past biome dynamics may have caused diversification in the endemic four‐eyed frog genus Pleurodema . Location Caatinga biome. Methods We sampled 353 individuals of Pleurodema alium and Pleurodema diplolister from 60 localities and genotyped them at 12 ( P. alium ) or 20 ( P. diplolister ) microsatellite loci. We sequenced a mitochondrial fragment for a subset (199) of the samples. After exploratory analyses to infer genetic structure between and within species, we designed seven biogeographical scenarios based on the literature on species distributions, palaeomodels and geological palaeoindicators. We tested these hypotheses by calculating the posterior probability of models using multilocus approximate Bayesian computation ( ABC ). Results Both markers recovered well‐defined interspecific limits with restricted introgression, but population structure within P. diplolister is subtle and affected by isolation by distance. Model selection using ABC supported two scenarios of diversification that included recent demographic growth. Genetic breaks at intra‐ and interspecific levels were geographically coincident, and correlated with past forest invasions reported in the literature. Main conclusions Our data support the idea that past expansions of the Amazon and Atlantic forests over the current Caatinga distribution shaped the genetic structure in endemic four‐eyed frogs at more than one level by promoting intermittent vicariance. Additional support comes from the distribution patterns of forest and C aatinga taxa. Variation among groups suggests differential organismal responses to past habitat shifts, probably mediated by specific natural‐history traits. This paper provides the first direct evidence that taxa endemic to the C aatinga were affected by past forest interactions.

Mating system and pollen dispersal in Eugenia dysenterica (Myrtaceae) germplasm collection: tools for conservation and domestication - Eduardo B. Rodrigues; Rosane G. Collevatti; Lázaro J. Chaves; Lucas R. Moreira; Mariana P. C. Telles (Genetica, 2016)

Exposure to different glyphosate formulations on the oxidative and histological status of Rhamdia quelen - Camila R. Murussi; Maiara D. Costa; Jossiele W. Leitemperger; Luciana Guerra; Cintia C. R. Rodrigues; Charlene C. Menezes; Eduardo S. Severo; Fábio Flores-Lopes; Joseânia Salbego; Vania L. Loro (Fish Physiology and Biochemistry, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Leaf gas exchange and multiple enzymatic and non-enzymatic antioxidant strategies related to drought tolerance in two oil palm hybrids - Priscilla A. Silva; Igor V. Oliveira; Kátia C. B. Rodrigues; Vanessa S. Cosme; Abel J. R. Bastos; Kelly S. C. Detmann; Roberto L. Cunha; Reginaldo A. Festucci-Buselli; Fábio M. DaMatta; Hugo A. Pinheiro (Trees, 2016)

A novel N-acetyl-glucosamine lectin of Lonchocarpus araripensis attenuates acute cellular inflammation in mice - Alana F. Pires; Natália V. F. C. Rodrigues; Pedro Marcos G. Soares; Ronaldo de Albuquerque Ribeiro; Karoline S. Aragão; Márcia M. Marinho; Mayara T. L. da Silva; Benildo S. Cavada; Ana Maria S. Assreuy (Inflammation Research, 2016)

On the estimation of the bed-material transport and budget along a river segment: application to the Middle Loire River, France - B. Camenen; R. C. Grabowski; A. Latapie; A. Paquier; L. Solari; S. Rodrigues (Aquatic Sciences, 2016)

Long‐term elevated air [ CO 2 ] strengthens photosynthetic functioning and mitigates the impact of supra‐optimal temperatures in tropical Coffea arabica and C. canephora species - Weverton P. Rodrigues; Madlles Q. Martins; Ana S. Fortunato; Ana P. Rodrigues; José N. Semedo; Maria C. Simões‐Costa; Isabel P. Pais; António E. Leitão; Filipe Colwell; Luis Goulao; Cristina Máguas; Rodrigo Maia; et al. (Global Change Biology, 2016)
The tropical coffee crop has been predicted to be threatened by future climate changes and global warming. However, the real biological effects of such changes remain unknown. Therefore, this work aims to link the physiological and biochemical responses of photosynthesis to elevated air [ CO 2 ] and temperature in cultivated genotypes of C offea arabica L. (cv. Icatu and IPR 108) and Coffea canephora cv. Conilon CL 153. Plants were grown for ca. 10 months at 25/20 °C (day/night) and 380 or 700 μl CO 2 l −1 and then subjected to temperature increase (0.5 °C day −1 ) to 42/34 °C. Leaf impacts related to stomatal traits, gas exchanges, C isotope composition, fluorescence parameters, thylakoid electron transport and enzyme activities were assessed at 25/20, 31/25, 37/30 and 42/34 °C. The results showed that (1) both species were remarkably heat tolerant up to 37/30 °C, but at 42/34 °C a threshold for irreversible nonstomatal deleterious effects was reached. Impairments were greater in C. arabica (especially in Icatu) and under normal [ CO 2 ]. Photosystems and thylakoid electron transport were shown to be quite heat tolerant, contrasting to the enzymes related to energy metabolism, including RuBis CO , which were the most sensitive components. (2) Significant stomatal trait modifications were promoted almost exclusively by temperature and were species dependent. Elevated [ CO 2 ], (3) strongly mitigated the impact of temperature on both species, particularly at 42/34 °C, modifying the response to supra‐optimal temperatures, (4) promoted higher water‐use efficiency under moderately higher temperature (31/25 °C) and (5) did not provoke photosynthetic downregulation. Instead, enhancements in [ CO 2 ] strengthened photosynthetic photochemical efficiency, energy use and biochemical functioning at all temperatures. Our novel findings demonstrate a relevant heat resilience of coffee species and that elevated [ CO 2 ] remarkably mitigated the impact of heat on coffee physiology, therefore playing a key role in this crop sustainability under future climate change scenarios.

Fungi associated with rocks of the A tacama D esert: taxonomy, distribution, diversity, ecology and bioprospection for bioactive compounds - Vívian N. Gonçalves; Charles L. Cantrell; David E. Wedge; Mariana C. Ferreira; Marco Aurélio Soares; Melissa R. Jacob; Fabio S. Oliveira; Douglas Galante; Fabio Rodrigues; Tânia M. A. Alves; Carlos L. Zani; Policarpo A. S. Junior; et al. (Environmental Microbiology, 2016)
Summary This study assessed the diversity of cultivable rock‐associated fungi from A tacama D esert. A total of 81 fungal isolates obtained were identified as 29 Ascomycota taxa by sequencing different regions of DNA. C ladosporium halotolerans , P enicillium chrysogenum and P enicillium cf. citrinum were the most frequent species, which occur at least in four different altitudes. The diversity and similarity indices ranged in the fungal communities across the latitudinal gradient. The F isher‐α index displayed the higher values for the fungal communities obtained from the siltstone and fine matrix of pyroclastic rocks with finer grain size, which are more degraded. A total of 23 fungal extracts displayed activity against the different targets screened. The extract of P . chrysogenum afforded the compounds α‐linolenic acid and ergosterol endoperoxide, which were active against C ryptococcus neoformans and methicillin‐resistance S taphylococcus aureus respectively. Our study represents the first report of a new habitat of fungi associated with rocks of the A tacama D esert and indicated the presence of interesting fungal community, including species related with saprobes, parasite/pathogen and mycotoxigenic taxa. The geological characteristics of the rocks, associated with the presence of rich resident/resilient fungal communities suggests that the rocks may provide a favourable microenvironment fungal colonization, survival and dispersal in extreme conditions.

Changes in Cd and Zn bioavailability upon an experimental resuspension of highly contaminated coastal sediments from a tropical estuary - Christiane N. Monte; Ana P. C. Rodrigues; Renato C. Cordeiro; Aline S. Freire; Ricardo E. Santelli; W. Machado (Sustainable Water Resources Management, 2015)

Speciation with gene flow in whiptail lizards from a Neotropical xeric biome - Eliana F. Oliveira; Marcelo Gehara; Vinícius A. São‐Pedro; Xin Chen; Edward A. Myers; Frank T. Burbrink; Daniel O. Mesquita; Adrian A. Garda; Guarino R. Colli; Miguel T. Rodrigues; Federico J. Arias; Hussam Zaher; et al. (Molecular Ecology, 2015)
Two main hypotheses have been proposed to explain the diversification of the Caatinga biota. The riverine barrier hypothesis ( RBH ) claims that the São Francisco River ( SFR ) is a major biogeographic barrier to gene flow. The Pleistocene climatic fluctuation hypothesis ( PCH ) states that gene flow, geographic genetic structure and demographic signatures on endemic Caatinga taxa were influenced by Quaternary climate fluctuation cycles. Herein, we analyse genetic diversity and structure, phylogeographic history, and diversification of a widespread Caatinga lizard ( Cnemidophorus ocellifer ) based on large geographical sampling for multiple loci to test the predictions derived from the RBH and PCH . We inferred two well‐delimited lineages (Northeast and Southwest) that have diverged along the Cerrado–Caatinga border during the Mid‐Late Miocene (6–14 Ma) despite the presence of gene flow. We reject both major hypotheses proposed to explain diversification in the Caatinga. Surprisingly, our results revealed a striking complex diversification pattern where the Northeast lineage originated as a founder effect from a few individuals located along the edge of the Southwest lineage that eventually expanded throughout the Caatinga. The Southwest lineage is more diverse, older and associated with the Cerrado–Caatinga boundaries. Finally, we suggest that C. ocellifer from the Caatinga is composed of two distinct species. Our data support speciation in the presence of gene flow and highlight the role of environmental gradients in the diversification process.

The macroecology of phylogenetically structured hummingbird–plant networks - Ana M. Martín González; Bo Dalsgaard; David Nogués‐Bravo; Catherine H. Graham; Matthias Schleuning; Pietro K. Maruyama; Stefan Abrahamczyk; Ruben Alarcón; Andréa C. Araujo; Francielle P. Araújo; Severino Mendes de Azevedo; Andrea C. Baquero; et al. (Global Ecology and Biogeography, 2015)
Aim To investigate the association between hummingbird–plant network structure and species richness, phylogenetic signal on species' interaction pattern, insularity and historical and current climate. Location Fifty‐four communities along a c . 10,000 km latitudinal gradient across the A mericas (39° N –32° S ), ranging from sea level to c . 3700 m a.s.l., located on the mainland and on islands and covering a wide range of climate regimes. Methods We measured the level of specialization and modularity in mutualistic plant–hummingbird interaction networks. Using an ordinary least squares multimodel approach, we examined the influence of species richness, phylogenetic signal, insularity and current and historical climate conditions on network structure (null‐model‐corrected specialization and modularity). Results Phylogenetically related species, especially plants, showed a tendency to interact with a similar array of mutualistic partners. The spatial variation in network structure exhibited a constant association with species phylogeny ( R 2 = 0.18–0.19); however, network structure showed the strongest association with species richness and environmental factors ( R 2 = 0.20–0.44 and R 2 = 0.32–0.45, respectively). Specifically, higher levels of specialization and modularity were associated with species‐rich communities and communities in which closely related hummingbirds visited distinct sets of flowering species. On the mainland, specialization was also associated with warmer temperatures and greater historical temperature stability. Main conclusions Our results confirm the results of previous macroecological studies of interaction networks which have highlighted the importance of species richness and the environment in determining network structure. Additionally, for the first time, we report an association between network structure and species phylogenetic signal at a macroecological scale, indicating that high specialization and modularity are associated with high interspecific competition among closely related hummingbirds, subdividing the floral niche. This suggests a tighter co‐evolutionary association between hummingbirds and their plants than in previously studied plant–bird mutualistic systems.

Erratum to: Species distribution and in vitro antifungal susceptibility profiles of yeast isolates from invasive infections during a Portuguese multicenter survey - I. Faria-Ramos; J. Neves-Maia; E. Ricardo; J. Santos-Antunes; A. T. Silva; S. Costa-de-Oliveira; E. Cantón; A. G. Rodrigues; C. Pina-Vaz (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Oxidative stress markers in fish (Astyanax sp. and Danio rerio) exposed to urban and agricultural effluents in the Brazilian Pampa biome - D. G. Costa-Silva; M. E. M Nunes; G. L. Wallau; I. K. Martins; A. P. P Zemolin; L. C. Cruz; N. R. Rodrigues; A. R. Lopes; T. Posser; J. L. Franco (Environmental Science and Pollution Research, 2015)

Contribution to the study of deep coastal detritic bottoms: the algal communities of the continental shelf off the Balearic Islands, Western Mediterranean - S. JOHER; E. BALLESTEROS; C. RODRIGUES-PRIETO (Mediterranean Marine Science, 2015)
Three main algal-dominated coastal detritic communities from the continental shelf off Mallorca and Menorca (Balearic Islands, Western Mediterranean) are described herein: maërl beds dominated by Spongites fruticulosus and forests of Laminaria rodriguezii located in the Menorca channel, and Peyssonnelia inamoena beds found along the Southern coast of Menorca. There seems to be a gradient of disturbance from the highly disturbed Peyssonnelia beds to the almost undisturbed L. rodriguezii forests. Whether this gradient is the result of current and past anthropogenic pressure (e.g. trawling intensity) or is driven by natural environmental factors needs further assessment. Finally, the location of the target communities by means of ROV dives combined with the use of a Box-Corer dredge and beam trawl proved to be a good methodology in the study of the composition and structure of these deep water detritic communities.

Characterization of antiproliferative potential and biological targets of a copper compound containing 4′-phenyl terpyridine - Ana Soraia Mendo; Sara Figueiredo; Catarina Roma-Rodrigues; Paula A. Videira; Zhen Ma; Mário Diniz; Miguel Larguinho; Pedro M. Costa; João C. Lima; Armando J. L. Pombeiro; Pedro V. Baptista; Alexandra R. Fernandes (JBIC Journal of Biological Inorganic Chemistry, 2015)

Cytotoxic compounds from the marine-derived fungus Aspergillus sp. recovered from the sediments of the Brazilian coast - Natália N. Saraiva; Bárbara S.F. Rodrigues; Paula C. Jimenez; Larissa A. Guimarães; Maria C.M. Torres; Edson Rodrigues-Filho; Ludwig H. Pfenning; Lucas M. Abreu; Jair Mafezoli; Marcos C. de Mattos; Letícia V. Costa-Lotufo; Maria da Conceição F. de Oliveira (Natural Product Research, 2015)

Respecification of structural equation models for the P cycle in tropical soils - M. V. S. Sales; A. C. Gama-Rodrigues; N. B. Comerford; W. P. Cropper; E. F. Gama-Rodrigues; P. H. G. Oliveira (Nutrient Cycling in Agroecosystems, 2015)

MicroRNA-34a Modulates Neural Stem Cell Differentiation by Regulating Expression of Synaptic and Autophagic Proteins - Ana L. Morgado; Joana M. Xavier; Pedro A. Dionísio; Maria F. C. Ribeiro; Raquel B. Dias; Ana M. Sebastião; Susana Solá; Cecília M. P. Rodrigues (Molecular Neurobiology, 2015)

Assessing families’ and patients’ attitudes toward brain donation for research purposes in a Brazilian population sample - M. K. Fonseca; E. Rodrigues-Neto; A. S. R. Costa; M. A. B. C. Rockembach; R. S. Padilha; L. L. Fernandez; F. H. Oliveira; L. P. Garcia; A. Hilbig (Cell and Tissue Banking, 2015)

Molecular characterization of carbapenem-resistant Enterobacteriaceae at a tertiary care laboratory in Mumbai - M. Kazi; L. Drego; C. Nikam; K. Ajbani; R. Soman; A. Shetty; C. Rodrigues (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Escovopsis trichodermoides sp. nov., isolated from a nest of the lower attine ant Mycocepurus goeldii - Virginia E. Masiulionis; Marta N. Cabello; Keith A. Seifert; Andre Rodrigues; Fernando C. Pagnocca (Antonie van Leeuwenhoek, 2015)

REM Sleep Deprivation Reverses Neurochemical and Other Depressive-Like Alterations Induced by Olfactory Bulbectomy - Maira J. Maturana; Cláudia Pudell; Adriano D. S. Targa; Laís S. Rodrigues; Ana Carolina D. Noseda; Mariana H. Fortes; Patrícia dos Santos; Cláudio Da Cunha; Sílvio M. Zanata; Anete C. Ferraz; Marcelo M. S. Lima (Molecular Neurobiology, 2015)

Evaluation of (2S,3R)-2-(amino)-[4-(N-benzylarenesulfonamido)-3-hydroxy-1-phenylbutane derivatives: a promising class of anticancer agents - Victor Facchinetti; Marcele Moreth; Claudia R. B. Gomes; Cláudia do Ó Pessoa; Felipe A. R. Rodrigues; Bruno C. Cavalcanti; Augusto C. A. Oliveira; Teiliane R. Carneiro; Ivson Lelis Gama; Marcus V. N. de Souza (Medicinal Chemistry Research, 2015)

Oysters as hot spots for mimivirus isolation - Kétyllen R. Andrade; Paulo P. V. M. Boratto; Felipe P. Rodrigues; Lorena C. F. Silva; Fábio P. Dornas; Mariana R. Pilotto; Bernard La Scola; Gabriel M. F. Almeida; Erna G. Kroon; Jônatas S. Abrahão (Archives of Virology, 2015)

Ichthyofauna of the Selvagens Islands. Do small coastal areas show high species richness in the northeastern Atlantic? - Frederico Almada; David Abecasis; David Villegas-Ríos; Sofia Henriques; Miguel P. Pais; Marisa Batista; Bárbara Horta e Costa; Joana Martins; Inês Tojeira; Nuno Vasco Rodrigues; Ricardo Araújo; Miguel Souto; et al. (Marine Biology Research, 2015)

Anatomical and ultrastructural adaptations of seagrass leaves: an evaluation of the southern Atlantic groups - Chirle Ferreira; Paulo A. Horta; Gabriela M. Almeida; Carmen S. Zitta; Eliana de M. Oliveira; Marietou B. Y. B. Gueye; Ana C. Rodrigues (Protoplasma, 2015)

Identification of familial clustering for cancer through the family health strategy program in the municipality of Angra dos Reis, Rio de Janeiro, Brazil - Daniela Koeller Rodrigues Vieira; Margareth Attianezi; Ana Carolina Esposito; Anneliese Barth; Cecília Sequeira; Nathália Krause; Vivian Oliveira; Alexandre Lucidi; Cassio Serao; Juan C. Llerena (Journal of Community Genetics, 2015)

Tracking the expansion of the American mink (Neovison vison) range in NW Portugal - Diana C. Rodrigues; Luciana Simões; Jacinta Mullins; Simone Lampa; Raquel C. Mendes; Carlos Fernandes; Rui Rebelo; Margarida Santos-Reis (Biological Invasions, 2015)

Novel isomannide-based peptide mimetics containing a tartaric acid backbone as serine protease inhibitors - Bárbara Abrahim-Vieira; Emmerson C. B. da Costa; Pedro H. R. de A. Azevedo; Aline C. Portela; Luiza R. S. Dias; Sergio Pinheiro; Amilcar Tanuri; Anne M. Capaccia; Gustavo T. Ventura; Ronaldo Mohana-Borges; Carlos R. Rodrigues; Alessandra M. T. de Souza; et al. (Medicinal Chemistry Research, 2014)

Species distribution and in vitro antifungal susceptibility profiles of yeast isolates from invasive infections during a Portuguese multicenter survey - I. Faria-Ramos; J. Neves-Maia; E. Ricardo; J. Santos-Antunes; A. T. Silva; S. Costa-de-Oliveira; E. Cantón; A. G. Rodrigues; C. Pina-Vaz (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Fresh and vitrified bovine preantral follicles have different nutritional requirements during in vitro culture - S. V. Castro; A. A. Carvalho; C. M. G. Silva; F. W. Santos; C. C. Campello; J. R. Figueiredo; A. P. R. Rodrigues (Cell and Tissue Banking, 2014)

The Impact of Uranium Mine Contamination of Soils on Plant Litter Decomposition - Ana C. Freitas; Dina Rodrigues; Teresa A. P. Rocha-Santos; Fernando Gonçalves; Armando C. Duarte; Ruth Pereira (Archives of Environmental Contamination and Toxicology, 2014)

Nutrient stocks in litterfall and litter in cocoa agroforests in Brazil - A. G. Fontes; A. C. Gama-Rodrigues; E. F. Gama-Rodrigues; M. V. S. Sales; M. G. Costa; R. C. R. Machado (Plant and Soil, 2014)

Differential Effects of Fluoride During Osteoblasts Mineralization in C57BL/6J and C3H/HeJ Inbred Strains of Mice - Sandra S. Matsuda; Thelma L. Silva; Marília A. Buzalaf; Antonio C Rodrigues; Rodrigo Cardoso de Oliveira (Biological Trace Element Research, 2014)

Relative mRNA expression and immunolocalization for transforming growth factor-beta (TGF-β) and their effect on in vitro development of caprine preantral follicles - G. Q. Rodrigues; M. J. Bertoldo; I. R. Brito; C. M. G. Silva; A. D. Sales; S. V. Castro; N. Duffard; Y. Locatelli; P. Mermillod; C. H. Lobo; C. C. Campello; A. P. R. Rodrigues; et al. (In Vitro Cellular & Developmental Biology - Animal, 2014)

Exploring N-Acylhydrazone Derivatives Against Clinical Resistant Bacterial Strains - Andressa C. Lannes; Bruno Leal; Juliana S. Novais; Viviane Lione; Georgia C. T. S. Monteiro; André L. Lourenço; Plínio C. Sathler; Alessandro K. Jordão; Carlos R. Rodrigues; Lúcio M. Cabral; Anna Claudia Cunha; Vinicius Campos; et al. (Current Microbiology, 2014)

Description of a strain from an atypical population of Aspergillus parasiticus that produces aflatoxins B only, and the impact of temperature on fungal growth and mycotoxin production - Arita C; Calado T; Venâncio A; Lima N; Rodrigues P (European Journal of Plant Pathology, 2014)

Mercury Bioaccumulation in the Egyptian Mongoose (Herpestes ichneumon): Geographical, Tissue, Gender and Age Differences - S. Rodrigues; J. P. Coelho; V. Bandeira; T. Barros; A. C. Duarte; C. Fonseca; M. E. Pereira (Water, Air, & Soil Pollution, 2014)

Alterations in the extracellular catabolism of nucleotides and platelet aggregation induced by high-fat diet in rats: effects of α-tocopherol - Jessié M. Gutierres; Fabiano B. Carvalho; Maria Rosa C. Schetinger; Marília V. Rodrigues; Juliano M. Vieira; Paula Maldonado; Maria do Carmo S. Araújo; Roberta Schmatz; Naiara Stefanello; Jeandre A. S. Jaques; Marcio Costa; Vera Morsch; et al. (Journal of Physiology and Biochemistry, 2014)

Land use change alters functional gene diversity, composition and abundance in Amazon forest soil microbial communities - Fabiana S. Paula; Jorge L. M. Rodrigues; Jizhong Zhou; Liyou Wu; Rebecca C. Mueller; Babur S. Mirza; Brendan J. M. Bohannan; Klaus Nüsslein; Ye Deng; James M. Tiedje; Vivian H. Pellizari (Molecular Ecology, 2014)
Land use change in the Amazon rainforest alters the taxonomic structure of soil microbial communities, but whether it alters their functional gene composition is unknown. We used the highly parallel microarray technology GeoChip 4.0, which contains 83 992 probes specific for genes linked nutrient cycling and other processes, to evaluate how the diversity, abundance and similarity of the targeted genes responded to forest‐to‐pasture conversion. We also evaluated whether these parameters were reestablished with secondary forest growth. A spatially nested scheme was employed to sample a primary forest, two pastures (6 and 38 years old) and a secondary forest. Both pastures had significantly lower microbial functional genes richness and diversity when compared to the primary forest. Gene composition and turnover were also significantly modified with land use change. Edaphic traits associated with soil acidity, iron availability, soil texture and organic matter concentration were correlated with these gene changes. Although primary and secondary forests showed similar functional gene richness and diversity, there were differences in gene composition and turnover, suggesting that community recovery was not complete in the secondary forest. Gene association analysis revealed that response to ecosystem conversion varied significantly across functional gene groups, with genes linked to carbon and nitrogen cycling mostly altered. This study indicates that diversity and abundance of numerous environmentally important genes respond to forest‐to‐pasture conversion and hence have the potential to affect the related processes at an ecosystem scale.

Adaptations of aortic and pulmonary artery flow parameters measured by phase-contrast magnetic resonance angiography during supine aerobic exercise - Guido E. Pieles; Gergely Szantho; Jonathan C. L. Rodrigues; Christopher B. Lawton; A. Graham Stuart; Chiara Bucciarelli-Ducci; Mark S. Turner; Craig A. Williams; Robert M. R. Tulloh; Mark C. K. Hamilton (European Journal of Applied Physiology, 2014)

Candida glabrata: a review of its features and resistance - C. F. Rodrigues; S. Silva; M. Henriques (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Light and temperature induce variations in the density and ultrastructure of the secretory spaces in the diesel-tree (Copaifera langsdorffii Desf.—Leguminosae) - T. M. Rodrigues; P. F. S. M. Buarque; A. G. Coneglian; D. C. Reis (Trees, 2014)

Cold impact and acclimation response of Coffea spp. plants - J. C. Ramalho; F. M. DaMatta; A. P. Rodrigues; P. Scotti-Campos; I. Pais; P. Batista-Santos; F. L. Partelli; A. Ribeiro; F. C. Lidon; A. E. Leitão (Theoretical and Experimental Plant Physiology, 2014)

Resveratrol Induces Pro-oxidant Effects and Time-Dependent Resistance to Cytotoxicity in Activated Hepatic Stellate Cells - Leo A. Meira Martins; Bárbara P. Coelho; Guilherme Behr; Letícia F. Pettenuzzo; Izabel C. C. Souza; José Cláudio F. Moreira; Radovan Borojevic; Carmem Gottfried; Fátima Costa Rodrigues Guma (Cell Biochemistry and Biophysics, 2014)

Anti-biofilm activity of low-molecular weight chitosan hydrogel against Candida species - A. Silva-Dias; A. Palmeira-de-Oliveira; I. M. Miranda; J. Branco; L. Cobrado; M. Monteiro-Soares; J. A. Queiroz; C. Pina-Vaz; A. G. Rodrigues (Medical Microbiology and Immunology, 2014)

Effect of ultraviolet-B radiation in laboratory on morphological and ultrastructural characteristics and physiological parameters of selected cultivar of Oryza sativa L. - Sérgio L. de Almeida; Éder C. Schmidt; Debora Tomazi Pereira; Marianne Kreusch; Marthiellen R. de L. Felix; Luz K. P. Osorio; Roberta de Paula Martins; Alexandra Latini; Fernanda Ramlov; Fungyi Chow; Marcelo Maraschin; Ana C. Rodrigues; et al. (Protoplasma, 2013)

BbrizAGL6 Is Differentially Expressed During Embryo Sac Formation of Apomictic and Sexual Brachiaria brizantha Plants - Larissa Arrais Guimarães; Diva Maria de A. Dusi; Simona Masiero; Francesca Resentini; Ana Cristina M. M. Gomes; Érica Duarte Silveira; Lilian Hasegawa Florentino; Júlio Carlyle M. Rodrigues; Lucia Colombo; Vera Tavares de C. Carneiro (Plant Molecular Biology Reporter, 2013)

Six-Year Trend Analysis of Nosocomial Candidemia and Risk factors in Two Intensive Care Hospitals in Mato Grosso, Midwest Region of Brazil - Hugo Dias Hoffmann-Santos; Claudete Rodrigues Paula; Ana Caroline Akeme Yamamoto; Tomoko Tadano; Rosane C. Hahn (Mycopathologia, 2013)

Interaction of warm acclimation, low salinity, and trophic fluoride on plasmatic constituents of the Antarctic fish Notothenia rossii Richardson, 1844 - E. Rodrigues; M. Feijó-Oliveira; G. S. Vani; C. N. K. Suda; C. S. Carvalho; L. Donatti; H. P. Lavrado; E. Rodrigues (Fish Physiology and Biochemistry, 2013)

Amoebas as mimivirus bunkers: increased resistance to UV light, heat and chemical biocides when viruses are carried by amoeba hosts - Paulo V. M. Boratto; Fábio P. Dornas; Kétyllen R. Andrade; Rodrigo Rodrigues; Felipe Peixoto; Lorena C. F. Silva; Bernard La Scola; Adriana Oliveira Costa; Gabriel Magno Freitas de Almeida; Erna G. Kroon; Jônatas S. Abrahão (Archives of Virology, 2013)

Mauritic acid: a new dammarane triterpene from the roots of Mauritia flexuosa L.f. (Arecaceae) - Hector H.F. Koolen; Elzalina R. Soares; Felipe M.A. da Silva; Aimêe A. de Oliveira; Antonia Q.L. de Souza; Lívia S. de Medeiros; Edson Rodrigues-Filho; Bruno C. Cavalcanti; Cláudia O. Pessoa; Manoel O. Moraes; Marcos J. Salvador; Afonso D.L. de Souza (Natural Product Research, 2013)

Humpback whales washed ashore in southeastern Brazil from 1981 to 2011: stranding patterns and microbial pathogens survey - Jailson F. Moura; Dália P. Rodrigues; Emily M. Roges; Roberta L. Souza; Paulo H. Ott; Maurício Tavares; Leila S. Lemos; Davi C. Tavares; Salvatore Siciliano (Biologia, 2013)

Late Anxiety-Like Behavior and Neuroinflammation in Mice Subjected to Sublethal Polymicrobial Sepsis - Allan C. Calsavara; David H. Rodrigues; Aline S. Miranda; Priscila A. Costa; Cristiano X. Lima; Márcia C. Vilela; Milene A. Rachid; Antônio L. Teixeira (Neurotoxicity Research, 2013)

Biological impacts of ocean acidification: a postgraduate perspective on research priorities - Samantha L. Garrard; R. C. Hunter; A. Y. Frommel; A. C. Lane; J. C. Phillips; R. Cooper; R. Dineshram; U. Cardini; S. J. McCoy; M. Arnberg; B. G. Rodrigues Alves; S. Annane; et al. (Marine Biology, 2013)

Mercury Toxicity to Freshwater Organisms: Extrapolation Using Species Sensitivity Distribution - Andreia C. M. Rodrigues; Fátima T. Jesus; Marco A. F. Fernandes; Fernando Morgado; Amadeu M. V. M. Soares; Sizenando N. Abreu (Bulletin of Environmental Contamination and Toxicology, 2013)

Characterization of water and wildlife strains as a subgroup of C ampylobacter jejuni using DNA microarrays - Richard A. Stabler; Jonas T. Larsson; Suaad Al‐Jaberi; Eva M. Nielsen; Emily Kay; Clarence C. Tam; Craig D. Higgins; Laura C. Rodrigues; Judith F. Richardson; Sarah J. O'Brien; Brendan W. Wren (Environmental Microbiology, 2013)
Summary C ampylobacter jejuni is the leading cause of human bacterial gastroenteritis worldwide, but source attribution of the organism is difficult. Previously, DNA microarrays were used to investigate isolate source, which suggested a non‐livestock source of infection. In this study we analysed the genome content of 162 clinical, livestock and water and wildlife ( WW ) associated isolates combined with the previous study. Isolates were grouped by genotypes into nine clusters ( C 1 to C 9). Multilocus sequence typing ( MLST ) data demonstrated that livestock associated clonal complexes dominated clusters C 1– C 6. The majority of WW isolates were present in the C 9 cluster. Analysis of previously reported genomic variable regions demonstrated that these regions were linked to specific clusters. Two novel variable regions were identified. A six gene multiplex PCR ( mPCR ) assay, designed to effectively differentiated strains into clusters, was validated with 30 isolates. A further five WW isolates were tested by m PCR and were assigned to the C 7‐ C 9 group of clusters. The predictive mPCR test could be used to indicate if a clinical case has come from domesticated or WW sources. Our findings provide further evidence that WW C . jejuni subtypes show niche adaptation and may be important in causing human infection.

Systematics of spiny‐backed treefrogs ( H ylidae: O steocephalus ): an A mazonian puzzle - Karl‐Heinz Jungfer; Julián Faivovich; José M. Padial; Santiago Castroviejo‐Fisher; Mariana M. Lyra; Bianca V. M. Berneck; Patricia P. Iglesias; Philippe J. R. Kok; Ross D. MacCulloch; Miguel T. Rodrigues; Vanessa K. Verdade; Claudia P. Torres Gastello; et al. (Zoologica Scripta, 2013)
Spiny‐backed tree frogs of the genus O steocephalus are conspicuous components of the tropical wet forests of the A mazon and the G uiana S hield. Here, we revise the phylogenetic relationships of O steocephalus and its sister group T epuihyla , using up to 6134 bp of DNA sequences of nine mitochondrial and one nuclear gene for 338 specimens from eight countries and 218 localities, representing 89% of the 28 currently recognized nominal species. Our phylogenetic analyses reveal (i) the paraphyly of O steocephalus with respect to T epuihyla , (ii) the placement of ‘ H yla’ warreni as sister to T epuihyla , (iii) the non‐monophyly of several currently recognized species within O steocephalus and (iv) the presence of low ( O . taurinus and O . oophagus ) for the 16 S gene fragment used in amphibian DNA barcoding. We propose a new taxonomy, securing the monophyly of O steocephalus and T epuihyla by rearranging and redefining the content of both genera and also erect a new genus for the sister group of O steocephalus . The colouration of newly metamorphosed individuals is proposed as a morphological synapomorphy for O steocephalus . We recognize and define five monophyletic species groups within O steocephalus , synonymize three species of O steocephalus ( O . germani , O . phasmatus and O . vilmae ) and three species of T epuihyla ( T . celsae , T . galani and T . talbergae ) and reallocate three species ( H yla helenae to O steocephalus , O . exophthalmus to T epuihyla and O . pearsoni to D ryaderces gen. n.). Furthermore, we flag nine putative new species (an increase to 138% of the current diversity). We conclude that species numbers are largely underestimated, with most hidden diversity centred on widespread and polymorphic nominal species. The evolutionary origin of breeding strategies within O steocephalus is discussed in the light of this new phylogenetic hypothesis, and a novel type of amplexus (gular amplexus) is described.

Soil attributes and leaf nitrogen estimating sugar cane quality parameters: Brix, pol and fibre - F. A. Rodrigues; P. S. G. Magalhães; H. C. J. Franco (Precision Agriculture, 2013)

Ubiquitin–Proteasome System Impairment and MPTP-Induced Oxidative Stress in the Brain of C57BL/6 Wild-type and GSTP Knockout Mice - Andreia Neves Carvalho; Carla Marques; Elsa Rodrigues; Colin J. Henderson; C. Roland Wolf; Paulo Pereira; Maria João Gama (Molecular Neurobiology, 2013)

Genetic and QTL analyses of yield and a set of physiological traits in pepper - N. A. Alimi; M. C. A. M. Bink; J. A. Dieleman; M. Nicolaï; M. Wubs; E. Heuvelink; J. Magan; R. E. Voorrips; J. Jansen; P. C. Rodrigues; G. W. A. M. van der Heijden; A. Vercauteren; et al. (Euphytica, 2013)

Sums, Products and Ratios for Crovelli’s Bivariate Gamma Distribution - Ana Paula C. Madeira Silva; Jailson de Araujo Rodrigues; Lucas Monteiro Chaves; Devanil Jaques de Souza (Water Resources Management, 2013)

Isolation and characterization of 18 microsatellites for Lycengraulis grossidens (Pisces: Clupeiformes) - Ana C. G. Mai; João P. Vieira; Alicia A. Plavan; Marcelo F. Nobrega; Leonardo E. Moraes; Fábio L. Rodrigues; Luis F. Marins (Conservation Genetics Resources, 2013)

Development of Probiotic Tablets Using Microparticles: Viability Studies and Stability Studies - J. P. Sousa e Silva; Sérgio C. Sousa; Paulo Costa; Emília Cerdeira; Maria H. Amaral; José Sousa Lobo; Ana M. Gomes; Maria M. Pintado; Dina Rodrigues; Teresa Rocha-Santos; Ana C. Freitas (AAPS PharmSciTech, 2013)

Intraspecific variation and emendation of Hannaella kunmingensis - Ifeloju Dayo-Owoyemi; Andre Rodrigues; Melissa F. Landell; Patricia Valente; Ulrich G. Mueller; Jesus Pais Ramos; Fernando C. Pagnocca (Mycological Progress, 2013)

Brevipalpus mites (Acari: Tenuipalpidae): vectors of invasive, non-systemic cytoplasmic and nuclear viruses in plants - Jose Carlos Verle Rodrigues; Carl C. Childers (Experimental and Applied Acarology, 2013)

Eriophorum angustifolium and Lolium perenne metabolic adaptations to metals- and metalloids-induced anomalies in the vicinity of a chemical industrial complex - Naser A. Anjum; Iqbal Ahmad; Sónia M. Rodrigues; Bruno Henriques; Nuno Cruz; Cláudia Coelho; Mário Pacheco; Armando C. Duarte; Eduarda Pereira (Environmental Science and Pollution Research, 2013)

Derivation of soil to plant transfer functions for metals and metalloids: impact of contaminant’s availability - S. M. Rodrigues; E. Pereira; A. C. Duarte; P. F. A. M. Römkens (Plant and Soil, 2012)

Changes in Liver Proteome Expression of Senegalese Sole (Solea senegalensis) in Response to Repeated Handling Stress - Odete D. Cordeiro; Tomé S. Silva; Ricardo N. Alves; Benjamin Costas; Tune Wulff; Nadège Richard; Mahaut de Vareilles; Luís E. C. Conceição; Pedro M. Rodrigues (Marine Biotechnology, 2012)

Isolation and Characterization of Antibacterial Compound from a Mangrove-Endophytic Fungus, Penicillium chrysogenum MTCC 5108 - Prabha Devi; Cheryl Rodrigues; C. G. Naik; L. D’Souza (Indian Journal of Microbiology, 2012)

Detection of Legionella pneumophila on clinical samples and susceptibility assessment by flow cytometry - I. Faria-Ramos; S. Costa-de-Oliveira; J. Barbosa; A. Cardoso; J. Santos-Antunes; A. G. Rodrigues; C. Pina-Vaz (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Spread of an OmpK36-modified ST15 Klebsiella pneumoniae variant during an outbreak involving multiple carbapenem-resistant Enterobacteriaceae species and clones - Â. Novais; C. Rodrigues; R. Branquinho; P. Antunes; F. Grosso; L. Boaventura; G. Ribeiro; L. Peixe (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Infective endocarditis in intravenous drug abusers: an update - C. Sousa; C. Botelho; D. Rodrigues; J. Azeredo; R. Oliveira (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Tauroursodeoxycholic Acid Prevents MPTP-Induced Dopaminergic Cell Death in a Mouse Model of Parkinson’s Disease - M. Castro-Caldas; A. Neves Carvalho; E. Rodrigues; C. J. Henderson; C. R. Wolf; C. M. P. Rodrigues; M. J. Gama (Molecular Neurobiology, 2012)

Dietary Lysine Imbalance Affects Muscle Proteome in Zebrafish (Danio rerio): A Comparative 2D-DIGE Study - Mahaut de Vareilles; Luis E. C. Conceição; Pedro Gómez-Requeni; Katerina Kousoulaki; Nadège Richard; Pedro M. Rodrigues; Kari E. Fladmark; Ivar Rønnestad (Marine Biotechnology, 2012)

Tuberculosis: Finding a New Potential Antimycobacterium Derivative in a Aldehyde–Arylhydrazone–Oxoquinoline Series - Fernanda C. Santos; Helena C. Castro; Maria Cristina S. Lourenço; Paula A. Abreu; Pedro N. Batalha; Anna C. Cunha; Guilherme S. L. Carvalho; Carlos R. Rodrigues; Cid A. Medeiros; Simone D. Souza; Vitor F. Ferreira; Maria C. B. V. Souza (Current Microbiology, 2012)

Carbon, nitrogen, organic phosphorus, microbial biomass and N mineralization in soils under cacao agroforestry systems in Bahia, Brazil - F. C. Zaia; A. C. Gama-Rodrigues; E. F. Gama-Rodrigues; M. K. S. Moço; A. G. Fontes; R. C. R. Machado; V. C. Baligar (Agroforestry Systems, 2012)

Immunological Aspects in Amyotrophic Lateral Sclerosis - Maria Carolina O. Rodrigues; Júlio C. Voltarelli; Paul R. Sanberg; Cesario V. Borlongan; Svitlana Garbuzova-Davis (Translational Stroke Research, 2012)

Long-Term Power Transmission Failures in Southeastern Brazil and the Geophysical Environment - Magda A. S. Duro; Pierre Kaufmann; Fernando C. P. Bertoni; Emilio C. N. Rodrigues; José Pissolato Filho (Surveys in Geophysics, 2012)

Revising the M235T Polymorphism Position for the AGT Gene and Reporting a Modifying Variant in the Brazilian Population with Potential Cardiac and Neural Impact - R. R. Lemos; S. G. de Lima; J. E. Gomes da Cunha; D. F. Oliveira; M. B. Rodrigues de Souza; C. F. J. Ayres; M. F. P. M. Albuquerque; J. R. M. Oliveira (Journal of Molecular Neuroscience, 2012)

Influence of soil water content and atmospheric conditions on leaf water potential in cv. “Touriga Nacional” deep-rooted vineyards - P. Rodrigues; V. Pedroso; J. P. Gouveia; S. Martins; C. Lopes; I. Alves (Irrigation Science, 2012)

First record of a whale shark Rhincodon typus in continental Europe - N. V. Rodrigues; J. P. S. Correia; J. T. C. Graça; F. Rodrigues; R. Pinho; M. Hirofumi (Journal of Fish Biology, 2012)
A whale shark Rhincodon typus was found in a set‐net in southern Portugal in October 2011. This was the first record for continental Europe and represents an increase of the species' known range. Upwelling events and increase in sea‐surface temperatures are possible reasons for this occurrence.

Spatial distributions of the red palm mite, Raoiella indica (Acari: Tenuipalpidae) on coconut and their implications for development of efficient sampling plans - A. Roda; G. Nachman; F. Hosein; J. C. V. Rodrigues; J. E. Peña (Experimental and Applied Acarology, 2012)

Male-Produced Sex Pheromone of the Stink Bug Edessa meditabunda - Paulo H. G. Zarbin; Carla F. Fávaro; Diogo M. Vidal; Mauro A. C. M. Rodrigues (Journal of Chemical Ecology, 2012)

The Male-produced Sex Pheromone of the True Bug, Phthia picta, is an Unusual Hydrocarbon - Rafael A. Soldi; Mauro A. C. M. Rodrigues; Jeffrey R. Aldrich; Paulo H. G. Zarbin (Journal of Chemical Ecology, 2012)

Glutathione S-Transferase pi Mediates MPTP-Induced c-Jun N-Terminal Kinase Activation in the Nigrostriatal Pathway - Margarida Castro-Caldas; Andreia Neves Carvalho; Elsa Rodrigues; Colin Henderson; C. Roland Wolf; Maria João Gama (Molecular Neurobiology, 2012)

TUDCA, a Bile Acid, Attenuates Amyloid Precursor Protein Processing and Amyloid-β Deposition in APP/PS1 Mice - Ana F. Nunes; Joana D. Amaral; Adrian C. Lo; Maria B. Fonseca; Ricardo J. S. Viana; Zsuzsanna Callaerts-Vegh; Rudi D’Hooge; Cecília M. P. Rodrigues (Molecular Neurobiology, 2012)

Development of 14 microsatellite markers for a montane meadow frog (Bokermannohyla saxicola, Hylidae) in southeastern Brazil - Paula C. Eterovick; Ryan Franckowiak; Cibele Velloso-Rodrigues; João Bruno G. C. Santos; Rauber S. Garcia; Josiane A. Gomes (Conservation Genetics Resources, 2012)

Overexpression of inducible 70-kDa heat shock protein in mouse improves structural and functional recovery of skeletal muscles from atrophy - Elen H. Miyabara; Tabata L. Nascimento; Débora C. Rodrigues; Anselmo S. Moriscot; Wilmer F. Davila; Younss AitMou; Pieter P. deTombe; Ruben Mestril (Pflügers Archiv - European Journal of Physiology, 2012)

Statistical Optimization of Sugarcane Leaves Hydrolysis into Simple Sugars by Dilute Sulfuric Acid Catalyzed Process - R. O. Moutta; Anuj K. Chandel; R. C. L. B. Rodrigues; M. B. Silva; G. J. M. Rocha; S. S. Silva (Sugar Tech, 2012)

The dual crop coefficient approach using a density factor to simulate the evapotranspiration of a peach orchard: SIMDualKc model versus eddy covariance measurements - T. A. Paço; M. I. Ferreira; R. D. Rosa; P. Paredes; G. C. Rodrigues; N. Conceição; C. A. Pacheco; L. S. Pereira (Irrigation Science, 2012)

Effect of pH and Temperature on Enzyme Activity of Chitosanase Produced Under Solid Stated Fermentation by Trichoderma spp. - Luis C. A. da Silva; Talita L. Honorato; Rosane S. Cavalcante; Telma T. Franco; Sueli Rodrigues (Indian Journal of Microbiology, 2012)

Hg transfer from contaminated soils to plants and animals - S. M. Rodrigues; B. Henriques; A. T. Reis; A. C. Duarte; E. Pereira; P. F. A. M. Römkens (Environmental Chemistry Letters, 2012)

The habitat vegetational structure and the success of the blue alcon, Maculinea alcon (Denis & Schiffermüller) - P. O. Soares; A. L. Crespi; M. C. Rodrigues; P. S. Arnaldo (Plant Biosystems, 2012)

Pattern of asthma medication use among children from a large urban center in Brazil - Djanilson Barbosa Santos; Alvaro A. Cruz; Silvia de Magalhães Simões; Laura C. Rodrigues; Paulo Augusto Moreira Camargos; Helena Lutescia Luna Coelho; Mauricio L. Barreto (European Journal of Clinical Pharmacology, 2012)

Heavy Metals Contamination in Century-Old Manmade Technosols of Hope Bay, Antarctic Peninsula - Marcelo Braga Bueno Guerra; Carlos Ernesto G. R. Schaefer; Paula de Freitas Rosa; Felipe N. B. Simas; Thiago T. C. Pereira; Edenir Rodrigues Pereira-Filho (Water, Air, & Soil Pollution, 2011)

Vascular endothelial growth factor-A165 (VEGF-A165) stimulates the in vitro development and oocyte competence of goat preantral follicles - V. R. Araújo; G. M. Silva; A. B. G. Duarte; D. M. Magalhães; A. P. Almeida; R. F. B. Gonçalves; J. B. Bruno; T. F. P. Silva; C. C. Campello; A. P. R. Rodrigues; J. R. Figueiredo (Cell and Tissue Research, 2011)

Application of flow cytometry for the identification of Staphylococcus epidermidis by peptide nucleic acid fluorescence in situ hybridization (PNA FISH) in blood samples - N. F. Azevedo; T. Jardim; C. Almeida; L. Cerqueira; A. J. Almeida; F. Rodrigues; C. W. Keevil; M. J. Vieira (Antonie van Leeuwenhoek, 2011)

Iron exposure modifies acetylcholinesterase activity in zebrafish (Danio rerio) tissues: distinct susceptibility of tissues to iron overload - M. C. B. Sant’Anna; Vanessa de Matas Soares; Kelly Juliana Seibt; Gabriele Ghisleni; Eduardo Pacheco Rico; Denis Broock Rosemberg; Jarbas Rodrigues de Oliveira; Nadja Schröder; Carla Denise Bonan; Mauricio Reis Bogo (Fish Physiology and Biochemistry, 2011)

Analysis of the activation mechanism of Pseudomonas stutzeri cytochrome c peroxidase through an electron transfer chain - P. M. Paes de Sousa; D. Rodrigues; C. G. Timóteo; M. L. Simões Gonçalves; G. W. Pettigrew; I. Moura; J. J. G. Moura; M. M. Correia dos Santos (JBIC Journal of Biological Inorganic Chemistry, 2011)

Kanagawa-Negative, tdh- and trh-Positive Vibrio parahaemolyticus Isolated from Fresh Oysters Marketed in Fortaleza, Brazil - Regine H. S. F. Vieira; Renata A. Costa; Francisca G. R. Menezes; Giselle C. Silva; Grace N. D. Theophilo; Dália P. Rodrigues; Rodrigo Maggioni (Current Microbiology, 2011)

Paracrine-mediated osteoclastogenesis by the osteosarcoma MG63 cell line: is RANKL/RANK signalling really important? - J. Costa-Rodrigues; C. A. Teixeira; M. H. Fernandes (Clinical & Experimental Metastasis, 2011)

Evaluation of Cu potential bioavailability changes upon coastal sediment resuspension: an example on how to improve the assessment of sediment dredging environmental risks - Wilson Machado; Ana Paula C. Rodrigues; Edison D. Bidone; Silvia M. Sella; Ricardo E. Santelli (Environmental Science and Pollution Research, 2011)

C and N Content in Density Fractions of Whole Soil and Soil Size Fraction Under Cacao Agroforestry Systems and Natural Forest in Bahia, Brazil - Joice Cleide O. Rita; Emanuela Forestieri Gama-Rodrigues; Antonio Carlos Gama-Rodrigues; Jose Carlos Polidoro; Regina Cele R. Machado; Virupax C. Baligar (Environmental Management, 2011)

A new race of Puccinia psidii defeats rust resistance in eucalypt - Rodrigo N. Graça; Cristina P. Aun; Lúcio M. S. Guimarães; Bruno V. A. Rodrigues; Edival A. V. Zauza; Acelino C. Alfenas (Australasian Plant Pathology, 2011)

Alterations on rice leaf physiology during infection by Bipolaris oryzae - Leandro J. Dallagnol; Fabrício A. Rodrigues; Samuel C. V. Martins; Paulo C. Cavatte; Fábio M. DaMatta (Australasian Plant Pathology, 2011)

Evaluation Antimicrobial and Antiadhesive Properties of the Biosurfactant Lunasan Produced by Candida sphaerica UCP 0995 - Juliana M. Luna; Raquel D. Rufino; Leonie A. Sarubbo; Lígia R. M. Rodrigues; José A. C. Teixeira; Galba M. de Campos-Takaki (Current Microbiology, 2011)

Oxoquinoline Derivatives: Identification and Structure–Activity Relationship (SAR) Analysis of New Anti-HSV-1 Agents - Paula A. Abreu; Viveca A. G. G. da Silva; Fernanda C. Santos; Helena C. Castro; Cecília S. Riscado; Mariana T. de Souza; Camilly P. Ribeiro; Juliana E. Barbosa; Cláudio C. C. dos Santos; Carlos R. Rodrigues; Viviane Lione; Bianca A. M. Correa; et al. (Current Microbiology, 2011)

Haplotypes of the bovine IgG2 heavy gamma chain in tick-resistant and tick-susceptible breeds of cattle - Wanessa Araújo Carvalho; Patricia Ianella; Frederico G. C. Arnoldi; Alexandre Rodrigues Caetano; Sandra Regina Maruyama; Beatriz Rossetti Ferreira; Luís Henrique Andreucci Conti; Marcia Ramos Monteiro da Silva; José Otavio F. Paula; Antonio Augusto Mendes Maia; Isabel K. Ferreira de Miranda Santos (Immunogenetics, 2011)

Soil organic matter, nutrient cycling and biological dinitrogen-fixation in agroforestry systems - Antonio C. Gama-Rodrigues (Agroforestry Systems, 2011)

Distribution of oxidizable organic C fractions in soils under cacao agroforestry systems in Southern Bahia, Brazil - Patrícia A. B. Barreto; Emanuela F. Gama-Rodrigues; A. C. Gama-Rodrigues; Alexandre G. Fontes; José C. Polidoro; Maria Kellen S. Moço; Regina C. R. Machado; V. C. Baligar (Agroforestry Systems, 2011)

Unraveling new genes associated with seed development and metabolism in Bixa orellana L. by expressed sequence tag (EST) analysis - Virgínia L. F. Soares; Simone M. Rodrigues; Tahise M. de Oliveira; Talisson O. de Queiroz; Lívia S. Lima; Braz T. Hora-Júnior; Karina P. Gramacho; Fabienne Micheli; Júlio C. M. Cascardo; Wagner C. Otoni; Abelmon S. Gesteira; Marcio G. C. Costa (Molecular Biology Reports, 2011)

Identification of Nor-β-Lapachone Derivatives as Potential Antibacterial Compounds against Enterococcus faecalis Clinical Strain - André L. Lourenço; Paula A. Abreu; Bruno Leal; Eufrânio N. da Silva Júnior; Antonio V. Pinto; Maria do Carmo F. R. Pinto; Alessandra M. T. Souza; Juliana S. Novais; Marcela B. Paiva; Lucio M. Cabral; Carlos R. Rodrigues; Vitor F. Ferreira; et al. (Current Microbiology, 2011)

Manayunkia speciosa Leidy (Polychaeta: Sabellidae): introduction of this nonindigenous species in the Neotropical Region (Uruguay river, South America) - Laura C. Armendáriz; Analía Paola; Alberto Rodrigues Capítulo (Biological Invasions, 2011)

Modulation of the response to a somatosensory stimulation of the hand during the observation of manual actions - Julien I. A. Voisin; Erika C. Rodrigues; Sébastien Hétu; Philip L. Jackson; Claudia D. Vargas; Francine Malouin; C. Elaine Chapman; Catherine Mercier (Experimental Brain Research, 2011)

Matrix effect on paralytic shellfish toxins quantification and toxicity estimation in mussels exposed to Gymnodinium catenatum - M.J. Botelho; C. Vale; A.M. Mota; S.M. Rodrigues; P.R. Costa; M.L.S. Simões Gonçalves (Food Additives & Contaminants: Part A, 2010)

Intake and digestibility in cattle fed low-quality tropical forage and supplemented with nitrogenous compounds - Claudia B. Sampaio; Edenio Detmann; Mario F. Paulino; Sebastiao C. Valadares Filho; Marjorrie A. de Souza; Isis Lazzarini; Pedro V. Rodrigues Paulino; Augusto C. de Queiroz (Tropical Animal Health and Production, 2010)

A new method for the detection of Pneumocystis jirovecii using flow cytometry - J. Barbosa; C. Bragada; S. Costa-de-Oliveira; E. Ricardo; A. G. Rodrigues; C. Pina-Vaz (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Factorial analysis of the trihalomethane formation in the reaction of colloidal, hydrophobic, and transphilic fractions of DOM with free chlorine - Stefan Platikanov; Roma Tauler; Pedro M. S. M. Rodrigues; Maria Cristina G. Antunes; Dilson Pereira; Joaquim C. G. Esteves da Silva (Environmental Science and Pollution Research, 2010)

Meiotic analysis of XX/XY and neo-XX/XY sex chromosomes in Phyllostomidae by cross-species chromosome painting revealing a common chromosome 15-XY rearrangement in Stenodermatinae - Renata Coelho Rodrigues Noronha; Cleusa Yoshiko Nagamachi; Patricia C. M. O’Brien; Malcolm A. Ferguson-Smith; Julio Cesar Pieczarka (Chromosome Research, 2010)

Seroprevalence of orthopoxvirus in an Amazonian rural village, Acre, Brazil - B. E. F. Mota; G. S. Trindade; T. C. Diniz; M. da Silva-Nunes; E. M. Braga; M. Urbano-Ferreira; G. O. L. Rodrigues; C. A. Bonjardim; P. C. P. Ferreira; E. G. Kroon (Archives of Virology, 2010)

Characterization of two recessive genes controlling resistance to all races of bacterial spot in peppers - C. Eduardo Vallejos; Valerie Jones; Robert E. Stall; Jeffrey B. Jones; Gerald V. Minsavage; Diana C. Schultz; Rosana Rodrigues; Lisa E. Olsen; Michael Mazourek (Theoretical and Applied Genetics, 2010)

Using taxonomically unbiased criteria to prioritize resource allocation for oceanic island species conservation - José L. Martín; Pedro Cardoso; Manuel Arechavaleta; Paulo A. V. Borges; Bernardo F. Faria; Cristina Abreu; António F. Aguiar; José A. Carvalho; Ana C. Costa; Regina T. Cunha; Francisco M. Fernandes; Rosalina Gabriel; et al. (Biodiversity and Conservation, 2010)

Horizontal nutrient fluxes and food safety in urban and peri-urban vegetable and millet cultivation of Niamey, Niger - Rodrigue V. C. Diogo; Andreas Buerkert; Eva Schlecht (Nutrient Cycling in Agroecosystems, 2010)

Growth of Hydrilla verticillata (L.f.) Royle under controlled conditions - I. Bianchini; M. B. Cunha-Santino; J. A. M. Milan; C. J. Rodrigues; J. H. P. Dias (Hydrobiologia, 2010)

Biodiversity of the urban homegardens of São Luís city, Northeastern Brazil - Festus Kehinde Akinnifesi; Gudeta W. Sileshi; Oluyede C. Ajayi; Adetutu I. Akinnifesi; Emanoel G. de Moura; Jairo F. P. Linhares; Ivanilde Rodrigues (Urban Ecosystems, 2010)

Bacterial Communities in the Rhizosphere of Biofuel Crops Grown on Marginal Lands as Evaluated by 16S rRNA Gene Pyrosequences - Ederson da C. Jesus; Endang Susilawati; Stephanie L. Smith; Qiong Wang; Benli Chai; Ryan Farris; Jorge L. M. Rodrigues; Kurt D. Thelen; James M. Tiedje (BioEnergy Research, 2010)

Carbon Storage in Soil Size Fractions Under Two Cacao Agroforestry Systems in Bahia, Brazil - Emanuela F. Gama-Rodrigues; P. K. Ramachandran Nair; Vimala D. Nair; Antonio C. Gama-Rodrigues; Virupax C. Baligar; Regina C. R. Machado (Environmental Management, 2010)

Vasodilator effects of Diocleinae lectins from the Canavalia genus - Ana Maria Sampaio Assreuy; Sabrina Rodrigues Fontenele; Alana de Freitas Pires; Débora Costa Fernandes; Natália Velloso Fontenelle C. Rodrigues; Eduardo Henrique Salviano Bezerra; Tales Rocha Moura; Kyria Santiago do Nascimento; Benildo Sousa Cavada (Naunyn-Schmiedeberg's Archives of Pharmacology, 2009)

Beta-Amyloid Deposition and the Aging Brain - Karen M. Rodrigue; Kristen M. Kennedy; Denise C. Park (Neuropsychology Review, 2009)

Isolation and characterization of microsatellites loci for “piramutaba” (Brachyplatystoma vaillantii, Siluriformes: Pimelodidae), one of the commercially most important migratory catfishes in the Amazon Basin - Fabiola C. Rodrigues; Izeni P. Farias; Jacqueline S. Batista; José Alves-Gomes (Conservation Genetics Resources, 2009)

The potential ecological costs and cobenefits of REDD: a critical review and case study from the Amazon region - CLAUDIA M. STICKLER; DANIEL C. NEPSTAD; MICHAEL T. COE; DAVID G. McGRATH; HERMANN O. RODRIGUES; WAYNE S. WALKER; BRITALDO S. SOARES‐FILHO; ERIC A. DAVIDSON (Global Change Biology, 2009)
The United Nations climate treaty may soon include a mechanism for compensating tropical nations that succeed in reducing carbon emissions from deforestation and forest degradation, source of nearly one fifth of global carbon emissions. We review the potential for this mechanism [reducing emissions from deforestation and degradation (REDD)] to provoke ecological damages and promote ecological cobenefits. Nations could potentially participate in REDD by slowing clear‐cutting of mature tropical forest, slowing or decreasing the impact of selective logging, promoting forest regeneration and restoration, and expanding tree plantations. REDD could also foster efforts to reduce the incidence of forest fire. Potential ecological costs include the accelerated loss (through displaced agricultural expansion) of low‐biomass, high‐conservation‐value ecosystems, and substitution of low‐biomass vegetation by monoculture tree plantations. These costs could be avoided through measures that protect low‐biomass native ecosystems. Substantial ecological cobenefits should be conferred under most circumstances, and include the maintenance or restoration of (1) watershed functions, (2) local and regional climate regimes, (3) soils and biogeochemical processes, (4) water quality and aquatic habitat, and (5) terrestrial habitat. Some tools already being developed to monitor, report and verify (MRV) carbon emissions performance can also be used to measure other elements of ecosystem function, making development of MRV systems for ecological cobenefits a concrete possibility. Analysis of possible REDD program interventions in a large‐scale Amazon landscape indicates that even modest flows of forest carbon funding can provide substantial cobenefits for aquatic ecosystems, but that the functional integrity of the landscape's myriad small watersheds would be best protected under a more even spatial distribution of forests. Because of its focus on an ecosystem service with global benefits, REDD could access a large pool of global stakeholders willing to pay to maintain carbon in forests, thereby providing a potential cascade of ecosystem services to local stakeholders who would otherwise be unable to afford them.

Effect of Batch and Fed-Batch Growth Modes on Biofilm Formation by Listeria monocytogenes at Different Temperatures - Diana A. Rodrigues; Marta A. Almeida; Pilar A. Teixeira; Rosário T. Oliveira; Joana C. Azeredo (Current Microbiology, 2009)

Leishmania amazonensis Growth Inhibitors: Biological and Theoretical Features of Sulfonamide 4-Methoxychalcone Derivatives - Alessandra M. T. Souza; Helena C. Castro; Monique A. Brito; Carla R. Andrighetti-Fröhner; Uiaran Magalhães; Kely N. Oliveira; Daniela Gaspar-Silva; Letícia K. Pacheco; Antônio C. Joussef; Mário Steindel; Cláudia M. O. Simões; Dilvani O. Santos; et al. (Current Microbiology, 2009)

Antagonistic interactions between garden yeasts and microfungal garden pathogens of leaf-cutting ants - Andre Rodrigues; Rachel N. Cable; Ulrich G. Mueller; Maurício Bacci; Fernando C. Pagnocca (Antonie van Leeuwenhoek, 2009)

Evaluating the resistance to posaconazole by E-test and CLSI broth microdilution methodologies of Candida spp. and pathogenic moulds - R. Araujo; S. Costa-de-Oliveira; I. Coutinho; A. G. Rodrigues; C. Pina-Vaz (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

Influence of high-pressure processing on the structure and memory effect of synthetic layered double hydroxides - Jaqueline C. Rodrigues; Tania Maria Haas Costa; Márcia R. Gallas; Celso C. Moro (Physics and Chemistry of Minerals, 2009)

Mercury pollution in Ria de Aveiro (Portugal): a review of the system assessment - M. E. Pereira; A. I. Lillebø; P. Pato; M. Válega; J. P. Coelho; C. B. Lopes; S. Rodrigues; A. Cachada; M. Otero; M. A. Pardal; A. C. Duarte (Environmental Monitoring and Assessment, 2009)

The influence of anthropogenic and natural geochemical factors on urban soil quality variability: a comparison between Glasgow, UK and Aveiro, Portugal - Sonia Rodrigues; Graham Urquhart; Iain Hossack; Ma Eduarda Pereira; Armando C. Duarte; Christine Davidson; Andrew Hursthouse; Peter Tucker; Douglas Roberston (Environmental Chemistry Letters, 2009)

Conservation of dual-targeted proteins in Arabidopsis and rice points to a similar pattern of gene-family evolution - Carolina V. Morgante; Ricardo A. O. Rodrigues; Phellippe A. S. Marbach; Camila M. Borgonovi; Daniel S. Moura; Marcio C. Silva-Filho (Molecular Genetics and Genomics, 2009)

Soil and litter fauna of cacao agroforestry systems in Bahia, Brazil - M. K. da Silva Moço; E. F. da Gama-Rodrigues; A. C. da Gama-Rodrigues; R. C. R. Machado; V. C. Baligar (Agroforestry Systems, 2009)

A role for atorvastatin and insulin combination in protecting from liver injury in a model of type 2 diabetes with hyperlipidemia - P. Matafome; E. Nunes; T. Louro; C. Amaral; J. Crisóstomo; L. Rodrigues; A. R. Moedas; P. Monteiro; A. Cipriano; R. Seiça (Naunyn-Schmiedeberg's Archives of Pharmacology, 2009)

Temperature-dependent development rates of Bracon vulgaris, a parasitoid of boll weevil - F. S. Ramalho; P. A. Wanderley; J. B. Malaquias; K. C. V. Rodrigues; J. V. S. Souza; J. C. Zanuncio (Phytoparasitica, 2009)

Foliar application of potassium silicate reduces the intensity of soybean rust - F. A. Rodrigues; H. S. S. Duarte; G. P. Domiciano; C. A. Souza; G. H. Korndörfer; L. Zambolim (Australasian Plant Pathology, 2009)

Effect of root and foliar applications of silicon on brown spot development in rice - D. C. Rezende; F. Á. Rodrigues; V. Carré-Missio; D. A. Schurt; I. K. Kawamura; G. H. Korndörfer (Australasian Plant Pathology, 2009)

Identification of a Potential Lead Structure for Designing New Antimicrobials to Treat Infections Caused by Staphylococcus epidermidis-Resistant Strains - Luiz C. S. Pinheiro; Paula A. Abreu; Ilidio F. Afonso; Bruno Leal; Luiz C. D. Corrêa; Júlio C. Borges; Isakelly P. Marques; André L. Lourenço; Plinio Sathler; Andre L. dos Santos; Cid A. Medeiros; Lúcio M. Cabral; et al. (Current Microbiology, 2008)

Yeasts and filamentous fungi carried by the gynes of leaf-cutting ants - Fernando C. Pagnocca; André Rodrigues; Nilson S. Nagamoto; Maurício Bacci (Antonie van Leeuwenhoek, 2008)

Resveratrol inhibits cell growth by inducing cell cycle arrest in activated hepatic stellate cells - Izabel C. Souza; Leo Anderson M. Martins; Barbara P. Coelho; Ivana Grivicich; Regina M. Guaragna; Carmem Gottfried; Radovan Borojevic; Fátima Costa Rodrigues Guma (Molecular and Cellular Biochemistry, 2008)

Loss of heterozygosity at 19p13.2 and 2q21 in tumours from familial clusters of non-medullary thyroid carcinoma - Hugo João Prazeres; Fernando Rodrigues; Paula Soares; Plamen Naidenov; Paulo Figueiredo; Beatriz Campos; Manuela Lacerda; Teresa C. Martins (Familial Cancer, 2008)

A first Portuguese epidemiological survey of fungaemia in a university hospital - S. Costa-de-Oliveira; C. Pina-Vaz; D. Mendonça; A. Gonçalves Rodrigues (European Journal of Clinical Microbiology & Infectious Diseases, 2008)

Preliminary data on microcharacters and chromosome number in Tornabenea species (Apiaceae) from Cape Verde Islands - A. C. Grosso; L. Rodrigues; I. Gomes; E. S. Martins; G. Teixeira (Plant Biosystems, 2008)

Physicochemical Properties and Dissolution Studies of Dexamethasone Acetate-β-Cyclodextrin Inclusion Complexes Produced by Different Methods - Mayara M. Doile; Keila A. Fortunato; Iára C. Schmücker; Sacha K. Schucko; Marcos A.S. Silva; Patrik O. Rodrigues (AAPS PharmSciTech, 2008)

First report of bristleworm predator of the reef octocoral Carijoa riisei - J. R. B. Souza; H. A. Rodrigues; B. M. Neves; C. D. Perez (Coral Reefs, 2007)

Time sequence of the damage to the acceptor and donor sides of photosystem II by UV-B radiation as evaluated by chlorophyll a fluorescence - Jack J. S. van Rensen; Wim J. Vredenberg; Gustavo C. Rodrigues (Photosynthesis Research, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Comparative phylogeography of Trypanosoma rangeli and Rhodnius (Hemiptera: Reduviidae) supports a long coexistence of parasite lineages and their sympatric vectors - F. MAIA DA SILVA; A. C. V. JUNQUEIRA; M. CAMPANER; A. C. RODRIGUES; G. CRISANTE; L. E. RAMIREZ; Z. C. E. CABALLERO; F. A. MONTEIRO; J. R. COURA; N. AÑEZ; M. M. G. TEIXEIRA (Molecular Ecology, 2007)
To make reliable interpretations about evolutionary relationships between Trypanosoma rangeli lineages and their insect vectors (triatomine bugs of the genus Rhodnius ) and, thus, about the determinant factors of lineage segregation within T. rangeli , we compared phylogenies of parasite isolates and vector species. Sixty‐one T. rangeli isolates from invertebrate and vertebrate hosts were initially evaluated in terms of polymorphism of the spliced‐leader gene (SL). Further analysis based on SL and SSUrRNA sequences from 33 selected isolates, representative of the overall phylogenetic diversity and geographical range of T. rangeli , supported four phylogenetic lineages within this species. By comparing the phylogeny of Rhodnius species with that inferred for T. rangeli isolates and through analysis of the geographical range of the isolates, we showed that there is a very significant overlap in the distribution of Rhodnius species and T. rangeli lineages. Congruence between phylogeographical analysis of both T. rangeli lineages and complexes of Rhodnius species are consistent with the hypothesis of a long coexistence of parasites and their vectors, with lineage divergence associated with sympatric species of Rhodnius apparently without association with particular vertebrate hosts. Separation of T. rangeli isolates from vectors of distinct complexes living in sympatry favours the absence of gene flow between the lineages and suggests evolution of T. rangeli lineages in independent transmission cycles, probably associated to specific Rhodnius spp. ecotopes. A polymerase chain reaction assay based on SL intergenic sequences was developed for simultaneous identification and lineage genotyping of T. rangeli in epidemiological surveys.

Automatic identification of erosion gullies with ASTER imagery in the Brazilian Cerrados - A. Vrieling; S. C. Rodrigues; H. Bartholomeus; G. Sterk (International Journal of Remote Sensing, 2007)

Repeated-Batch Xylitol Bioproduction Using Yeast Cells Entrapped in Polyvinyl Alcohol–Hydrogel - M. A. A. Cunha; R. C. B. Rodrigues; J. C. Santos; A. Converti; S. S. da Silva (Current Microbiology, 2007)

Acute heat exposure increases high-intensity performance during sprint cycle exercise - Ana Cristina R. Lacerda; Fernando Gripp; Luiz Oswaldo C. Rodrigues; Emerson Silami-Garcia; Cândido C. Coimbra; Luciano S. Prado (European Journal of Applied Physiology, 2006)

Antiinflammatory effects of natural tetranortriterpenoids isolated from Carapa guianensis Aublet on zymosan-induced arthritis in mice - C. Penido; F. P. Conte; M. S. S. Chagas; C. A. B. Rodrigues; J. F. G. Pereira; M. G. M. O. Henriques (Inflammation Research, 2006)

Response of the zoobenthos community along the dispersion plume of a highly polluted stream in the receiving waters of a large river (Rio de la Plata, Argentina) - Analía C. Paggi; Carolina Ocón; Mariana Tangorra; Alberto Rodrigues Capítulo (Hydrobiologia, 2006)

Susceptibility of the ant-cultivated fungus Leucoagaricus gongylophorus (Agaricales: Basidiomycota) towards microfungi - A. Silva; A. Rodrigues; M. Bacci; F. C. Pagnocca; O. C. Bueno (Mycopathologia, 2006)

The effects of fructose-1,6-bisphosphate and dexamethasone on acute inflammation and T-cell proliferation - R. Pestana Lopes; A. Lunardelli; T. Preissler; C. E. Leite; J. C. F. Alves-Filho; F. Bordignon Nunes; J. Rodrigues de Oliveira; M. E. Bauer (Inflammation Research, 2006)

Enhanced Xylitol Production by Precultivation of Candida guilliermondii Cells in Sugarcane Bagasse Hemicellulosic Hydrolysate - Rita C.L.B. Rodrigues; Luciane Sene; Gilvane S. Matos; Inês C. Roberto; Adalberto Pessoa; Maria G.A. Felipe (Current Microbiology, 2006)

Characterization of an ecto-ATPase activity in Fonsecaea pedrosoi - Ítalo Collopy-Junior; Lucimar F. Kneipp; Fernanda C. da Silva; Marcio L. Rodrigues; Celuta S. Alviano; José Roberto Meyer-Fernandes (Archives of Microbiology, 2006)

Contamination Levels and Preliminary Assessment of the Technical Feasibility of Employing Natural Attenuation in 5 Priority Areas of Presidente Bernardes Refinery in Cubatão, São Paulo, Brazil - René P. Schneider; Sandra C. Morano; Maria Alejandra C. Gigena; Silvia K. Missawa; Rafael C. S. Rocha; Lucimara Rodrigues Da Silva; Nelson Ellert; Sérgio Kataoka; Carlos Katsuragi; Carlos Da Silva Rosa; Luiz Calixto De Oliveira Filho (Environmental Monitoring and Assessment, 2006)

Extract of the bristles of Dirphia sp. increases nitric oxide in a rat pleurisy model - A. Lunardelli; C. E. Leite; M. Guerra Simões Pires; J. Rodrigues de Oliveira (Inflammation Research, 2006)

Decreased Susceptibility to Nitroimidazoles Among Bacteroides Species in Brazil - Jessica Manya B. D. Vieira; Renata F. Boente; Karla Rodrigues Miranda; Kátia E. S. Avelar; Regina M. C. P. Domingues; Maria Candida de S. Ferreira (Current Microbiology, 2006)

Influence of the time of occlusion on the quantitative parameters obtained by modelling trans-epidermal water loss curves to describe the human cutaneous barrier functionin vivo - P. C. Pinto; L. M. Rodrigues (Medical & Biological Engineering & Computing, 2005)

Modulation of endocytosis in pollen tube growth by phosphoinositides and phospholipids - D. Monteiro; P. Castanho Coelho; C. Rodrigues; L. Camacho; H. Quader; R. Malhó (Protoplasma, 2005)

Anti-inflammatory properties of kefir and its polysaccharide extract - K. L. Rodrigues; J. C. T. Carvalho; J. M. Schneedorf (Inflammopharmacology, 2005)

Ecophysiology of selected tree species in different plant communities at the periphery of the Atlantic Forest of SE—Brazil III. Three legume trees in a semi-deciduous dry forest - A. Geßler; H. M. Duarte; A. C. Franco; U. Lüttge; E. A. de Mattos; M. Nahm; P. J. F. P. Rodrigues; F. R. Scarano; H. Rennenberg (Trees, 2005)

Endosperm-preferred Expression of Maize Genes as Revealed by Transcriptome-wide Analysis of Expressed Sequence Tags - Natalia C. Verza; Thaís Rezende e Silva; Germano Cord Neto; Fábio T. S. Nogueira; Paulo H. Fisch; Vincente E. de Rosa; Marcelo M. Rebello; André L. Vettore; Felipe Rodrigues da Silva; Paulo Arruda (Plant Molecular Biology, 2005)

Vasopressin release during endotoxaemic shock in mice lacking inducible nitric oxide synthase - Evelin C. Carnio; Angelita M. Stabile; Marcelo E. Batalhão; João Santana Silva; José Antunes-Rodrigues; Luiz G. S. Branco; Sheldon Magder (Pflügers Archiv - European Journal of Physiology, 2005)

Variability of non-mutualistic filamentous fungi associated withAtta sexdens rubropilosa nests - A. Rodrigues; F. C. Pagnocca; M. Bacci; M. J. A. Hebling; O. C. Bueno; L. H. Pfenning (Folia Microbiologica, 2005)

Larval Cryptothelea gloverii (Lepidoptera: Psycidae), an arthropod predator and herbivore on Florida citrus - Raul T. Villanueva; Jose C. V. Rodrigues; Carl C. Childers (Experimental and Applied Acarology, 2005)

Identification and pathogenic characterization of endophytic Fusarium species from cowpea seeds - A. A. C. Rodrigues; Maria Menezes (Mycopathologia, 2005)

Mitochondrial DNA and RAPD polymorphisms in the haploid mite Brevipalpus phoenicis (Acari: Tenuipalpidae) - J. C. V. Rodrigues; M. Gallo-meagher; R. Ochoa; C. C. Childers; B. J. Adams (Experimental and Applied Acarology, 2004)

Element-Enrichment Factors in Lichens from Terceira, Santa Maria and Madeira Islands (Azores and Madeira Archipelagoes) - B. J. Vieira; M. C. Freitas; A. F. Rodrigues; A. M. G. Pacheco; P. M. Soares; N. Correia (Journal of Atmospheric Chemistry, 2004)

Spatial and temporal variability in forest–atmosphere CO 2 exchange - D. Y. Hollinger; J. Aber; B. Dail; E. A. Davidson; S. M. Goltz; H. Hughes; M. Y. Leclerc; J. T. Lee; A. D. Richardson; C. Rodrigues; N.A. Scott; D. Achuatavarier; et al. (Global Change Biology, 2004)
Seven years of carbon dioxide flux measurements indicate that a ∼90‐year‐old spruce dominated forest in Maine, USA, has been sequestering 174±46 g C m −2 yr −1 (mean±1 standard deviation, nocturnal friction velocity ( u * ) threshold >0.25 m s −1 ). An analysis of monthly flux anomalies showed that above‐average spring and fall temperatures were significantly correlated with greater monthly C uptake while above‐average summer temperatures were correlated with decreased net C uptake. Summer months with significantly drier or wetter soils than normal were also characterized by lower rates of C uptake. Years with above‐average C storage were thus typically characterized by warmer than average spring and fall temperatures and adequate summer soil moisture. Environmental and forest–atmosphere flux data recorded from a second tower surrounded by similar forest, but sufficiently distant that flux source regions (‘footprints’), did not overlap significantly showed almost identical temperature and solar radiation conditions, but some differences in energy partitioning could be seen. Half‐hourly as well as integrated (annual) C exchange values recorded at the separate towers were very similar, with average annual net C uptake differing between the two towers by

Lipids and stable carbon isotopes in two species of Hawaiian corals, Porites compressa and Montipora verrucosa, following a bleaching event - A.G. Grottoli; L.J. Rodrigues; C. Juarez (Marine Biology, 2004)

p53 dephosphorylation and p21Cip1/Waf1 translocation correlate with caspase-3 activation in TGF-β1-induced apoptosis of HuH-7 cells - G. Fan; X. Ma; P. Y. Wong; C. M. P. Rodrigues; C. J. Steer (Apoptosis, 2004)

Role of nitric oxide in thermoregulation during septic shock: involvement of vasopressin - Alexandre Giusti-Paiva; Luiz G. S. Branco; Margareth de Castro; José Antunes-Rodrigues; Evelin C. Carnio (Pflügers Archiv - European Journal of Physiology, 2003)

Impairment of inflammatory response in adult rats submitted to maternal undernutrition during early lactation: Role of insulin and glucocorticoid - C. Barja-Fidalgo; E. P. G. Souza; S. V. Silva; A. L. Rodrigues; E. A. Anjos-Valotta; P. Sannomyia; M. S. DeFreitas; A. S. Moura (Inflammation Research, 2003)

Resistance to common bacterial blight in Phaseolus vulgaris L. recombinant inbred lines under natural infection of Xanthomonas axonopodis pv. phaseoli - C. Fortes Ferreira; M. Gonzaga Pereira; A. da Silva dos Santos; R. Rodrigues; R.E. Bressan-Smith; A. PioViana; R. Figueiredo Daher (Euphytica, 2003)

Electrophysiological Responses of Female and Male Hypsipyla grandella (Zeller) to Swietenia macrophylla Essential Oils - Marisi G. Soares; Luciane G. Batista-Pereira; João B. Fernandes; Arlene G. Corrêa; M. Fátima G. F. Da Silva; Paulo C. Vieira; Edson Rodrigues Filho; Orlando S. Ohashi (Journal of Chemical Ecology, 2003)

Severe Disseminated Tuberculosis After Intravesical Instillation of Bacillus Calmette-Gurin - R. Proena; M. Toscano Rico; O. Cardoso; C. Salvado; P. Rodrigues; J. Machado (European Journal of Clinical Microbiology & Infectious Diseases, 2003)

Host Plants of Brevipalpus californicus, B. obovatus, and B. phoenicis (Acari: Tenuipalpidae) and their Potential Involvement in the Spread of Viral Diseases Vectored by these Mites - Carl C. Childers; Jose Carlos V. Rodrigues; Warren C. Welbourn (Experimental and Applied Acarology, 2003)

Brevipalpus californicus, B. obovatus, B. phoenicis, and B. lewisi (Acari: Tenuipalpidae): a Review of their Biology, Feeding Injury and Economic Importance - Carl C. Childers; J. Victor French; Jose Carlos V. Rodrigues (Experimental and Applied Acarology, 2003)

Chromosomal studies in Callicebus donacophilus pallescens, with classic and molecular cytogenetic approaches: Multicolour FISH using human and Saguinus oedipus painting probes - R. M. S. Barros; C. Y. Nagamachi; J. C. Pieczarka; L. R. R. Rodrigues; M. Neusser; E. H. de Oliveira; J. Wienberg; J. A. P. C. Muniz; J. D. Rissino; S. Muller (Chromosome Research, 2003)

Tissue-specific regulation of BiP genes: a cis-acting regulatory domain is required for BiP promoter activity in plant meristems - Reginaldo A.A. Buzeli; Júlio C.M. Cascardo; Leonardo A.Z. Rodrigues; Maxuel O. Andrade; Raul S. Almeida; Marcelo E. Loureiro; Wagner C. Otoni; Elizabeth P.B. Fontes (Plant Molecular Biology, 2002)

Associations between smoking and adenocarcinomas and squamous cell carcinomas of the uterine cervix (United States) - James V. Lacey; Morten Frisch; Louise A. Brinton; Fouad M. Abbas; Willard A. Barnes; Patti E. Gravitt; Mitchell D. Greenberg; Sarah M. Greene; Olympia C. Hadjimichael; Larry McGowan; Rodrigue Mortel; Peter E. Schwartz; et al. (Cancer Causes & Control, 2001)

Low resistance against novel 2-benzylamino-1,3,5-triazine herbicides in atrazine-resistant Chenopodium album plants - Hitoshi Kohno; Aiko Ohki; Shinpei Ohki; Kazuya Koizumi; Maria E. Van den Noort; Gustavo C. Rodrigues; Jack J.S. Van Rensen; Ko Wakabayashi (Photosynthesis Research, 2000)

Varying responses of herbivorous and invertebrate-feeding fishes to macroalgal reduction on a coral reef - T. R. McClanahan; V. Hendrick; M. J. Rodrigues; N. V. C. Polunin (Coral Reefs, 1999)

An industrial photosynthetic system for Skeletonema costatum in arid regions - M.R. Kitto; C. Regunathan; Alphonse Rodrigues (Journal of Applied Phycology, 1999)

Air pollution and mortality in Madrid, Spain: a time-series analysis - J. C. Alberdi Odriozola; J. Díaz Jiménez; J. C. Montero Rubio; I. J. Mirón Pérez; M. S. Pajares Ortíz; P. Ribera Rodrigues (International Archives of Occupational and Environmental Health, 1998)

Metabolic disturbances in diabetic cardiomyopathy - Brian Rodrigues; Margaret C. Cam; John H. McNeill (Molecular and Cellular Biochemistry, 1998)

Effect of selenium supplementation on some blood biochemical parameters in male rats - A. M. Viegas Crespo; M. J. Lança; S. Vasconcelos; V. Andrade; H. Rodrigues; M. C. Santos (Biological Trace Element Research, 1995)

The effect of age and selenium on some biochemical parameters in rat liver - M. C. Santos; H. Rodrigues; S. Vasconcelos; V. Andrade; M. J. Lança; A. M. Viegas Crespo (Biological Trace Element Research, 1995)

Redefinition ofCandida Berkhout and the consequent emendation ofCryptococcus Kützing andRhodotorula Harrison - A. C. M. Weijman; L. Rodrigues de Miranda; J. P. Van Der Walt (Antonie van Leeuwenhoek, 1988)

Carbohydrate patterns ofCandida, Cryptococcus andRhodotorula species - A. C. M. Weijman; L. Rodrigues De Miranda (Antonie van Leeuwenhoek, 1988)

Xylose distribution within and taxonomy of the genera Bullera and Sporobolomyces - A. C. M. Weijman; L. Rodrigues de Miranda (Antonie van Leeuwenhoek, 1983)